Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.

Association of Genetic Variation With Cirrhosis: A Multi-Trait Genome-Wide Association and Gene-Environment Interaction Study. - Emdin, Connor A; Haas, Mary; Ajmera, Veeral; Simon, Tracey G; Homburger, Julian; Neben, Cynthia; Jiang, Lan; Wei, Wei-Qi; Feng, Qiping; Zhou, Alicia; Denny, Joshua; Corey, Kathleen; et al. (Gastroenterology, 2021)
BACKGROUND & AIMS: In contrast to most other common diseases, few genetic variants have been identified that impact risk of cirrhosis. We aimed to identify new genetic variants that predispose to cirrhosis, to test whether such variants, aggregated into a polygenic score, enable genomic risk stratification, and to test whether alcohol intake or body mass index interacts with polygenic predisposition. METHODS: We conducted a multi-trait genome-wide association study combining cirrhosis and alanine aminotransferase levels performed in 5 discovery studies (UK Biobank, Vanderbilt BioVU, Atherosclerosis Risk in Communities study, and 2 case-control studies including 4829 individuals with cirrhosis and 72,705 controls and 362,539 individuals with alanine aminotransferase levels). Identified variants were replicated in 3 studies (Partners HealthCare Biobank, FinnGen, and Biobank Japan including 3554 individuals with cirrhosis and 343,826 controls). A polygenic score was tested in Partners HealthCare Biobank. RESULTS: Five previously reported and 7 newly identified genetic variants were associated with cirrhosis in both the discovery studies multi-trait genome-wide association study (P < 5 × 10) and the replication studies (P < .05), including a missense variant in the APOE gene and a noncoding variant near EFN1A. These 12 variants were used to generate a polygenic score. Among Partners HealthCare Biobank individuals, high polygenic score-defined as the top quintile of the distribution-was associated with significantly increased risk of cirrhosis (odds ratio, 2.26; P < .001) and related comorbidities compared with the lowest quintile. Risk was even more pronounced among those with extreme polygenic risk (top 1% of the distribution, odds ratio, 3.16; P < .001). The impact of extreme polygenic risk was substantially more pronounced in those with elevated alcohol consumption or body mass index. Modeled as risk by age 75 years, probability of cirrhosis with extreme polygenic risk was 13.7%, 20.1%, and 48.2% among individuals with no or modest, moderate, and increased alcohol consumption, respectively (P < .001). Similarly, probability among those with extreme polygenic risk was 6.5%, 10.3%, and 19.5% among individuals with normal weight, overweight, and obesity, respectively (P < .001). CONCLUSIONS: Twelve independent genetic variants, 7 of which are newly identified in this study, conferred risk for cirrhosis. Aggregated into a polygenic score, these variants identified a subset of the population at substantially increased risk who are most susceptible to the hepatotoxic effects of excess alcohol consumption or obesity.

Auto-antibodies to type I IFNs can underlie adverse reactions to yellow fever live attenuated vaccine. - Bastard, Paul; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Chbihi, Marwa; Le Voyer, Tom; Rosain, Jérémie; Philippot, Quentin; Seeleuthner, Yoann; Gervais, Adrian; Materna, Marie; de Oliveira, Patricia Mouta Nunes; Maia, Maria de Lourdes S; et al. (J Exp Med, 2021)
Yellow fever virus (YFV) live attenuated vaccine can, in rare cases, cause life-threatening disease, typically in patients with no previous history of severe viral illness. Autosomal recessive (AR) complete IFNAR1 deficiency was reported in one 12-yr-old patient. Here, we studied seven other previously healthy patients aged 13 to 80 yr with unexplained life-threatening YFV vaccine-associated disease. One 13-yr-old patient had AR complete IFNAR2 deficiency. Three other patients vaccinated at the ages of 47, 57, and 64 yr had high titers of circulating auto-Abs against at least 14 of the 17 individual type I IFNs. These antibodies were recently shown to underlie at least 10% of cases of life-threatening COVID-19 pneumonia. The auto-Abs were neutralizing in vitro, blocking the protective effect of IFN-α2 against YFV vaccine strains. AR IFNAR1 or IFNAR2 deficiency and neutralizing auto-Abs against type I IFNs thus accounted for more than half the cases of life-threatening YFV vaccine-associated disease studied here. Previously healthy subjects could be tested for both predispositions before anti-YFV vaccination.
Keywords: Adolescent; Adult; Aged; Antibodies, Neutralizing; Autoantibodies; Autoimmune Diseases; COVID-19; Female; Genetic Diseases, Inborn; HEK293 Cells; Humans; Interferon-alpha; Male; Middle Aged; Receptor, Interferon alpha-beta; SARS-CoV-2; Vaccines, Attenuated; Yellow Fever Vaccine; Yellow fever virus

Biallelic variants in HPDL, encoding 4-hydroxyphenylpyruvate dioxygenase-like protein, lead to an infantile neurodegenerative condition. - Ghosh, Shereen G; Lee, Sangmoon; Fabunan, Rudy; Chai, Guoliang; Zaki, MAH S; Abdel-Salam, Ghada; Sultan, Tipu; Ben-Omran, Tawfeg; Alvi, Javeria Raza; McEvoy-Venneri, Jennifer; Stanley, Valentina; Patel, Aakash; et al. (Genet Med, 2021)
PURPOSE: Dioxygenases are oxidoreductase enzymes with roles in metabolic pathways necessary for aerobic life. 4-hydroxyphenylpyruvate dioxygenase-like protein (HPDL), encoded by HPDL, is an orphan paralogue of 4-hydroxyphenylpyruvate dioxygenase (HPD), an iron-dependent dioxygenase involved in tyrosine catabolism. The function and association of HPDL with human diseases remain unknown. METHODS: We applied exome sequencing in a cohort of over 10,000 individuals with neurodevelopmental diseases. Effects of HPDL loss were investigated in vitro and in vivo, and through mass spectrometry analysis. Evolutionary analysis was performed to investigate the potential functional separation of HPDL from HPD. RESULTS: We identified biallelic variants in HPDL in eight families displaying recessive inheritance. Knockout mice closely phenocopied humans and showed evidence of apoptosis in multiple cellular lineages within the cerebral cortex. HPDL is a single-exonic gene that likely arose from a retrotransposition event at the base of the tetrapod lineage, and unlike HPD, HPDL is mitochondria-localized. Metabolic profiling of HPDL mutant cells and mice showed no evidence of altered tyrosine metabolites, but rather notable accumulations in other metabolic pathways. CONCLUSION: The mitochondrial localization, along with its disrupted metabolic profile, suggests HPDL loss in humans links to a unique neurometabolic mitochondrial infantile neurodegenerative condition.
Keywords: 4-Hydroxyphenylpyruvate Dioxygenase; Animals; Dioxygenases; Exons; Mice; Mice, Knockout; Phenotype

Clinical and molecular evaluation of 13 Brazilian patients with Gomez-López-Hernández syndrome. - Perrone, Eduardo; Perez, Ana Beatriz Alvarez; D'Almeida, Vânia; de Mello, Claudia Berlim; Jacobina, Marcela Amaral Avelino; Loureiro, Rafael Maffei; Burlin, Stênio; Migliavacca, Michele; do Amaral Virmond, Luiza; Graziadio, Carla; Pedroso, José Luiz; Mendes, Elaine Lustosa; et al. (Am J Med Genet A, 2021)
We aim to characterize patients with Gomez-López-Hernández syndrome (GLHS) clinically and to investigate them molecularly. A clinical protocol, including a morphological and neuropsychological assessment, was applied to 13 patients with GLHS. Single-nucleotide polymorphism (SNP) array and whole-exome sequencing were undertaken; magnetic resonance imaging was performed in 12 patients, including high-resolution, heavily T2-weighted sequences (HRT2) in 6 patients to analyze the trigeminal nerves. All patients presented alopecia; two did not present rhombencephalosynapsis (RES); trigeminal anesthesia was present in 5 of the 11 patients (45.4%); brachycephaly/brachyturricephaly and mid-face retrusion were found in 84.6 and 92.3% of the patients, respectively. One patient had intellectual disability. HRT2 sequences showed trigeminal nerve hypoplasia in four of the six patients; all four had clinical signs of trigeminal anesthesia. No common candidate gene was found to explain GLHS phenotype. RES does not seem to be an obligatory finding in respect of GLHS diagnosis. We propose that a diagnosis of GLHS should be considered in patients with at least two of the following criteria: focal non-scarring alopecia, rhombencephalosynapsis, craniofacial anomalies (brachyturrycephaly, brachycephaly or mid-face retrusion), trigeminal anesthesia or anatomic abnormalities of the trigeminal nerve. Studies focusing on germline whole genome sequencing or DNA and/or RNA sequencing of the alopecia tissue may be the next step for the better understanding of GLHS etiology.

CSNK2B: A broad spectrum of neurodevelopmental disability and epilepsy severity. - Ernst, Michelle E; Baugh, Evan H; Thomas, Amanda; Bier, Louise; Lippa, Natalie; Stong, Nicholas; Mulhern, Maureen S; Kushary, Sulagna; Akman, Cigdem I; Heinzen, Erin L; Yeh, Raymond; Bi, Weimin; et al. (Epilepsia, 2021)
CSNK2B has recently been implicated as a disease gene for neurodevelopmental disability (NDD) and epilepsy. Information about developmental outcomes has been limited by the young age and short follow-up for many of the previously reported cases, and further delineation of the spectrum of associated phenotypes is needed. We present 25 new patients with variants in CSNK2B and refine the associated NDD and epilepsy phenotypes. CSNK2B variants were identified by research or clinical exome sequencing, and investigators from different centers were connected via GeneMatcher. Most individuals had developmental delay and generalized epilepsy with onset in the first 2 years. However, we found a broad spectrum of phenotypic severity, ranging from early normal development with pharmacoresponsive seizures to profound intellectual disability with intractable epilepsy and recurrent refractory status epilepticus. These findings suggest that CSNK2B should be considered in the diagnostic evaluation of patients with a broad range of NDD with treatable or intractable seizures.

De novo TRIM8 variants impair its protein localization to nuclear bodies and cause developmental delay, epilepsy, and focal segmental glomerulosclerosis. - Weng, Patricia L; Majmundar, Amar J; Khan, Kamal; Lim, Tze Y; Shril, Shirlee; Jin, Gina; Musgrove, John; Wang, Minxian; Ahram, Dina F; Aggarwal, Vimla S; Bier, Louise E; Heinzen, Erin L; et al. (Am J Hum Genet, 2021)
Focal segmental glomerulosclerosis (FSGS) is the main pathology underlying steroid-resistant nephrotic syndrome (SRNS) and a leading cause of chronic kidney disease. Monogenic forms of pediatric SRNS are predominantly caused by recessive mutations, while the contribution of de novo variants (DNVs) to this trait is poorly understood. Using exome sequencing (ES) in a proband with FSGS/SRNS, developmental delay, and epilepsy, we discovered a nonsense DNV in TRIM8, which encodes the E3 ubiquitin ligase tripartite motif containing 8. To establish whether TRIM8 variants represent a cause of FSGS, we aggregated exome/genome-sequencing data for 2,501 pediatric FSGS/SRNS-affected individuals and 48,556 control subjects, detecting eight heterozygous TRIM8 truncating variants in affected subjects but none in control subjects (p = 3.28 × 10). In all six cases with available parental DNA, we demonstrated de novo inheritance (p = 2.21 × 10). Reverse phenotyping revealed neurodevelopmental disease in all eight families. We next analyzed ES from 9,067 individuals with epilepsy, yielding three additional families with truncating TRIM8 variants. Clinical review revealed FSGS in all. All TRIM8 variants cause protein truncation clustering within the last exon between residues 390 and 487 of the 551 amino acid protein, indicating a correlation between this syndrome and loss of the TRIM8 C-terminal region. Wild-type TRIM8 overexpressed in immortalized human podocytes and neuronal cells localized to nuclear bodies, while constructs harboring patient-specific variants mislocalized diffusely to the nucleoplasm. Co-localization studies demonstrated that Gemini and Cajal bodies frequently abut a TRIM8 nuclear body. Truncating TRIM8 DNVs cause a neuro-renal syndrome via aberrant TRIM8 localization, implicating nuclear bodies in FSGS and developmental brain disease.
Keywords: Adult; Animals; Carrier Proteins; Cell Line; Child; Child, Preschool; Codon, Nonsense; Developmental Disabilities; Epilepsy; Female; Glomerulosclerosis, Focal Segmental; Humans; Intranuclear Space; Kidney; Male; Mice; Mutation; Nephrotic Syndrome; Nerve Tissue Proteins; Phenotype; Podocytes; Whole Exome Sequencing

Deforming Polyarthritis in a North Indian Family-Clinical Expansion of STING-Associated Vasculopathy with Onset in Infancy (SAVI). - Anjani, Gummadi; Jindal, Ankur Kumar; Prithvi, Ashwini; Kaur, Anit; Rawat, Amit; Sharma, Madhubala; Yuan, Bo; Chinn, Ivan K; Singh, Surjit (J Clin Immunol, 2021)

Deletion of CTCF sites in the SHH locus alters enhancer-promoter interactions and leads to acheiropodia. - Ushiki, Aki; Zhang, Yichi; Xiong, Chenling; Zhao, Jingjing; Georgakopoulos-Soares, Ilias; Kane, Lauren; Jamieson, Kirsty; Bamshad, Michael J; Nickerson, Deborah A; Shen, Yin; Lettice, Laura A; Silveira-Lucas, Elizabeth Lemos; et al. (Nat Commun, 2021)
Acheiropodia, congenital limb truncation, is associated with homozygous deletions in the LMBR1 gene around ZRS, an enhancer regulating SHH during limb development. How these deletions lead to this phenotype is unknown. Using whole-genome sequencing, we fine-mapped the acheiropodia-associated region to 12 kb and show that it does not function as an enhancer. CTCF and RAD21 ChIP-seq together with 4C-seq and DNA FISH identify three CTCF sites within the acheiropodia-deleted region that mediate the interaction between the ZRS and the SHH promoter. This interaction is substituted with other CTCF sites centromeric to the ZRS in the disease state. Mouse knockouts of the orthologous 12 kb sequence have no apparent abnormalities, showcasing the challenges in modelling CTCF alterations in animal models due to inherent motif differences between species. Our results show that alterations in CTCF motifs can lead to a Mendelian condition due to altered enhancer-promoter interactions.
Keywords: Animals; Binding Sites; CCCTC-Binding Factor; Chromatin Immunoprecipitation Sequencing; Disease Models, Animal; Embryo, Mammalian; Enhancer Elements, Genetic; Exons; Extremities; Female; Foot Deformities, Congenital; Gene Expression Regulation, Developmental; Genetic Loci; Genetic Testing; Hand Deformities, Congenital; Hedgehog Proteins; Humans; Introns; Male; Membrane Proteins; Mice; Mice, Knockout; Promoter Regions, Genetic; Sequence Deletion; Species Specificity; Whole Genome Sequencing

Diagnostic yield and clinical impact of exome sequencing in early-onset scoliosis (EOS). - Zhao, Sen; Zhang, Yuanqiang; Chen, Weisheng; Li, Weiyu; Wang, Shengru; Wang, Lianlei; Zhao, Yanxue; Lin, Mao; Ye, Yongyu; Lin, Jiachen; Zheng, Yu; Liu, Jiaqi; et al. (J Med Genet, 2021)
BACKGROUND: Early-onset scoliosis (EOS), defined by an onset age of scoliosis less than 10 years, conveys significant health risk to affected children. Identification of the molecular aetiology underlying patients with EOS could provide valuable information for both clinical management and prenatal screening. METHODS: In this study, we consecutively recruited a cohort of 447 Chinese patients with operative EOS. We performed exome sequencing (ES) screening on these individuals and their available family members (totaling 670 subjects). Another cohort of 13 patients with idiopathic early-onset scoliosis (IEOS) from the USA who underwent ES was also recruited. RESULTS: After ES data processing and variant interpretation, we detected molecular diagnostic variants in 92 out of 447 (20.6%) Chinese patients with EOS, including 8 patients with molecular confirmation of their clinical diagnosis and 84 patients with molecular diagnoses of previously unrecognised diseases underlying scoliosis. One out of 13 patients with IEOS from the US cohort was molecularly diagnosed. The age at presentation, the number of organ systems involved and the Cobb angle were the three top features predictive of a molecular diagnosis. CONCLUSION: ES enabled the molecular diagnosis/classification of patients with EOS. Specific clinical features/feature pairs are able to indicate the likelihood of gaining a molecular diagnosis through ES.

A DNA repair disorder caused by de novo monoallelic DDB1 variants is associated with a neurodevelopmental syndrome. - White, Susan M; Bhoj, Elizabeth; Nellaker, Christoffer; Lachmeijer, Augusta M A; Marshall, Aren E; Boycott, Kym M; Li, Dong; Smith, Wendy; Hartley, Taila; McBride, Arran; Ernst, Michelle E; May, Alison S; et al. (Am J Hum Genet, 2021)
The DNA damage-binding protein 1 (DDB1) is part of the CUL4-DDB1 ubiquitin E3 ligase complex (CRL4), which is essential for DNA repair, chromatin remodeling, DNA replication, and signal transduction. Loss-of-function variants in genes encoding the complex components CUL4 and PHIP have been reported to cause syndromic intellectual disability with hypotonia and obesity, but no phenotype has been reported in association with DDB1 variants. Here, we report eight unrelated individuals, identified through Matchmaker Exchange, with de novo monoallelic variants in DDB1, including one recurrent variant in four individuals. The affected individuals have a consistent phenotype of hypotonia, mild to moderate intellectual disability, and similar facies, including horizontal or slightly bowed eyebrows, deep-set eyes, full cheeks, a short nose, and large, fleshy and forward-facing earlobes, demonstrated in the composite face generated from the cohort. Digital anomalies, including brachydactyly and syndactyly, were common. Three older individuals have obesity. We show that cells derived from affected individuals have altered DDB1 function resulting in abnormal DNA damage signatures and histone methylation following UV-induced DNA damage. Overall, our study adds to the growing family of neurodevelopmental phenotypes mediated by disruption of the CRL4 ubiquitin ligase pathway and begins to delineate the phenotypic and molecular effects of DDB1 misregulation.
Keywords: Adolescent; Alleles; Child; Child, Preschool; DNA Repair; DNA-Binding Proteins; Female; Humans; Male; Mutation; Neurodevelopmental Disorders; Phenotype; Syndrome

Dominant mitochondrial membrane protein-associated neurodegeneration (MPAN) variants cluster within a specific C19orf12 isoform. - Rickman, Olivia J; Salter, Claire G; Gunning, Adam C; Fasham, James; Voutsina, Nikol; Leslie, Joseph S; McGavin, Lucy; Cross, Harold E; Posey, Jennifer E; Akdemir, Zeynep Coban; Jhangiani, Shalini N; Lupski, James R; et al. (Parkinsonism Relat Disord, 2021)
Mitochondria membrane protein-associated neurodegeneration (MPAN) neurodegenerative disorder is typically associated with biallelic C19orf12 variants. Here we describe a new and review candidate previous monoallelic de novo C19orf12 variants to define loss of function mutations located in the putative non-membrane spanning C19orf12 isoform as the potential basis of monoallelic MPAN.

Exome sequencing reveals predominantly de novo variants in disorders with intellectual disability (ID) in the founder population of Finland. - Järvelä, Irma; Määttä, Tuomo; Acharya, Anushree; Leppälä, Juha; Jhangiani, Shalini N; Arvio, Maria; Siren, Auli; Kankuri-Tammilehto, Minna; Kokkonen, Hannaleena; Palomäki, Maarit; Varilo, Teppo; Fang, Mary; et al. (Hum Genet, 2021)
The genetics of autosomal recessive intellectual disability (ARID) has mainly been studied in consanguineous families, however, founder populations may also be of interest to study intellectual disability (ID) and the contribution of ARID. Here, we used a genotype-driven approach to study the genetic landscape of ID in the founder population of Finland. A total of 39 families with syndromic and non-syndromic ID were analyzed using exome sequencing, which revealed a variant in a known ID gene in 27 families. Notably, 75% of these variants in known ID genes were de novo or suspected de novo (64% autosomal dominant; 11% X-linked) and 25% were inherited (14% autosomal recessive; 7% X-linked; and 4% autosomal dominant). A dual molecular diagnosis was suggested in two families (5%). Via additional analysis and molecular testing, we identified three cases with an abnormal molecular karyotype, including chr21q22.12q22.2 uniparental disomy with a mosaic interstitial 2.7 Mb deletion covering DYRK1A and KCNJ6. Overall, a pathogenic or likely pathogenic variant was identified in 64% (25/39) of the families. Last, we report an alternate inheritance model for 3 known ID genes (UBA7, DDX47, DHX58) and discuss potential candidate genes for ID, including SYPL1 and ERGIC3 with homozygous founder variants and de novo variants in POLR2F and DNAH3. In summary, similar to other European populations, de novo variants were the most common variants underlying ID in the studied Finnish population, with limited contribution of ARID to ID etiology, though mainly driven by founder and potential founder variation in the latter case.

Exome-wide rare variant analysis in familial essential tremor. - Diez-Fairen, Monica; Houle, Gabrielle; Ortega-Cubero, Sara; Bandres-Ciga, Sara; Alvarez, Ignacio; Carcel, Maria; Ibañez, Laura; Fernandez, Maria Victoria; Budde, John P; Trotta, Jean-Rémi; Tonda, Raúl; Chong, Jessica X; et al. (Parkinsonism Relat Disord, 2021)
INTRODUCTION: Essential tremor (ET) is one of the most common movement disorders. Despite its high prevalence and heritability, its genetic etiology remains elusive with only a few susceptibility genes identified and poorly replicated. Our aim was to find novel candidate genes involved in ET predisposition through whole exome sequencing. METHODS: We studied eight multigenerational families (N = 40 individuals) with an autosomal-dominant inheritance using a comprehensive strategy combining whole exome sequencing followed by case-control association testing of prioritized variants in a separate cohort comprising 521 ET cases and 596 controls. We further performed gene-based burden analyses in an additional dataset comprising 789 ET patients and 770 healthy individuals to investigate whether there was an enrichment of rare deleterious variants within our candidate genes. RESULTS: Fifteen variants co-segregated with disease status in at least one of the families, among which rs749875462 in CCDC183, rs535864157 in MMP10 and rs114285050 in GPR151 showed a nominal association with ET. However, we found no significant enrichment of rare variants within these genes in cases compared with controls. Interestingly, MMP10 protein is involved in the inflammatory response to neuronal damage and has been previously associated with other neurological disorders. CONCLUSIONS: We prioritized a set of promising genes, especially MMP10, for further genetic and functional studies in ET. Our study suggests that rare deleterious coding variants that markedly increase susceptibility to ET are likely to be found in many genes. Future studies are needed to replicate and further infer biological mechanisms and potential disease causality for our identified genes.

Genetic and non-genetic factors affecting the expression of COVID-19-relevant genes in the large airway epithelium. - Kasela, Silva; Ortega, Victor E; Martorella, Molly; Garudadri, Suresh; Nguyen, Jenna; Ampleford, Elizabeth; Pasanen, Anu; Nerella, Srilaxmi; Buschur, Kristina L; Barjaktarevic, Igor Z; Barr, R Graham; Bleecker, Eugene R; et al. (Genome Med, 2021)
BACKGROUND: The large airway epithelial barrier provides one of the first lines of defense against respiratory viruses, including SARS-CoV-2 that causes COVID-19. Substantial inter-individual variability in individual disease courses is hypothesized to be partially mediated by the differential regulation of the genes that interact with the SARS-CoV-2 virus or are involved in the subsequent host response. Here, we comprehensively investigated non-genetic and genetic factors influencing COVID-19-relevant bronchial epithelial gene expression. METHODS: We analyzed RNA-sequencing data from bronchial epithelial brushings obtained from uninfected individuals. We related ACE2 gene expression to host and environmental factors in the SPIROMICS cohort of smokers with and without chronic obstructive pulmonary disease (COPD) and replicated these associations in two asthma cohorts, SARP and MAST. To identify airway biology beyond ACE2 binding that may contribute to increased susceptibility, we used gene set enrichment analyses to determine if gene expression changes indicative of a suppressed airway immune response observed early in SARS-CoV-2 infection are also observed in association with host factors. To identify host genetic variants affecting COVID-19 susceptibility in SPIROMICS, we performed expression quantitative trait (eQTL) mapping and investigated the phenotypic associations of the eQTL variants. RESULTS: We found that ACE2 expression was higher in relation to active smoking, obesity, and hypertension that are known risk factors of COVID-19 severity, while an association with interferon-related inflammation was driven by the truncated, non-binding ACE2 isoform. We discovered that expression patterns of a suppressed airway immune response to early SARS-CoV-2 infection, compared to other viruses, are similar to patterns associated with obesity, hypertension, and cardiovascular disease, which may thus contribute to a COVID-19-susceptible airway environment. eQTL mapping identified regulatory variants for genes implicated in COVID-19, some of which had pheWAS evidence for their potential role in respiratory infections. CONCLUSIONS: These data provide evidence that clinically relevant variation in the expression of COVID-19-related genes is associated with host factors, environmental exposures, and likely host genetic variation.
Keywords: Adult; Aged; Aged, 80 and over; Angiotensin-Converting Enzyme 2; Asthma; Bronchi; Cardiovascular Diseases; COVID-19; Gene Expression; Genetic Variation; Humans; Middle Aged; Obesity; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; Respiratory Mucosa; Risk Factors; SARS-CoV-2; Smoking

Germline mutation in : a heterogeneous, multi-systemic developmental disorder characterized by transcriptional dysregulation. - Hansen, Adam W; Arora, Payal; Khayat, Michael M; Smith, Leah J; Lewis, Andrea M; Rossetti, Linda Z; Jayaseelan, Joy; Cristian, Ingrid; Haynes, Devon; DiTroia, Stephanie; Meeks, Naomi; Delgado, Mauricio R; et al. (HGG Adv, 2021)
germline variation in was recently reported to associate with a neurodevelopmental disorder. We report twelve individuals harboring putatively pathogenic or inherited variants in , detail their phenotypes, and map all known variants to the domain structure of and crystal structure of RNA polymerase II. Affected individuals were ascertained from a local data lake, pediatric genetics clinic, and an online community of families of affected individuals. These include six affected by missense variants (including one previously reported individual), four clinical laboratory samples affected by missense variation with unknown inheritance-with yeast functional assays further supporting altered function-one affected by a in-frame deletion, and one affected by a C-terminal frameshift variant inherited from a largely asymptomatic mother. Recurrently observed phenotypes include ataxia, joint hypermobility, short stature, skin abnormalities, congenital cardiac abnormalities, immune system abnormalities, hip dysplasia, and short Achilles tendons. We report a significantly higher occurrence of epilepsy (8/12, 66.7%) than previously reported (3/15, 20%) (p value = 0.014196; chi-square test) and a lower occurrence of hypotonia (8/12, 66.7%) than previously reported (14/15, 93.3%) (p value = 0.076309). -related developmental disorders likely represent a spectrum of related, multi-systemic developmental disorders, driven by distinct mechanisms, converging at a single locus.

GIMAP5 maintains liver endothelial cell homeostasis and prevents portal hypertension. - Drzewiecki, Kaela; Choi, Jungmin; Brancale, Joseph; Leney-Greene, Michael A; Sari, Sinan; Dalgiç, Buket; Ünlüsoy Aksu, Aysel; Evirgen Şahin, Gülseren; Ozen, Ahmet; Baris, Safa; Karakoc-Aydiner, Elif; Jain, Dhanpat; et al. (J Exp Med, 2021)
Portal hypertension is a major contributor to decompensation and death from liver disease, a global health problem. Here, we demonstrate homozygous damaging mutations in GIMAP5, a small organellar GTPase, in four families with unexplained portal hypertension. We show that GIMAP5 is expressed in hepatic endothelial cells and that its loss in both humans and mice results in capillarization of liver sinusoidal endothelial cells (LSECs); this effect is also seen when GIMAP5 is selectively deleted in endothelial cells. Single-cell RNA-sequencing analysis in a GIMAP5-deficient mouse model reveals replacement of LSECs with capillarized endothelial cells, a reduction of macrovascular hepatic endothelial cells, and places GIMAP5 upstream of GATA4, a transcription factor required for LSEC specification. Thus, GIMAP5 is a critical regulator of liver endothelial cell homeostasis and, when absent, produces portal hypertension. These findings provide new insight into the pathogenesis of portal hypertension, a major contributor to morbidity and mortality from liver disease.

Identification of Required Host Factors for SARS-CoV-2 Infection in Human Cells. - Daniloski, Zharko; Jordan, Tristan X; Wessels, Hans-Hermann; Hoagland, Daisy A; Kasela, Silva; Legut, Mateusz; Maniatis, Silas; Mimitou, Eleni P; Lu, Lu; Geller, Evan; Danziger, Oded; Rosenberg, Brad R; et al. (Cell, 2021)
To better understand host-virus genetic dependencies and find potential therapeutic targets for COVID-19, we performed a genome-scale CRISPR loss-of-function screen to identify host factors required for SARS-CoV-2 viral infection of human alveolar epithelial cells. Top-ranked genes cluster into distinct pathways, including the vacuolar ATPase proton pump, Retromer, and Commander complexes. We validate these gene targets using several orthogonal methods such as CRISPR knockout, RNA interference knockdown, and small-molecule inhibitors. Using single-cell RNA-sequencing, we identify shared transcriptional changes in cholesterol biosynthesis upon loss of top-ranked genes. In addition, given the key role of the ACE2 receptor in the early stages of viral entry, we show that loss of RAB7A reduces viral entry by sequestering the ACE2 receptor inside cells. Overall, this work provides a genome-scale, quantitative resource of the impact of the loss of each host gene on fitness/response to viral infection.
Keywords: A549 Cells; Alveolar Epithelial Cells; Angiotensin-Converting Enzyme 2; Biosynthetic Pathways; Cholesterol; Clustered Regularly Interspaced Short Palindromic Repeats; COVID-19; Endosomes; Gene Expression Profiling; Gene Knockdown Techniques; Gene Knockout Techniques; Genome-Wide Association Study; Host-Pathogen Interactions; Humans; rab GTP-Binding Proteins; RNA Interference; SARS-CoV-2; Single-Cell Analysis; Viral Load

Inhibition of HECT E3 ligases as potential therapy for COVID-19. - Novelli, Giuseppe; Liu, Jing; Biancolella, Michela; Alonzi, Tonino; Novelli, Antonio; Patten, J J; Cocciadiferro, Dario; Agolini, Emanuele; Colona, Vito Luigi; Rizzacasa, Barbara; Giannini, Rosalinda; Bigio, Benedetta; et al. (Cell Death Dis, 2021)
SARS-CoV-2 is responsible for the ongoing world-wide pandemic which has already taken more than two million lives. Effective treatments are urgently needed. The enzymatic activity of the HECT-E3 ligase family members has been implicated in the cell egression phase of deadly RNA viruses such as Ebola through direct interaction of its VP40 Protein. Here we report that HECT-E3 ligase family members such as NEDD4 and WWP1 interact with and ubiquitylate the SARS-CoV-2 Spike protein. Furthermore, we find that HECT family members are overexpressed in primary samples derived from COVID-19 infected patients and COVID-19 mouse models. Importantly, rare germline activating variants in the NEDD4 and WWP1 genes are associated with severe COVID-19 cases. Critically, I3C, a natural NEDD4 and WWP1 inhibitor from Brassicaceae, displays potent antiviral effects and inhibits viral egression. In conclusion, we identify the HECT family members of E3 ligases as likely novel biomarkers for COVID-19, as well as new potential targets of therapeutic strategy easily testable in clinical trials in view of the established well-tolerated nature of the Brassicaceae natural compounds.
Keywords: Adult; Aged; Animals; Antiviral Agents; Chlorocebus aethiops; COVID-19; Endosomal Sorting Complexes Required for Transport; Female; Humans; Indoles; Male; Mice; Mice, Inbred BALB C; Middle Aged; Nedd4 Ubiquitin Protein Ligases; SARS-CoV-2; Spike Glycoprotein, Coronavirus; Ubiquitin-Protein Ligases; Ubiquitination; Vero Cells

Loss of function mutations in GEMIN5 cause a neurodevelopmental disorder. - Kour, Sukhleen; Rajan, Deepa S; Fortuna, Tyler R; Anderson, Eric N; Ward, Caroline; Lee, Youngha; Lee, Sangmoon; Shin, Yong Beom; Chae, Jong-Hee; Choi, Murim; Siquier, Karine; Cantagrel, Vincent; et al. (Nat Commun, 2021)
GEMIN5, an RNA-binding protein is essential for assembly of the survival motor neuron (SMN) protein complex and facilitates the formation of small nuclear ribonucleoproteins (snRNPs), the building blocks of spliceosomes. Here, we have identified 30 affected individuals from 22 unrelated families presenting with developmental delay, hypotonia, and cerebellar ataxia harboring biallelic variants in the GEMIN5 gene. Mutations in GEMIN5 perturb the subcellular distribution, stability, and expression of GEMIN5 protein and its interacting partners in patient iPSC-derived neurons, suggesting a potential loss-of-function mechanism. GEMIN5 mutations result in disruption of snRNP complex assembly formation in patient iPSC neurons. Furthermore, knock down of rigor mortis, the fly homolog of human GEMIN5, leads to developmental defects, motor dysfunction, and a reduced lifespan. Interestingly, we observed that GEMIN5 variants disrupt a distinct set of transcripts and pathways as compared to SMA patient neurons, suggesting different molecular pathomechanisms. These findings collectively provide evidence that pathogenic variants in GEMIN5 perturb physiological functions and result in a neurodevelopmental delay and ataxia syndrome.
Keywords: Alleles; Amino Acid Sequence; Animals; Child, Preschool; Developmental Disabilities; Drosophila; Female; Gene Expression Regulation, Developmental; Gene Knockdown Techniques; Gene Ontology; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Loss of Function Mutation; Male; Muscle Hypotonia; Myoclonic Cerebellar Dyssynergia; Neurodevelopmental Disorders; Neurons; Pedigree; Polymorphism, Single Nucleotide; Ribonucleoproteins, Small Nuclear; Rigor Mortis; RNA-Seq; SMN Complex Proteins

MED27 Variants Cause Developmental Delay, Dystonia, and Cerebellar Hypoplasia. - Meng, Linyan; Isohanni, Pirjo; Shao, Yunru; GrAHm, Brett H; Hickey, Scott E; Brooks, Stephanie; Suomalainen, Anu; Joset, Pascal; Steindl, Katharina; Rauch, Anita; Hackenberg, Annette; High, Frances A; et al. (Ann Neurol, 2021)
The Mediator multiprotein complex functions as a regulator of RNA polymerase II-catalyzed gene transcription. In this study, exome sequencing detected biallelic putative disease-causing variants in MED27, encoding Mediator complex subunit 27, in 16 patients from 11 families with a novel neurodevelopmental syndrome. Patient phenotypes are highly homogeneous, including global developmental delay, intellectual disability, axial hypotonia with distal spasticity, dystonic movements, and cerebellar hypoplasia. Seizures and cataracts were noted in severely affected individuals. Identification of multiple patients with biallelic MED27 variants supports the critical role of MED27 in normal human neural development, particularly for the cerebellum. ANN NEUROL 2021;89:828-833.
Keywords: Adolescent; Adult; Amino Acid Sequence; Cataract; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Dystonia; Epilepsy; Genetic Variation; Humans; Infant; Mediator Complex; Nervous System Malformations; Phenotype; Whole Exome Sequencing

Mutations in Spliceosomal Genes PPIL1 and PRP17 Cause Neurodegenerative Pontocerebellar Hypoplasia with Microcephaly. - Chai, Guoliang; Webb, Alice; Li, Chen; Antaki, Danny; Lee, Sangmoon; Breuss, Martin W; Lang, Nhi; Stanley, Valentina; Anzenberg, Paula; Yang, Xiaoxu; Marshall, Trevor; Gaffney, Patrick; et al. (Neuron, 2021)
Autosomal-recessive cerebellar hypoplasia and ataxia constitute a group of heterogeneous brain disorders caused by disruption of several fundamental cellular processes. Here, we identified 10 families showing a neurodegenerative condition involving pontocerebellar hypoplasia with microcephaly (PCHM). Patients harbored biallelic mutations in genes encoding the spliceosome components Peptidyl-Prolyl Isomerase Like-1 (PPIL1) or Pre-RNA Processing-17 (PRP17). Mouse knockouts of either gene were lethal in early embryogenesis, whereas PPIL1 patient mutation knockin mice showed neuron-specific apoptosis. Loss of either protein affected splicing integrity, predominantly affecting short and high GC-content introns and genes involved in brain disorders. PPIL1 and PRP17 form an active isomerase-substrate interaction, but we found that isomerase activity is not critical for function. Thus, we establish disrupted splicing integrity and "major spliceosome-opathies" as a new mechanism underlying PCHM and neurodegeneration and uncover a non-enzymatic function of a spliceosomal proline isomerase.
Keywords: Amino Acid Sequence; Animals; Cell Cycle Proteins; Cerebellar Diseases; Cohort Studies; Female; Gene Knockout Techniques; HEK293 Cells; Heredodegenerative Disorders, Nervous System; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microcephaly; Mutation; Pedigree; Peptidylprolyl Isomerase; Protein Structure, Secondary; Protein Structure, Tertiary; RNA Splicing Factors; Spliceosomes

Neurodevelopmental disorder in an Egyptian family with a biallelic ALKBH8 variant. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Du, Haowei; Rafat, Karima; Fatih, Jawid M; Jhangiani, Shalini N; Coban-Akdemir, Zeynep; Gibbs, Richard A; Pehlivan, Davut; Hunter, Jill V; Posey, Jennifer E; et al. (Am J Med Genet A, 2021)
Alkylated DNA repair protein AlkB homolog 8 (ALKBH8) is a member of the AlkB family of dioxygenases. ALKBH8 is a methyltransferase of the highly variable wobble nucleoside position in the anticodon loop of tRNA and thus plays a critical role in tRNA modification by preserving codon recognition and preventing errors in amino acid incorporation during translation. Moreover, its activity catalyzes uridine modifications that are proposed to be critical for accurate protein translation. Previously, two distinct homozygous truncating variants in the final exon of ALKBH8 were described in two unrelated large Saudi Arabian kindreds with intellectual developmental disorder and autosomal recessive 71 (MRT71) syndrome (MIM# 618504). Here, we report a third family-of Egyptian descent-harboring a novel homozygous frame-shift variant in the last exon of ALKBH8. Two affected siblings in this family exhibit global developmental delay and intellectual disability as shared characteristic features of MRT71 syndrome, and we further characterize their observed dysmorphic features and brain MRI findings. This description of a third family with a truncating ALKBH8 variant from a distinct population broadens the phenotypic and genotypic spectrum of MRT71 syndrome, affirms that perturbations in tRNA biogenesis can contribute to neurogenetic disease traits, and firmly establishes ALKBH8 as a novel neurodevelopmental disease gene.

A novel homozygous SLC13A5 whole-gene deletion generated by Alu/Alu-mediated rearrangement in an Iraqi family with epileptic encephalopathy. - Duan, Ruizhi; Saadi, Nebal Waill; Grochowski, Christopher M; Bhadila, Ghalia; Faridoun, Afnan; Mitani, Tadahiro; Du, Haowei; Fatih, Jawid M; Jhangiani, Shalini N; Akdemir, Zeynep C; Gibbs, Richard A; Pehlivan, Davut; et al. (Am J Med Genet A, 2021)
Biallelic loss-of-function (LoF) of SLC13A5 (solute carrier family 13, member 5) induced deficiency in sodium/citrate transporter (NaCT) causes autosomal recessive developmental epileptic encephalopathy 25 with hypoplastic amelogenesis imperfecta (DEE25; MIM #615905). Many pathogenic SLC13A5 single nucleotide variants (SNVs) and small indels have been described; however, no cases with copy number variants (CNVs) have been sufficiently investigated. We describe a consanguineous Iraqi family harboring an 88.5 kb homozygous deletion including SLC13A5 in Chr17p13.1. The three affected male siblings exhibit neonatal-onset epilepsy with fever-sensitivity, recurrent status epilepticus, global developmental delay/intellectual disability (GDD/ID), and other variable neurological findings as shared phenotypical features of DEE25. Two of the three affected subjects exhibit hypoplastic amelogenesis imperfecta (AI), while the proband shows no evidence of dental abnormalities or AI at 2 years of age with apparently unaffected primary dentition. Characterization of the genomic architecture at this locus revealed evidence for genomic instability generated by an Alu/Alu-mediated rearrangement; confirmed by break-point junction Sanger sequencing. This multiplex family from a distinct population elucidates the phenotypic consequence of complete LoF of SLC13A5 and illustrates the importance of read-depth-based CNV detection in comprehensive exome sequencing analysis to solve cases that otherwise remain molecularly unsolved.

Novel variants in TUBA1A cause congenital fibrosis of the extraocular muscles with or without malformations of cortical brain development. - Jurgens, Julie A; Barry, Brenda J; Lemire, Gabrielle; Chan, Wai-Man; Whitman, Mary C; Shaaban, Sherin; Robson, Caroline D; MacKinnon, Sarah; England, Eleina M; McMillan, Hugh J; Kelly, Christopher; Pratt, Brandon M; et al. (Eur J Hum Genet, 2021)
Variants in multiple tubulin genes have been implicated in neurodevelopmental disorders, including malformations of cortical development (MCD) and congenital fibrosis of the extraocular muscles (CFEOM). Distinct missense variants in the beta-tubulin encoding genes TUBB3 and TUBB2B cause MCD, CFEOM, or both, suggesting substitution-specific mechanisms. Variants in the alpha tubulin-encoding gene TUBA1A have been associated with MCD, but not with CFEOM. Using exome sequencing (ES) and genome sequencing (GS), we identified 3 unrelated probands with CFEOM who harbored novel heterozygous TUBA1A missense variants c.1216C>G, p.(His406Asp); c.467G>A, p.(Arg156His); and c.1193T>G, p.(Met398Arg). MRI revealed small oculomotor-innervated muscles and asymmetrical caudate heads and lateral ventricles with or without corpus callosal thinning. Two of the three probands had MCD. Mutated amino acid residues localize either to the longitudinal interface at which α and β tubulins heterodimerize (Met398, His406) or to the lateral interface at which tubulin protofilaments interact (Arg156), and His406 interacts with the motor domain of kinesin-1. This series of individuals supports TUBA1A variants as a cause of CFEOM and expands our knowledge of tubulinopathies.

Pathogenic deep intronic MTM1 variant activates a pseudo-exon encoding a nonsense codon resulting in severe X-linked myotubular myopathy. - Bryen, Samantha J; Oates, Emily C; Evesson, Frances J; Lu, Jessica K; Waddell, Leigh B; Joshi, Himanshu; Ryan, Monique M; Cummings, Beryl B; McLean, Catriona A; MacArthur, Daniel G; Kornberg, Andrew J; Cooper, Sandra T (Eur J Hum Genet, 2021)
X-linked myotubular myopathy (XLMTM) is a severe congenital myopathy characterised by generalised weakness and respiratory insufficiency. XLMTM is associated with pathogenic variants in MTM1; a gene encoding the lipid phosphatase myotubularin. Whole genome sequencing (WGS) of an exome-negative male proband with severe hypotonia, respiratory insufficiency and centralised nuclei on muscle biopsy identified a deep intronic MTM1 variant NG_008199.1(NM_000252.2):c.1468-577A>G, which strengthened a cryptic 5' splice site (A>G substitution at the +5 position). Muscle RNA sequencing was non-diagnostic due to low read depth. Reverse transcription PCR (RT-PCR) of muscle RNA confirmed the c.1468-577A>G variant activates inclusion of a pseudo-exon encoding a premature stop codon into all detected MTM1 transcripts. Western blot analysis establishes deficiency of myotubularin protein, consistent with the severe XLMTM phenotype. We expand the genotypic spectrum of XLMTM and highlight benefits of screening non-coding regions of MTM1 in male probands with phenotypically concordant XLMTM who remain undiagnosed following exome sequencing.

Perturbations of genes essential for Müllerian duct and Wölffian duct development in Mayer-Rokitansky-Küster-Hauser syndrome. - Chen, Na; Zhao, Sen; Jolly, Angad; Wang, Lianlei; Pan, Hongxin; Yuan, Jian; Chen, Shaoke; Koch, André; Ma, Congcong; Tian, Weijie; Jia, Ziqi; Kang, Jia; et al. (Am J Hum Genet, 2021)
Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) is associated with congenital absence of the uterus, cervix, and the upper part of the vagina; it is a sex-limited trait. Disrupted development of the Müllerian ducts (MD)/Wölffian ducts (WD) through multifactorial mechanisms has been proposed to underlie MRKHS. In this study, exome sequencing (ES) was performed on a Chinese discovery cohort (442 affected subjects and 941 female control subjects) and a replication MRKHS cohort (150 affected subjects of mixed ethnicity from North America, South America, and Europe). Phenotypic follow-up of the female reproductive system was performed on an additional cohort of PAX8-associated congenital hypothyroidism (CH) (n = 5, Chinese). By analyzing 19 candidate genes essential for MD/WD development, we identified 12 likely gene-disrupting (LGD) variants in 7 genes: PAX8 (n = 4), BMP4 (n = 2), BMP7 (n = 2), TBX6 (n = 1), HOXA10 (n = 1), EMX2 (n = 1), and WNT9B (n = 1), while LGD variants in these genes were not detected in control samples (p = 1.27E-06). Interestingly, a sex-limited penetrance with paternal inheritance was observed in multiple families. One additional PAX8 LGD variant from the replication cohort and two missense variants from both cohorts were revealed to cause loss-of-function of the protein. From the PAX8-associated CH cohort, we identified one individual presenting a syndromic condition characterized by CH and MRKHS (CH-MRKHS). Our study demonstrates the comprehensive utilization of knowledge from developmental biology toward elucidating genetic perturbations, i.e., rare pathogenic alleles involving the same loci, contributing to human birth defects.
Keywords: 46, XX Disorders of Sex Development; Adult; Bone Morphogenetic Protein 4; Bone Morphogenetic Protein 7; Codon, Nonsense; Congenital Abnormalities; Female; Genetic Association Studies; Genetic Pleiotropy; Homeobox A10 Proteins; Homeodomain Proteins; Humans; Mullerian Ducts; Mutation; Paternal Inheritance; PAX8 Transcription Factor; Penetrance; T-Box Domain Proteins; Transcription Factors; Wnt Proteins; Wolffian Ducts

Phenotypic and protein localization heterogeneity associated with AHDC1 pathogenic protein-truncating alleles in Xia-Gibbs syndrome. - Khayat, Michael M; Li, He; Chander, Varuna; Hu, Jianhong; Hansen, Adam W; Li, Shoudong; Traynelis, Josh; Shen, Hua; Weissenberger, George; Stossi, Fabio; Johnson, Hannah L; Lupski, James R; et al. (Hum Mutat, 2021)
Xia-Gibbs syndrome (XGS) is a rare Mendelian disease typically caused by de novo stop-gain or frameshift mutations in the AT-hook DNA binding motif containing 1 (AHDC1) gene. Patients usually present in early infancy with hypotonia and developmental delay and later exhibit intellectual disability (ID). The overall presentation is variable, however, and the emerging clinical picture is still evolving. A detailed phenotypic analysis of 34 XGS individuals revealed five core phenotypes (delayed motor milestones, speech delay, low muscle tone, ID, and hypotonia) in more than 80% of individuals and an additional 12 features that occurred more variably. Seizures and scoliosis were more frequently associated with truncations that arise before the midpoint of the protein although the occurrence of most features could not be predicted by the mutation position. Transient expression of wild type and different patient truncated AHDC1 protein forms in human cell lines revealed abnormal patterns of nuclear localization including a diffuse distribution of a short truncated form and nucleolar aggregation in mid-protein truncated forms. Overall, both the occurrence of variable phenotypes and the different distribution of the expressed protein reflect the heterogeneity of this syndrome.

Preexisting autoantibodies to type I IFNs underlie critical COVID-19 pneumonia in patients with APS-1. - Bastard, Paul; Orlova, Elizaveta; Sozaeva, Leila; Lévy, Romain; James, Alyssa; Schmitt, Monica M; Ochoa, Sebastian; Kareva, Maria; Rodina, Yulia; Gervais, Adrian; Le Voyer, Tom; Rosain, Jérémie; et al. (J Exp Med, 2021)
Patients with biallelic loss-of-function variants of AIRE suffer from autoimmune polyendocrine syndrome type-1 (APS-1) and produce a broad range of autoantibodies (auto-Abs), including circulating auto-Abs neutralizing most type I interferons (IFNs). These auto-Abs were recently reported to account for at least 10% of cases of life-threatening COVID-19 pneumonia in the general population. We report 22 APS-1 patients from 21 kindreds in seven countries, aged between 8 and 48 yr and infected with SARS-CoV-2 since February 2020. The 21 patients tested had auto-Abs neutralizing IFN-α subtypes and/or IFN-ω; one had anti-IFN-β and another anti-IFN-ε, but none had anti-IFN-κ. Strikingly, 19 patients (86%) were hospitalized for COVID-19 pneumonia, including 15 (68%) admitted to an intensive care unit, 11 (50%) who required mechanical ventilation, and four (18%) who died. Ambulatory disease in three patients (14%) was possibly accounted for by prior or early specific interventions. Preexisting auto-Abs neutralizing type I IFNs in APS-1 patients confer a very high risk of life-threatening COVID-19 pneumonia at any age.
Keywords: Adolescent; Adult; Autoantibodies; Child; COVID-19; Female; Humans; Interferon Type I; Male; Middle Aged; Pneumonia; Polyendocrinopathies, Autoimmune; SARS-CoV-2; Young Adult

Rapid response to the alpha-1 adrenergic agent phenylephrine in the perioperative period is impacted by genomics and ancestry. - Wenric, Stephane; Jeff, Janina M; Joseph, Thomas; Yee, Muh-Ching; Belbin, Gillian M; Owusu Obeng, Aniwaa; Ellis, Stephen B; Bottinger, Erwin P; Gottesman, Omri; Levin, Matthew A; Kenny, Eimear E (Pharmacogenomics J, 2021)
The emergence of genomic data in biobanks and health systems offers new ways to derive medically important phenotypes, including acute phenotypes occurring during inpatient clinical care. Here we study the genetic underpinnings of the rapid response to phenylephrine, an α1-adrenergic receptor agonist commonly used to treat hypotension during anesthesia and surgery. We quantified this response by extracting blood pressure (BP) measurements 5 min before and after the administration of phenylephrine. Based on this derived phenotype, we show that systematic differences exist between self-reported ancestry groups: European-Americans (EA; n = 1387) have a significantly higher systolic response to phenylephrine than African-Americans (AA; n = 1217) and Hispanic/Latinos (HA; n = 1713) (31.3% increase, p value < 6e-08 and 22.9% increase, p value < 5e-05 respectively), after adjusting for genetic ancestry, demographics, and relevant clinical covariates. We performed a genome-wide association study to investigate genetic factors underlying individual differences in this derived phenotype. We discovered genome-wide significant association signals in loci and genes previously associated with BP measured in ambulatory settings, and a general enrichment of association in these genes. Finally, we discovered two low frequency variants, present at ~1% in EAs and AAs, respectively, where patients carrying one copy of these variants show no phenylephrine response. This work demonstrates our ability to derive a quantitative phenotype suited for comparative statistics and genome-wide association studies from dense clinical and physiological measures captured for managing patients during surgery. We identify genetic variants underlying non response to phenylephrine, with implications for preemptive pharmacogenomic screening to improve safety during surgery.

A relatively common homozygous TRAPPC4 splicing variant is associated with an early-infantile neurodegenerative syndrome. - Ghosh, Shereen G; Scala, Marcello; Beetz, Christian; Helman, Guy; Stanley, Valentina; Yang, Xiaoxu; Breuss, Martin W; Mazaheri, Neda; Selim, Laila; Hadipour, Fatemeh; Pais, Lynn; Stutterd, Chloe A; et al. (Eur J Hum Genet, 2021)
Trafficking protein particle (TRAPP) complexes, which include the TRAPPC4 protein, regulate membrane trafficking between lipid organelles in a process termed vesicular tethering. TRAPPC4 was recently implicated in a recessive neurodevelopmental condition in four unrelated families due to a shared c.454+3A>G splice variant. Here, we report 23 patients from 17 independent families with an early-infantile-onset neurodegenerative presentation, where we also identified the homozygous variant hg38:11:119020256 A>G (NM_016146.5:c.454+3A>G) in TRAPPC4 through exome or genome sequencing. No other clinically relevant TRAPPC4 variants were identified among any of over 10,000 patients with neurodevelopmental conditions. We found the carrier frequency of TRAPPC4 c.454+3A>G was 2.4-5.4 per 10,000 healthy individuals. Affected individuals with the homozygous TRAPPC4 c.454+3A>G variant showed profound psychomotor delay, developmental regression, early-onset epilepsy, microcephaly and progressive spastic tetraplegia. Based upon RNA sequencing, the variant resulted in partial exon 3 skipping and generation of an aberrant transcript owing to use of a downstream cryptic splice donor site, predicting a premature stop codon and nonsense mediated decay. These data confirm the pathogenicity of the TRAPPC4 c.454+3A>G variant, and refine the clinical presentation of TRAPPC4-related encephalopathy.

SARS-CoV-2 induces human plasmacytoid predendritic cell diversification via UNC93B and IRAK4. - Onodi, Fanny; Bonnet-Madin, Lucie; Meertens, Laurent; Karpf, Léa; Poirot, Justine; Zhang, Shen-Ying; Picard, Capucine; Puel, Anne; Jouanguy, Emmanuelle; Zhang, Qian; Le Goff, Jérôme; Molina, Jean-Michel; et al. (J Exp Med, 2021)
Several studies have analyzed antiviral immune pathways in late-stage severe COVID-19. However, the initial steps of SARS-CoV-2 antiviral immunity are poorly understood. Here we have isolated primary SARS-CoV-2 viral strains and studied their interaction with human plasmacytoid predendritic cells (pDCs), a key player in antiviral immunity. We show that pDCs are not productively infected by SARS-CoV-2. However, they efficiently diversified into activated P1-, P2-, and P3-pDC effector subsets in response to viral stimulation. They expressed CD80, CD86, CCR7, and OX40 ligand at levels similar to influenza virus-induced activation. They rapidly produced high levels of interferon-α, interferon-λ1, IL-6, IP-10, and IL-8. All major aspects of SARS-CoV-2-induced pDC activation were inhibited by hydroxychloroquine. Mechanistically, SARS-CoV-2-induced pDC activation critically depended on IRAK4 and UNC93B1, as established using pDC from genetically deficient patients. Overall, our data indicate that human pDC are efficiently activated by SARS-CoV-2 particles and may thus contribute to type I IFN-dependent immunity against SARS-CoV-2 infection.
Keywords: Biomarkers; Cell Plasticity; COVID-19; Cytokines; Dendritic Cells; Host-Pathogen Interactions; Humans; Hydroxychloroquine; Immunomodulation; Immunophenotyping; Inflammation Mediators; Interferon Type I; Interferons; Interleukin-1 Receptor-Associated Kinases; Membrane Transport Proteins; SARS-CoV-2

SARS-CoV-2 induces human plasmacytoid pre-dendritic cell diversification via UNC93B and IRAK4. - Onodi, Fanny; Bonnet-Madin, Lucie; Meertens, Laurent; Karpf, Léa; Poirot, Justine; Zhang, Shen-Ying; Picard, Capucine; Puel, Anne; Jouanguy, Emmanuelle; Zhang, Qian; Le Goff, Jérôme; Molina, Jean-Michel; et al. (bioRxiv, 2021)
Several studies have analyzed antiviral immune pathways in late-stage severe COVID-19. However, the initial steps of SARS-CoV-2 antiviral immunity are poorly understood. Here, we have isolated primary SARS-CoV-2 viral strains, and studied their interaction with human plasmacytoid pre-dendritic cells (pDC), a key player in antiviral immunity. We show that pDC are not productively infected by SARS-CoV-2. However, they efficiently diversified into activated P1-, P2-, and P3-pDC effector subsets in response to viral stimulation. They expressed CD80, CD86, CCR7, and OX40 ligand at levels similar to influenza virus-induced activation. They rapidly produced high levels of interferon-α, interferon-λ1, IL-6, IP-10, and IL-8. All major aspects of SARS-CoV-2-induced pDC activation were inhibited by hydroxychloroquine. Mechanistically, SARS-CoV-2-induced pDC activation critically depended on IRAK4 and UNC93B1, as established using pDC from genetically deficient patients. Overall, our data indicate that human pDC are efficiently activated by SARS-CoV-2 particles and may thus contribute to type I IFN-dependent immunity against SARS-CoV-2 infection.

SPEN haploinsufficiency causes a neurodevelopmental disorder overlapping proximal 1p36 deletion syndrome with an episignature of X chromosomes in females. - Radio, Francesca Clementina; Pang, Kaifang; Ciolfi, Andrea; Levy, Michael A; Hernandez-Garcia, Andres; Pedace, Lucia; Pantaleoni, Francesca; Liu, Zhandong; de Boer, Elke; Jackson, Adam; Bruselles, Alessandro; McConkey, Haley; et al. (Am J Hum Genet, 2021)
Deletion 1p36 (del1p36) syndrome is the most common human disorder resulting from a terminal autosomal deletion. This condition is molecularly and clinically heterogeneous. Deletions involving two non-overlapping regions, known as the distal (telomeric) and proximal (centromeric) critical regions, are sufficient to cause the majority of the recurrent clinical features, although with different facial features and dysmorphisms. SPEN encodes a transcriptional repressor commonly deleted in proximal del1p36 syndrome and is located centromeric to the proximal 1p36 critical region. Here, we used clinical data from 34 individuals with truncating variants in SPEN to define a neurodevelopmental disorder presenting with features that overlap considerably with those of proximal del1p36 syndrome. The clinical profile of this disease includes developmental delay/intellectual disability, autism spectrum disorder, anxiety, aggressive behavior, attention deficit disorder, hypotonia, brain and spine anomalies, congenital heart defects, high/narrow palate, facial dysmorphisms, and obesity/increased BMI, especially in females. SPEN also emerges as a relevant gene for del1p36 syndrome by co-expression analyses. Finally, we show that haploinsufficiency of SPEN is associated with a distinctive DNA methylation episignature of the X chromosome in affected females, providing further evidence of a specific contribution of the protein to the epigenetic control of this chromosome, and a paradigm of an X chromosome-specific episignature that classifies syndromic traits. We conclude that SPEN is required for multiple developmental processes and SPEN haploinsufficiency is a major contributor to a disorder associated with deletions centromeric to the previously established 1p36 critical regions.
Keywords: Adolescent; Autism Spectrum Disorder; Child; Child, Preschool; Chromosome Deletion; Chromosome Disorders; Chromosomes, Human, Pair 1; Chromosomes, Human, X; DNA Methylation; DNA-Binding Proteins; Epigenesis, Genetic; Female; Haploinsufficiency; Humans; Intellectual Disability; Male; Neurodevelopmental Disorders; Phenotype; RNA-Binding Proteins; Young Adult

SVEP1 is a human coronary artery disease locus that promotes atherosclerosis. - Jung, In-Hyuk; Elenbaas, Jared S; Alisio, Arturo; Santana, Katherine; Young, Erica P; Kang, Chul Joo; Kachroo, Puja; Lavine, Kory J; Razani, Babak; Mecham, Robert P; Stitziel, Nathan O (Sci Transl Med, 2021)
A low-frequency variant of sushi, von Willebrand factor type A, EGF, and pentraxin domain-containing protein 1 (SVEP1), an extracellular matrix protein, is associated with risk of coronary disease in humans independent of plasma lipids. Despite a robust statistical association, if and how SVEP1 might contribute to atherosclerosis remained unclear. Here, using Mendelian randomization and complementary mouse models, we provide evidence that SVEP1 promotes atherosclerosis in humans and mice and is expressed by vascular smooth muscle cells (VSMCs) within the atherosclerotic plaque. VSMCs also interact with SVEP1, causing proliferation and dysregulation of key differentiation pathways, including integrin and Notch signaling. Fibroblast growth factor receptor transcription increases in VSMCs interacting with SVEP1 and is further increased by the coronary disease-associated variant p.D2702G. These effects ultimately drive inflammation and promote atherosclerosis. Together, our results suggest that VSMC-derived SVEP1 is a proatherogenic factor and support the concept that pharmacological inhibition of SVEP1 should protect against atherosclerosis in humans.

Two novel bi-allelic KDELR2 missense variants cause osteogenesis imperfecta with neurodevelopmental features. - Efthymiou, Stephanie; Herman, Isabella; Rahman, Fatima; Anwar, Najwa; Maroofian, Reza; Yip, Janice; Mitani, Tadahiro; Calame, Daniel G; Hunter, Jill V; Sutton, V Reid; Yilmaz Gulec, Elif; Duan, Ruizhi; et al. (Am J Med Genet A, 2021)

Variants in GNAI1 cause a syndrome associated with variable features including developmental delay, seizures, and hypotonia. - Muir, Alison M; Gardner, Jennifer F; van Jaarsveld, Richard H; de Lange, Iris M; van der Smagt, Jasper J; Wilson, Golder N; Dubbs, Holly; Goldberg, Ethan M; Zitano, Lia; Bupp, Caleb; Martinez, Jose; Srour, Myriam; et al. (Genet Med, 2021)
PURPOSE: Neurodevelopmental disorders (NDDs) encompass a spectrum of genetically heterogeneous disorders with features that commonly include developmental delay, intellectual disability, and autism spectrum disorders. We sought to delineate the molecular and phenotypic spectrum of a novel neurodevelopmental disorder caused by variants in the GNAI1 gene. METHODS: Through large cohort trio-based exome sequencing and international data-sharing, we identified 24 unrelated individuals with NDD phenotypes and a variant in GNAI1, which encodes the inhibitory Gαi1 subunit of heterotrimeric G-proteins. We collected detailed genotype and phenotype information for each affected individual. RESULTS: We identified 16 unique variants in GNAI1 in 24 affected individuals; 23 occurred de novo and 1 was inherited from a mosaic parent. Most affected individuals have a severe neurodevelopmental disorder. Core features include global developmental delay, intellectual disability, hypotonia, and epilepsy. CONCLUSION: This collaboration establishes GNAI1 variants as a cause of NDDs. GNAI1-related NDD is most often characterized by severe to profound delays, hypotonia, epilepsy that ranges from self-limiting to intractable, behavior problems, and variable mild dysmorphic features.
Keywords: Child; Developmental Disabilities; Humans; Intellectual Disability; Muscle Hypotonia; Neurodevelopmental Disorders; Seizures; Whole Exome Sequencing

Whole-genome sequencing of African Americans implicates differential genetic architecture in inflammatory bowel disease. - Somineni, Hari K; Nagpal, Sini; Venkateswaran, Suresh; Cutler, David J; Okou, David T; Haritunians, Talin; Simpson, Claire L; Begum, Ferdouse; Datta, Lisa W; Quiros, Antonio J; Seminerio, Jenifer; Mengesha, Emebet; et al. (Am J Hum Genet, 2021)
Whether or not populations diverge with respect to the genetic contribution to risk of specific complex diseases is relevant to understanding the evolution of susceptibility and origins of health disparities. Here, we describe a large-scale whole-genome sequencing study of inflammatory bowel disease encompassing 1,774 affected individuals and 1,644 healthy control Americans with African ancestry (African Americans). Although no new loci for inflammatory bowel disease are discovered at genome-wide significance levels, we identify numerous instances of differential effect sizes in combination with divergent allele frequencies. For example, the major effect at PTGER4 fine maps to a single credible interval of 22 SNPs corresponding to one of four independent associations at the locus in European ancestry individuals but with an elevated odds ratio for Crohn disease in African Americans. A rare variant aggregate analysis implicates Ca-binding neuro-immunomodulator CALB2 in ulcerative colitis. Highly significant overall overlap of common variant risk for inflammatory bowel disease susceptibility between individuals with African and European ancestries was observed, with 41 of 241 previously known lead variants replicated and overall correlations in effect sizes of 0.68 for combined inflammatory bowel disease. Nevertheless, subtle differences influence the performance of polygenic risk scores, and we show that ancestry-appropriate weights significantly improve polygenic prediction in the highest percentiles of risk. The median amount of variance explained per locus remains the same in African and European cohorts, providing evidence for compensation of effect sizes as allele frequencies diverge, as expected under a highly polygenic model of disease.
Keywords: African Americans; Aged; Aged, 80 and over; Calbindin 2; Colitis, Ulcerative; Crohn Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inflammatory Bowel Diseases; Male; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Receptors, Prostaglandin E, EP4 Subtype; Whole Genome Sequencing

ASC-1 Is a Cell Cycle Regulator Associated with Severe and Mild Forms of Myopathy. - Villar-Quiles, Rocío N; Catervi, Fabio; Cabet, Eva; Juntas-Morales, Raul; Genetti, Casie A; Gidaro, Teresa; Koparir, Asuman; Yuksel, Adnan; Coppens, Sandra; Deconinck, Nicolas; Pierce-Hoffman, Emma; Lornage, Xavière; et al. (Ann Neurol, 2020)
OBJECTIVE: Recently, the ASC-1 complex has been identified as a mechanistic link between amyotrophic lateral sclerosis and spinal muscular atrophy (SMA), and 3 mutations of the ASC-1 gene TRIP4 have been associated with SMA or congenital myopathy. Our goal was to define ASC-1 neuromuscular function and the phenotypical spectrum associated with TRIP4 mutations. METHODS: Clinical, molecular, histological, and magnetic resonance imaging studies were made in 5 families with 7 novel TRIP4 mutations. Fluorescence activated cell sorting and Western blot were performed in patient-derived fibroblasts and muscles and in Trip4 knocked-down C2C12 cells. RESULTS: All mutations caused ASC-1 protein depletion. The clinical phenotype was purely myopathic, ranging from lethal neonatal to mild ambulatory adult patients. It included early onset axial and proximal weakness, scoliosis, rigid spine, dysmorphic facies, cutaneous involvement, respiratory failure, and in the older cases, dilated cardiomyopathy. Muscle biopsies showed multiminicores, nemaline rods, cytoplasmic bodies, caps, central nuclei, rimmed fibers, and/or mild endomysial fibrosis. ASC-1 depletion in C2C12 and in patient-derived fibroblasts and muscles caused accelerated proliferation, altered expression of cell cycle proteins, and/or shortening of the G0/G1 cell cycle phase leading to cell size reduction. INTERPRETATION: Our results expand the phenotypical and molecular spectrum of TRIP4-associated disease to include mild adult forms with or without cardiomyopathy, associate ASC-1 depletion with isolated primary muscle involvement, and establish TRIP4 as a causative gene for several congenital muscle diseases, including nemaline, core, centronuclear, and cytoplasmic-body myopathies. They also identify ASC-1 as a novel cell cycle regulator with a key role in cell proliferation, and underline transcriptional coregulation defects as a novel pathophysiological mechanism. ANN NEUROL 2020;87:217-232.
Keywords: Adult; Amino Acid Transport System y+; Cell Cycle; Cells, Cultured; Child; Child, Preschool; Female; Fibroblasts; Humans; Infant; Male; Middle Aged; Muscle Proteins; Muscle, Skeletal; Muscular Diseases; Mutation; Pedigree; Phenotype; Transcription Factors

Autoantibodies against type I IFNs in patients with life-threatening COVID-19. - Bastard, Paul; Rosen, Lindsey B; Zhang, Qian; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Zhang, Yu; Dorgham, Karim; Philippot, Quentin; Rosain, Jérémie; Béziat, Vivien; Manry, Jeremy; Shaw, Elana; et al. (Science, 2020)
Interindividual clinical variability in the course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is vast. We report that at least 101 of 987 patients with life-threatening coronavirus disease 2019 (COVID-19) pneumonia had neutralizing immunoglobulin G (IgG) autoantibodies (auto-Abs) against interferon-ω (IFN-ω) (13 patients), against the 13 types of IFN-α (36), or against both (52) at the onset of critical disease; a few also had auto-Abs against the other three type I IFNs. The auto-Abs neutralize the ability of the corresponding type I IFNs to block SARS-CoV-2 infection in vitro. These auto-Abs were not found in 663 individuals with asymptomatic or mild SARS-CoV-2 infection and were present in only 4 of 1227 healthy individuals. Patients with auto-Abs were aged 25 to 87 years and 95 of the 101 were men. A B cell autoimmune phenocopy of inborn errors of type I IFN immunity accounts for life-threatening COVID-19 pneumonia in at least 2.6% of women and 12.5% of men.
Keywords: Adult; Aged; Aged, 80 and over; Antibodies, Neutralizing; Asymptomatic Infections; Autoantibodies; Betacoronavirus; Case-Control Studies; Coronavirus Infections; COVID-19; Critical Illness; Female; Humans; Immunoglobulin G; Interferon alpha-2; Interferon Type I; Male; Middle Aged; Pandemics; Pneumonia, Viral; SARS-CoV-2

Beyond the tubule: pathological variants of , encoding the megalin receptor, result in glomerular loss and early progressive chronic kidney disease. - Charlton, Jennifer R; Tan, Weizhen; Daouk, Ghaleb; Teot, Lisa; Rosen, Seymour; Bennett, Kevin M; Cwiek, Aleksandra; Nam, Sejin; Emma, Francesco; Jouret, François; Oliveira, João Paulo; Tranebjærg, Lisbeth; et al. (Am J Physiol Renal Physiol, 2020)
Pathogenic variants in the gene, encoding the multiligand receptor megalin, cause a rare autosomal recessive syndrome: Donnai-Barrow/Facio-Oculo-Acoustico-Renal (DB/FOAR) syndrome. Because of the rarity of the syndrome, the long-term consequences of the tubulopathy on human renal health have been difficult to ascertain, and the human clinical condition has hitherto been characterized as a benign tubular condition with asymptomatic low-molecular-weight proteinuria. We investigated renal function and morphology in a murine model of DB/FOAR syndrome and in patients with DB/FOAR. We analyzed glomerular filtration rate in mice by FITC-inulin clearance and clinically characterized six families, including nine patients with DB/FOAR and nine family members. Urine samples from patients were analyzed by Western blot analysis and biopsy materials were analyzed by histology. In the mouse model, we used histological methods to assess nephrogenesis and postnatal renal structure and contrast-enhanced magnetic resonance imaging to assess glomerular number. In megalin-deficient mice, we found a lower glomerular filtration rate and an increase in the abundance of injury markers, such as kidney injury molecule-1 and -acetyl-β-d-glucosaminidase. Renal injury was validated in patients, who presented with increased urinary kidney injury molecule-1, classical markers of chronic kidney disease, and glomerular proteinuria early in life. Megalin-deficient mice had normal nephrogenesis, but they had 19% fewer nephrons in early adulthood and an increased fraction of nephrons with disconnected glomerulotubular junction. In conclusion, megalin dysfunction, as present in DB/FOAR syndrome, confers an increased risk of progression into chronic kidney disease.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Kidney Glomerulus; Low Density Lipoprotein Receptor-Related Protein-2; Male; Mice; Mice, Knockout; Middle Aged; Renal Insufficiency, Chronic; Young Adult

Bi-allelic ADARB1 Variants Associated with Microcephaly, Intellectual Disability, and Seizures. - Tan, Tiong Yang; Sedmík, Jiří; Fitzgerald, Mark P; Halevy, Rivka Sukenik; Keegan, Liam P; Helbig, Ingo; Basel-Salmon, Lina; Cohen, Lior; Straussberg, Rachel; Chung, Wendy K; Helal, Mayada; Maroofian, Reza; et al. (Am J Hum Genet, 2020)
The RNA editing enzyme ADAR2 is essential for the recoding of brain transcripts. Impaired ADAR2 editing leads to early-onset epilepsy and premature death in a mouse model. Here, we report bi-allelic variants in ADARB1, the gene encoding ADAR2, in four unrelated individuals with microcephaly, intellectual disability, and epilepsy. In one individual, a homozygous variant in one of the double-stranded RNA-binding domains (dsRBDs) was identified. In the others, variants were situated in or around the deaminase domain. To evaluate the effects of these variants on ADAR2 enzymatic activity, we performed in vitro assays with recombinant proteins in HEK293T cells and ex vivo assays with fibroblasts derived from one of the individuals. We demonstrate that these ADAR2 variants lead to reduced editing activity on a known ADAR2 substrate. We also demonstrate that one variant leads to changes in splicing of ADARB1 transcript isoforms. These findings reinforce the importance of RNA editing in brain development and introduce ADARB1 as a genetic etiology in individuals with intellectual disability, microcephaly, and epilepsy.
Keywords: Adenosine Deaminase; Alleles; Alternative Splicing; Child; Child, Preschool; Genetic Predisposition to Disease; Genetic Variation; HEK293 Cells; Humans; Intellectual Disability; Male; Microcephaly; RNA Splicing; RNA-Binding Proteins; Seizures

Biallelic GRM7 variants cause epilepsy, microcephaly, and cerebral atrophy. - Marafi, Dana; Mitani, Tadahiro; Isikay, Sedat; Hertecant, Jozef; Almannai, Mohammed; Manickam, Kandamurugu; Abou Jamra, Rami; El-Hattab, Ayman W; Rajah, Jaishen; Fatih, Jawid M; Du, Haowei; Karaca, Ender; et al. (Ann Clin Transl Neurol, 2020)
OBJECTIVE: Defects in ion channels and neurotransmitter receptors are implicated in developmental and epileptic encephalopathy (DEE). Metabotropic glutamate receptor 7 (mGluR7), encoded by GRM7, is a presynaptic G-protein-coupled glutamate receptor critical for synaptic transmission. We previously proposed GRM7 as a candidate disease gene in two families with neurodevelopmental disorders (NDDs). One additional family has been published since. Here, we describe three additional families with GRM7 biallelic variants and deeply characterize the associated clinical neurological and electrophysiological phenotype and molecular data in 11 affected individuals from six unrelated families. METHODS: Exome sequencing and family-based rare variant analyses on a cohort of 220 consanguineous families with NDDs revealed three families with GRM7 biallelic variants; three additional families were identified through literature search and collaboration with a clinical molecular laboratory. RESULTS: We compared the observed clinical features and variants of 11 affected individuals from the six unrelated families. Identified novel deleterious variants included two homozygous missense variants (c.2671G>A:p.Glu891Lys and c.1973G>A:p.Arg685Gln) and one homozygous stop-gain variant (c.1975C>T:p.Arg659Ter). Developmental delay, neonatal- or infantile-onset epilepsy, and microcephaly were universal. Three individuals had hypothalamic-pituitary-axis dysfunction without pituitary structural abnormality. Neuroimaging showed cerebral atrophy and hypomyelination in a majority of cases. Two siblings demonstrated progressive loss of myelination by 2 years in both and an acquired microcephaly pattern in one. Five individuals died in early or late childhood. CONCLUSION: Detailed clinical characterization of 11 individuals from six unrelated families demonstrates that rare biallelic GRM7 pathogenic variants can cause DEEs, microcephaly, hypomyelination, and cerebral atrophy.
Keywords: Adolescent; Alleles; Atrophy; Child; Child, Preschool; Cohort Studies; Consanguinity; Epilepsy; Female; Humans; Infant; Male; Microcephaly; Neurodevelopmental Disorders; Pedigree; Phenotype; Receptors, Metabotropic Glutamate; Whole Exome Sequencing

Biallelic in-frame deletion in TRAPPC4 in a family with developmental delay and cerebellar atrophy. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Jolly, Angad; Du, Haowei; Elbendary, Hasnaa M; Jhangiani, Shalini N; Akdemir, Zeynep C; Gibbs, Richard A; Hunter, Jill V; Carvalho, Claudia M B C; Pehlivan, Davut; et al. (Brain, 2020)
Keywords: Atrophy; Cerebellar Diseases; Humans; Intellectual Disability; Sequence Deletion

Biallelic loss of function variants in SYT2 cause a treatable congenital onset presynaptic myasthenic syndrome. - Donkervoort, Sandra; Mohassel, Payam; Laugwitz, Lucia; Zaki, MAH S; Kamsteeg, Erik-Jan; Maroofian, Reza; Chao, Katherine R; Verschuuren-Bemelmans, Corien C; Horber, Veronka; Fock, Annemarie J M; McCarty, Riley M; Jain, Minal S; et al. (Am J Med Genet A, 2020)
Synaptotagmins are integral synaptic vesicle membrane proteins that function as calcium sensors and regulate neurotransmitter release at the presynaptic nerve terminal. Synaptotagmin-2 (SYT2), is the major isoform expressed at the neuromuscular junction. Recently, dominant missense variants in SYT2 have been reported as a rare cause of distal motor neuropathy and myasthenic syndrome, manifesting with stable or slowly progressive distal weakness of variable severity along with presynaptic NMJ impairment. These variants are thought to have a dominant-negative effect on synaptic vesicle exocytosis, although the precise pathomechanism remains to be elucidated. Here we report seven patients of five families, with biallelic loss of function variants in SYT2, clinically manifesting with a remarkably consistent phenotype of severe congenital onset hypotonia and weakness, with variable degrees of respiratory involvement. Electrodiagnostic findings were consistent with a presynaptic congenital myasthenic syndrome (CMS) in some. Treatment with an acetylcholinesterase inhibitor pursued in three patients showed clinical improvement with increased strength and function. This series further establishes SYT2 as a CMS-disease gene and expands its clinical and genetic spectrum to include recessive loss-of-function variants, manifesting as a severe congenital onset presynaptic CMS with potential treatment implications.
Keywords: Adolescent; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Muscle Hypotonia; Muscle Weakness; Mutation, Missense; Myasthenic Syndromes, Congenital; Pedigree; Phenotype; Synaptic Transmission; Synaptotagmin II

Combining Imaging and Genetics to Predict Recurrence of Anticoagulation-Associated Intracerebral Hemorrhage. - Biffi, Alessandro; Urday, Sebastian; Kubiszewski, Patryk; Gilkerson, Lee; Sekar, Padmini; Rodriguez-Torres, Axana; Bettin, Margaret; Charidimou, Andreas; Pasi, Marco; Kourkoulis, Christina; Schwab, Kristin; DiPucchio, Zora; et al. (Stroke, 2020)
BACKGROUND AND PURPOSE: For survivors of oral anticoagulation therapy (OAT)-associated intracerebral hemorrhage (OAT-ICH) who are at high risk for thromboembolism, the benefits of OAT resumption must be weighed against increased risk of recurrent hemorrhagic stroke. The ε2/ε4 alleles of the () gene, MRI-defined cortical superficial siderosis, and cerebral microbleeds are the most potent risk factors for recurrent ICH. We sought to determine whether combining MRI markers and genotype could have clinical impact by identifying ICH survivors in whom the risks of OAT resumption are highest. METHODS: Joint analysis of data from 2 longitudinal cohort studies of OAT-ICH survivors: (1) MGH-ICH study (Massachusetts General Hospital ICH) and (2) longitudinal component of the ERICH study (Ethnic/Racial Variations of Intracerebral Hemorrhage). We evaluated whether MRI markers and genotype predict ICH recurrence. We then developed and validated a combined -MRI classification scheme to predict ICH recurrence, using Classification and Regression Tree analysis. RESULTS: Cortical superficial siderosis, cerebral microbleed, and ε2/ε4 variants were independently associated with ICH recurrence after OAT-ICH (all <0.05). Combining genotype and MRI data resulted in improved prediction of ICH recurrence (Harrell C: 0.79 versus 0.55 for clinical data alone, =0.033). In the MGH (training) data set, CSS, cerebral microbleed, and ε2/ε4 stratified likelihood of ICH recurrence into high-, medium-, and low-risk categories. In the ERICH (validation) data set, yearly ICH recurrence rates for high-, medium-, and low-risk individuals were 6.6%, 2.5%, and 0.9%, respectively, with overall area under the curve of 0.91 for prediction of recurrent ICH. CONCLUSIONS: Combining MRI and genotype stratifies likelihood of ICH recurrence into high, medium, and low risk. If confirmed in prospective studies, this combined -MRI classification scheme may prove useful for selecting individuals for OAT resumption after ICH.
Keywords: Aged; Anticoagulants; Apolipoprotein E4; Cerebral Hemorrhage; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Recurrence

Complex mosaic structural variations in human fetal brains. - Sekar, Shobana; Tomasini, Livia; Proukakis, Christos; Bae, Taejeong; Manlove, Logan; Jang, Yeongjun; Scuderi, Soraya; Zhou, Bo; Kalyva, Maria; Amiri, Anahita; Mariani, Jessica; Sedlazeck, Fritz J; et al. (Genome Res, 2020)
Somatic mosaicism, manifesting as single nucleotide variants (SNVs), mobile element insertions, and structural changes in the DNA, is a common phenomenon in human brain cells, with potential functional consequences. Using a clonal approach, we previously detected 200-400 mosaic SNVs per cell in three human fetal brains (15-21 wk postconception). However, structural variation in the human fetal brain has not yet been investigated. Here, we discover and validate four mosaic structural variants (SVs) in the same brains and resolve their precise breakpoints. The SVs were of kilobase scale and complex, consisting of deletion(s) and rearranged genomic fragments, which sometimes originated from different chromosomes. Sequences at the breakpoints of these rearrangements had microhomologies, suggesting their origin from replication errors. One SV was found in two clones, and we timed its origin to ∼14 wk postconception. No large scale mosaic copy number variants (CNVs) were detectable in normal fetal human brains, suggesting that previously reported megabase-scale CNVs in neurons arise at later stages of development. By reanalysis of public single nuclei data from adult brain neurons, we detected an extrachromosomal circular DNA event. Our study reveals the existence of mosaic SVs in the developing human brain, likely arising from cell proliferation during mid-neurogenesis. Although relatively rare compared to SNVs and present in ∼10% of neurons, SVs in developing human brain affect a comparable number of bases in the genome (∼6200 vs. ∼4000 bp), implying that they may have similar functional consequences.

Congenital diaphragmatic hernia as a prominent feature of a SPECC1L-related syndrome. - Wild, K Taylor; Gordon, Tia; Bhoj, Elizabeth J; Du, Haowei; Jhangiani, Shalini N; Posey, Jennifer E; Lupski, James R; Scott, Daryl A; Zackai, Elaine H (Am J Med Genet A, 2020)
Congenital diaphragmatic hernias (CDH) confer substantial morbidity and mortality. Genetic defects, including chromosomal anomalies, copy number variants, and sequence variants are identified in ~30% of patients with CDH. A genetic etiology is not yet found in 70% of patients, however there is a growing number of genetic syndromes and single gene disorders associated with CDH. While there have been two reported individuals with X-linked Opitz G/BBB syndrome with MID1 mutations who have CDH as an associated feature, CDH appears to be a much more prominent feature of a SPECC1L-related autosomal dominant Opitz G/BBB syndrome. Features unique to autosomal dominant Opitz G/BBB syndrome include branchial fistulae, omphalocele, and a bicornuate uterus. Here we present one new individual and five previously reported individuals with CDH found to have SPECC1L mutations. These cases provide strong evidence that SPECC1L is a bona fide CDH gene. We conclude that a SPECC1L-related Opitz G/BBB syndrome should be considered in any patient with CDH who has additional features of hypertelorism, a prominent forehead, a broad nasal bridge, anteverted nares, cleft lip/palate, branchial fistulae, omphalocele, and/or bicornuate uterus.

Copy number variants and fixed duplications among 198 rhesus macaques (Macaca mulatta). - Brasó-Vives, Marina; Povolotskaya, Inna S; Hartasánchez, Diego A; Farré, Xavier; Fernandez-Callejo, Marcos; Raveendran, Muthuswamy; Harris, R Alan; Rosene, Douglas L; Lorente-Galdos, Belen; Navarro, Arcadi; Marques-Bonet, Tomas; Rogers, Jeffrey; et al. (PLoS Genet, 2020)
The rhesus macaque is an abundant species of Old World monkeys and a valuable model organism for biomedical research due to its close phylogenetic relationship to humans. Copy number variation is one of the main sources of genomic diversity within and between species and a widely recognized cause of inter-individual differences in disease risk. However, copy number differences among rhesus macaques and between the human and macaque genomes, as well as the relevance of this diversity to research involving this nonhuman primate, remain understudied. Here we present a high-resolution map of sequence copy number for the rhesus macaque genome constructed from a dataset of 198 individuals. Our results show that about one-eighth of the rhesus macaque reference genome is composed of recently duplicated regions, either copy number variable regions or fixed duplications. Comparison with human genomic copy number maps based on previously published data shows that, despite overall similarities in the genome-wide distribution of these regions, there are specific differences at the chromosome level. Some of these create differences in the copy number profile between human disease genes and their rhesus macaque orthologs. Our results highlight the importance of addressing the number of copies of target genes in the design of experiments and cautions against human-centered assumptions in research conducted with model organisms. Overall, we present a genome-wide copy number map from a large sample of rhesus macaque individuals representing an important novel contribution concerning the evolution of copy number in primate genomes.
Keywords: Animals; Chromosome Mapping; DNA Copy Number Variations; Female; Gene Duplication; Genetics, Population; Genome; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Open Reading Frames; Phylogeny; Sequence Analysis, DNA; Species Specificity

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder. - Mirzaa, Ghayda M; Chong, Jessica X; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A; Sajan, Samin A; Tang, Sha; et al. (Genet Med, 2020)
PURPOSE: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). METHODS: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype-phenotype relationships. RESULTS: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. CONCLUSION: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Nerve Tissue Proteins; Neurodevelopmental Disorders; Neuroimaging; Whole Exome Sequencing

De novo EIF2AK1 and EIF2AK2 Variants Are Associated with Developmental Delay, Leukoencephalopathy, and Neurologic Decompensation. - Mao, Dongxue; Reuter, Chloe M; Ruzhnikov, Maura R Z; Beck, Anita E; Farrow, Emily G; Emrick, Lisa T; Rosenfeld, Jill A; Mackenzie, Katherine M; Robak, Laurie; Wheeler, Matthew T; Burrage, Lindsay C; Jain, Mahim; et al. (Am J Hum Genet, 2020)
EIF2AK1 and EIF2AK2 encode members of the eukaryotic translation initiation factor 2 alpha kinase (EIF2AK) family that inhibits protein synthesis in response to physiologic stress conditions. EIF2AK2 is also involved in innate immune response and the regulation of signal transduction, apoptosis, cell proliferation, and differentiation. Despite these findings, human disorders associated with deleterious variants in EIF2AK1 and EIF2AK2 have not been reported. Here, we describe the identification of nine unrelated individuals with heterozygous de novo missense variants in EIF2AK1 (1/9) or EIF2AK2 (8/9). Features seen in these nine individuals include white matter alterations (9/9), developmental delay (9/9), impaired language (9/9), cognitive impairment (8/9), ataxia (6/9), dysarthria in probands with verbal ability (6/9), hypotonia (7/9), hypertonia (6/9), and involuntary movements (3/9). Individuals with EIF2AK2 variants also exhibit neurological regression in the setting of febrile illness or infection. We use mammalian cell lines and proband-derived fibroblasts to further confirm the pathogenicity of variants in these genes and found reduced kinase activity. EIF2AKs phosphorylate eukaryotic translation initiation factor 2 subunit 1 (EIF2S1, also known as EIF2α), which then inhibits EIF2B activity. Deleterious variants in genes encoding EIF2B proteins cause childhood ataxia with central nervous system hypomyelination/vanishing white matter (CACH/VWM), a leukodystrophy characterized by neurologic regression in the setting of febrile illness and other stressors. Our findings indicate that EIF2AK2 missense variants cause a neurodevelopmental syndrome that may share phenotypic and pathogenic mechanisms with CACH/VWM.
Keywords: Adolescent; Ataxia; Child; Child, Preschool; Developmental Disabilities; eIF-2 Kinase; Female; Genetic Variation; Hereditary Central Nervous System Demyelinating Diseases; Humans; Infant; Leukoencephalopathies; Male; Nervous System Malformations; White Matter

Defective glycosylation and multisystem abnormalities characterize the primary immunodeficiency XMEN disease. - Ravell, Juan C; Matsuda-Lennikov, Mami; Chauvin, Samuel D; Zou, Juan; Biancalana, Matthew; Deeb, Sally J; Price, Susan; Su, Helen C; Notarangelo, Giulia; Jiang, Ping; Morawski, Aaron; Kanellopoulou, Chrysi; et al. (J Clin Invest, 2020)
X-linked immunodeficiency with magnesium defect, EBV infection, and neoplasia (XMEN) disease are caused by deficiency of the magnesium transporter 1 (MAGT1) gene. We studied 23 patients with XMEN, 8 of whom were EBV naive. We observed lymphadenopathy (LAD), cytopenias, liver disease, cavum septum pellucidum (CSP), and increased CD4-CD8-B220-TCRαβ+ T cells (αβDNTs), in addition to the previously described features of an inverted CD4/CD8 ratio, CD4+ T lymphocytopenia, increased B cells, dysgammaglobulinemia, and decreased expression of the natural killer group 2, member D (NKG2D) receptor. EBV-associated B cell malignancies occurred frequently in EBV-infected patients. We studied patients with XMEN and patients with autoimmune lymphoproliferative syndrome (ALPS) by deep immunophenotyping (32 immune markers) using time-of-flight mass cytometry (CyTOF). Our analysis revealed that the abundance of 2 populations of naive B cells (CD20+CD27-CD22+IgM+HLA-DR+CXCR5+CXCR4++CD10+CD38+ and CD20+CD27-CD22+IgM+HLA-DR+CXCR5+CXCR4+CD10-CD38-) could differentially classify XMEN, ALPS, and healthy individuals. We also performed glycoproteomics analysis on T lymphocytes and show that XMEN disease is a congenital disorder of glycosylation that affects a restricted subset of glycoproteins. Transfection of MAGT1 mRNA enabled us to rescue proteins with defective glycosylation. Together, these data provide new clinical and pathophysiological foundations with important ramifications for the diagnosis and treatment of XMEN disease.
Keywords: Antigens, CD; Autoimmune Lymphoproliferative Syndrome; Cation Transport Proteins; CD4-CD8 Ratio; Female; Glycosylation; Humans; Magnesium Deficiency; Male; X-Linked Combined Immunodeficiency Diseases

Deficiencies in vesicular transport mediated by TRAPPC4 are associated with severe syndromic intellectual disability. - Van Bergen, Nicole J; Guo, Yiran; Al-Deri, Noraldin; Lipatova, Zhanna; Stanga, Daniela; Zhao, Sarah; Murtazina, Rakhilya; Gyurkovska, Valeriya; Pehlivan, Davut; Mitani, Tadahiro; Gezdirici, Alper; Antony, Jayne; et al. (Brain, 2020)
The conserved transport protein particle (TRAPP) complexes regulate key trafficking events and are required for autophagy. TRAPPC4, like its yeast Trs23 orthologue, is a core component of the TRAPP complexes and one of the essential subunits for guanine nucleotide exchange factor activity for Rab1 GTPase. Pathogenic variants in specific TRAPP subunits are associated with neurological disorders. We undertook exome sequencing in three unrelated families of Caucasian, Turkish and French-Canadian ethnicities with seven affected children that showed features of early-onset seizures, developmental delay, microcephaly, sensorineural deafness, spastic quadriparesis and progressive cortical and cerebellar atrophy in an effort to determine the genetic aetiology underlying neurodevelopmental disorders. All seven affected subjects shared the same identical rare, homozygous, potentially pathogenic variant in a non-canonical, well-conserved splice site within TRAPPC4 (hg19:chr11:g.118890966A>G; TRAPPC4: NM_016146.5; c.454+3A>G). Single nucleotide polymorphism array analysis revealed there was no haplotype shared between the tested Turkish and Caucasian families suggestive of a variant hotspot region rather than a founder effect. In silico analysis predicted the variant to cause aberrant splicing. Consistent with this, experimental evidence showed both a reduction in full-length transcript levels and an increase in levels of a shorter transcript missing exon 3, suggestive of an incompletely penetrant splice defect. TRAPPC4 protein levels were significantly reduced whilst levels of other TRAPP complex subunits remained unaffected. Native polyacrylamide gel electrophoresis and size exclusion chromatography demonstrated a defect in TRAPP complex assembly and/or stability. Intracellular trafficking through the Golgi using the marker protein VSVG-GFP-ts045 demonstrated significantly delayed entry into and exit from the Golgi in fibroblasts derived from one of the affected subjects. Lentiviral expression of wild-type TRAPPC4 in these fibroblasts restored trafficking, suggesting that the trafficking defect was due to reduced TRAPPC4 levels. Consistent with the recent association of the TRAPP complex with autophagy, we found that the fibroblasts had a basal autophagy defect and a delay in autophagic flux, possibly due to unsealed autophagosomes. These results were validated using a yeast trs23 temperature sensitive variant that exhibits constitutive and stress-induced autophagic defects at permissive temperature and a secretory defect at restrictive temperature. In summary we provide strong evidence for pathogenicity of this variant in a member of the core TRAPP subunit, TRAPPC4 that associates with vesicular trafficking and autophagy defects. This is the first report of a TRAPPC4 variant, and our findings add to the growing number of TRAPP-associated neurological disorders.
Keywords: Atrophy; Autophagy; Cerebellum; Cerebral Cortex; Child; Child, Preschool; Craniofacial Abnormalities; Deafness; Developmental Disabilities; Epilepsy; Female; Fibroblasts; Hearing Loss, Sensorineural; Humans; Infant; Infant, Newborn; Intellectual Disability; Male; Microcephaly; Microscopy, Fluorescence; Muscle Spasticity; Nerve Tissue Proteins; Neurodevelopmental Disorders; Pedigree; Quadriplegia; RNA Splice Sites; Syndrome; Vesicular Transport Proteins

Determinants of telomere length across human tissues. - Demanelis, Kathryn; Jasmine, Farzana; Chen, Lin S; Chernoff, Meytal; Tong, Lin; Delgado, Dayana; Zhang, Chenan; Shinkle, Justin; Sabarinathan, Mekala; Lin, Hannah; Ramirez, Eduardo; Oliva, Meritxell; et al. (Science, 2020)
Telomere shortening is a hallmark of aging. Telomere length (TL) in blood cells has been studied extensively as a biomarker of human aging and disease; however, little is known regarding variability in TL in nonblood, disease-relevant tissue types. Here, we characterize variability in TLs from 6391 tissue samples, representing >20 tissue types and 952 individuals from the Genotype-Tissue Expression (GTEx) project. We describe differences across tissue types, positive correlation among tissue types, and associations with age and ancestry. We show that genetic variation affects TL in multiple tissue types and that TL may mediate the effect of age on gene expression. Our results provide the foundational knowledge regarding TL in healthy tissues that is needed to interpret epidemiological studies of TL and human health.
Keywords: Aging; Genetic Markers; Genetic Variation; Humans; Organ Specificity; Telomere; Telomere Homeostasis; Telomere Shortening

A diagnostic ceiling for exome sequencing in cerebellar ataxia and related neurological disorders. - Ngo, Kathie J; Rexach, Jessica E; Lee, Hane; Petty, Lauren E; Perlman, Susan; Valera, Juliana M; Deignan, Joshua L; Mao, Yuanming; Aker, Mamdouh; Posey, Jennifer E; Jhangiani, Shalini N; Coban-Akdemir, Zeynep H; et al. (Hum Mutat, 2020)
Genetic ataxias are associated with mutations in hundreds of genes with high phenotypic overlap complicating the clinical diagnosis. Whole-exome sequencing (WES) has increased the overall diagnostic rate considerably. However, the upper limit of this method remains ill-defined, hindering efforts to address the remaining diagnostic gap. To further assess the role of rare coding variation in ataxic disorders, we reanalyzed our previously published exome cohort of 76 predominantly adult and sporadic-onset patients, expanded the total number of cases to 260, and introduced analyses for copy number variation and repeat expansion in a representative subset. For new cases (n = 184), our resulting clinically relevant detection rate remained stable at 47% with 24% classified as pathogenic. Reanalysis of the previously sequenced 76 patients modestly improved the pathogenic rate by 7%. For the combined cohort (n = 260), the total observed clinical detection rate was 52% with 25% classified as pathogenic. Published studies of similar neurological phenotypes report comparable rates. This consistency across multiple cohorts suggests that, despite continued technical and analytical advancements, an approximately 50% diagnostic rate marks a relative ceiling for current WES-based methods and a more comprehensive genome-wide assessment is needed to identify the missing causative genetic etiologies for cerebellar ataxia and related neurodegenerative diseases.

Disease-associated CTNNBL1 mutation impairs somatic hypermutation by decreasing nuclear AID. - Kuhny, Marcel; Forbes, Lisa R; Çakan, Elif; Vega-Loza, Andrea; Kostiuk, Valentyna; Dinesh, Ravi K; Glauzy, Salomé; Stray-Pedersen, Asbjorg; Pezzi, Ashley E; Hanson, I Celine; Vargas-Hernandez, Alexander; Xu, Mina LuQuing; et al. (J Clin Invest, 2020)
Patients with common variable immunodeficiency associated with autoimmune cytopenia (CVID+AIC) generate few isotype-switched B cells with severely decreased frequencies of somatic hypermutations (SHMs), but their underlying molecular defects remain poorly characterized. We identified a CVID+AIC patient who displays a rare homozygous missense M466V mutation in β-catenin-like protein 1 (CTNNBL1). Because CTNNBL1 binds activation-induced cytidine deaminase (AID) that catalyzes SHM, we tested AID interactions with the CTNNBL1 M466V variant. We found that the M466V mutation interfered with the association of CTNNBL1 with AID, resulting in decreased AID in the nuclei of patient EBV-transformed B cell lines and of CTNNBL1 466V/V Ramos B cells engineered to express only CTNNBL1 M466V using CRISPR/Cas9 technology. As a consequence, the scarce IgG+ memory B cells from the CTNNBL1 466V/V patient showed a low SHM frequency that averaged 6.7 mutations compared with about 18 mutations per clone in healthy-donor counterparts. In addition, CTNNBL1 466V/V Ramos B cells displayed a decreased incidence of SHM that was reduced by half compared with parental WT Ramos B cells, demonstrating that the CTNNBL1 M466V mutation is responsible for defective SHM induction. We conclude that CTNNBL1 plays an important role in regulating AID-dependent antibody diversification in humans.
Keywords: Amino Acid Substitution; Apoptosis Regulatory Proteins; B-Lymphocytes; Cell Line; Child, Preschool; Common Variable Immunodeficiency; Cytidine Deaminase; Female; Homozygote; Humans; Immunologic Memory; Mutation, Missense; Nuclear Proteins; Somatic Hypermutation, Immunoglobulin

Dominant-negative mutations in human IL6ST underlie hyper-IgE syndrome. - Béziat, Vivien; Tavernier, Simon J; Chen, Yin-Huai; Ma, Cindy S; Materna, Marie; Laurence, Arian; Staal, Jens; Aschenbrenner, Dominik; Roels, Lisa; Worley, Lisa; Claes, Kathleen; Gartner, Lisa; et al. (J Exp Med, 2020)
Autosomal dominant hyper-IgE syndrome (AD-HIES) is typically caused by dominant-negative (DN) STAT3 mutations. Patients suffer from cold staphylococcal lesions and mucocutaneous candidiasis, severe allergy, and skeletal abnormalities. We report 12 patients from 8 unrelated kindreds with AD-HIES due to DN IL6ST mutations. We identified seven different truncating mutations, one of which was recurrent. The mutant alleles encode GP130 receptors bearing the transmembrane domain but lacking both the recycling motif and all four STAT3-recruiting tyrosine residues. Upon overexpression, the mutant proteins accumulate at the cell surface and are loss of function and DN for cellular responses to IL-6, IL-11, LIF, and OSM. Moreover, the patients' heterozygous leukocytes and fibroblasts respond poorly to IL-6 and IL-11. Consistently, patients with STAT3 and IL6ST mutations display infectious and allergic manifestations of IL-6R deficiency, and some of the skeletal abnormalities of IL-11R deficiency. DN STAT3 and IL6ST mutations thus appear to underlie clinical phenocopies through impairment of the IL-6 and IL-11 response pathways.
Keywords: Adolescent; Alleles; C-Reactive Protein; Cell Membrane; Cells, Cultured; Child; Cytokine Receptor gp130; Cytokines; Female; Fibroblasts; Genes, Dominant; Genetics, Population; HEK293 Cells; Humans; Job Syndrome; Kinetics; Loss of Function Mutation; Male; Middle Aged; Models, Biological; Mutation; Pedigree; Phenotype; Th2 Cells; Up-Regulation; Young Adult

Exome sequencing implicates genetic disruption of prenatal neuro-gliogenesis in sporadic congenital hydrocephalus. - Jin, Sheng Chih; Dong, Weilai; Kundishora, Adam J; Panchagnula, Shreyas; Moreno-De-Luca, Andres; Furey, Charuta G; Allocco, August A; Walker, Rebecca L; Nelson-Williams, Carol; Smith, Hannah; Dunbar, Ashley; Conine, Sierra; et al. (Nat Med, 2020)
Congenital hydrocephalus (CH), characterized by enlarged brain ventricles, is considered a disease of excessive cerebrospinal fluid (CSF) accumulation and thereby treated with neurosurgical CSF diversion with high morbidity and failure rates. The poor neurodevelopmental outcomes and persistence of ventriculomegaly in some post-surgical patients highlight our limited knowledge of disease mechanisms. Through whole-exome sequencing of 381 patients (232 trios) with sporadic, neurosurgically treated CH, we found that damaging de novo mutations account for >17% of cases, with five different genes exhibiting a significant de novo mutation burden. In all, rare, damaging mutations with large effect contributed to ~22% of sporadic CH cases. Multiple CH genes are key regulators of neural stem cell biology and converge in human transcriptional networks and cell types pertinent for fetal neuro-gliogenesis. These data implicate genetic disruption of early brain development, not impaired CSF dynamics, as the primary pathomechanism of a significant number of patients with sporadic CH.
Keywords: Brain; Cerebral Ventricles; Exome; Female; Genetic Predisposition to Disease; Humans; Hydrocephalus; Male; Mutation; Neural Stem Cells; Neurogenesis; Neuroglia; Transcription Factors; Tripartite Motif Proteins; Ubiquitin-Protein Ligases; Whole Exome Sequencing

Exome Sequencing Implicates Impaired GABA Signaling and Neuronal Ion Transport in Trigeminal Neuralgia. - Dong, Weilai; Jin, Sheng Chih; Allocco, August; Zeng, Xue; Sheth, Amar H; Panchagnula, Shreyas; Castonguay, Annie; Lorenzo, Louis-Étienne; Islam, Barira; Brindle, Geneviève; Bachand, Karine; Hu, Jamie; et al. (iScience, 2020)
Trigeminal neuralgia (TN) is a common, debilitating neuropathic face pain syndrome often resistant to therapy. The familial clustering of TN cases suggests that genetic factors play a role in disease pathogenesis. However, no unbiased, large-scale genomic study of TN has been performed to date. Analysis of 290 whole exome-sequenced TN probands, including 20 multiplex kindreds and 70 parent-offspring trios, revealed enrichment of rare, damaging variants in GABA receptor-binding genes in cases. Mice engineered with a TN-associated mutation (p.Cys188Trp) in the GABA receptor Cl channel γ-1 subunit () exhibited trigeminal mechanical allodynia and face pain behavior. Other TN probands harbored rare damaging variants in Na and Ca channels, including a significant variant burden in the α-1H subunit of the voltage-gated Ca channel Ca3.2 (). These results provide exome-level insight into TN and implicate genetically encoded impairment of GABA signaling and neuronal ion transport in TN pathogenesis.

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gözde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Yuan, Bo; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Gain-of-function variants identified in vigabatrin-hypersensitive epileptic encephalopathies. - Absalom, Nathan L; Liao, Vivian W Y; Kothur, Kavitha; Indurthi, Dinesh C; Bennetts, Bruce; Troedson, Christopher; Mohammad, Shekeeb S; Gupta, Sachin; McGregor, Iain S; Bowen, Michael T; Lederer, Damien; Mary, Sandrine; et al. (Brain Commun, 2020)
Variants in the gene encoding the β3-subunit of the γ-aminobutyric acid type A ( receptor are associated with various developmental and epileptic encephalopathies. Typically, these variants cause a loss-of-function molecular phenotype whereby γ-aminobutyric acid has reduced inhibitory effectiveness leading to seizures. Drugs that potentiate inhibitory GABAergic activity, such as nitrazepam, phenobarbital or vigabatrin, are expected to compensate for this and thereby reduce seizure frequency. However, vigabatrin, a drug that inhibits γ-aminobutyric acid transaminase to increase tonic γ-aminobutyric acid currents, has mixed success in treating seizures in patients with variants: some patients experience seizure cessation, but there is hypersensitivity in some patients associated with hypotonia, sedation and respiratory suppression. A variant that responds well to vigabatrin involves a truncation variant (p.Arg194*) resulting in a clear loss-of-function. We hypothesized that patients with a hypersensitive response to vigabatrin may exhibit a different γ-aminobutyric acid A receptor phenotype. To test this hypothesis, we evaluated the phenotype of variants in (p.Glu77Lys and p.Thr287Ile) associated with patients who are clinically hypersensitive to vigabatrin. We introduced the p.Glu77Lys and p.Thr287Ile variants into a concatenated synaptic and extrasynaptic γ-aminobutyric acid A receptor construct, to resemble the γ-aminobutyric acid A receptor expression by a patient heterozygous for the variant. The mRNA of these constructs was injected into oocytes and activation properties of each receptor measured by two-electrode voltage clamp electrophysiology. Results showed an atypical gain-of-function molecular phenotype in the p.Glu77Lys and p.Thr287Ile variants characterized by increased potency of γ-aminobutyric acid A without change to the estimated maximum open channel probability, deactivation kinetics or absolute currents. Modelling of the activation properties of the receptors indicated that either variant caused increased chloride flux in response to low concentrations of γ-aminobutyric acid that mediate tonic currents. We therefore propose that the hypersensitivity reaction to vigabatrin is a result of variants that exacerbate GABAergic tonic currents and caution is required when prescribing vigabatrin. In contrast, drug strategies increasing tonic currents in loss-of-function variants are likely to be a safe and effective therapy. This study demonstrates that functional genomics can explain beneficial and adverse anti-epileptic drug effects, and propose that vigabatrin should be considered in patients with clear loss-of-function variants.

Gain-of-Function Variants in Dilated Cardiomyopathy. - Cowan, Jason R; Salyer, Lorien; Wright, Nathan T; Kinnamon, Daniel D; Amaya, Pedro; Jordan, Elizabeth; Bamshad, Michael J; Nickerson, Deborah A; Hershberger, Ray E (Circ Genom Precis Med, 2020)
BACKGROUND: Dilated cardiomyopathy (DCM) is a genetically heterogeneous cardiac disease characterized by progressive ventricular enlargement and reduced systolic function. Here, we report genetic and functional analyses implicating the rat sarcoma signaling protein, SOS1 (Son of sevenless homolog 1), in DCM pathogenesis. METHODS: Exome sequencing was performed on 412 probands and family members from our DCM cohort, identifying several variants with potential disease involvement. As several lines of evidence have implicated dysregulated rat sarcoma signaling in the pathogenesis of DCM, we assessed functional impact of each variant on the activation of ERK (extracellular signal-regulated kinase), AKT (protein kinase B), and JNK (c-Jun N-terminal kinase) pathways. Relative expression levels were determined by Western blot in HEK293T cells transfected with variant or wild-type human expression constructs. RESULTS: A rare variant [c.571G>A, p.(Glu191Lys)] was found to segregate alongside an A-band truncating variant in a pedigree with aggressive, early-onset DCM. Reduced disease severity in the absence of the variant suggested its potential involvement as a genetic risk factor for DCM in this family. Exome sequencing identified 5 additional variants with potential disease involvement in 4 other families [c.1820T>C, p.(Ile607Thr); c.2156G>C, p.(Gly719Ala); c.2230A>G, p.(Arg744Gly); c.2728G>C, p.(Asp910His); c.3601C>T, p.(Arg1201Trp)]. Impacted amino acids occupied a number of functional domains relevant to SOS1 activity, including the N-terminal histone fold, as well as the C-terminal REM (rat sarcoma exchange motif), CDC25 (cell division cycle 25), and PR (proline-rich) tail domains. Increased phosphorylated ERK expression relative to wild-type levels was seen for all 6 variants, paralleling known disease-relevant signaling profiles. CONCLUSIONS: These data support gain-of-function variation in as a contributing factor to isolated DCM.

Genetic Burden Contributing to Extremely Low or High Bone Mineral Density in a Senior Male Population From the Osteoporotic Fractures in Men Study (MrOS). - Chen, Shan; Jain, Mahim; Jhangiani, Shalini; Akdemir, Zeynep C; Campeau, Philippe M; Klein, Robert F; Nielson, Carrie; Dai, Hongzheng; Muzny, Donna M; Boerwinkle, Eric; Gibbs, Richard A; Orwoll, Eric S; et al. (JBMR Plus, 2020)
Worldwide, one in five men aged over 50 years will experience osteoporosis or a clinical bone fracture, with a greater fracture-related mortality rate than women. However, the genetic etiology of osteoporosis in men is still poorly understood. We aimed to identify the genetic variants and candidate genes associated with extremely low or high BMD for a better understanding of the biology underlying low bone density that may point to potential therapeutic targets for increasing bone mass. Subjects from the Osteoporotic Fractures in Men Study (MrOS) cohort were evaluated by age and BMI-adjusted total hip BMD. Those with BMD values 3 SDs away from the mean were selected and the remaining individuals whose adjusted BMD ranked at the highest or lowest 100 were included. Men with the lowest adjusted BMD ( = 98) and highest adjusted BMD ( = 110) were chosen for exome sequencing. Controls ( = 82) were men of Northern and Western European descent from the US Utah population of the 1000 Genomes Project. Fisher's exact test was performed to compare low- or high-BMD subjects with controls for single-gene associations. Additionally, sets of candidate genes causative of heritable disorders of connective tissue, including osteogenesis imperfecta (OI) and Ehlers-Danlos syndrome (EDS), were grouped for multigene and mutation burden analyses. No single-gene associations with rare variants were found for either the low BMD group (33 genes) or high BMD group (18 genes). In the group of OI genes, we detected a significant threefold increased accumulation of rare variants in low-BMD subjects compared with controls ( = 0.009). Additionally, genes associated with EDS had a twofold increased frequency in low-BMD subjects compared with controls ( = 0.03). These findings reveal a rare variant burden in OI and EDS disease genes at low BMD, which suggests a potential gene-panel approach to screen for multivariant associations in larger cohorts. © 2019 The Authors. published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.

HEM1 deficiency disrupts mTORC2 and F-actin control in inherited immunodysregulatory disease. - Cook, Sarah A; Comrie, William A; Poli, M Cecilia; Similuk, Morgan; Oler, Andrew J; Faruqi, Aiman J; Kuhns, Douglas B; Yang, Sheng; Vargas-Hernandez, Alexander; Carisey, Alexandre F; Fournier, Benjamin; Anderson, D Eric; et al. (Science, 2020)
Immunodeficiency often coincides with hyperactive immune disorders such as autoimmunity, lymphoproliferation, or atopy, but this coincidence is rarely understood on a molecular level. We describe five patients from four families with immunodeficiency coupled with atopy, lymphoproliferation, and cytokine overproduction harboring mutations in , which encodes the hematopoietic-specific HEM1 protein. These mutations cause the loss of the HEM1 protein and the WAVE regulatory complex (WRC) or disrupt binding to the WRC regulator, Arf1, thereby impairing actin polymerization, synapse formation, and immune cell migration. Diminished cortical actin networks caused by WRC loss led to uncontrolled cytokine release and immune hyperresponsiveness. HEM1 loss also blocked mechanistic target of rapamycin complex 2 (mTORC2)-dependent AKT phosphorylation, T cell proliferation, and selected effector functions, leading to immunodeficiency. Thus, the evolutionarily conserved HEM1 protein simultaneously regulates filamentous actin (F-actin) and mTORC2 signaling to achieve equipoise in immune responses.
Keywords: Actins; ADP-Ribosylation Factor 1; CD4-Positive T-Lymphocytes; Cell Proliferation; Cytokines; Humans; Immunologic Deficiency Syndromes; Lymphoproliferative Disorders; Mechanistic Target of Rapamycin Complex 2; Membrane Proteins; Pedigree; Phosphorylation; Wiskott-Aldrich Syndrome Protein Family

Heterozygous loss of WBP11 function causes multiple congenital defects in humans and mice. - Martin, Ella M M A; Enriquez, Annabelle; Sparrow, Duncan B; Humphreys, David T; McInerney-Leo, Aideen M; Leo, Paul J; Duncan, Emma L; Iyer, Kavitha R; Greasby, Joelene A; Ip, Eddie; Giannoulatou, Eleni; Sheng, Delicia; et al. (Hum Mol Genet, 2020)
The genetic causes of multiple congenital anomalies are incompletely understood. Here, we report novel heterozygous predicted loss-of-function (LoF) and predicted damaging missense variants in the WW domain binding protein 11 (WBP11) gene in seven unrelated families with a variety of overlapping congenital malformations, including cardiac, vertebral, tracheo-esophageal, renal and limb defects. WBP11 encodes a component of the spliceosome with the ability to activate pre-messenger RNA splicing. We generated a Wbp11 null allele in mouse using CRISPR-Cas9 targeting. Wbp11 homozygous null embryos die prior to E8.5, indicating that Wbp11 is essential for development. Fewer Wbp11 heterozygous null mice are found than expected due to embryonic and postnatal death. Importantly, Wbp11 heterozygous null mice are small and exhibit defects in axial skeleton, kidneys and esophagus, similar to the affected individuals, supporting the role of WBP11 haploinsufficiency in the development of congenital malformations in humans. LoF WBP11 variants should be considered as a possible cause of VACTERL association as well as isolated Klippel-Feil syndrome, renal agenesis or esophageal atresia.

Human and mouse studies establish TBX6 in Mendelian CAKUT and as a potential driver of kidney defects associated with the 16p11.2 microdeletion syndrome. - Yang, Nan; Wu, Nan; Dong, Shuangshuang; Zhang, Ling; Zhao, Yanxue; Chen, Weisheng; Du, Renqian; Song, Chengcheng; Ren, Xiaojun; Liu, Jiaqi; Pehlivan, Davut; Liu, Zhenlei; et al. (Kidney Int, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUTs) are the most common cause of chronic kidney disease in children. Human 16p11.2 deletions have been associated with CAKUT, but the responsible molecular mechanism remains to be illuminated. To explore this, we investigated 102 carriers of 16p11.2 deletion from multi-center cohorts, among which we retrospectively ascertained kidney morphologic and functional data from 37 individuals (12 Chinese and 25 Caucasian/Hispanic). Significantly higher CAKUT rates were observed in 16p11.2 deletion carriers (about 25% in Chinese and 16% in Caucasian/Hispanic) than those found in the non-clinically ascertained general populations (about 1/1000 found at autopsy). Furthermore, we identified seven additional individuals with heterozygous loss-of-function variants in TBX6, a gene that maps to the 16p11.2 region. Four of these seven cases showed obvious CAKUT. To further investigate the role of TBX6 in kidney development, we engineered mice with mutated Tbx6 alleles. The Tbx6 heterozygous null (i.e., loss-of-function) mutant (Tbx6) resulted in 13% solitary kidneys. Remarkably, this incidence increased to 29% in a compound heterozygous model (Tbx6) that reduced Tbx6 gene dosage to below haploinsufficiency, by combining the null allele with a novel mild hypomorphic allele (mh). Renal hypoplasia was also frequently observed in these Tbx6-mutated mouse models. Thus, our findings in patients and mice establish TBX6 as a novel gene involved in CAKUT and its gene dosage insufficiency as a potential driver for kidney defects observed in the 16p11.2 microdeletion syndrome.

Human NK cell deficiency as a result of biallelic mutations in MCM10. - Mace, Emily M; Paust, Silke; Conte, Matilde I; Baxley, Ryan M; Schmit, Megan M; Patil, Sagar L; Guilz, Nicole C; Mukherjee, Malini; Pezzi, Ashley E; Chmielowiec, Jolanta; Tatineni, Swetha; Chinn, Ivan K; et al. (J Clin Invest, 2020)
Human natural killer cell deficiency (NKD) arises from inborn errors of immunity that lead to impaired NK cell development, function, or both. Through the understanding of the biological perturbations in individuals with NKD, requirements for the generation of terminally mature functional innate effector cells can be elucidated. Here, we report a cause of NKD resulting from compound heterozygous mutations in minichromosomal maintenance complex member 10 (MCM10) that impaired NK cell maturation in a child with fatal susceptibility to CMV. MCM10 has not been previously associated with monogenic disease and plays a critical role in the activation and function of the eukaryotic DNA replisome. Through evaluation of patient primary fibroblasts, modeling patient mutations in fibroblast cell lines, and MCM10 knockdown in human NK cell lines, we have shown that loss of MCM10 function leads to impaired cell cycle progression and induction of DNA damage-response pathways. By modeling MCM10 deficiency in primary NK cell precursors, including patient-derived induced pluripotent stem cells, we further demonstrated that MCM10 is required for NK cell terminal maturation and acquisition of immunological system function. Together, these data define MCM10 as an NKD gene and provide biological insight into the requirement for the DNA replisome in human NK cell maturation and function.
Keywords: Alleles; Cell Cycle Checkpoints; Cell Differentiation; Cell Line; Codon, Nonsense; DNA Damage; Fatal Outcome; Female; Gene Knockdown Techniques; Heterozygote; Humans; Induced Pluripotent Stem Cells; Infant; Killer Cells, Natural; Male; Minichromosome Maintenance Proteins; Models, Immunological; Mutation; Mutation, Missense; Pedigree; Primary Immunodeficiency Diseases

Immunodeficiency, centromeric instability, and facial anomalies (ICF) syndrome with NK dysfunction and EBV-driven malignancy treated with stem cell transplantation. - Burk, Caitlin M; Coffey, Kara E; Mace, Emily M; Bostwick, Bret L; Chinn, Ivan K; Coban-Akdemir, Zeynep H; Jhangiani, Shalini N; Lupski, James R; Ortiz, Damara; Barnum, Jessie L; Allen, Steven W; Robertson, Leanna-Marie; et al. (J Allergy Clin Immunol Pract, 2020)
Keywords: Herpesvirus 4, Human; Humans; Immunologic Deficiency Syndromes; Mutation; Neoplasms; Primary Immunodeficiency Diseases; Stem Cell Transplantation

Inborn errors of type I IFN immunity in patients with life-threatening COVID-19. - Zhang, Qian; Bastard, Paul; Liu, Zhiyong; Le Pen, Jérémie; Moncada-Velez, Marcela; Chen, Jie; Ogishi, Masato; Sabli, Ira K D; Hodeib, Stephanie; Korol, Cecilia; Rosain, Jérémie; Bilguvar, Kaya; et al. (Science, 2020)
Clinical outcome upon infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ranges from silent infection to lethal coronavirus disease 2019 (COVID-19). We have found an enrichment in rare variants predicted to be loss-of-function (LOF) at the 13 human loci known to govern Toll-like receptor 3 (TLR3)- and interferon regulatory factor 7 (IRF7)-dependent type I interferon (IFN) immunity to influenza virus in 659 patients with life-threatening COVID-19 pneumonia relative to 534 subjects with asymptomatic or benign infection. By testing these and other rare variants at these 13 loci, we experimentally defined LOF variants underlying autosomal-recessive or autosomal-dominant deficiencies in 23 patients (3.5%) 17 to 77 years of age. We show that human fibroblasts with mutations affecting this circuit are vulnerable to SARS-CoV-2. Inborn errors of TLR3- and IRF7-dependent type I IFN immunity can underlie life-threatening COVID-19 pneumonia in patients with no prior severe infection.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Asymptomatic Infections; Betacoronavirus; Child; Child, Preschool; Coronavirus Infections; COVID-19; Female; Genetic Loci; Genetic Predisposition to Disease; Humans; Infant; Interferon Regulatory Factor-7; Interferon Type I; Loss of Function Mutation; Male; Middle Aged; Pandemics; Pneumonia, Viral; Receptor, Interferon alpha-beta; SARS-CoV-2; Toll-Like Receptor 3; Young Adult

Increased gene dosages induce congenital cervical vertebral malformations in humans and mice. - Ren, Xiaojun; Yang, Nan; Wu, Nan; Xu, Ximing; Chen, Weisheng; Zhang, Ling; Li, Yingping; Du, Ren-Qian; Dong, Shuangshuang; Zhao, Sen; Chen, Shuxia; Jiang, Li-Ping; et al. (J Med Genet, 2020)
BACKGROUND: Congenital vertebral malformations (CVMs) manifest with abnormal vertebral morphology. Genetic factors have been implicated in CVM pathogenesis, but the underlying pathogenic mechanisms remain unclear in most subjects. We previously reported that the human 16p11.2 BP4-BP5 deletion and its associated dosage reduction caused CVMs. We aim to investigate the reciprocal 16p11.2 BP4-BP5 duplication and its potential genetic contributions to CVMs. METHODS AND RESULTS: Patients who were found to carry the 16p11.2 BP4-BP5 duplication by chromosomal microarray analysis were retrospectively analysed for their vertebral phenotypes. The spinal assessments in seven duplication carriers showed that four (57%) presented characteristics of CVMs, supporting the contention that increased dosage could induce CVMs. For further in vivo functional investigation in a model organism, we conducted genome editing of the upstream regulatory region of mouse using CRISPR-Cas9 and obtained three mouse mutant alleles ( to ) with elevated expression levels of . Luciferase reporter assays showed that the allele presented with the 160% expression level of that observed in the reference (+) allele. Therefore, the homozygous mice could functionally mimic the dosage of heterozygous carriers of 16p11.2 BP4-BP5 duplication (approximately 150%, ie, 3/2 gene dosage of the normal level). Remarkably, 60% of the mice manifested with CVMs. Consistent with our observations in humans, the CVMs induced by increased dosage in mice mainly affected the cervical vertebrae. CONCLUSION: Our findings in humans and mice consistently support that an increased dosage contributes to the risk of developing cervical CVMs.

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.
Keywords: Adult; Africa; African Continental Ancestry Group; Aged; Aged, 80 and over; alpha Karyopherins; Cell Self Renewal; Clonal Hematopoiesis; DNA-Binding Proteins; Female; Genetic Predisposition to Disease; Genome, Human; Germ-Line Mutation; Hematopoietic Stem Cells; Humans; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Proto-Oncogene Proteins; Tripartite Motif Proteins; United States; Whole Genome Sequencing

KMT2B-related disorders: expansion of the phenotypic spectrum and long-term efficacy of deep brain stimulation. - Cif, Laura; Demailly, Diane; Lin, Jean-Pierre; Barwick, Katy E; Sa, Mario; Abela, Lucia; Malhotra, Sony; Chong, Wui K; Steel, Dora; Sanchis-Juan, Alba; Ngoh, Adeline; Trump, Natalie; et al. (Brain, 2020)
Heterozygous mutations in KMT2B are associated with an early-onset, progressive and often complex dystonia (DYT28). Key characteristics of typical disease include focal motor features at disease presentation, evolving through a caudocranial pattern into generalized dystonia, with prominent oromandibular, laryngeal and cervical involvement. Although KMT2B-related disease is emerging as one of the most common causes of early-onset genetic dystonia, much remains to be understood about the full spectrum of the disease. We describe a cohort of 53 patients with KMT2B mutations, with detailed delineation of their clinical phenotype and molecular genetic features. We report new disease presentations, including atypical patterns of dystonia evolution and a subgroup of patients with a non-dystonic neurodevelopmental phenotype. In addition to the previously reported systemic features, our study has identified co-morbidities, including the risk of status dystonicus, intrauterine growth retardation, and endocrinopathies. Analysis of this study cohort (n = 53) in tandem with published cases (n = 80) revealed that patients with chromosomal deletions and protein truncating variants had a significantly higher burden of systemic disease (with earlier onset of dystonia) than those with missense variants. Eighteen individuals had detailed longitudinal data available after insertion of deep brain stimulation for medically refractory dystonia. Median age at deep brain stimulation was 11.5 years (range: 4.5-37.0 years). Follow-up after deep brain stimulation ranged from 0.25 to 22 years. Significant improvement of motor function and disability (as assessed by the Burke Fahn Marsden's Dystonia Rating Scales, BFMDRS-M and BFMDRS-D) was evident at 6 months, 1 year and last follow-up (motor, P = 0.001, P = 0.004, and P = 0.012; disability, P = 0.009, P = 0.002 and P = 0.012). At 1 year post-deep brain stimulation, >50% of subjects showed BFMDRS-M and BFMDRS-D improvements of >30%. In the long-term deep brain stimulation cohort (deep brain stimulation inserted for >5 years, n = 8), improvement of >30% was maintained in 5/8 and 3/8 subjects for the BFMDRS-M and BFMDRS-D, respectively. The greatest BFMDRS-M improvements were observed for trunk (53.2%) and cervical (50.5%) dystonia, with less clinical impact on laryngeal dystonia. Improvements in gait dystonia decreased from 20.9% at 1 year to 16.2% at last assessment; no patient maintained a fully independent gait. Reduction of BFMDRS-D was maintained for swallowing (52.9%). Five patients developed mild parkinsonism following deep brain stimulation. KMT2B-related disease comprises an expanding continuum from infancy to adulthood, with early evidence of genotype-phenotype correlations. Except for laryngeal dysphonia, deep brain stimulation provides a significant improvement in quality of life and function with sustained clinical benefit depending on symptoms distribution.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosome Deletion; Cohort Studies; Computer Simulation; Deep Brain Stimulation; Disease Progression; Dystonic Disorders; Endocrine System Diseases; Female; Fetal Growth Retardation; Gait Disorders, Neurologic; Histone-Lysine N-Methyltransferase; Humans; Laryngeal Diseases; Male; Mutation; Mutation, Missense; Phenotype; Quality of Life; Treatment Outcome; Young Adult

Low-level parental somatic mosaic SNVs in exomes from a large cohort of trios with diverse suspected Mendelian conditions. - Gambin, Tomasz; Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Xie, Nina G; Wu, Lucia R; Yan, Yan Helen; Cao, Ye; Coban Akdemir, Zeynep H; Wilson, Theresa A; Jhangiani, Shalini N; Chen, Ed; et al. (Genet Med, 2020)
PURPOSE: The goal of this study was to assess the scale of low-level parental mosaicism in exome sequencing (ES) databases. METHODS: We analyzed approximately 2000 family trio ES data sets from the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) and Baylor Genetics (BG). Among apparent de novo single-nucleotide variants identified in the affected probands, we selected rare unique variants with variant allele fraction (VAF) between 30% and 70% in the probands and lower than 10% in one of the parents. RESULTS: Of 102 candidate mosaic variants validated using amplicon-based next-generation sequencing, droplet digital polymerase chain reaction, or blocker displacement amplification, 27 (26.4%) were confirmed to be low- (VAF between 1% and 10%) or very low (VAF <1%) level mosaic. Detection precision in parental samples with two or more alternate reads was 63.6% (BHCMG) and 43.6% (BG). In nine investigated individuals, we observed variability of mosaic ratios among blood, saliva, fibroblast, buccal, hair, and urine samples. CONCLUSION: Our computational pipeline enables robust discrimination between true and false positive candidate mosaic variants and efficient detection of low-level mosaicism in ES samples. We confirm that the presence of two or more alternate reads in the parental sample is a reliable predictor of low-level parental somatic mosaicism.
Keywords: Exome; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents; Whole Exome Sequencing

Lung Function in African American Children with Asthma Is Associated with Novel Regulatory Variants of the KIT Ligand and Gene-By-Air-Pollution Interaction. - Mak, Angel C Y; Sajuthi, Satria; Joo, Jaehyun; Xiao, Shujie; Sleiman, Patrick M; White, Marquitta J; Lee, Eunice Y; Saef, Benjamin; Hu, Donglei; Gui, Hongsheng; Keys, Kevin L; Lurmann, Fred; et al. (Genetics, 2020)
Baseline lung function, quantified as forced expiratory volume in the first second of exhalation (FEV), is a standard diagnostic criterion used by clinicians to identify and classify lung diseases. Using whole-genome sequencing data from the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine project, we identified a novel genetic association with FEV on chromosome 12 in 867 African American children with asthma ( = 1.26 × 10, β = 0.302). Conditional analysis within 1 Mb of the tag signal (rs73429450) yielded one major and two other weaker independent signals within this peak. We explored statistical and functional evidence for all variants in linkage disequilibrium with the three independent signals and yielded nine variants as the most likely candidates responsible for the association with FEV Hi-C data and expression QTL analysis demonstrated that these variants physically interacted with (KIT ligand, also known as ), and their minor alleles were associated with increased expression of the gene in nasal epithelial cells. Gene-by-air-pollution interaction analysis found that the candidate variant rs58475486 interacted with past-year ambient sulfur dioxide exposure ( = 0.003, β = 0.32). This study identified a novel protective genetic association with FEV, possibly mediated through , in African American children with asthma. This is the first study that has identified a genetic association between lung function and , which has established a role in orchestrating allergic inflammation in asthma.

Missense variant contribution to USP9X-female syndrome. - Jolly, Lachlan A; Parnell, Euan; Gardner, Alison E; Corbett, Mark A; Pérez-Jurado, Luis A; Shaw, Marie; Lesca, Gaetan; Keegan, Catherine; Schneider, Michael C; Griffin, Emily; Maier, Felicitas; Kiss, Courtney; et al. (NPJ Genom Med, 2020)
USP9X is an X-chromosome gene that escapes X-inactivation. Loss or compromised function of USP9X leads to neurodevelopmental disorders in males and females. While males are impacted primarily by hemizygous partial loss-of-function missense variants, in females de novo heterozygous complete loss-of-function mutations predominate, and give rise to the clinically recognisable USP9X-female syndrome. Here we provide evidence of the contribution of USP9X missense and small in-frame deletion variants in USP9X-female syndrome also. We scrutinise the pathogenicity of eleven such variants, ten of which were novel. Combined application of variant prediction algorithms, protein structure modelling, and assessment under clinically relevant guidelines universally support their pathogenicity. The core phenotype of this cohort overlapped with previous descriptions of USP9X-female syndrome, but exposed heightened variability. Aggregate phenotypic information of 35 currently known females with predicted pathogenic variation in USP9X reaffirms the clinically recognisable USP9X-female syndrome, and highlights major differences when compared to USP9X-male associated neurodevelopmental disorders.

A missense variant in Mitochondrial Amidoxime Reducing Component 1 gene and protection against liver disease. - Emdin, Connor A; Haas, Mary E; Khera, Amit V; Aragam, Krishna; Chaffin, Mark; Klarin, Derek; Hindy, George; Jiang, Lan; Wei, Wei-Qi; Feng, Qiping; Karjalainen, Juha; Havulinna, Aki; et al. (PLoS Genet, 2020)
Analyzing 12,361 all-cause cirrhosis cases and 790,095 controls from eight cohorts, we identify a common missense variant in the Mitochondrial Amidoxime Reducing Component 1 gene (MARC1 p.A165T) that associates with protection from all-cause cirrhosis (OR 0.91, p = 2.3*10-11). This same variant also associates with lower levels of hepatic fat on computed tomographic imaging and lower odds of physician-diagnosed fatty liver as well as lower blood levels of alanine transaminase (-0.025 SD, 3.7*10-43), alkaline phosphatase (-0.025 SD, 1.2*10-37), total cholesterol (-0.030 SD, p = 1.9*10-36) and LDL cholesterol (-0.027 SD, p = 5.1*10-30) levels. We identified a series of additional MARC1 alleles (low-frequency missense p.M187K and rare protein-truncating p.R200Ter) that also associated with lower cholesterol levels, liver enzyme levels and reduced risk of cirrhosis (0 cirrhosis cases for 238 R200Ter carriers versus 17,046 cases of cirrhosis among 759,027 non-carriers, p = 0.04) suggesting that deficiency of the MARC1 enzyme may lower blood cholesterol levels and protect against cirrhosis.
Keywords: Alleles; Cholesterol, LDL; Coronary Artery Disease; Datasets as Topic; Fatty Liver; Female; Genetic Predisposition to Disease; Homozygote; Humans; Liver; Liver Cirrhosis; Liver Cirrhosis, Alcoholic; Loss of Function Mutation; Male; Middle Aged; Mitochondrial Proteins; Mutation, Missense; Oxidoreductases

MN1 C-terminal truncation syndrome is a novel neurodevelopmental and craniofacial disorder with partial rhombencephalosynapsis. - Mak, Christopher C Y; Doherty, Dan; Lin, Angela E; Vegas, Nancy; Cho, Megan T; Viot, Géraldine; Dimartino, Clémantine; Weisfeld-Adams, James D; Lessel, Davor; Joss, Shelagh; Li, Chumei; Gonzaga-Jauregui, Claudia; et al. (Brain, 2020)
MN1 encodes a transcriptional co-regulator without homology to other proteins, previously implicated in acute myeloid leukaemia and development of the palate. Large deletions encompassing MN1 have been reported in individuals with variable neurodevelopmental anomalies and non-specific facial features. We identified a cluster of de novo truncating mutations in MN1 in a cohort of 23 individuals with strikingly similar dysmorphic facial features, especially midface hypoplasia, and intellectual disability with severe expressive language delay. Imaging revealed an atypical form of rhombencephalosynapsis, a distinctive brain malformation characterized by partial or complete loss of the cerebellar vermis with fusion of the cerebellar hemispheres, in 8/10 individuals. Rhombencephalosynapsis has no previously known definitive genetic or environmental causes. Other frequent features included perisylvian polymicrogyria, abnormal posterior clinoid processes and persistent trigeminal artery. MN1 is encoded by only two exons. All mutations, including the recurrent variant p.Arg1295* observed in 8/21 probands, fall in the terminal exon or the extreme 3' region of exon 1, and are therefore predicted to result in escape from nonsense-mediated mRNA decay. This was confirmed in fibroblasts from three individuals. We propose that the condition described here, MN1 C-terminal truncation (MCTT) syndrome, is not due to MN1 haploinsufficiency but rather is the result of dominantly acting C-terminally truncated MN1 protein. Our data show that MN1 plays a critical role in human craniofacial and brain development, and opens the door to understanding the biological mechanisms underlying rhombencephalosynapsis.
Keywords: Abnormalities, Multiple; Adolescent; Basilar Artery; Carotid Arteries; Cerebellar Vermis; Cerebellum; Child; Child, Preschool; Cohort Studies; Comparative Genomic Hybridization; Craniofacial Abnormalities; Female; Fibroblasts; Humans; Imaging, Three-Dimensional; Infant; Intellectual Disability; Language Development Disorders; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Nervous System Malformations; Nonsense Mediated mRNA Decay; Polymicrogyria; Real-Time Polymerase Chain Reaction; RNA-Seq; Syndrome; Tomography, X-Ray Computed; Trans-Activators; Tumor Suppressor Proteins; Whole Exome Sequencing; Whole Genome Sequencing

Monogenic variants in dystonia: an exome-wide sequencing study. - Zech, Michael; Jech, Robert; Boesch, Sylvia; Škorvánek, Matej; Weber, Sandrina; Wagner, Matias; Zhao, Chen; Jochim, Angela; Necpál, Ján; Dincer, Yasemin; Vill, Katharina; Distelmaier, Felix; et al. (Lancet Neurol, 2020)
BACKGROUND: Dystonia is a clinically and genetically heterogeneous condition that occurs in isolation (isolated dystonia), in combination with other movement disorders (combined dystonia), or in the context of multisymptomatic phenotypes (isolated or combined dystonia with other neurological involvement). However, our understanding of its aetiology is still incomplete. We aimed to elucidate the monogenic causes for the major clinical categories of dystonia. METHODS: For this exome-wide sequencing study, study participants were identified at 33 movement-disorder and neuropaediatric specialty centres in Austria, Czech Republic, France, Germany, Poland, Slovakia, and Switzerland. Each individual with dystonia was diagnosed in accordance with the dystonia consensus definition. Index cases were eligible for this study if they had no previous genetic diagnosis and no indication of an acquired cause of their illness. The second criterion was not applied to a subset of participants with a working clinical diagnosis of dystonic cerebral palsy. Genomic DNA was extracted from blood of participants and whole-exome sequenced. To find causative variants in known disorder-associated genes, all variants were filtered, and unreported variants were classified according to American College of Medical Genetics and Genomics guidelines. All considered variants were reviewed in expert round-table sessions to validate their clinical significance. Variants that survived filtering and interpretation procedures were defined as diagnostic variants. In the cases that went undiagnosed, candidate dystonia-causing genes were prioritised in a stepwise workflow. FINDINGS: We sequenced the exomes of 764 individuals with dystonia and 346 healthy parents who were recruited between June 1, 2015, and July 31, 2019. We identified causative or probable causative variants in 135 (19%) of 728 families, involving 78 distinct monogenic disorders. We observed a larger proportion of individuals with diagnostic variants in those with dystonia (either isolated or combined) with coexisting non-movement disorder-related neurological symptoms (100 [45%] of 222; excepting cases with evidence of perinatal brain injury) than in those with combined (19 [19%] of 98) or isolated (16 [4%] of 388) dystonia. Across all categories of dystonia, 104 (65%) of the 160 detected variants affected genes which are associated with neurodevelopmental disorders. We found diagnostic variants in 11 genes not previously linked to dystonia, and propose a predictive clinical score that could guide the implementation of exome sequencing in routine diagnostics. In cases without perinatal sentinel events, genomic alterations contributed substantively to the diagnosis of dystonic cerebral palsy. In 15 families, we delineated 12 candidate genes. These include IMPDH2, encoding a key purine biosynthetic enzyme, for which robust evidence existed for its involvement in a neurodevelopmental disorder with dystonia. We identified six variants in IMPDH2, collected from four independent cohorts, that were predicted to be deleterious de-novo variants and expected to result in deregulation of purine metabolism. INTERPRETATION: In this study, we have determined the role of monogenic variants across the range of dystonic disorders, providing guidance for the introduction of personalised care strategies and fostering follow-up pathophysiological explorations. FUNDING: Else Kröner-Fresenius-Stiftung, Technische Universität München, Helmholtz Zentrum München, Medizinische Universität Innsbruck, Charles University in Prague, Czech Ministry of Education, the Slovak Grant and Development Agency, the Slovak Research and Grant Agency.
Keywords: Adolescent; Child; Child, Preschool; Dystonia; Exome; Female; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Pedigree; Whole Exome Sequencing; Young Adult

Multi-omic studies on missense PLG variants in families with otitis media. - Bootpetch, Tori C; Hafrén, Lena; Elling, Christina L; Baschal, Erin E; Manichaikul, Ani W; Pine, Harold S; Szeremeta, Wasyl; Scholes, Melissa A; Cass, Stephen P; Larson, Eric D; Chan, Kenny H; Ishaq, Rafaqat; et al. (Sci Rep, 2020)
Otitis media (OM), a very common disease in young children, can result in hearing loss. In order to potentially replicate previously reported associations between OM and PLG, exome and Sanger sequencing, RNA-sequencing of saliva and middle ear samples, 16S rRNA sequencing, molecular modeling, and statistical analyses including transmission disequilibrium tests (TDT) were performed in a multi-ethnic cohort of 718 families and simplex cases with OM. We identified four rare PLG variants c.112A > G (p.Lys38Glu), c.782G > A (p.Arg261His), c.1481C > T (p.Ala494Val) and c.2045 T > A (p.Ile682Asn), and one common variant c.1414G > A (p.Asp472Asn). However TDT analyses for these PLG variants did not demonstrate association with OM in 314 families. Additionally PLG expression is very low or absent in normal or diseased middle ear in mouse and human, and salivary expression and microbial α-diversity were non-significant in c.1414G > A (p.Asp472Asn) carriers. Based on molecular modeling, the novel rare variants particularly c.782G > A (p.Arg261His) and c.2045 T > A (p.Ile682Asn) were predicted to affect protein structure. Exploration of other potential disease mechanisms will help elucidate how PLG contributes to OM susceptibility in humans. Our results underline the importance of following up findings from genome-wide association through replication studies, preferably using multi-omic datasets.
Keywords: Animals; Ear, Middle; Female; Genomics; Humans; Male; Mice; Microbiota; Mutation, Missense; Otitis Media; Pedigree; Plasminogen; Polymorphism, Single Nucleotide; Saliva

Multiplexed Functional Assessment of Genetic Variants in CARD11. - Meitlis, Iana; Allenspach, Eric J; Bauman, Bradly M; Phan, Isabelle Q; Dabbah, Gina; Schmitt, Erica G; Camp, Nathan D; Torgerson, Troy R; Nickerson, Deborah A; Bamshad, Michael J; Hagin, David; Luthers, Christopher R; et al. (Am J Hum Genet, 2020)
Genetic testing has increased the number of variants identified in disease genes, but the diagnostic utility is limited by lack of understanding variant function. CARD11 encodes an adaptor protein that expresses dominant-negative and gain-of-function variants associated with distinct immunodeficiencies. Here, we used a "cloning-free" saturation genome editing approach in a diploid cell line to simultaneously score 2,542 variants for decreased or increased function in the region of CARD11 associated with immunodeficiency. We also described an exon-skipping mechanism for CARD11 dominant-negative activity. The classification of reported clinical variants was sensitive (94.6%) and specific (88.9%), which rendered the data immediately useful for interpretation of seven coding and splicing variants implicated in immunodeficiency found in our clinic. This approach is generalizable for variant interpretation in many other clinically actionable genes, in any relevant cell type.
Keywords: Adenine; B-Cell CLL-Lymphoma 10 Protein; B-Lymphocytes; CARD Signaling Adaptor Proteins; Cell Line; Diploidy; Exons; Genes, Dominant; Genetic Variation; Guanylate Cyclase; Humans; Immunologic Deficiency Syndromes; Jurkat Cells; Lymphoma; NF-kappa B p50 Subunit; Piperidines; Polymorphism, Single Nucleotide; Primary Immunodeficiency Diseases; Sensitivity and Specificity

A mutation affecting laminin alpha 5 polymerisation gives rise to a syndromic developmental disorder. - Jones, Lynelle K; Lam, Rachel; McKee, Karen K; Aleksandrova, Maya; Dowling, John; Alexander, Stephen I; Mallawaarachchi, Amali; Cottle, Denny L; Short, Kieran M; Pais, Lynn; Miner, Jeffery H; Mallett, Andrew J; et al. (Development, 2020)
Laminin alpha 5 (LAMA5) is a member of a large family of proteins that trimerise and then polymerise to form a central component of all basement membranes. Consequently, the protein plays an instrumental role in shaping the normal development of the kidney, skin, neural tube, lung and limb, and many other organs and tissues. Pathogenic mutations in some laminins have been shown to cause a range of largely syndromic conditions affecting the competency of the basement membranes to which they contribute. We report the identification of a mutation in the polymerisation domain of LAMA5 in a patient with a complex syndromic disease characterised by defects in kidney, craniofacial and limb development, and by a range of other congenital defects. Using CRISPR-generated mouse models and biochemical assays, we demonstrate the pathogenicity of this variant, showing that the change results in a failure of the polymerisation of α/β/γ laminin trimers. Comparing these phenotypes with those apparent upon gene deletion in mice provides insights into the specific functional importance of laminin polymerisation during development and tissue homeostasis.
Keywords: Amino Acid Sequence; Animals; Animals, Newborn; Child, Preschool; Developmental Disabilities; Fetal Development; Fetus; Humans; Hydronephrosis; Infant, Newborn; Kidney; Laminin; Lung; Male; Mice; Mutation; Polymerization; Protein Domains; Syndrome

Mutation Distribution and Type Suggests Genetic Differences between the Etiology of Orofacial Clefting and Gastric Cancer. - Selvanathan, Arthavan; Nixon, Cheng Yee; Zhu, Ying; Scietti, Luigi; Forneris, Federico; Uribe, Lina M Moreno; Lidral, Andrew C; Jezewski, Peter A; Mulliken, John B; Murray, Jeffrey C; Buckley, Michael F; Cox, Timothy C; et al. (Genes (Basel), 2020)
Pathogenic variants in , encoding epithelial cadherin (E-cadherin), have been implicated in hereditary diffuse gastric cancer (HDGC), lobular breast cancer, and both syndromic and non-syndromic cleft lip/palate (CL/P). Despite the large number of mutations described, the nature of the phenotypic consequence of such mutations is currently not able to be predicted, creating significant challenges for genetic counselling. This study collates the phenotype and molecular data for available variants that have been classified, using the American College of Medical Genetics and Genomics criteria, as at least 'likely pathogenic', and correlates their molecular and structural characteristics to phenotype. We demonstrate that variant type and location differ between HDGC and CL/P, and that there is clustering of CL/P variants within linker regions between the extracellular domains of the cadherin protein. While these differences do not provide for exact prediction of the phenotype for a given mutation, they may contribute to more accurate assessments of risk for HDGC or CL/P for individuals with specific variants.
Keywords: Antigens, CD; Brain; Cadherins; Cleft Lip; Cleft Palate; Female; Genetic Counseling; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Male; Pedigree; Phenotype; Stomach Neoplasms

The mutational constraint spectrum quantified from variation in 141,456 humans. - Karczewski, Konrad J; Francioli, Laurent C; Tiao, Grace; Cummings, Beryl B; Alföldi, Jessica; Wang, Qingbo; Collins, Ryan L; Laricchia, Kristen M; Ganna, Andrea; Birnbaum, Daniel P; Gauthier, Laura D; Brand, Harrison; et al. (Nature, 2020)
Genetic variants that inactivate protein-coding genes are a powerful source of information about the phenotypic consequences of gene disruption: genes that are crucial for the function of an organism will be depleted of such variants in natural populations, whereas non-essential genes will tolerate their accumulation. However, predicted loss-of-function variants are enriched for annotation errors, and tend to be found at extremely low frequencies, so their analysis requires careful variant annotation and very large sample sizes. Here we describe the aggregation of 125,748 exomes and 15,708 genomes from human sequencing studies into the Genome Aggregation Database (gnomAD). We identify 443,769 high-confidence predicted loss-of-function variants in this cohort after filtering for artefacts caused by sequencing and annotation errors. Using an improved model of human mutation rates, we classify human protein-coding genes along a spectrum that represents tolerance to inactivation, validate this classification using data from model organisms and engineered human cells, and show that it can be used to improve the power of gene discovery for both common and rare diseases.
Keywords: Adult; Brain; Cardiovascular Diseases; Cohort Studies; Databases, Genetic; Exome; Female; Genes, Essential; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Loss of Function Mutation; Male; Mutation Rate; Proprotein Convertase 9; Reproducibility of Results; RNA, Messenger; Whole Exome Sequencing; Whole Genome Sequencing

Mutations disrupting neuritogenesis genes confer risk for cerebral palsy. - Jin, Sheng Chih; Lewis, Sara A; Bakhtiari, Somayeh; Zeng, Xue; Sierant, Michael C; Shetty, Sheetal; Nordlie, Sandra M; Elie, Aureliane; Corbett, Mark A; Norton, Bethany Y; van Eyk, Clare L; Haider, Shozeb; et al. (Nat Genet, 2020)
In addition to commonly associated environmental factors, genomic factors may cause cerebral palsy. We performed whole-exome sequencing of 250 parent-offspring trios, and observed enrichment of damaging de novo mutations in cerebral palsy cases. Eight genes had multiple damaging de novo mutations; of these, two (TUBA1A and CTNNB1) met genome-wide significance. We identified two novel monogenic etiologies, FBXO31 and RHOB, and showed that the RHOB mutation enhances active-state Rho effector binding while the FBXO31 mutation diminishes cyclin D levels. Candidate cerebral palsy risk genes overlapped with neurodevelopmental disorder genes. Network analyses identified enrichment of Rho GTPase, extracellular matrix, focal adhesion and cytoskeleton pathways. Cerebral palsy risk genes in enriched pathways were shown to regulate neuromotor function in a Drosophila reverse genetics screen. We estimate that 14% of cases could be attributed to an excess of damaging de novo or recessive variants. These findings provide evidence for genetically mediated dysregulation of early neuronal connectivity in cerebral palsy.
Keywords: Animals; beta Catenin; Cerebral Palsy; Cyclin D; Cytoskeleton; Drosophila; Exome; Extracellular Matrix; F-Box Proteins; Female; Focal Adhesions; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Mutation; Neurites; rhoB GTP-Binding Protein; Risk Factors; Sequence Analysis, DNA; Signal Transduction; Tubulin; Tumor Suppressor Proteins; Whole Exome Sequencing

Mutations in MYLPF Cause a Novel Segmental Amyoplasia that Manifests as Distal Arthrogryposis. - Chong, Jessica X; Talbot, Jared C; Teets, Emily M; Previs, Samantha; Martin, Brit L; Shively, Kathryn M; Marvin, Colby T; Aylsworth, Arthur S; Saadeh-Haddad, Reem; Schatz, Ulrich A; Inzana, Francesca; Ben-Omran, Tawfeg; et al. (Am J Hum Genet, 2020)
We identified ten persons in six consanguineous families with distal arthrogryposis (DA) who had congenital contractures, scoliosis, and short stature. Exome sequencing revealed that each affected person was homozygous for one of two different rare variants (c.470G>T [p.Cys157Phe] or c.469T>C [p.Cys157Arg]) affecting the same residue of myosin light chain, phosphorylatable, fast skeletal muscle (MYLPF). In a seventh family, a c.487G>A (p.Gly163Ser) variant in MYLPF arose de novo in a father, who transmitted it to his son. In an eighth family comprised of seven individuals with dominantly inherited DA, a c.98C>T (p.Ala33Val) variant segregated in all four persons tested. Variants in MYLPF underlie both dominant and recessively inherited DA. Mylpf protein models suggest that the residues associated with dominant DA interact with myosin whereas the residues altered in families with recessive DA only indirectly impair this interaction. Pathological and histological exam of a foot amputated from an affected child revealed complete absence of skeletal muscle (i.e., segmental amyoplasia). To investigate the mechanism for this finding, we generated an animal model for partial MYLPF impairment by knocking out zebrafish mylpfa. The mylpfa mutant had reduced trunk contractile force and complete pectoral fin paralysis, demonstrating that mylpf impairment most severely affects limb movement. mylpfa mutant muscle weakness was most pronounced in an appendicular muscle and was explained by reduced myosin activity and fiber degeneration. Collectively, our findings demonstrate that partial loss of MYLPF function can lead to congenital contractures, likely as a result of degeneration of skeletal muscle in the distal limb.
Keywords: Adolescent; Amino Acid Sequence; Animals; Arthrogryposis; Child; Contracture; Extremities; Female; Humans; Male; Muscle, Skeletal; Musculoskeletal Abnormalities; Mutation; Myosin Light Chains; Myosins; Pedigree; Young Adult; Zebrafish

NEMF mutations that impair ribosome-associated quality control are associated with neuromuscular disease. - Martin, Paige B; Kigoshi-Tansho, Yu; Sher, Roger B; Ravenscroft, Gianina; Stauffer, Jennifer E; Kumar, Rajesh; Yonashiro, Ryo; Müller, Tina; Griffith, Christopher; Allen, William; Pehlivan, Davut; Harel, Tamar; et al. (Nat Commun, 2020)
A hallmark of neurodegeneration is defective protein quality control. The E3 ligase Listerin (LTN1/Ltn1) acts in a specialized protein quality control pathway-Ribosome-associated Quality Control (RQC)-by mediating proteolytic targeting of incomplete polypeptides produced by ribosome stalling, and Ltn1 mutation leads to neurodegeneration in mice. Whether neurodegeneration results from defective RQC and whether defective RQC contributes to human disease have remained unknown. Here we show that three independently-generated mouse models with mutations in a different component of the RQC complex, NEMF/Rqc2, develop progressive motor neuron degeneration. Equivalent mutations in yeast Rqc2 selectively interfere with its ability to modify aberrant translation products with C-terminal tails which assist with RQC-mediated protein degradation, suggesting a pathomechanism. Finally, we identify NEMF mutations expected to interfere with function in patients from seven families presenting juvenile neuromuscular disease. These uncover NEMF's role in translational homeostasis in the nervous system and implicate RQC dysfunction in causing neurodegeneration.
Keywords: Amino Acid Sequence; Animals; Female; Humans; Male; Mice; Mice, Knockout; Mutation; Neuromuscular Diseases; Proteolysis; Ribosomes; RNA-Binding Proteins; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Sequence Alignment

Novel congenital disorder of O-linked glycosylation caused by GALNT2 loss of function. - Zilmer, Monica; Edmondson, Andrew C; Khetarpal, Sumeet A; Alesi, Viola; Zaki, MAH S; Rostasy, Kevin; Madsen, Camilla G; Lepri, Francesca R; Sinibaldi, Lorenzo; Cusmai, Raffaella; Novelli, Antonio; Issa, Mahmoud Y; et al. (Brain, 2020)
Congenital disorders of glycosylation are a growing group of rare genetic disorders caused by deficient protein and lipid glycosylation. Here, we report the clinical, biochemical, and molecular features of seven patients from four families with GALNT2-congenital disorder of glycosylation (GALNT2-CDG), an O-linked glycosylation disorder. GALNT2 encodes the Golgi-localized polypeptide N-acetyl-d-galactosamine-transferase 2 isoenzyme. GALNT2 is widely expressed in most cell types and directs initiation of mucin-type protein O-glycosylation. All patients showed loss of O-glycosylation of apolipoprotein C-III, a non-redundant substrate for GALNT2. Patients with GALNT2-CDG generally exhibit a syndrome characterized by global developmental delay, intellectual disability with language deficit, autistic features, behavioural abnormalities, epilepsy, chronic insomnia, white matter changes on brain MRI, dysmorphic features, decreased stature, and decreased high density lipoprotein cholesterol levels. Rodent (mouse and rat) models of GALNT2-CDG recapitulated much of the human phenotype, including poor growth and neurodevelopmental abnormalities. In behavioural studies, GALNT2-CDG mice demonstrated cerebellar motor deficits, decreased sociability, and impaired sensory integration and processing. The multisystem nature of phenotypes in patients and rodent models of GALNT2-CDG suggest that there are multiple non-redundant protein substrates of GALNT2 in various tissues, including brain, which are critical to normal growth and development.
Keywords: Adolescent; Animals; Apolipoprotein C-III; Child; Child, Preschool; Developmental Disabilities; Female; Glycosylation; Humans; Loss of Function Mutation; Male; Mice; N-Acetylgalactosaminyltransferases; Pedigree; Rats; Young Adult

Novel pathogenic genomic variants leading to autosomal dominant and recessive Robinow syndrome. - Zhang, Chaofan; Mazzeu, Juliana F; Eisfeldt, Jesper; Grochowski, Christopher M; White, Janson; Akdemir, Zeynep C; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lindstrand, Anna; Lupski, James R; Sutton, V Reid; et al. (Am J Med Genet A, 2020)
Robinow syndrome (RS) is a genetically heterogeneous disorder characterized by skeletal dysplasia and a distinctive facial appearance. Previous studies have revealed locus heterogeneity with rare variants in DVL1, DVL3, FZD2, NXN, ROR2, and WNT5A underlying the etiology of RS. The aforementioned "Robinow-associated genes" and their gene products all play a role in the WNT/planar cell polarity signaling pathway. We performed gene-targeted Sanger sequencing, exome sequencing, genome sequencing, and array comparative genomic hybridization on four subjects with a clinical diagnosis of RS who had not had prior DNA testing. Individuals in our cohort were found to carry pathogenic or likely pathogenic variants in three RS related genes: DVL1, ROR2, and NXN. One subject was found to have a nonsense variant (c.817C > T [p.Gln273*]) in NXN in trans with an ~1 Mb telomeric deletion on chromosome 17p containing NXN, which supports our contention that biallelic NXN variant alleles are responsible for a novel autosomal recessive RS locus. These findings provide increased understanding of the role of WNT signaling in skeletal development and maintenance. These data further support the hypothesis that dysregulation of the noncanonical WNT pathway in humans gives rise to RS.

Organic Solute Transporter Alpha Deficiency: A Disorder With Cholestasis, Liver Fibrosis, and Congenital Diarrhea. - Gao, Emily; Cheema, Huma; Waheed, Nadia; Mushtaq, Iqra; Erden, Nihan; Nelson-Williams, Carol; Jain, Dhanpat; Soroka, Carol J; Boyer, James L; Khalil, Youssef; Clayton, Peter T; Mistry, Pramod K; et al. (Hepatology, 2020)
Keywords: Child, Preschool; Cholestasis; Diarrhea; Humans; Liver; Liver Cirrhosis; Male; Mutation; Pedigree; Receptors, G-Protein-Coupled

Parliament2: Accurate structural variant calling at scale. - Zarate, Samantha; Carroll, Andrew; Mahmoud, Medhat; Krasheninina, Olga; Jun, Goo; Salerno, William J; Schatz, Michael C; Boerwinkle, Eric; Gibbs, Richard A; Sedlazeck, Fritz J (Gigascience, 2020)
BACKGROUND: Structural variants (SVs) are critical contributors to genetic diversity and genomic disease. To predict the phenotypic impact of SVs, there is a need for better estimates of both the occurrence and frequency of SVs, preferably from large, ethnically diverse cohorts. Thus, the current standard approach requires the use of short paired-end reads, which remain challenging to detect, especially at the scale of hundreds to thousands of samples. FINDINGS: We present Parliament2, a consensus SV framework that leverages multiple best-in-class methods to identify high-quality SVs from short-read DNA sequence data at scale. Parliament2 incorporates pre-installed SV callers that are optimized for efficient execution in parallel to reduce the overall runtime and costs. We demonstrate the accuracy of Parliament2 when applied to data from NovaSeq and HiSeq X platforms with the Genome in a Bottle (GIAB) SV call set across all size classes. The reported quality score per SV is calibrated across different SV types and size classes. Parliament2 has the highest F1 score (74.27%) measured across the independent gold standard from GIAB. We illustrate the compute performance by processing all 1000 Genomes samples (2,691 samples) in <1 day on GRCH38. Parliament2 improves the runtime performance of individual methods and is open source (https://github.com/slzarate/parliament2), and a Docker image, as well as a WDL implementation, is available. CONCLUSION: Parliament2 provides both a highly accurate single-sample SV call set from short-read DNA sequence data and enables cost-efficient application over cloud or cluster environments, processing thousands of samples.

Pathogenic Variants in CEP85L Cause Sporadic and Familial Posterior Predominant Lissencephaly. - Tsai, Meng-Han; Muir, Alison M; Wang, Won-Jing; Kang, Yi-Ning; Yang, Kun-Chuan; Chao, Nian-Hsin; Wu, Mei-Feng; Chang, Ying-Chao; Porter, Brenda E; Jansen, Laura A; Sebire, Guillaume; Deconinck, Nicolas; et al. (Neuron, 2020)
Lissencephaly (LIS), denoting a "smooth brain," is characterized by the absence of normal cerebral convolutions with abnormalities of cortical thickness. Pathogenic variants in over 20 genes are associated with LIS. The majority of posterior predominant LIS is caused by pathogenic variants in LIS1 (also known as PAFAH1B1), although a significant fraction remains without a known genetic etiology. We now implicate CEP85L as an important cause of posterior predominant LIS, identifying 13 individuals with rare, heterozygous CEP85L variants, including 2 families with autosomal dominant inheritance. We show that CEP85L is a centrosome protein localizing to the pericentriolar material, and knockdown of Cep85l causes a neuronal migration defect in mice. LIS1 also localizes to the centrosome, suggesting that this organelle is key to the mechanism of posterior predominant LIS.
Keywords: Adolescent; Adult; Age of Onset; Animals; Centrosome; Child; Child, Preschool; Chromosome Aberrations; Classical Lissencephalies and Subcortical Band Heterotopias; Cytoskeletal Proteins; Female; Gene Knockdown Techniques; Genetic Variation; Heterozygote; Humans; Infant; Magnetic Resonance Imaging; Male; Mice; Mutation; Oncogene Proteins, Fusion; Pedigree; Seizures; Young Adult

Phenotypic expansion in KIF1A-related dominant disorders: A description of novel variants and review of published cases. - Montenegro-Garreaud, Ximena; Hansen, Adam W; Khayat, Michael M; Chander, Varuna; Grochowski, Christopher M; Jiang, Yunyun; Li, He; Mitani, Tadahiro; Kessler, Elena; Jayaseelan, Joy; Shen, Hua; Gezdirici, Alper; et al. (Hum Mutat, 2020)
KIF1A is a molecular motor for membrane-bound cargo important to the development and survival of sensory neurons. KIF1A dysfunction has been associated with several Mendelian disorders with a spectrum of overlapping phenotypes, ranging from spastic paraplegia to intellectual disability. We present a novel pathogenic in-frame deletion in the KIF1A molecular motor domain inherited by two affected siblings from an unaffected mother with apparent germline mosaicism. We identified eight additional cases with heterozygous, pathogenic KIF1A variants ascertained from a local data lake. Our data provide evidence for the expansion of KIF1A-associated phenotypes to include hip subluxation and dystonia as well as phenotypes observed in only a single case: gelastic cataplexy, coxa valga, and double collecting system. We review the literature and suggest that KIF1A dysfunction is better understood as a single neuromuscular disorder with variable involvement of other organ systems than a set of discrete disorders converging at a single locus.

Phenotypic spectrum and transcriptomic profile associated with germline variants in TRAF7. - Castilla-Vallmanya, Laura; Selmer, Kaja K; Dimartino, Clémantine; Rabionet, Raquel; Blanco-Sánchez, Bernardo; Yang, Sandra; Reijnders, Margot R F; van Essen, Antonie J; Oufadem, Myriam; Vigeland, Magnus D; Stadheim, Barbro; Houge, Gunnar; et al. (Genet Med, 2020)
PURPOSE: Somatic variants in tumor necrosis factor receptor-associated factor 7 (TRAF7) cause meningioma, while germline variants have recently been identified in seven patients with developmental delay and cardiac, facial, and digital anomalies. We aimed to define the clinical and mutational spectrum associated with TRAF7 germline variants in a large series of patients, and to determine the molecular effects of the variants through transcriptomic analysis of patient fibroblasts. METHODS: We performed exome, targeted capture, and Sanger sequencing of patients with undiagnosed developmental disorders, in multiple independent diagnostic or research centers. Phenotypic and mutational comparisons were facilitated through data exchange platforms. Whole-transcriptome sequencing was performed on RNA from patient- and control-derived fibroblasts. RESULTS: We identified heterozygous missense variants in TRAF7 as the cause of a developmental delay-malformation syndrome in 45 patients. Major features include a recognizable facial gestalt (characterized in particular by blepharophimosis), short neck, pectus carinatum, digital deviations, and patent ductus arteriosus. Almost all variants occur in the WD40 repeats and most are recurrent. Several differentially expressed genes were identified in patient fibroblasts. CONCLUSION: We provide the first large-scale analysis of the clinical and mutational spectrum associated with the TRAF7 developmental syndrome, and we shed light on its molecular etiology through transcriptome studies.
Keywords: Exome; Germ Cells; Humans; Intellectual Disability; Mutation, Missense; Phenotype; Transcriptome; Tumor Necrosis Factor Receptor-Associated Peptides and Proteins

POGLUT1 biallelic mutations cause myopathy with reduced satellite cells, α-dystroglycan hypoglycosylation and a distinctive radiological pattern. - Servián-Morilla, E; Cabrera-Serrano, M; Johnson, K; Pandey, A; Ito, A; Rivas, E; Chamova, T; Muelas, N; Mongini, T; Nafissi, S; Claeys, K G; Grewal, R P; et al. (Acta Neuropathol, 2020)
Protein O-glucosyltransferase 1 (POGLUT1) activity is critical for the Notch signaling pathway, being one of the main enzymes responsible for the glycosylation of the extracellular domain of Notch receptors. A biallelic mutation in the POGLUT1 gene has been reported in one family as the cause of an adult-onset limb-girdle muscular dystrophy (LGMD R21; OMIM# 617232). As the result of a collaborative international effort, we have identified the first cohort of 15 patients with LGMD R21, from nine unrelated families coming from different countries, providing a reliable phenotype-genotype and mechanistic insight. Patients carrying novel mutations in POGLUT1 all displayed a clinical picture of limb-girdle muscle weakness. However, the age at onset was broadened from adult to congenital and infantile onset. Moreover, we now report that the unique muscle imaging pattern of "inside-to-outside" fatty degeneration observed in the original cases is indeed a defining feature of POGLUT1 muscular dystrophy. Experiments on muscle biopsies from patients revealed a remarkable and consistent decrease in the level of the NOTCH1 intracellular domain, reduction of the pool of satellite cells (SC), and evidence of α-dystroglycan hypoglycosylation. In vitro biochemical and cell-based assays suggested a pathogenic role of the novel POGLUT1 mutations, leading to reduced enzymatic activity and/or protein stability. The association between the POGLUT1 variants and the muscular phenotype was established by in vivo experiments analyzing the indirect flight muscle development in transgenic Drosophila, showing that the human POGLUT1 mutations reduced its myogenic activity. In line with the well-known role of the Notch pathway in the homeostasis of SC and muscle regeneration, SC-derived myoblasts from patients' muscle samples showed decreased proliferation and facilitated differentiation. Together, these observations suggest that alterations in SC biology caused by reduced Notch1 signaling result in muscular dystrophy in LGMD R21 patients, likely with additional contribution from α-dystroglycan hypoglycosylation. This study settles the muscular clinical phenotype linked to POGLUT1 mutations and establishes the pathogenic mechanism underlying this muscle disorder. The description of a specific imaging pattern of fatty degeneration and muscle pathology with a decrease of α-dystroglycan glycosylation provides excellent tools which will help diagnose and follow up LGMD R21 patients.
Keywords: Animals; Animals, Genetically Modified; Drosophila melanogaster; Dystroglycans; Female; Genetic Association Studies; Glucosyltransferases; Glycosylation; Humans; Male; Muscle, Skeletal; Muscular Dystrophies, Limb-Girdle; Mutation; Pedigree; Satellite Cells, Skeletal Muscle

Recurrent arginine substitutions in the ACTG2 gene are the primary driver of disease burden and severity in visceral myopathy. - Assia Batzir, Nurit; Kishor Bhagwat, Pranjali; Larson, Austin; Coban Akdemir, Zeynep; Bagłaj, Maciej; Bofferding, Leon; Bosanko, Katherine B; Bouassida, Skander; Callewaert, Bert; Cannon, Ashley; Enchautegui Colon, Yazmin; Garnica, Adolfo D; et al. (Hum Mutat, 2020)
Visceral myopathy with abnormal intestinal and bladder peristalsis includes a clinical spectrum with megacystis-microcolon intestinal hypoperistalsis syndrome and chronic intestinal pseudo-obstruction. The vast majority of cases are caused by dominant variants in ACTG2; however, the overall genetic architecture of visceral myopathy has not been well-characterized. We ascertained 53 families, with visceral myopathy based on megacystis, functional bladder/gastrointestinal obstruction, or microcolon. A combination of targeted ACTG2 sequencing and exome sequencing was used. We report a molecular diagnostic rate of 64% (34/53), of which 97% (33/34) is attributed to ACTG2. Strikingly, missense mutations in five conserved arginine residues involving CpG dinucleotides accounted for 49% (26/53) of disease in the cohort. As a group, the ACTG2-negative cases had a more favorable clinical outcome and more restricted disease. Within the ACTG2-positive group, poor outcomes (characterized by total parenteral nutrition dependence, death, or transplantation) were invariably due to one of the arginine missense alleles. Analysis of specific residues suggests a severity spectrum of p.Arg178>p.Arg257>p.Arg40 along with other less-frequently reported sites p.Arg63 and p.Arg211. These results provide genotype-phenotype correlation for ACTG2-related disease and demonstrate the importance of arginine missense changes in visceral myopathy.

Recurrent De Novo NAHR Reciprocal Duplications in the ATAD3 Gene Cluster Cause a Neurogenetic Trait with Perturbed Cholesterol and Mitochondrial Metabolism. - Gunning, Adam C; Strucinska, Klaudia; Muñoz Oreja, Mikel; Parrish, Andrew; Caswell, Richard; Stals, Karen L; Durigon, Romina; Durlacher-Betzer, Karina; Cunningham, Mitchell H; Grochowski, Christopher M; Baptista, Julia; Tysoe, Carolyn; et al. (Am J Hum Genet, 2020)
Recent studies have identified both recessive and dominant forms of mitochondrial disease that result from ATAD3A variants. The recessive form includes subjects with biallelic deletions mediated by non-allelic homologous recombination. We report five unrelated neonates with a lethal metabolic disorder characterized by cardiomyopathy, corneal opacities, encephalopathy, hypotonia, and seizures in whom a monoallelic reciprocal duplication at the ATAD3 locus was identified. Analysis of the breakpoint junction fragment indicated that these 67 kb heterozygous duplications were likely mediated by non-allelic homologous recombination at regions of high sequence identity in ATAD3A exon 11 and ATAD3C exon 7. At the recombinant junction, the duplication allele produces a fusion gene derived from ATAD3A and ATAD3C, the protein product of which lacks key functional residues. Analysis of fibroblasts derived from two affected individuals shows that the fusion gene product is expressed and stable. These cells display perturbed cholesterol and mitochondrial DNA organization similar to that observed for individuals with severe ATAD3A deficiency. We hypothesize that the fusion protein acts through a dominant-negative mechanism to cause this fatal mitochondrial disorder. Our data delineate a molecular diagnosis for this disorder, extend the clinical spectrum associated with structural variation at the ATAD3 locus, and identify a third mutational mechanism for ATAD3 gene cluster variants. These results further affirm structural variant mutagenesis mechanisms in sporadic disease traits, emphasize the importance of copy number analysis in molecular genomic diagnosis, and highlight some of the challenges of detecting and interpreting clinically relevant rare gene rearrangements from next-generation sequencing data.
Keywords: Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Brain Diseases; Cardiomyopathies; Cholesterol; Corneal Opacity; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Homologous Recombination; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Diseases; Mitochondrial Proteins; Muscle Hypotonia; Mutation; Protein Conformation; Seizures; Sequence Homology

Recurrent TTN metatranscript-only c.39974-11T>G splice variant associated with autosomal recessive arthrogryposis multiplex congenita and myopathy. - Bryen, Samantha J; Ewans, Lisa J; Pinner, Jason; MacLennan, Suzanna C; Donkervoort, Sandra; Castro, Diana; Topf, Ana; O'Grady, Gina; Cummings, Beryl; Chao, Katherine R; Weisburd, Ben; Francioli, Laurent; et al. (Hum Mutat, 2020)
We present eight families with arthrogryposis multiplex congenita and myopathy bearing a TTN intron 213 extended splice-site variant (NM_001267550.1:c.39974-11T>G), inherited in trans with a second pathogenic TTN variant. Muscle-derived RNA studies of three individuals confirmed mis-splicing induced by the c.39974-11T>G variant; in-frame exon 214 skipping or use of a cryptic 3' splice-site effecting a frameshift. Confounding interpretation of pathogenicity is the absence of exons 213-217 within the described skeletal muscle TTN N2A isoform. However, RNA-sequencing from 365 adult human gastrocnemius samples revealed that 56% specimens predominantly include exons 213-217 in TTN transcripts (inclusion rate ≥66%). Further, RNA-sequencing of five fetal muscle samples confirmed that 4/5 specimens predominantly include exons 213-217 (fifth sample inclusion rate 57%). Contractures improved significantly with age for four individuals, which may be linked to decreased expression of pathogenic fetal transcripts. Our study extends emerging evidence supporting a vital developmental role for TTN isoforms containing metatranscript-only exons.

Regulation of human cerebral cortical development by EXOC7 and EXOC8, components of the exocyst complex, and roles in neural progenitor cell proliferation and survival. - Coulter, Michael E; Musaev, Damir; DeGennaro, Ellen M; Zhang, Xiaochang; Henke, Katrin; James, Kiely N; Smith, Richard S; Hill, R Sean; Partlow, Jennifer N; Kamumbu, A Stacy; Hatem, Nicole; Barkovich, A James; et al. (Genet Med, 2020)
PURPOSE: The exocyst complex is a conserved protein complex that mediates fusion of intracellular vesicles to the plasma membrane and is implicated in processes including cell polarity, cell migration, ciliogenesis, cytokinesis, autophagy, and fusion of secretory vesicles. The essential role of these genes in human genetic disorders, however, is unknown. METHODS: We performed homozygosity mapping and exome sequencing of consanguineous families with recessively inherited brain development disorders. We modeled an EXOC7 splice variant in vitro and examined EXOC7 messenger RNA (mRNA) expression in developing mouse and human cortex. We modeled exoc7 loss-of-function in a zebrafish knockout. RESULTS: We report variants in exocyst complex members, EXOC7 and EXOC8, in a novel disorder of cerebral cortex development. In EXOC7, we identified four independent partial loss-of-function (LOF) variants in a recessively inherited disorder characterized by brain atrophy, seizures, and developmental delay, and in severe cases, microcephaly and infantile death. In EXOC8, we found a homozygous truncating variant in a family with a similar clinical disorder. We modeled exoc7 deficiency in zebrafish and found the absence of exoc7 causes microcephaly. CONCLUSION: Our results highlight the essential role of the exocyst pathway in normal cortical development and how its perturbation causes complex brain disorders.
Keywords: Animals; Brain Diseases; Cell Proliferation; Homozygote; Humans; Mice; Microcephaly; Zebrafish

Sequential targeted exome sequencing of 1001 patients affected by unexplained limb-girdle weakness. - Topf, Ana; Johnson, Katherine; Bates, Adam; Phillips, Lauren; Chao, Katherine R; England, Eleina M; Laricchia, Kristen M; Mullen, Thomas; Valkanas, Elise; Xu, Liwen; Bertoli, Marta; Blain, Alison; et al. (Genet Med, 2020)
PURPOSE: Several hundred genetic muscle diseases have been described, all of which are rare. Their clinical and genetic heterogeneity means that a genetic diagnosis is challenging. We established an international consortium, MYO-SEQ, to aid the work-ups of muscle disease patients and to better understand disease etiology. METHODS: Exome sequencing was applied to 1001 undiagnosed patients recruited from more than 40 neuromuscular disease referral centers; standardized phenotypic information was collected for each patient. Exomes were examined for variants in 429 genes associated with muscle conditions. RESULTS: We identified suspected pathogenic variants in 52% of patients across 87 genes. We detected 401 novel variants, 116 of which were recurrent. Variants in CAPN3, DYSF, ANO5, DMD, RYR1, TTN, COL6A2, and SGCA collectively accounted for over half of the solved cases; while variants in newer disease genes, such as BVES and POGLUT1, were also found. The remaining well-characterized unsolved patients (48%) need further investigation. CONCLUSION: Using our unique infrastructure, we developed a pathway to expedite muscle disease diagnoses. Our data suggest that exome sequencing should be used for pathogenic variant detection in patients with suspected genetic muscle diseases, focusing first on the most common disease genes described here, and subsequently in rarer and newly characterized disease genes.
Keywords: Anoctamins; Exome; Glucosyltransferases; Humans; Muscular Dystrophies, Limb-Girdle; Whole Exome Sequencing

truncations cause arrhythmogenic right ventricular cardiomyopathy. - Brun, Francesca; Gigli, Marta; Graw, Sharon L; Judge, Daniel P; Merlo, Marco; Murray, Brittney; Calkins, Hugh; Sinagra, Gianfranco; Taylor, Matthew Rg; Mestroni, Luisa; James, Cynthia A (J Med Genet, 2020)
BACKGROUND: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heart muscle disease that affects predominantly the right ventricle and is part of the spectrum of arrythmogenic cardiomyopathies (ACMs). ARVC is a genetic condition; however, a pathogenic gene variant is found in only half of patients. OBJECTIVE: Filamin C gene truncations () have recently been identified in dilated cardiomyopathy with ventricular arrhythmia and sudden cardiac death, a phenotype partially overlapping with ARVC and part of the ACM spectrum. We hypothesised that could be a novel gene associated with ARVC. METHODS: One hundred fifty-six patients meeting 2010 ARVC Task Force Criteria and lacking variants in known ARVC genes were evaluated for variants. Available family members were tested for cosegregation. RESULTS: We identified two unique variants in two families (c.6565 G>T, p.Glu2189Ter and c.8107delG, p.Asp2703ThrfsTer69), with phenotypes of dominant RV disease fulfilling 'definite' diagnosis of ARVC according to the 2010 Task Force Criteria. Variants in other cardiomyopathy genes were excluded in both kindreds, and segregation analysis revealed that p.Asp2703ThrfsTer69 was a de novo variant. In both families, the disease phenotype was characterised by prominent ventricular arrhythmias and sudden cardiac arrest. CONCLUSION: The identification of as a novel cause of ARVC in two unrelated families expands the spectrum of ARVC disease genes for this disorder. Our findings should prompt inclusion of genetic testing in ARVC to improve diagnostic yield and testing of at-risk relatives in ARVC.
Keywords: Adult; Aged; Arrhythmogenic Right Ventricular Dysplasia; Female; Filamins; Genetic Predisposition to Disease; Genetic Testing; Heart Ventricles; Humans; Male; Middle Aged; Mutation; Phenotype

Type 2 and interferon inflammation regulate SARS-CoV-2 entry factor expression in the airway epithelium. - Sajuthi, Satria P; DeFord, Peter; Li, Yingchun; Jackson, Nathan D; Montgomery, Michael T; Everman, Jamie L; Rios, Cydney L; Pruesse, Elmar; Nolin, James D; Plender, Elizabeth G; Wechsler, Michael E; Mak, Angel C Y; et al. (Nat Commun, 2020)
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2, an emerging virus that utilizes host proteins ACE2 and TMPRSS2 as entry factors. Understanding the factors affecting the pattern and levels of expression of these genes is important for deeper understanding of SARS-CoV-2 tropism and pathogenesis. Here we explore the role of genetics and co-expression networks in regulating these genes in the airway, through the analysis of nasal airway transcriptome data from 695 children. We identify expression quantitative trait loci for both ACE2 and TMPRSS2, that vary in frequency across world populations. We find TMPRSS2 is part of a mucus secretory network, highly upregulated by type 2 (T2) inflammation through the action of interleukin-13, and that the interferon response to respiratory viruses highly upregulates ACE2 expression. IL-13 and virus infection mediated effects on ACE2 expression were also observed at the protein level in the airway epithelium. Finally, we define airway responses to common coronavirus infections in children, finding that these infections generate host responses similar to other viral species, including upregulation of IL6 and ACE2. Our results reveal possible mechanisms influencing SARS-CoV-2 infectivity and COVID-19 clinical outcomes.
Keywords: Angiotensin-Converting Enzyme 2; Betacoronavirus; Child; Coronavirus Infections; COVID-19; Epithelial Cells; Gene Expression Profiling; Gene Expression Regulation; Genetic Variation; Host-Pathogen Interactions; Humans; Inflammation; Interferons; Interleukin-13; Middle Aged; Nasal Mucosa; Pandemics; Peptidyl-Dipeptidase A; Pneumonia, Viral; SARS-CoV-2; Serine Endopeptidases; Virus Internalization

Type 2 and interferon inflammation strongly regulate SARS-CoV-2 related gene expression in the airway epithelium. - Sajuthi, Satria P; DeFord, Peter; Jackson, Nathan D; Montgomery, Michael T; Everman, Jamie L; Rios, Cydney L; Pruesse, Elmar; Nolin, James D; Plender, Elizabeth G; Wechsler, Michael E; Mak, Angel Cy; Eng, Celeste; et al. (bioRxiv, 2020)
Coronavirus disease 2019 (COVID-19) outcomes vary from asymptomatic infection to death. This disparity may reflect different airway levels of the SARS-CoV-2 receptor, ACE2, and the spike protein activator, TMPRSS2. Here we explore the role of genetics and co-expression networks in regulating these genes in the airway, through the analysis of nasal airway transcriptome data from 695 children. We identify expression quantitative trait loci (eQTL) for both and , that vary in frequency across world populations. Importantly, we find is part of a mucus secretory network, highly upregulated by T2 inflammation through the action of interleukin-13, and that interferon response to respiratory viruses highly upregulates expression. Finally, we define airway responses to coronavirus infections in children, finding that these infections upregulate while also stimulating a more pronounced cytotoxic immune response relative to other respiratory viruses. Our results reveal mechanisms likely influencing SARS-CoV-2 infectivity and COVID-19 clinical outcomes.

The utility of exome sequencing for fetal pleural effusions. - Jelin, Angie C; Sobreira, Nara; Wohler, Elizabeth; Solomon, Benjamin; Sparks, Teresa; Sagaser, Katelynn G; Forster, Katherine R; Miller, Jena; Witmer, P Dane; Hamosh, Ada; Valle, David; Blakemore, Karin (Prenat Diagn, 2020)
OBJECTIVE: We sought to evaluate the performance of exome sequencing (ES) in determining an underlying genetic etiology for cases of fetal pleural effusions. STUDY DESIGN: We examined a prospective cohort series of fetal pleural effusions visualized sonographically between 1 April 2016 and 31 August 2017. Fetal pleural effusions attributed to twin sharing, anemia, or structural anomalies were excluded, as were all cases with a genetic diagnosis established by karyotype or chromosomal microarray analysis. The remaining cases with pleural effusions of unclear etiology were offered ES. ES was performed by clinical sequencing and/or sequencing under the Baylor-Hopkins Center for Mendelian Genomics' (BHCMG) research platform. All cases were evaluated for novel genes or phenotypic expansion of disease-causing genes. RESULTS: ES was performed on six probands affected by pleural effusions. A pathogenic variant was identified in one case (16.7%). Four additional cases had variants of uncertain significance (VUS) in candidate genes of pathological interest. Neither clinical nor candidate genes were evident in the final case. CONCLUSION: ES should be considered in the evaluation of prenatally detected idiopathic pleural effusions when other diagnostic workup for a genetic etiology has failed.

variants are associated with multiple congenital anomalies including ciliopathy phenotypes. - Marquez, Jonathan; Mann, Nina; Arana, Kathya; Deniz, Engin; Ji, Weizhen; Konstantino, Monica; Mis, Emily K; Deshpande, Charu; Jeffries, Lauren; McGlynn, Julie; Hugo, Hannah; Widmeier, Eugen; et al. (J Med Genet, 2020)
BACKGROUND: Cilia are dynamic cellular extensions that generate and sense signals to orchestrate proper development and tissue homeostasis. They rely on the underlying polarisation of cells to participate in signalling. Cilia dysfunction is a well-known cause of several diseases that affect multiple organ systems including the kidneys, brain, heart, respiratory tract, skeleton and retina. METHODS: Among individuals from four unrelated families, we identified variants in ( that manifested in a variety of pathologies. In our proband, we also examined patient tissues. We depleted in frog embryos to generate a loss-of-function model. Finally, we tested the pathogenicity of patient variants through rescue experiments in the frog model. RESULTS: Patients with variants of were found to have a variety of phenotypes including cystic kidneys, nephrotic syndrome, hydrocephalus, limb abnormalities, congenital heart disease and craniofacial malformations. We also observed a loss of cilia in cystic kidney tissue of our proband. Knockdown of in embryos recapitulated many of these phenotypes and resulted in a loss of cilia in multiple tissues. Unlike introduction of wildtype in frog embryos depleted of introduction of patient variants was largely ineffective in restoring proper ciliation and tissue morphology in the kidney and brain suggesting that the variants were indeed detrimental to function. CONCLUSION: These findings in both patient tissues and shed light on how mutations in may lead to tissue-specific manifestations of disease. DLG5 is essential for cilia and many of the patient phenotypes are in the ciliopathy spectrum.

Variants in CAPZA2, a member of an F-actin capping complex, cause intellectual disability and developmental delay. - Huang, Yan; Mao, Xiao; van Jaarsveld, Richard H; Shu, Li; Terhal, Paulien A; Jia, Zhengjun; Xi, Hui; Peng, Ying; Yan, Huiming; Yuan, Shan; Li, Qibin; Wang, Hua; et al. (Hum Mol Genet, 2020)
The actin cytoskeleton is regulated by many proteins including capping proteins that stabilize actin filaments (F-actin) by inhibiting actin polymerization and depolymerization. Here, we report two pediatric probands who carry damaging heterozygous de novo mutations in CAPZA2 (HGNC: 1490) and exhibit neurological symptoms with shared phenotypes including global motor development delay, speech delay, intellectual disability, hypotonia and a history of seizures. CAPZA2 encodes a subunit of an F-actin-capping protein complex (CapZ). CapZ is an obligate heterodimer consisting of α and β heterodimer conserved from yeast to human. Vertebrate genomes contain three α subunits encoded by three different genes and CAPZA2 encodes the α2 subunit. The single orthologue of CAPZA genes in Drosophila is cpa. Loss of cpa leads to lethality in early development and expression of the human reference; CAPZA2 rescues this lethality. However, the two CAPZA2 variants identified in the probands rescue this lethality at lower efficiency than the reference. Moreover, expression of the CAPZA2 variants affects bristle morphogenesis, a process that requires extensive actin polymerization and bundling during development. Taken together, our findings suggest that variants in CAPZA2 lead to a non-syndromic neurodevelopmental disorder in children.

Whole exome sequencing identified ATP6V1C2 as a novel candidate gene for recessive distal renal tubular acidosis. - Jobst-Schwan, Tilman; Klämbt, Verena; Tarsio, Maureen; Heneghan, John F; Majmundar, Amar J; Shril, Shirlee; Buerger, Florian; Ottlewski, Isabel; Shmukler, Boris E; Topaloglu, Rezan; Hashmi, Seema; Hafeez, Farkhanda; et al. (Kidney Int, 2020)
Distal renal tubular acidosis is a rare renal tubular disorder characterized by hyperchloremic metabolic acidosis and impaired urinary acidification. Mutations in three genes (ATP6V0A4, ATP6V1B1 and SLC4A1) constitute a monogenic causation in 58-70% of familial cases of distal renal tubular acidosis. Recently, mutations in FOXI1 have been identified as an additional cause. Therefore, we hypothesized that further monogenic causes of distal renal tubular acidosis remain to be discovered. Panel sequencing and/or whole exome sequencing was performed in a cohort of 17 families with 19 affected individuals with pediatric onset distal renal tubular acidosis. A causative mutation was detected in one of the three "classical" known distal renal tubular acidosis genes in 10 of 17 families. The seven unsolved families were then subjected to candidate whole exome sequencing analysis. Potential disease causing mutations in three genes were detected: ATP6V1C2, which encodes another kidney specific subunit of the V-type proton ATPase (1 family); WDR72 (2 families), previously implicated in V-ATPase trafficking in cells; and SLC4A2 (1 family), a paralog of the known distal renal tubular acidosis gene SLC4A1. Two of these mutations were assessed for deleteriousness through functional studies. Yeast growth assays for ATP6V1C2 revealed loss-of-function for the patient mutation, strongly supporting ATP6V1C2 as a novel distal renal tubular acidosis gene. Thus, we provided a molecular diagnosis in a known distal renal tubular acidosis gene in 10 of 17 families (59%) with this disease, identified mutations in ATP6V1C2 as a novel human candidate gene, and provided further evidence for phenotypic expansion in WDR72 mutations from amelogenesis imperfecta to distal renal tubular acidosis.

Whole exome sequencing in a large pedigree with DCM identifies a novel mutation in . - Robyns, Tomas; Willems, Rik; Van Cleemput, Johan; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Breckpot, Jeroen; Devriendt, Koenraad; Corveleyn, Anniek (Acta Cardiol, 2020)
Familial dilated cardiomyopathy (DCM) is genetically heterogeneous and is associated with mutations in at least 40 different genes. Apart from encoding the giant protein Titin, none of these genes have an expected diagnostic yield of more than 5% complicating genetic diagnosis. Whole exome sequencing (WES) is a powerful alternative for the identification of the causal gene, however variant interpretation remains challenging. We report on WES in a large family with autosomal dominant DCM complicated by end stage heart failure and non-sustained ventricular arrhythmias in whom no causative mutation was identified using a targeted gene panel including 28 genes. WES was applied on 2 affected cousins. Stringent filtering of the identified genetic variants was performed including population variant frequencies, in silico analysis, orthologous and paralogous conservation. Subsequently Sanger sequencing was performed for 10 potential disease causing variants in order to confirm the presence of the variant and to evaluate co-segregation. Only one variant in exon 9 of the RBM20 gene (c.2714T > A, p.Met950Lys, NM_001334363) showed full co-segregation in the 7 affected family members resulting in a maximum 2-point LOD score of 2.1 and suggesting this as the pathogenic mutation responsible for the phenotype. Recently mutations in RBM20 have been linked to arrhythmogenic dilated cardiomyopathy caused by defective splicing of the giant sarcomere protein titin and abnormal calcium handling. We report the identification of a novel mutation in RBM20 by WES in a large pedigree with DCM.

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Whole Exome Sequencing; Wolff-Parkinson-White Syndrome; Young Adult

Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation

A2ML1 and otitis media: novel variants, differential expression, and relevant pathways. - Larson, Eric D; Magno, Jose Pedrito M; Steritz, Matthew J; Llanes, Erasmo Gonzalo D V; Cardwell, Jonathan; Pedro, Melquiadesa; Roberts, Tori Bootpetch; Einarsdottir, Elisabet; Rosanes, Rose Anne Q; Greenlee, Christopher; Santos, Rachel Ann P; Yousaf, Ayesha; et al. (Hum Mutat, 2019)
A genetic basis for otitis media is established, however, the role of rare variants in disease etiology is largely unknown. Previously a duplication variant within A2ML1 was identified as a significant risk factor for otitis media in an indigenous Filipino population and in US children. In this report exome and Sanger sequencing was performed using DNA samples from the indigenous Filipino population, Filipino cochlear implantees, US probands, Finnish, and Pakistani families with otitis media. Sixteen novel, damaging A2ML1 variants identified in otitis media patients were rare or low-frequency in population-matched controls. In the indigenous population, both gingivitis and A2ML1 variants including the known duplication variant and the novel splice variant c.4061 + 1 G>C were independently associated with otitis media. Sequencing of salivary RNA samples from indigenous Filipinos demonstrated lower A2ML1 expression according to the carriage of A2ML1 variants. Sequencing of additional salivary RNA samples from US patients with otitis media revealed differentially expressed genes that are highly correlated with A2ML1 expression levels. In particular, RND3 is upregulated in both A2ML1 variant carriers and high-A2ML1 expressors. These findings support a role for A2ML1 in keratinocyte differentiation within the middle ear as part of otitis media pathology and the potential application of ROCK inhibition in otitis media.

Atlas-CNV: a validated approach to call single-exon CNVs in the eMERGESeq gene panel. - Chiang, Theodore; Liu, Xiuping; Wu, Tsung-Jung; Hu, Jianhong; Sedlazeck, Fritz J; White, Simon; Schaid, Daniel; Andrade, Mariza de; Jarvik, Gail P; Crosslin, David; Stanaway, Ian; Carrell, David S; et al. (Genet Med, 2019)
PURPOSE: To provide a validated method to confidently identify exon-containing copy-number variants (CNVs), with a low false discovery rate (FDR), in targeted sequencing data from a clinical laboratory with particular focus on single-exon CNVs. METHODS: DNA sequence coverage data are normalized within each sample and subsequently exonic CNVs are identified in a batch of samples, when the target log ratio of the sample to the batch median exceeds defined thresholds. The quality of exonic CNV calls is assessed by C-scores (Z-like scores) using thresholds derived from gold standard samples and simulation studies. We integrate an ExonQC threshold to lower FDR and compare performance with alternate software (VisCap). RESULTS: Thirteen CNVs were used as a truth set to validate Atlas-CNV and compared with VisCap. We demonstrated FDR reduction in validation, simulation, and 10,926 eMERGESeq samples without sensitivity loss. Sixty-four multiexon and 29 single-exon CNVs with high C-scores were assessed by Multiplex Ligation-dependent Probe Amplification (MLPA). CONCLUSION: Atlas-CNV is validated as a method to identify exonic CNVs in targeted sequencing data generated in the clinical laboratory. The ExonQC and C-score assignment can reduce FDR (identification of targets with high variance) and improve calling accuracy of single-exon CNVs respectively. We propose guidelines and criteria to identify high confidence single-exon CNVs.

Biallelic CACNA2D2 variants in epileptic encephalopathy and cerebellar atrophy. - Punetha, Jaya; Karaca, Ender; Gezdirici, Alper; Lamont, Ryan E; Pehlivan, Davut; Marafi, Dana; Appendino, Juan P; Hunter, Jill V; Akdemir, Zeynep C; Fatih, Jawid M; Jhangiani, Shalini N; Gibbs, Richard A; et al. (Ann Clin Transl Neurol, 2019)
OBJECTIVE: To characterize the molecular and clinical phenotypic basis of developmental and epileptic encephalopathies caused by rare biallelic variants in CACNA2D2. METHODS: Two affected individuals from a family with clinical features of early onset epileptic encephalopathy were recruited for exome sequencing at the Centers for Mendelian Genomics to identify their molecular diagnosis. GeneMatcher facilitated identification of a second family with a shared candidate disease gene identified through clinical gene panel-based testing. RESULTS: Rare biallelic CACNA2D2 variants have been previously reported in three families with developmental and epileptic encephalopathy, and one family with congenital ataxia. We identified three individuals in two unrelated families with novel homozygous rare variants in CACNA2D2 with clinical features of developmental and epileptic encephalopathy and cerebellar atrophy. Family 1 includes two affected siblings with a likely damaging homozygous rare missense variant c.1778G>C; p.(Arg593Pro) in CACNA2D2. Family 2 includes a proband with a homozygous rare nonsense variant c.485_486del; p.(Tyr162Ter) in CACNA2D2. We compared clinical and molecular findings from all nine individuals reported to date and note that cerebellar atrophy is shared among all. INTERPRETATION: Our study supports the candidacy of CACNA2D2 as a disease gene associated with a phenotypic spectrum of neurological disease that include features of developmental and epileptic encephalopathy, ataxia, and cerebellar atrophy. Age at presentation may affect apparent penetrance of neurogenetic trait manifestations and of a particular clinical neurological endophenotype, for example, seizures or ataxia.

Bi-allelic GOT2 Mutations Cause a Treatable Malate-Aspartate Shuttle-Related Encephalopathy. - van Karnebeek, Clara D M; Ramos, Rúben J; Wen, Xiao-Yan; Tarailo-Graovac, Maja; Gleeson, Joseph G; Skrypnyk, Cristina; Brand-Arzamendi, Koroboshka; Karbassi, Farhad; Issa, Mahmoud Y; van der Lee, Robin; Drögemöller, Britt I; Koster, Janet; et al. (Am J Hum Genet, 2019)
Early-infantile encephalopathies with epilepsy are devastating conditions mandating an accurate diagnosis to guide proper management. Whole-exome sequencing was used to investigate the disease etiology in four children from independent families with intellectual disability and epilepsy, revealing bi-allelic GOT2 mutations. In-depth metabolic studies in individual 1 showed low plasma serine, hypercitrullinemia, hyperlactatemia, and hyperammonemia. The epilepsy was serine and pyridoxine responsive. Functional consequences of observed mutations were tested by measuring enzyme activity and by cell and animal models. Zebrafish and mouse models were used to validate brain developmental and functional defects and to test therapeutic strategies. GOT2 encodes the mitochondrial glutamate oxaloacetate transaminase. GOT2 enzyme activity was deficient in fibroblasts with bi-allelic mutations. GOT2, a member of the malate-aspartate shuttle, plays an essential role in the intracellular NAD(H) redox balance. De novo serine biosynthesis was impaired in fibroblasts with GOT2 mutations and GOT2-knockout HEK293 cells. Correcting the highly oxidized cytosolic NAD-redox state by pyruvate supplementation restored serine biosynthesis in GOT2-deficient cells. Knockdown of got2a in zebrafish resulted in a brain developmental defect associated with seizure-like electroencephalography spikes, which could be rescued by supplying pyridoxine in embryo water. Both pyridoxine and serine synergistically rescued embryonic developmental defects in zebrafish got2a morphants. The two treated individuals reacted favorably to their treatment. Our data provide a mechanistic basis for the biochemical abnormalities in GOT2 deficiency that may also hold for other MAS defects.

Bi-allelic Mutations in FAM149B1 Cause Abnormal Primary Cilium and a Range of Ciliopathy Phenotypes in Humans. - Shaheen, Ranad; Jiang, Nan; Alzahrani, Fatema; Ewida, Nour; Al-Sheddi, Tarfa; Alobeid, Eman; Musaev, Damir; Stanley, Valentina; Hashem, Mais; Ibrahim, Niema; Abdulwahab, Firdous; Alshenqiti, Abduljabbar; et al. (Am J Hum Genet, 2019)
Ciliopathies are clinical disorders of the primary cilium with widely recognized phenotypic and genetic heterogeneity. In two Arab consanguineous families, we mapped a ciliopathy phenotype that most closely matches Joubert syndrome (hypotonia, developmental delay, typical facies, oculomotor apraxia, polydactyly, and subtle posterior fossa abnormalities) to a single locus in which a founder homozygous truncating variant in FAM149B1 was identified by exome sequencing. We subsequently identified a third Arab consanguineous multiplex family in which the phenotype of Joubert syndrome/oral-facial-digital syndrome (OFD VI) was found to co-segregate with the same founder variant in FAM149B1. Independently, autozygosity mapping and exome sequencing in a consanguineous Turkish family with Joubert syndrome highlighted a different homozygous truncating variant in the same gene. FAM149B1 encodes a protein of unknown function. Mutant fibroblasts were found to have normal ciliogenesis potential. However, distinct cilia-related abnormalities were observed in these cells: abnormal accumulation IFT complex at the distal tips of the cilia, which assumed bulbous appearance, increased length of the primary cilium, and dysregulated SHH signaling. We conclude that FAM149B1 is required for normal ciliary biology and that its deficiency results in a range of ciliopathy phenotypes in humans along the spectrum of Joubert syndrome.

Biallelic mutations in valyl-tRNA synthetase gene VARS are associated with a progressive neurodevelopmental epileptic encephalopathy. - Friedman, Jennifer; Smith, Desiree E; Issa, Mahmoud Y; Stanley, Valentina; Wang, Rengang; Mendes, Marisa I; Wright, Meredith S; Wigby, Kristen; Hildreth, Amber; Crawford, John R; Koehler, Alanna E; Chowdhury, Shimul; et al. (Nat Commun, 2019)
Aminoacyl-tRNA synthetases (ARSs) function to transfer amino acids to cognate tRNA molecules, which are required for protein translation. To date, biallelic mutations in 31 ARS genes are known to cause recessive, early-onset severe multi-organ diseases. VARS encodes the only known valine cytoplasmic-localized aminoacyl-tRNA synthetase. Here, we report seven patients from five unrelated families with five different biallelic missense variants in VARS. Subjects present with a range of global developmental delay, epileptic encephalopathy and primary or progressive microcephaly. Longitudinal assessment demonstrates progressive cortical atrophy and white matter volume loss. Variants map to the VARS tRNA binding domain and adjacent to the anticodon domain, and disrupt highly conserved residues. Patient primary cells show intact VARS protein but reduced enzymatic activity, suggesting partial loss of function. The implication of VARS in pediatric neurodegeneration broadens the spectrum of human diseases due to mutations in tRNA synthetase genes.
Keywords: Alleles; Anticodon; Child; Child, Preschool; Disease Progression; Epilepsy; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Mutation; Neurodevelopmental Disorders; Pedigree; Protein Biosynthesis; Protein Interaction Domains and Motifs; RNA, Transfer; Valine-tRNA Ligase; Whole Exome Sequencing; Whole Genome Sequencing

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes. - Burrage, Lindsay C; Reynolds, John J; Baratang, Nissan Vida; Phillips, Jennifer B; Wegner, Jeremy; McFarquhar, Ashley; Higgs, Martin R; Christiansen, Audrey E; Lanza, Denise G; Seavitt, John R; Jain, Mahim; Li, Xiaohui; et al. (Am J Hum Genet, 2019)
SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomal-recessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in individuals with SPONASTRIME dysplasia. Here, we identified bi-allelic variants in TONSL, which encodes the Tonsoku-like DNA repair protein, in nine subjects (from eight families) with SPONASTRIME dysplasia, and four subjects (from three families) with short stature of varied severity and spondylometaphyseal dysplasia with or without immunologic and hematologic abnormalities, but no definitive metaphyseal striations at diagnosis. The finding of early embryonic lethality in a Tonsl murine model and the discovery of reduced length, spinal abnormalities, reduced numbers of neutrophils, and early lethality in a tonsl zebrafish model both support the hypomorphic nature of the identified TONSL variants. Moreover, functional studies revealed increased amounts of spontaneous replication fork stalling and chromosomal aberrations, as well as fewer camptothecin (CPT)-induced RAD51 foci in subject-derived cell lines. Importantly, these cellular defects were rescued upon re-expression of wild-type (WT) TONSL; this rescue is consistent with the hypothesis that hypomorphic TONSL variants are pathogenic. Overall, our studies in humans, mice, zebrafish, and subject-derived cell lines confirm that pathogenic variants in TONSL impair DNA replication and homologous recombination-dependent repair processes, and they lead to a spectrum of skeletal dysplasia phenotypes with numerous extra-skeletal manifestations.

Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish. - Siekierska, Aleksandra; Stamberger, Hannah; Deconinck, Tine; Oprescu, Stephanie N; Partoens, Michèle; Zhang, Yifan; Sourbron, Jo; Adriaenssens, Elias; Mullen, Patrick; Wiencek, Patrick; Hardies, Katia; Lee, Jeong-Soo; et al. (Nat Commun, 2019)
Aminoacyl tRNA synthetases (ARSs) link specific amino acids with their cognate transfer RNAs in a critical early step of protein translation. Mutations in ARSs have emerged as a cause of recessive, often complex neurological disease traits. Here we report an allelic series consisting of seven novel and two previously reported biallelic variants in valyl-tRNA synthetase (VARS) in ten patients with a developmental encephalopathy with microcephaly, often associated with early-onset epilepsy. In silico, in vitro, and yeast complementation assays demonstrate that the underlying pathomechanism of these mutations is most likely a loss of protein function. Zebrafish modeling accurately recapitulated some of the key neurological disease traits. These results provide both genetic and biological insights into neurodevelopmental disease and pave the way for further in-depth research on ARS related recessive disorders and precision therapies.
Keywords: Alleles; Animals; Brain Diseases; Cell Line; Disease Models, Animal; Epilepsy; Female; Fibroblasts; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Neurodevelopmental Disorders; Pedigree; Prosencephalon; Valine-tRNA Ligase; Zebrafish

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Yuan, Bo; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

Clinical, genetic, and pathologic characterization of Mexican founder mutation c.1387A>G. - Lee, Angela J; Jones, Karra A; Butterfield, Russell J; Cox, Mary O; Konersman, Chamindra G; Grosmann, Carla; Abdenur, Jose E; Boyer, Monica; Beson, Brent; Wang, Ching; Dowling, James J; Gibbons, Melissa A; et al. (Neurol Genet, 2019)
Objective: To characterize the clinical phenotype, genetic origin, and muscle pathology of patients with the c.1387A>G mutation. Methods: Standardized clinical data were collected for all patients known to the authors with c.1387A>G mutations in . Muscle biopsies were reviewed and used for histopathology, immunostaining, Western blotting, and DNA extraction. Genetic analysis was performed on extracted DNA. Results: We report the clinical phenotypes of 6 patients homozygous for the c.1387A>G mutation in . Onset of symptoms was <2 years, and 5 of the 6 patients never learned to walk. Brain MRIs were normal. Cognition was normal to mildly impaired. Microarray analysis of 5 homozygous c.1387A>G patients revealed a 500-kb region of shared homozygosity at 19q13.32, including . All 4 muscle biopsies available for review showed end-stage dystrophic pathology, near absence of glycosylated α-dystroglycan (α-DG) by immunofluorescence, and reduced molecular weight of α-DG compared with controls and patients with homozygous c.826C>A limb-girdle muscular dystrophy. Conclusions: The clinical features and muscle pathology in these newly reported patients homozygous for c.1387A>G confirm that this mutation causes congenital muscular dystrophy. The clinical severity might be explained by the greater reduction in α-DG glycosylation compared with that seen with the c.826C>A mutation. The shared region of homozygosity at 19q13.32 indicates that c.1387A>G is a founder mutation with an estimated age of 60 generations (∼1,200-1,500 years).

A combined immunodeficiency with severe infections, inflammation, and allergy caused by ARPC1B deficiency. - Volpi, Stefano; Cicalese, Maria Pia; Tuijnenburg, Paul; Tool, Anton T J; Cuadrado, Eloy; Abu-Halaweh, Marwan; Ahanchian, Hamid; Alzyoud, Raed; Akdemir, Zeynep Coban; Barzaghi, Federica; Blank, Alexander; Boisson, Bertrand; et al. (J Allergy Clin Immunol, 2019)

Complex Compound Inheritance of Lethal Lung Developmental Disorders Due to Disruption of the TBX-FGF Pathway. - Karolak, Justyna A; Vincent, Marie; Deutsch, Gail; Gambin, Tomasz; Cogné, Benjamin; Pichon, Olivier; Vetrini, Francesco; Mefford, Heather C; Dines, Jennifer N; Golden-Grant, Katie; Dipple, Katrina; Freed, Amanda S; et al. (Am J Hum Genet, 2019)
Primary defects in lung branching morphogenesis, resulting in neonatal lethal pulmonary hypoplasias, are incompletely understood. To elucidate the pathogenetics of human lung development, we studied a unique collection of samples obtained from deceased individuals with clinically and histopathologically diagnosed interstitial neonatal lung disorders: acinar dysplasia (n = 14), congenital alveolar dysplasia (n = 2), and other lethal lung hypoplasias (n = 10). We identified rare heterozygous copy-number variant deletions or single-nucleotide variants (SNVs) involving TBX4 (n = 8 and n = 2, respectively) or FGF10 (n = 2 and n = 2, respectively) in 16/26 (61%) individuals. In addition to TBX4, the overlapping ∼2 Mb recurrent and nonrecurrent deletions at 17q23.1q23.2 identified in seven individuals with lung hypoplasia also remove a lung-specific enhancer region. Individuals with coding variants involving either TBX4 or FGF10 also harbored at least one non-coding SNV in the predicted lung-specific enhancer region, which was absent in 13 control individuals with the overlapping deletions but without any structural lung anomalies. The occurrence of rare coding variants involving TBX4 or FGF10 with the putative hypomorphic non-coding SNVs implies a complex compound inheritance of these pulmonary hypoplasias. Moreover, they support the importance of TBX4-FGF10-FGFR2 epithelial-mesenchymal signaling in human lung organogenesis and help to explain the histopathological continuum observed in these rare lethal developmental disorders of the lung.
Keywords: DNA Copy Number Variations; Female; Fibroblast Growth Factor 10; Gene Expression Regulation; Gestational Age; Humans; Infant, Newborn; Infant, Newborn, Diseases; Lung; Lung Diseases; Male; Maternal Inheritance; Organogenesis; Paternal Inheritance; Pedigree; Polymorphism, Single Nucleotide; Receptor, Fibroblast Growth Factor, Type 2; Signal Transduction; T-Box Domain Proteins

Contribution of noncoding pathogenic variants to RPGRIP1-mediated inherited retinal degeneration. - Jamshidi, Farzad; Place, Emily M; Mehrotra, Sudeep; Navarro-Gomez, Daniel; Maher, Mathew; Branham, Kari E; Valkanas, Elise; Cherry, Timothy J; Lek, Monkol; Macarthur, Daniel; Pierce, Eric A; Bujakowska, Kinga M (Genet Med, 2019)
PURPOSE: With the advent of gene therapies for inherited retinal degenerations (IRDs), genetic diagnostics will have an increasing role in clinical decision-making. Yet the genetic cause of disease cannot be identified using exon-based sequencing for a significant portion of patients. We hypothesized that noncoding pathogenic variants contribute significantly to the genetic causality of IRDs and evaluated patients with single coding pathogenic variants in RPGRIP1 to test this hypothesis. METHODS: IRD families underwent targeted panel sequencing. Unsolved cases were explored by exome and genome sequencing looking for additional pathogenic variants. Candidate pathogenic variants were then validated by Sanger sequencing, quantitative polymerase chain reaction, and in vitro splicing assays in two cell lines analyzed through amplicon sequencing. RESULTS: Among 1722 families, 3 had biallelic loss-of-function pathogenic variants in RPGRIP1 while 7 had a single disruptive coding pathogenic variants. Exome and genome sequencing revealed potential noncoding pathogenic variants in these 7 families. In 6, the noncoding pathogenic variants were shown to lead to loss of function in vitro. CONCLUSION: Noncoding pathogenic variants were identified in 6 of 7 families with single coding pathogenic variants in RPGRIP1. The results suggest that noncoding pathogenic variants contribute significantly to the genetic causality of IRDs and RPGRIP1-mediated IRDs are more common than previously thought.
Keywords: Adult; Chromosome Mapping; DNA Mutational Analysis; DNA, Intergenic; Female; HEK293 Cells; Humans; Male; Mutation; Pedigree; Proteins; Retinal Degeneration; Whole Exome Sequencing; Whole Genome Sequencing

Copy number variant and runs of homozygosity detection by microarrays enabled more precise molecular diagnoses in 11,020 clinical exome cases. - Dharmadhikari, Avinash V; Ghosh, Rajarshi; Yuan, Bo; Liu, Pengfei; Dai, Hongzheng; Al Masri, Sami; Scull, Jennifer; Posey, Jennifer E; Jiang, Allen H; He, Weimin; Vetrini, Francesco; Braxton, Alicia A; et al. (Genome Med, 2019)
BACKGROUND: Exome sequencing (ES) has been successfully applied in clinical detection of single nucleotide variants (SNVs) and small indels. However, identification of copy number variants (CNVs) using ES data remains challenging. The purpose of this study is to understand the contribution of CNVs and copy neutral runs of homozygosity (ROH) in molecular diagnosis of patients referred for ES. METHODS: In a cohort of 11,020 consecutive ES patients, an Illumina SNP array analysis interrogating mostly coding SNPs was performed as a quality control (QC) measurement and for CNV/ROH detection. Among these patients, clinical chromosomal microarray analysis (CMA) was performed at Baylor Genetics (BG) on 3229 patients, either before, concurrently, or after ES. We retrospectively analyzed the findings from CMA and the QC array. RESULTS: The QC array can detect ~ 70% of pathogenic/likely pathogenic CNVs (PCNVs) detectable by CMA. Out of the 11,020 ES cases, the QC array identified PCNVs in 327 patients and uniparental disomy (UPD) disorder-related ROH in 10 patients. The overall PCNV/UPD detection rate was 5.9% in the 3229 ES patients who also had CMA at BG; PCNV/UPD detection rate was higher in concurrent ES and CMA than in ES with prior CMA (7.2% vs 4.6%). The PCNVs/UPD contributed to the molecular diagnoses in 17.4% (189/1089) of molecularly diagnosed ES cases with CMA and were estimated to contribute in 10.6% of all molecularly diagnosed ES cases. Dual diagnoses with both PCNVs and SNVs were detected in 38 patients. PCNVs affecting single recessive disorder genes in a compound heterozygous state with SNVs were detected in 4 patients, and homozygous deletions (mostly exonic deletions) were detected in 17 patients. A higher PCNV detection rate was observed for patients with syndromic phenotypes and/or cardiovascular abnormalities. CONCLUSIONS: Our clinical genomics study demonstrates that detection of PCNV/UPD through the QC array or CMA increases ES diagnostic rate, provides more precise molecular diagnosis for dominant as well as recessive traits, and enables more complete genetic diagnoses in patients with dual or multiple molecular diagnoses. Concurrent ES and CMA using an array with exonic coverage for disease genes enables most effective detection of both CNVs and SNVs and therefore is recommended especially in time-sensitive clinical situations.

CTCF variants in 39 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum. - Konrad, Enrico D H; Nardini, Niels; Caliebe, Almuth; Nagel, Inga; Young, Dana; Horvath, Gabriella; Santoro, Stephanie L; Shuss, Christine; Ziegler, Alban; Bonneau, Dominique; Kempers, Marlies; Pfundt, Rolph; et al. (Genet Med, 2019)
PURPOSE: Pathogenic variants in the chromatin organizer CTCF were previously reported in seven individuals with a neurodevelopmental disorder (NDD). METHODS: Through international collaboration we collected data from 39 subjects with variants in CTCF. We performed transcriptome analysis on RNA from blood samples and utilized Drosophila melanogaster to investigate the impact of Ctcf dosage alteration on nervous system development and function. RESULTS: The individuals in our cohort carried 2 deletions, 8 likely gene-disruptive, 2 splice-site, and 20 different missense variants, most of them de novo. Two cases were familial. The associated phenotype was of variable severity extending from mild developmental delay or normal IQ to severe intellectual disability. Feeding difficulties and behavioral abnormalities were common, and variable other findings including growth restriction and cardiac defects were observed. RNA-sequencing in five individuals identified 3828 deregulated genes enriched for known NDD genes and biological processes such as transcriptional regulation. Ctcf dosage alteration in Drosophila resulted in impaired gross neurological functioning and learning and memory deficits. CONCLUSION: We significantly broaden the mutational and clinical spectrum ofCTCF-associated NDDs. Our data shed light onto the functional role of CTCF by identifying deregulated genes and show that Ctcf alterations result in nervous system defects in Drosophila.

De Novo Pathogenic Variants in N-cadherin Cause a Syndromic Neurodevelopmental Disorder with Corpus Collosum, Axon, Cardiac, Ocular, and Genital Defects. - Accogli, Andrea; Calabretta, Sara; St-Onge, Judith; Boudrahem-Addour, Nassima; Dionne-Laporte, Alexandre; Joset, Pascal; Azzarello-Burri, Silvia; Rauch, Anita; Krier, Joel; Fieg, Elizabeth; Pallais, Juan C; McConkie-Rosell, Allyn; et al. (Am J Hum Genet, 2019)
Cadherins constitute a family of transmembrane proteins that mediate calcium-dependent cell-cell adhesion. The extracellular domain of cadherins consists of extracellular cadherin (EC) domains, separated by calcium binding sites. The EC interacts with other cadherin molecules in cis and in trans to mechanically hold apposing cell surfaces together. CDH2 encodes N-cadherin, whose essential roles in neural development include neuronal migration and axon pathfinding. However, CDH2 has not yet been linked to a Mendelian neurodevelopmental disorder. Here, we report de novo heterozygous pathogenic variants (seven missense, two frameshift) in CDH2 in nine individuals with a syndromic neurodevelopmental disorder characterized by global developmental delay and/or intellectual disability, variable axon pathfinding defects (corpus callosum agenesis or hypoplasia, mirror movements, Duane anomaly), and ocular, cardiac, and genital anomalies. All seven missense variants (c.1057G>A [p.Asp353Asn]; c.1789G>A [p.Asp597Asn]; c.1789G>T [p.Asp597Tyr]; c.1802A>C [p.Asn601Thr]; c.1839C>G [p.Cys613Trp]; c.1880A>G [p.Asp627Gly]; c.2027A>G [p.Tyr676Cys]) result in substitution of highly conserved residues, and six of seven cluster within EC domains 4 and 5. Four of the substitutions affect the calcium-binding site in the EC4-EC5 interdomain. We show that cells expressing these variants in the EC4-EC5 domains have a defect in cell-cell adhesion; this defect includes impaired binding in trans with N-cadherin-WT expressed on apposing cells. The two frameshift variants (c.2563_2564delCT [p.Leu855Valfs4]; c.2564_2567dupTGTT [p.Leu856Phefs5]) are predicted to lead to a truncated cytoplasmic domain. Our study demonstrates that de novo heterozygous variants in CDH2 impair the adhesive activity of N-cadherin, resulting in a multisystemic developmental disorder, that could be named ACOG syndrome (agenesis of corpus callosum, axon pathfinding, cardiac, ocular, and genital defects).

Deleterious de novo variants of X-linked ZC4H2 in females cause a variable phenotype with neurogenic arthrogryposis multiplex congenita. - Frints, Suzanna G M; Hennig, Friederike; Colombo, Roberto; Jacquemont, Sebastien; Terhal, Paulien; Zimmerman, Holly H; Hunt, David; Mendelsohn, Bryce A; Kordaß, Ulrike; Webster, Richard; Sinnema, Margje; Abdul-Rahman, Omar; et al. (Hum Mutat, 2019)
Pathogenic variants in the X-linked gene ZC4H2, which encodes a zinc-finger protein, cause an infrequently described syndromic form of arthrogryposis multiplex congenita (AMC) with central and peripheral nervous system involvement. We present genetic and detailed phenotypic information on 23 newly identified families and simplex cases that include 19 affected females from 18 families and 14 affected males from nine families. Of note, the 15 females with deleterious de novo ZC4H2 variants presented with phenotypes ranging from mild to severe, and their clinical features overlapped with those seen in affected males. By contrast, of the nine carrier females with inherited ZC4H2 missense variants that were deleterious in affected male relatives, four were symptomatic. We also compared clinical phenotypes with previously published cases of both sexes and provide an overview on 48 males and 57 females from 42 families. The spectrum of ZC4H2 defects comprises novel and recurrent mostly inherited missense variants in affected males, and de novo splicing, frameshift, nonsense, and partial ZC4H2 deletions in affected females. Pathogenicity of two newly identified missense variants was further supported by studies in zebrafish. We propose ZC4H2 as a good candidate for early genetic testing of males and females with a clinical suspicion of fetal hypo-/akinesia and/or (neurogenic) AMC.

Disruptive mutations in TANC2 define a neurodevelopmental syndrome associated with psychiatric disorders. - Guo, Hui; Bettella, Elisa; Marcogliese, Paul C; Zhao, Rongjuan; Andrews, Jonathan C; Nowakowski, Tomasz J; Gillentine, Madelyn A; Hoekzema, Kendra; Wang, Tianyun; Wu, Huidan; Jangam, Sharayu; Liu, Cenying; et al. (Nat Commun, 2019)
Postsynaptic density (PSD) proteins have been implicated in the pathophysiology of neurodevelopmental and psychiatric disorders. Here, we present detailed clinical and genetic data for 20 patients with likely gene-disrupting mutations in TANC2-whose protein product interacts with multiple PSD proteins. Pediatric patients with disruptive mutations present with autism, intellectual disability, and delayed language and motor development. In addition to a variable degree of epilepsy and facial dysmorphism, we observe a pattern of more complex psychiatric dysfunction or behavioral problems in adult probands or carrier parents. Although this observation requires replication to establish statistical significance, it also suggests that mutations in this gene are associated with a variety of neuropsychiatric disorders consistent with its postsynaptic function. We find that TANC2 is expressed broadly in the human developing brain, especially in excitatory neurons and glial cells, but shows a more restricted pattern in Drosophila glial cells where its disruption affects behavioral outcomes.

DPAGT1 Deficiency with Encephalopathy (DPAGT1-CDG): Clinical and Genetic Description of 11 New Patients. - Ng, Bobby G; Underhill, Hunter R; Palm, Lars; Bengtson, Per; Rozet, Jean-Michel; Gerber, Sylvie; Munnich, Arnold; Zanlonghi, Xavier; Stevens, Cathy A; Kircher, Martin; Nickerson, Deborah A; Buckingham, Kati J; et al. (JIMD Rep, 2019)
Pathogenic mutations in DPAGT1 cause a rare type of a congenital disorder of glycosylation termed DPAGT1-CDG or, alternatively, a milder version with only myasthenia known as DPAGT1-CMS. Fourteen disease-causing mutations in 28 patients from 10 families have previously been reported to cause the systemic form, DPAGT1-CDG. We here report on another 11 patients from 8 families and add 10 new mutations. Most patients have a very severe disease course, where common findings are pronounced muscular hypotonia, intractable epilepsy, global developmental delay/intellectual disability, and early death. We also present data on three affected females that are young adults and have a somewhat milder, stable disease. Our findings expand both the molecular and clinical knowledge of previously published data but also widen the phenotypic spectrum of DPAGT1-CDG.

EphrinB2-EphB4-RASA1 Signaling in Human Cerebrovascular Development and Disease. - Zeng, Xue; Hunt, Ava; Jin, Sheng Chih; Duran, Daniel; Gaillard, Jonathan; Kahle, Kristopher T (Trends Mol Med, 2019)
Recent whole exome sequencing studies in humans have provided novel insight into the importance of the ephrinB2-EphB4-RASA1 signaling axis in cerebrovascular development, corroborating and extending previous work in model systems. Here, we aim to review the human cerebrovascular phenotypes associated with ephrinB2-EphB4-RASA1 mutations, including those recently discovered in Vein of Galen malformation: the most common and severe brain arteriovenous malformation in neonates. We will also discuss emerging paradigms of the molecular and cellular pathophysiology of disease-causing ephrinB2-EphB4-RASA1 mutations, including the potential role of somatic mosaicism. These observations have potential diagnostic and therapeutic implications for patients with rare congenital cerebrovascular diseases and their families.

Exome Sequencing of a Primary Ovarian Insufficiency Cohort Reveals Common Molecular Etiologies for a Spectrum of Disease. - Jolly, Angad; Bayram, Yavuz; Turan, Serap; Aycan, Zehra; Tos, Tulay; Abali, Zehra Yavas; Hacihamdioglu, Bulent; Coban Akdemir, Zeynep Hande; Hijazi, Hadia; Bas, Serpil; Atay, Zeynep; Guran, Tulay; et al. (J Clin Endocrinol Metab, 2019)
CONTEXT: Primary ovarian insufficiency (POI) encompasses a spectrum of premature menopause, including both primary and secondary amenorrhea. For 75% to 90% of individuals with hypergonadotropic hypogonadism presenting as POI, the molecular etiology is unknown. Common etiologies include chromosomal abnormalities, environmental factors, and congenital disorders affecting ovarian development and function, as well as syndromic and nonsyndromic single gene disorders suggesting POI represents a complex trait. OBJECTIVE: To characterize the contribution of known disease genes to POI and identify molecular etiologies and biological underpinnings of POI. DESIGN, SETTING, AND PARTICIPANTS: We applied exome sequencing (ES) and family-based genomics to 42 affected female individuals from 36 unrelated Turkish families, including 31 with reported parental consanguinity. RESULTS: This analysis identified likely damaging, potentially contributing variants and molecular diagnoses in 16 families (44%), including 11 families with likely damaging variants in known genes and five families with predicted deleterious variants in disease genes (IGSF10, MND1, MRPS22, and SOHLH1) not previously associated with POI. Of the 16 families, 2 (13%) had evidence for potentially pathogenic variants at more than one locus. Absence of heterozygosity consistent with identity-by-descent mediated recessive disease burden contributes to molecular diagnosis in 15 of 16 (94%) families. GeneMatcher allowed identification of additional families from diverse genetic backgrounds. CONCLUSIONS: ES analysis of a POI cohort further characterized locus heterogeneity, reaffirmed the association of genes integral to meiotic recombination, demonstrated the likely contribution of genes involved in hypothalamic development, and documented multilocus pathogenic variation suggesting the potential for oligogenic inheritance contributing to the development of POI.

Exome sequencing of family trios from the National Birth Defects Prevention Study: Tapping into a rich resource of genetic and environmental data. - Jenkins, Mary M; Almli, Lynn M; Pangilinan, Faith; Chong, Jessica X; Blue, Elizabeth E; Shapira, Stuart K; White, Janson; McGoldrick, Daniel; Smith, Joshua D; Mullikin, James C; Bean, Christopher J; Nembhard, Wendy N; et al. (Birth Defects Res, 2019)
BACKGROUND: The National Birth Defects Prevention Study (NBDPS) is a multisite, population-based, case-control study of genetic and nongenetic risk factors for major structural birth defects. Eligible women had a pregnancy affected by a birth defect or a liveborn child without a birth defect between 1997 and 2011. They were invited to complete a telephone interview to collect pregnancy exposure data and were mailed buccal cell collection kits to collect specimens from themselves, their child (if living), and their child's father. Over 23,000 families representing more than 30 major structural birth defects provided DNA specimens. METHODS: To evaluate their utility for exome sequencing (ES), specimens from 20 children with colonic atresia were studied. Evaluations were conducted on specimens collected using cytobrushes stored and transported in open versus closed packaging, on native genomic DNA (gDNA) versus whole genome amplified (WGA) products and on a library preparation protocol adapted to low amounts of DNA. RESULTS: The DNA extracted from brushes in open packaging yielded higher quality sequence data than DNA from brushes in closed packaging. Quality metrics of sequenced gDNA were consistently higher than metrics from corresponding WGA products and were consistently high when using a low input protocol. CONCLUSIONS: This proof-of-principle study established conditions under which ES can be applied to NBDPS specimens. Successful sequencing of exomes from well-characterized NBDPS families indicated that this unique collection can be used to investigate the roles of genetic variation and gene-environment interaction effects in birth defect etiologies, providing a valuable resource for birth defect researchers.

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.

Genetic diagnosis in first or second trimester pregnancy loss using exome sequencing: a systematic review of human essential genes. - Robbins, Sarah M; Thimm, Matthew A; Valle, David; Jelin, Angie C (J Assist Reprod Genet, 2019)
PURPOSE: Non-aneuploid recurrent pregnancy loss (RPL) affects approximately 100,000 pregnancies worldwide annually. Exome sequencing (ES) may help uncover the genetic etiology of RPL and, more generally, pregnancy loss as a whole. Previous studies have attempted to predict the genes that, when disrupted, may cause human embryonic lethality. However, predictions by these early studies rarely point to the same genes. Case reports of pathogenic variants identified in RPL cases offer another clue. We evaluated known genetic etiologies of RPL identified by ES. METHODS: We gathered primary research articles from PubMed and Embase involving case reports of RPL reporting variants identified by ES. Two authors independently reviewed all articles for eligibility and extracted data based on predetermined criteria. Preliminary and amended analysis isolated 380 articles; 15 met all inclusion criteria. RESULTS: These 15 articles described 74 families with 279 reported RPLs with 34 candidate pathogenic variants in 19 genes (NOP14, FOXP3, APAF1, CASP9, CHRNA1, NLRP5, MMP10, FGA, FLT1, EPAS1, IDO2, STIL, DYNC2H1, IFT122, PADI6, CAPS, MUSK, NLRP2, NLRP7) and 26 variants of unknown significance in 25 genes. These genes cluster in four essential pathways: (1) gene expression, (2) embryonic development, (3) mitosis and cell cycle progression, and (4) inflammation and immunity. CONCLUSIONS: For future studies of RPL, we recommend trio-based ES in cases with normal parental karyotypes. In vitro fertilization with preimplantation genetic diagnosis can be pursued if causative variants are found. Utilization of other sequencing technologies in concert with ES should improve understanding of the causes of early embryonic lethality in humans.

Genetic regulatory variation in populations informs transcriptome analysis in rare disease. - Mohammadi, Pejman; Castel, Stephane E; Cummings, Beryl B; Einson, Jonah; Sousa, Christina; Hoffman, Paul; Donkervoort, Sandra; Jiang, Zhuoxun; Mohassel, Payam; Foley, A Reghan; Wheeler, Heather E; Im, Hae Kyung; et al. (Science, 2019)
Transcriptome data can facilitate the interpretation of the effects of rare genetic variants. Here, we introduce ANEVA (analysis of expression variation) to quantify genetic variation in gene dosage from allelic expression (AE) data in a population. Application of ANEVA to the Genotype-Tissues Expression (GTEx) data showed that this variance estimate is robust and correlated with selective constraint in a gene. Using these variance estimates in a dosage outlier test (ANEVA-DOT) applied to AE data from 70 Mendelian muscular disease patients showed accuracy in detecting genes with pathogenic variants in previously resolved cases and led to one confirmed and several potential new diagnoses. Using our reference estimates from GTEx data, ANEVA-DOT can be incorporated in rare disease diagnostic pipelines to use RNA-sequencing data more effectively.

Genetic variants in the LAMA5 gene in pediatric nephrotic syndrome. - Braun, Daniela A; Warejko, Jillian K; Ashraf, Shazia; Tan, Weizhen; Daga, Ankana; Schneider, Ronen; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J; Nakayama, Makiko; Schapiro, David; et al. (Nephrol Dial Transplant, 2019)
BACKGROUND: Nephrotic syndrome (NS), a chronic kidney disease, is characterized by significant loss of protein in the urine causing hypoalbuminemia and edema. In general, ∼15% of childhood-onset cases do not respond to steroid therapy and are classified as steroid-resistant NS (SRNS). In ∼30% of cases with SRNS, a causative mutation can be detected in one of 44 monogenic SRNS genes. The gene LAMA5 encodes laminin-α5, an essential component of the glomerular basement membrane. Mice with a hypomorphic mutation in the orthologous gene Lama5 develop proteinuria and hematuria. METHODS: To identify additional monogenic causes of NS, we performed whole exome sequencing in 300 families with pediatric NS. In consanguineous families we applied homozygosity mapping to identify genomic candidate loci for the underlying recessive mutation. RESULTS: In three families, in whom mutations in known NS genes were excluded, but in whom a recessive, monogenic cause of NS was strongly suspected based on pedigree information, we identified homozygous variants of unknown significance (VUS) in the gene LAMA5. While all affected individuals had nonsyndromic NS with an early onset of disease, their clinical outcome and response to immunosuppressive therapy differed notably. CONCLUSION: We here identify recessive VUS in the gene LAMA5 in patients with partially treatment-responsive NS. More data will be needed to determine the impact of these VUS in disease management. However, familial occurrence of disease, data from genetic mapping and a mouse model that recapitulates the NS phenotypes suggest that these genetic variants may be inherited factors that contribute to the development of NS in pediatric patients.

The Genomics of Arthrogryposis, a Complex Trait: Candidate Genes and Further Evidence for Oligogenic Inheritance. - Pehlivan, Davut; Bayram, Yavuz; Gunes, Nilay; Coban Akdemir, Zeynep; Shukla, Anju; Bierhals, Tatjana; Tabakci, Burcu; Sahin, Yavuz; Gezdirici, Alper; Fatih, Jawid M; Gulec, Elif Yilmaz; Yesil, Gözde; et al. (Am J Hum Genet, 2019)
Arthrogryposis is a clinical finding that is present either as a feature of a neuromuscular condition or as part of a systemic disease in over 400 Mendelian conditions. The underlying molecular etiology remains largely unknown because of genetic and phenotypic heterogeneity. We applied exome sequencing (ES) in a cohort of 89 families with the clinical sign of arthrogryposis. Additional molecular techniques including array comparative genomic hybridization (aCGH) and Droplet Digital PCR (ddPCR) were performed on individuals who were found to have pathogenic copy number variants (CNVs) and mosaicism, respectively. A molecular diagnosis was established in 65.2% (58/89) of families. Eleven out of 58 families (19.0%) showed evidence for potential involvement of pathogenic variation at more than one locus, probably driven by absence of heterozygosity (AOH) burden due to identity-by-descent (IBD). RYR3, MYOM2, ERGIC1, SPTBN4, and ABCA7 represent genes, identified in two or more families, for which mutations are probably causative for arthrogryposis. We also provide evidence for the involvement of CNVs in the etiology of arthrogryposis and for the idea that both mono-allelic and bi-allelic variants in the same gene cause either similar or distinct syndromes. We were able to identify the molecular etiology in nine out of 20 families who underwent reanalysis. In summary, our data from family-based ES further delineate the molecular etiology of arthrogryposis, yielded several candidate disease-associated genes, and provide evidence for mutational burden in a biological pathway or network. Our study also highlights the importance of reanalysis of individuals with unsolved diagnoses in conjunction with sequencing extended family members.

Heterozygous CTNNB1 and TBX4 variants in a patient with abnormal lung growth, pulmonary hypertension, microcephaly, and spasticity. - Karolak, Justyna A; Szafranski, Przemyslaw; Kilner, David; Patel, Chirag; Scurry, Bonnie; Kinning, Esther; Chandler, Kate; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Lupski, James R; Popek, Edwina; Stankiewicz, Paweł (Clin Genet, 2019)
The canonical wingless (Wnt) and fibroblast growth factor (FGF) signaling pathways involving CTNNB1 and TBX4, respectively, are crucial for the regulation of human development. Perturbations of these pathways and disruptions from biological homeostasis have been associated with abnormal morphogenesis of multiple organs, including the lung. The aim of this study was to identify the underlying genetic cause of abnormal lung growth, pulmonary hypertension (PAH), severe microcephaly, and muscle spasticity in a full-term newborn, who died at 4 months of age due to progressively worsening PAH and respiratory failure. Family trio exome sequencing showed a de novo heterozygous nonsense c.1603C>T (p.Arg535*) variant in CTNNB1 and a paternally inherited heterozygous missense c.1198G>A (p.Glu400Lys) variant in TBX4, both predicted to be likely deleterious. We expand the phenotypic spectrum associated with CTNNB1 and TBX4 variants and indicate that they could act synergistically to produce a distinct more severe phenotype. Our findings further support a recently proposed complex compound inheritance model in lethal lung developmental diseases and the contention that dual molecular diagnoses can parsimoniously explain blended phenotypes.

Heterozygous Variants in KMT2E Cause a Spectrum of Neurodevelopmental Disorders and Epilepsy. - O'Donnell-Luria, Anne H; Pais, Lynn S; Faundes, Víctor; Wood, Jordan C; Sveden, Abigail; Luria, Victor; Abou Jamra, Rami; Accogli, Andrea; Amburgey, Kimberly; Anderlid, Britt Marie; Azzarello-Burri, Silvia; Basinger, Alice A; et al. (Am J Hum Genet, 2019)
We delineate a KMT2E-related neurodevelopmental disorder on the basis of 38 individuals in 36 families. This study includes 31 distinct heterozygous variants in KMT2E (28 ascertained from Matchmaker Exchange and three previously reported), and four individuals with chromosome 7q22.2-22.23 microdeletions encompassing KMT2E (one previously reported). Almost all variants occurred de novo, and most were truncating. Most affected individuals with protein-truncating variants presented with mild intellectual disability. One-quarter of individuals met criteria for autism. Additional common features include macrocephaly, hypotonia, functional gastrointestinal abnormalities, and a subtle facial gestalt. Epilepsy was present in about one-fifth of individuals with truncating variants and was responsive to treatment with anti-epileptic medications in almost all. More than 70% of the individuals were male, and expressivity was variable by sex; epilepsy was more common in females and autism more common in males. The four individuals with microdeletions encompassing KMT2E generally presented similarly to those with truncating variants, but the degree of developmental delay was greater. The group of four individuals with missense variants in KMT2E presented with the most severe developmental delays. Epilepsy was present in all individuals with missense variants, often manifesting as treatment-resistant infantile epileptic encephalopathy. Microcephaly was also common in this group. Haploinsufficiency versus gain-of-function or dominant-negative effects specific to these missense variants in KMT2E might explain this divergence in phenotype, but requires independent validation. Disruptive variants in KMT2E are an under-recognized cause of neurodevelopmental abnormalities.

Homozygous Missense Variants in NTNG2, Encoding a Presynaptic Netrin-G2 Adhesion Protein, Lead to a Distinct Neurodevelopmental Disorder. - Dias, Caroline M; Punetha, Jaya; Zheng, Céline; Mazaheri, Neda; Rad, Abolfazl; Efthymiou, Stephanie; Petersen, Andrea; Dehghani, Mohammadreza; Pehlivan, Davut; Partlow, Jennifer N; Posey, Jennifer E; Salpietro, Vincenzo; et al. (Am J Hum Genet, 2019)
NTNG2 encodes netrin-G2, a membrane-anchored protein implicated in the molecular organization of neuronal circuitry and synaptic organization and diversification in vertebrates. In this study, through a combination of exome sequencing and autozygosity mapping, we have identified 16 individuals (from seven unrelated families) with ultra-rare homozygous missense variants in NTNG2; these individuals present with shared features of a neurodevelopmental disorder consisting of global developmental delay, severe to profound intellectual disability, muscle weakness and abnormal tone, autistic features, behavioral abnormalities, and variable dysmorphisms. The variants disrupt highly conserved residues across the protein. Functional experiments, including in silico analysis of the protein structure, in vitro assessment of cell surface expression, and in vitro knockdown, revealed potential mechanisms of pathogenicity of the variants, including loss of protein function and decreased neurite outgrowth. Our data indicate that appropriate expression of NTNG2 plays an important role in neurotypical development.

Hypomorphic caspase activation and recruitment domain 11 (CARD11) mutations associated with diverse immunologic phenotypes with or without atopic disease. - Dorjbal, Batsukh; Stinson, Jeffrey R; Ma, Chi A; Weinreich, Michael A; Miraghazadeh, Bahar; Hartberger, Julia M; Frey-Jakobs, Stefanie; Weidinger, Stephan; Moebus, Lena; Franke, Andre; Schäffer, Alejandro A; Bulashevska, Alla; et al. (J Allergy Clin Immunol, 2019)
BACKGROUND: Caspase activation and recruitment domain 11 (CARD11) encodes a scaffold protein in lymphocytes that links antigen receptor engagement with downstream signaling to nuclear factor κB, c-Jun N-terminal kinase, and mechanistic target of rapamycin complex 1. Germline CARD11 mutations cause several distinct primary immune disorders in human subjects, including severe combined immune deficiency (biallelic null mutations), B-cell expansion with nuclear factor κB and T-cell anergy (heterozygous, gain-of-function mutations), and severe atopic disease (loss-of-function, heterozygous, dominant interfering mutations), which has focused attention on CARD11 mutations discovered by using whole-exome sequencing. OBJECTIVES: We sought to determine the molecular actions of an extended allelic series of CARD11 and to characterize the expanding range of clinical phenotypes associated with heterozygous CARD11 loss-of-function alleles. METHODS: Cell transfections and primary T-cell assays were used to evaluate signaling and function of CARD11 variants. RESULTS: Here we report on an expanded cohort of patients harboring novel heterozygous CARD11 mutations that extend beyond atopy to include other immunologic phenotypes not previously associated with CARD11 mutations. In addition to (and sometimes excluding) severe atopy, heterozygous missense and indel mutations in CARD11 presented with immunologic phenotypes similar to those observed in signal transducer and activator of transcription 3 loss of function, dedicator of cytokinesis 8 deficiency, common variable immunodeficiency, neutropenia, and immune dysregulation, polyendocrinopathy, enteropathy, X-linked-like syndrome. Pathogenic variants exhibited dominant negative activity and were largely confined to the CARD or coiled-coil domains of the CARD11 protein. CONCLUSION: These results illuminate a broader phenotypic spectrum associated with CARD11 mutations in human subjects and underscore the need for functional studies to demonstrate that rare gene variants encountered in expected and unexpected phenotypes must nonetheless be validated for pathogenic activity.

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States; Whole Exome Sequencing

Interchromosomal template-switching as a novel molecular mechanism for imprinting perturbations associated with Temple syndrome. - Carvalho, Claudia M B; Coban-Akdemir, Zeynep; Hijazi, Hadia; Yuan, Bo; Pendleton, Matthew; Harrington, Eoghan; Beaulaurier, John; Juul, Sissel; Turner, Daniel J; Kanchi, Rupa S; Jhangiani, Shalini N; Muzny, Donna M; et al. (Genome Med, 2019)
BACKGROUND: Intrachromosomal triplications (TRP) can contribute to disease etiology via gene dosage effects, gene disruption, position effects, or fusion gene formation. Recently, post-zygotic de novo triplications adjacent to copy-number neutral genomic intervals with runs of homozygosity (ROH) have been shown to result in uniparental isodisomy (UPD). The genomic structure of these complex genomic rearrangements (CGRs) shows a consistent pattern of an inverted triplication flanked by duplications (DUP-TRP/INV-DUP) formed by an iterative DNA replisome template-switching mechanism during replicative repair of a single-ended, double-stranded DNA (seDNA), the ROH results from an interhomolog or nonsister chromatid template switch. It has been postulated that these CGRs may lead to genetic abnormalities in carriers due to dosage-sensitive genes mapping within the copy-number variant regions, homozygosity for alleles at a locus causing an autosomal recessive (AR) disease trait within the ROH region, or imprinting-associated diseases. METHODS: Here, we report a family wherein the affected subject carries a de novo 2.2-Mb TRP followed by 42.2 Mb of ROH and manifests clinical features overlapping with those observed in association with chromosome 14 maternal UPD (UPD(14)mat). UPD(14)mat can cause clinical phenotypic features enabling a diagnosis of Temple syndrome. This CGR was then molecularly characterized by high-density custom aCGH, genome-wide single-nucleotide polymorphism (SNP) and methylation arrays, exome sequencing (ES), and the Oxford Nanopore long-read sequencing technology. RESULTS: We confirmed the postulated DUP-TRP/INV-DUP structure by multiple orthogonal genomic technologies in the proband. The methylation status of known differentially methylated regions (DMRs) on chromosome 14 revealed that the subject shows the typical methylation pattern of UPD(14)mat. Consistent with these molecular findings, the clinical features overlap with those observed in Temple syndrome, including speech delay. CONCLUSIONS: These data provide experimental evidence that, in humans, triplication can lead to segmental UPD and imprinting disease. Importantly, genotype/phenotype analyses further reveal how a post-zygotically generated complex structural variant, resulting from a replication-based mutational mechanism, contributes to expanding the clinical phenotype of known genetic syndromes. Mechanistically, such events can distort transmission genetics resulting in homozygosity at a locus for which only one parent is a carrier as well as cause imprinting diseases.

Lack of GAS2L2 Causes PCD by Impairing Cilia Orientation and Mucociliary Clearance. - Bustamante-Marin, Ximena M; Yin, Wei-Ning; Sears, Patrick R; Werner, Michael E; Brotslaw, Eva J; Mitchell, Brian J; Jania, Corey M; Zeman, Kirby L; Rogers, Troy D; Herring, Laura E; Refabért, Luc; Thomas, Lucie; et al. (Am J Hum Genet, 2019)
Primary ciliary dyskinesia (PCD) is a genetic disorder in which impaired ciliary function leads to chronic airway disease. Exome sequencing of a PCD subject identified an apparent homozygous frameshift variant, c.887_890delTAAG (p.Val296Glyfs13), in exon 5; this frameshift introduces a stop codon in amino acid 308 of the growth arrest-specific protein 2-like 2 (GAS2L2). Further genetic screening of unrelated PCD subjects identified a second proband with a compound heterozygous variant carrying the identical frameshift variant and a large deletion (c.867_343+1207del; p.?) starting in exon 5. Both individuals had clinical features of PCD but normal ciliary axoneme structure. In this research, using human nasal cells, mouse models, and X.laevis embryos, we show that GAS2L2 is abundant at the apical surface of ciliated cells, where it localizes with basal bodies, basal feet, rootlets, and actin filaments. Cultured GAS2L2-deficient nasal epithelial cells from one of the affected individuals showed defects in ciliary orientation and had an asynchronous and hyperkinetic (GAS2L2-deficient = 19.8 Hz versus control = 15.8 Hz) ciliary-beat pattern. These results were recapitulated in Gas2l2 mouse tracheal epithelial cell (mTEC) cultures and in X. laevis embryos treated with Gas2l2 morpholinos. In mice, the absence of Gas2l2 caused neonatal death, and the conditional deletion of Gas2l2 impaired mucociliary clearance (MCC) and led to mucus accumulation. These results show that a pathogenic variant in GAS2L2 causes a genetic defect in ciliary orientation and impairs MCC and results in PCD.
Keywords: Animals; Cilia; Ciliary Motility Disorders; Disease Models, Animal; Exons; Female; Gene Deletion; Genes, Lethal; Humans; Male; Mice; Mice, Knockout; Microfilament Proteins; Microtubule-Associated Proteins; Phenotype; Rotation; Xenopus

Loss of SMPD4 Causes a Developmental Disorder Characterized by Microcephaly and Congenital Arthrogryposis. - Magini, Pamela; Smits, Daphne J; Vandervore, Laura; Schot, Rachel; Columbaro, Marta; Kasteleijn, Esmee; van der Ent, Mees; Palombo, Flavia; Lequin, Maarten H; Dremmen, Marjolein; de Wit, Marie Claire Y; Severino, Mariasavina; et al. (Am J Hum Genet, 2019)
Sphingomyelinases generate ceramide from sphingomyelin as a second messenger in intracellular signaling pathways involved in cell proliferation, differentiation, or apoptosis. Children from 12 unrelated families presented with microcephaly, simplified gyral pattern of the cortex, hypomyelination, cerebellar hypoplasia, congenital arthrogryposis, and early fetal/postnatal demise. Genomic analysis revealed bi-allelic loss-of-function variants in SMPD4, coding for the neutral sphingomyelinase-3 (nSMase-3/SMPD4). Overexpression of human Myc-tagged SMPD4 showed localization both to the outer nuclear envelope and the ER and additionally revealed interactions with several nuclear pore complex proteins by proteomics analysis. Fibroblasts from affected individuals showed ER cisternae abnormalities, suspected for increased autophagy, and were more susceptible to apoptosis under stress conditions, while treatment with siSMPD4 caused delayed cell cycle progression. Our data show that SMPD4 links homeostasis of membrane sphingolipids to cell fate by regulating the cross-talk between the ER and the outer nuclear envelope, while its loss reveals a pathogenic mechanism in microcephaly.

Loss of the sphingolipid desaturase DEGS1 causes hypomyelinating leukodystrophy. - Pant, Devesh C; Dorboz, Imen; Schluter, Agatha; Fourcade, Stéphane; Launay, Nathalie; Joya, Javier; Aguilera-Albesa, Sergio; Yoldi, Maria Eugenia; Casasnovas, Carlos; Willis, Mary J; Ruiz, Montserrat; Ville, Dorothée; et al. (J Clin Invest, 2019)
Sphingolipid imbalance is the culprit in a variety of neurological diseases, some affecting the myelin sheath. We have used whole-exome sequencing in patients with undetermined leukoencephalopathies to uncover the endoplasmic reticulum lipid desaturase DEGS1 as the causative gene in 19 patients from 13 unrelated families. Shared features among the cases include severe motor arrest, early nystagmus, dystonia, spasticity, and profound failure to thrive. MRI showed hypomyelination, thinning of the corpus callosum, and progressive thalamic and cerebellar atrophy, suggesting a critical role of DEGS1 in myelin development and maintenance. This enzyme converts dihydroceramide (DhCer) into ceramide (Cer) in the final step of the de novo biosynthesis pathway. We detected a marked increase of the substrate DhCer and DhCer/Cer ratios in patients' fibroblasts and muscle. Further, we used a knockdown approach for disease modeling in Danio rerio, followed by a preclinical test with the first-line treatment for multiple sclerosis, fingolimod (FTY720, Gilenya). The enzymatic inhibition of Cer synthase by fingolimod, 1 step prior to DEGS1 in the pathway, reduced the critical DhCer/Cer imbalance and the severe locomotor disability, increasing the number of myelinating oligodendrocytes in a zebrafish model. These proof-of-concept results pave the way to clinical translation.

MAGEL2-related disorders: A study and case series. - Patak, Jameson; Gilfert, James; Byler, Melissa; Neerukonda, Vamsee; Thiffault, Isabelle; Cross, Laura; Amudhavalli, Shivarajan; Pacio-Miguez, Marta; Palomares-Bralo, Maria; Garcia-Minaur, Sixto; Santos-Simarro, Fernando; Powis, Zöe; et al. (Clin Genet, 2019)
Pathogenic MAGEL2 variants result in the phenotypes of Chitayat-Hall syndrome (CHS), Schaaf-Yang syndrome (SYS) and Prader-Willi syndrome (PWS). We present five patients with mutations in MAGEL2, including the first patient reported with a missense variant, adding to the limited literature. Further, we performed a systematic review of the CHS and SYS literature, assess the overlap between CHS, SYS and PWS, and analyze genotype-phenotype correlations among them. We conclude that there is neither a clinical nor etiological difference between CHS and SYS, and propose that the two syndromes simply be referred to as MAGEL2-related disorders.

Megabase Length Hypermutation Accompanies Human Structural Variation at 17p11.2. - Beck, Christine R; Carvalho, Claudia M B; Akdemir, Zeynep C; Sedlazeck, Fritz J; Song, Xiaofei; Meng, Qingchang; Hu, Jianhong; Doddapaneni, Harsha; Chong, Zechen; Chen, Edward S; Thornton, Philip C; Liu, Pengfei; et al. (Cell, 2019)
DNA rearrangements resulting in human genome structural variants (SVs) are caused by diverse mutational mechanisms. We used long- and short-read sequencing technologies to investigate end products of de novo chromosome 17p11.2 rearrangements and query the molecular mechanisms underlying both recurrent and non-recurrent events. Evidence for an increased rate of clustered single-nucleotide variant (SNV) mutation in cis with non-recurrent rearrangements was found. Indel and SNV formation are associated with both copy-number gains and losses of 17p11.2, occur up to ∼1 Mb away from the breakpoint junctions, and favor C > G transversion substitutions; results suggest that single-stranded DNA is formed during the genesis of the SV and provide compelling support for a microhomology-mediated break-induced replication (MMBIR) mechanism for SV formation. Our data show an additional mutational burden of MMBIR consisting of hypermutation confined to the locus and manifesting as SNVs and indels predominantly within genes.

Missense Variants in the Histone Acetyltransferase Complex Component Gene TRRAP Cause Autism and Syndromic Intellectual Disability. - Cogné, Benjamin; Ehresmann, Sophie; Beauregard-Lacroix, Eliane; Rousseau, Justine; Besnard, Thomas; Garcia, Thomas; Petrovski, Slavé; Avni, Shiri; McWalter, Kirsty; Blackburn, Patrick R; Sanders, Stephan J; Uguen, Kévin; et al. (Am J Hum Genet, 2019)
Acetylation of the lysine residues in histones and other DNA-binding proteins plays a major role in regulation of eukaryotic gene expression. This process is controlled by histone acetyltransferases (HATs/KATs) found in multiprotein complexes that are recruited to chromatin by the scaffolding subunit transformation/transcription domain-associated protein (TRRAP). TRRAP is evolutionarily conserved and is among the top five genes intolerant to missense variation. Through an international collaboration, 17 distinct de novo or apparently de novo variants were identified in TRRAP in 24 individuals. A strong genotype-phenotype correlation was observed with two distinct clinical spectra. The first is a complex, multi-systemic syndrome associated with various malformations of the brain, heart, kidneys, and genitourinary system and characterized by a wide range of intellectual functioning; a number of affected individuals have intellectual disability (ID) and markedly impaired basic life functions. Individuals with this phenotype had missense variants clustering around the c.3127G>A p.(Ala1043Thr) variant identified in five individuals. The second spectrum manifested with autism spectrum disorder (ASD) and/or ID and epilepsy. Facial dysmorphism was seen in both groups and included upslanted palpebral fissures, epicanthus, telecanthus, a wide nasal bridge and ridge, a broad and smooth philtrum, and a thin upper lip. RNA sequencing analysis of skin fibroblasts derived from affected individuals skin fibroblasts showed significant changes in the expression of several genes implicated in neuronal function and ion transport. Thus, we describe here the clinical spectrum associated with TRRAP pathogenic missense variants, and we suggest a genotype-phenotype correlation useful for clinical evaluation of the pathogenicity of the variants.

MSTO1 mutations cause mtDNA depletion, manifesting as muscular dystrophy with cerebellar involvement. - Donkervoort, S; Sabouny, R; Yun, P; Gauquelin, L; Chao, K R; Hu, Y; Al Khatib, I; Töpf, A; Mohassel, P; Cummings, B B; Kaur, R; Saade, D; et al. (Acta Neuropathol, 2019)
MSTO1 encodes a cytosolic mitochondrial fusion protein, misato homolog 1 or MSTO1. While the full genotype-phenotype spectrum remains to be explored, pathogenic variants in MSTO1 have recently been reported in a small number of patients presenting with a phenotype of cerebellar ataxia, congenital muscle involvement with histologic findings ranging from myopathic to dystrophic and pigmentary retinopathy. The proposed underlying pathogenic mechanism of MSTO1-related disease is suggestive of impaired mitochondrial fusion secondary to a loss of function of MSTO1. Disorders of mitochondrial fusion and fission have been shown to also lead to mitochondrial DNA (mtDNA) depletion, linking them to the mtDNA depletion syndromes, a clinically and genetically diverse class of mitochondrial diseases characterized by a reduction of cellular mtDNA content. However, the consequences of pathogenic variants in MSTO1 on mtDNA maintenance remain poorly understood. We present extensive phenotypic and genetic data from 12 independent families, including 15 new patients harbouring a broad array of bi-allelic MSTO1 pathogenic variants, and we provide functional characterization from seven MSTO1-related disease patient fibroblasts. Bi-allelic loss-of-function variants in MSTO1 manifest clinically with a remarkably consistent phenotype of childhood-onset muscular dystrophy, corticospinal tract dysfunction and early-onset non-progressive cerebellar atrophy. MSTO1 protein was not detectable in the cultured fibroblasts of all seven patients evaluated, suggesting that pathogenic variants result in a loss of protein expression and/or affect protein stability. Consistent with impaired mitochondrial fusion, mitochondrial networks in fibroblasts were found to be fragmented. Furthermore, all fibroblasts were found to have depletion of mtDNA ranging from 30 to 70% along with alterations to mtDNA nucleoids. Our data corroborate the role of MSTO1 as a mitochondrial fusion protein and highlight a previously unrecognized link to mtDNA regulation. As impaired mitochondrial fusion is a recognized cause of mtDNA depletion syndromes, this novel link to mtDNA depletion in patient fibroblasts suggests that MSTO1-deficiency should also be considered a mtDNA depletion syndrome. Thus, we provide mechanistic insight into the disease pathogenesis associated with MSTO1 mutations and further define the clinical spectrum and the natural history of MSTO1-related disease.

Mutations in and previously unimplicated genes of the BMP, Wnt, and Hedgehog pathways in syndromic craniosynostosis. - Timberlake, Andrew T; Jin, Sheng Chih; Nelson-Williams, Carol; Wu, Robin; Furey, Charuta G; Islam, Barira; Haider, Shozeb; Loring, Erin; Galm, Amy; Steinbacher, Derek M; Larysz, Dawid; Staffenberg, David A; et al. (Proc Natl Acad Sci U S A, 2019)
Craniosynostosis (CS) is a frequent congenital anomaly featuring the premature fusion of 1 or more sutures of the cranial vault. Syndromic cases, featuring additional congenital anomalies, make up 15% of CS. While many genes underlying syndromic CS have been identified, the cause of many syndromic cases remains unknown. We performed exome sequencing of 12 syndromic CS cases and their parents, in whom previous genetic evaluations were unrevealing. Damaging de novo or transmitted loss of function (LOF) mutations were found in 8 genes that are highly intolerant to LOF mutation ( = 4.0 × 10); additionally, a rare damaging mutation in , which has a lower level of intolerance, was identified. Four probands had rare damaging mutations (2 de novo) in , a transcription factor that orchestrates neural crest cell migration and differentiation; this mutation burden is highly significant ( = 8.2 × 10). Three probands had rare damaging mutations in , , or , which function in the Hedgehog, BMP, and Wnt signaling pathways; other genes in these pathways have previously been implicated in syndromic CS. Similarly, damaging de novo mutations were identified in genes encoding the chromatin modifier , and , encoding catenin α-1. These findings establish as a CS gene, have implications for assessing risk to subsequent children in these families, and provide evidence implicating other genes in syndromic CS. This high yield indicates the value of performing exome sequencing of syndromic CS patients when sequencing of known disease loci is unrevealing.

Mutations in ANKLE2, a ZIKA Virus Target, Disrupt an Asymmetric Cell Division Pathway in Drosophila Neuroblasts to Cause Microcephaly. - Link, Nichole; Chung, Hyunglok; Jolly, Angad; Withers, Marjorie; Tepe, Burak; Arenkiel, Benjamin R; Shah, Priya S; Krogan, Nevan J; Aydin, Hatip; Geckinli, Bilgen B; Tos, Tulay; Isikay, Sedat; et al. (Dev Cell, 2019)
The apical Par complex, which contains atypical protein kinase C (aPKC), Bazooka (Par-3), and Par-6, is required for establishing polarity during asymmetric division of neuroblasts in Drosophila, and its activity depends on L(2)gl. We show that loss of Ankle2, a protein associated with microcephaly in humans and known to interact with Zika protein NS4A, reduces brain volume in flies and impacts the function of the Par complex. Reducing Ankle2 levels disrupts endoplasmic reticulum (ER) and nuclear envelope morphology, releasing the kinase Ballchen-VRK1 into the cytosol. These defects are associated with reduced phosphorylation of aPKC, disruption of Par-complex localization, and spindle alignment defects. Importantly, removal of one copy of ballchen or l(2)gl suppresses Ankle2 mutant phenotypes and restores viability and brain size. Human mutational studies implicate the above-mentioned genes in microcephaly and motor neuron disease. We suggest that NS4A, ANKLE2, VRK1, and LLGL1 define a pathway impinging on asymmetric determinants of neural stem cell division.

Novel Heterozygous Mutation in Is Associated With Early Onset CVID and a Functional Defect in NK Cells Complicated by Disseminated CMV Infection and Severe Nephrotic Syndrome. - Aird, Alejandra; Lagos, Macarena; Vargas-Hernandez, Alexander; Posey, Jennifer E; Coban-Akdemir, Zeynep; Jhangiani, Shalini; Mace, Emily M; Reyes, Anaid; King, Alejandra; Cavagnaro, Felipe; Forbes, Lisa R; Chinn, Ivan K; et al. (Front Pediatr, 2019)
Nuclear factor kappa-B subunit 2 (NF-κB2/p100/p52), encoded by (MIM: 164012) belongs to the NF-κB family of transcription factors that play a critical role in inflammation, immunity, cell proliferation, differentiation and survival. Heterozygous C-terminal mutations in have been associated with early-onset common variable immunodeficiency (CVID), central adrenal insufficiency and ectodermal dysplasia. Only two previously reported cases have documented decreased natural killer (NK) cell cytotoxicity, and little is known about the role of NF-κB2 in NK cell maturation and function. Here we report a 13-year-old female that presented at 6 years of age with a history of early onset recurrent sinopulmonary infections, progressive hair loss, and hypogamaglobulinemia consistent with a clinical diagnosis of CVID. At 9 years of age she had cytomegalovirus (CMV) pneumonia that responded to ganciclovir treatment. Functional NK cell testing demonstrated decreased NK cell cytotoxicity despite normal NK cell numbers, consistent with a greater susceptibility to systemic CMV infection. Research exome sequencing (ES) was performed and revealed a novel heterozygous nonsense mutation in (c.2611C>T, p.Gln871) that was not carried by either of her parents. The variant was Sanger sequenced and confirmed to be in the patient. At age 12, she presented with a reactivation of the systemic CMV infection that was associated with severe and progressive nephrotic syndrome with histologic evidence of pedicellar effacement and negative immunofluorescence. To our knowledge, this is the third NF-κB2 deficient patient in which an abnormal NK cell function has been observed, suggesting a role for non-canonical NF-κB2 signaling in NK cell cytotoxicity. NK cell function should be assessed in patients with mutations in the non-canonical NF-κB pathway to explore the risk for systemic viral infections that may lead to severe complications and impact patient survival. Similarly NF-κB2 should be considered in patients with combined immunodeficiency who have aberrant NK cell function. Further studies are needed to characterize the role of NF-κB2 in NK cell cytotoxic function.

Novel SPEG mutations in congenital myopathies: Genotype-phenotype correlations. - Qualls, Anita E; Donkervoort, Sandra; Herkert, Johanna C; D'Gama, Alissa M; Bharucha-Goebel, Diana; Collins, James; Chao, Katherine R; Foley, A Reghan; Schoots, Mirthe H; Jongbloed, Jan D H; Bönnemann, Carsten G; Agrawal, Pankaj B (Muscle Nerve, 2019)
INTRODUCTION: Centronuclear myopathies (CNMs) are a subtype of congenital myopathies (CMs) characterized by muscle weakness, predominant type 1 fibers, and increased central nuclei. SPEG (striated preferentially expressed protein kinase) mutations have recently been identified in 7 CM patients (6 with CNMs). We report 2 additional patients with SPEG mutations expanding the phenotype and evaluate genotype-phenotype correlations associated with SPEG mutations. METHODS: Using whole exome/genome sequencing in CM families, we identified novel recessive SPEG mutations in 2 patients. RESULTS: Patient 1, with severe muscle weakness requiring respiratory support, dilated cardiomyopathy, ophthalmoplegia, and findings of nonspecific CM on muscle biopsy carried a homozygous SPEG mutation (p.Val3062del). Patient 2, with milder muscle weakness, ophthalmoplegia, and CNM carried compound heterozygous mutations (p.Leu728Argfs*82) and (p.Val2997Glyfs*52). CONCLUSIONS: The 2 patients add insight into genotype-phenotype correlations of SPEG-associated CMs. Clinicians should consider evaluating a CM patient for SPEG mutations even in the absence of CNM features. Muscle Nerve 59:357-362, 2019.
Keywords: Biopsy; Child; Child, Preschool; Consanguinity; Exome; Female; Genetic Association Studies; Humans; Infant; Male; Muscle Proteins; Muscle Weakness; Muscle, Skeletal; Mutation; Myopathies, Structural, Congenital; Protein-Serine-Threonine Kinases; Sequence Analysis

Paralog Studies Augment Gene Discovery: DDX and DHX Genes. - Paine, Ingrid; Posey, Jennifer E; Grochowski, Christopher M; Jhangiani, Shalini N; Rosenheck, Sarah; Kleyner, Robert; Marmorale, Taylor; Yoon, Margaret; Wang, Kai; Robison, Reid; Cappuccio, Gerarda; Pinelli, Michele; et al. (Am J Hum Genet, 2019)
Members of a paralogous gene family in which variation in one gene is known to cause disease are eight times more likely to also be associated with human disease. Recent studies have elucidated DHX30 and DDX3X as genes for which pathogenic variant alleles are involved in neurodevelopmental disorders. We hypothesized that variants in paralogous genes encoding members of the DExD/H-box RNA helicase superfamily might also underlie developmental delay and/or intellectual disability (DD and/or ID) disease phenotypes. Here we describe 15 unrelated individuals who have DD and/or ID, central nervous system (CNS) dysfunction, vertebral anomalies, and dysmorphic features and were found to have probably damaging variants in DExD/H-box RNA helicase genes. In addition, these individuals exhibit a variety of other tissue and organ system involvement including ocular, outer ear, hearing, cardiac, and kidney tissues. Five individuals with homozygous (one), compound-heterozygous (two), or de novo (two) missense variants in DHX37 were identified by exome sequencing. We identified ten total individuals with missense variants in three other DDX/DHX paralogs: DHX16 (four individuals), DDX54 (three individuals), and DHX34 (three individuals). Most identified variants are rare, predicted to be damaging, and occur at conserved amino acid residues. Taken together, these 15 individuals implicate the DExD/H-box helicases in both dominantly and recessively inherited neurodevelopmental phenotypes and highlight the potential for more than one disease mechanism underlying these disorders.

Pathogenic Abnormal Splicing Due to Intronic Deletions that Induce Biophysical Space Constraint for Spliceosome Assembly. - Bryen, Samantha J; Joshi, Himanshu; Evesson, Frances J; Girard, Cyrille; Ghaoui, Roula; Waddell, Leigh B; Testa, Alison C; Cummings, Beryl; Arbuckle, Susan; Graf, Nicole; Webster, Richard; MacArthur, Daniel G; et al. (Am J Hum Genet, 2019)
A precise genetic diagnosis is the single most important step for families with genetic disorders to enable personalized and preventative medicine. In addition to genetic variants in coding regions (exons) that can change a protein sequence, abnormal pre-mRNA splicing can be devastating for the encoded protein, inducing a frameshift or in-frame deletion/insertion of multiple residues. Non-coding variants that disrupt splicing are extremely challenging to identify. Stemming from an initial clinical discovery in two index Australian families, we define 25 families with genetic disorders caused by a class of pathogenic non-coding splice variant due to intronic deletions. These pathogenic intronic deletions spare all consensus splice motifs, though they critically shorten the minimal distance between the 5' splice-site (5'SS) and branchpoint. The mechanistic basis for abnormal splicing is due to biophysical constraint precluding U1/U2 spliceosome assembly, which stalls in A-complexes (that bridge the 5'SS and branchpoint). Substitution of deleted nucleotides with non-specific sequences restores spliceosome assembly and normal splicing, arguing against loss of an intronic element as the primary causal basis. Incremental lengthening of 5'SS-branchpoint length in our index EMD case subject defines 45-47 nt as the critical elongation enabling (inefficient) spliceosome assembly for EMD intron 5. The 5'SS-branchpoint space constraint mechanism, not currently factored by genomic informatics pipelines, is relevant to diagnosis and precision medicine across the breadth of Mendelian disorders and cancer genomics.

A Patient with Berardinelli-Seip Syndrome, Novel Splicesite Mutation and Concomitant Development of Non-diabetic Polyneuropathy - Oswiecimska, Joanna; Dawidziuk, Mateusz; Gambin, Tomasz; Ziora, Katarzyna; Marek, Marta; Rzonca, Sylwia; Guilbride, D. Lys; Jhangiani, Shalini N.; Obuchowicz, Anna; Sikora, Alicja; Lupski, James R.; Wiszniewski, Wojciech; et al. (J Clin Res Pediatr Endocrinol, 2019)
Primary polyneuropathy in the context of Seip-Berardinelli type 1 seipinopathy, or congenital generalized lipodystrophy type 1 (CGL1) has not been previously reported. We report the case history of a 27 year old female CGL1 patient presenting with an unusual additional development of non-diabetic peripheral neuropathy and learning disabilities in early adolescence. Whole exome sequencing (WES) of the patient genome identified a novel variant, homozygous for a 52 bp intronic deletion in the locus, coding for 1-acylglycerol-3-phosphate O-acyltransferase 2, which is uniquely associated with CGL1 seipinopathies, with no molecular evidence for dual diagnosis. Functional studies using RNA isolated from patient peripheral blood leucocytes showed abnormal RNA splicing resulting in the loss of 25 amino acids from the patient AGPAT2 protein coding sequence. Stability and transcription levels for the misspliced mRNA in our patient nonetheless remained normal. Any AGPAT2 protein produced in our patient is therefore likely to be dysfunctional. However, formal linkage of this deletion to the neuropathy observed remains to be shown. The classical clinical presentation of a patient with -associated lipodystrophy shows normal cognition and no development of polyneuropathy. Cognitive disabilities and polyneuropathy are features associated exclusively with clinical CGL type 2 arising from seipin gene mutations. This case study suggests that in some genetic contexts, mutations can also produce phenotypes with primary polyneuropathy.

Recessive DES cardio/myopathy without myofibrillar aggregates: intronic splice variant silences one allele leaving only missense L190P-desmin. - Riley, Lisa G; Waddell, Leigh B; Ghaoui, Roula; Evesson, Frances J; Cummings, Beryl B; Bryen, Samantha J; Joshi, Himanshu; Wang, Min-Xia; Brammah, Susan; Kritharides, Leonard; Corbett, Alastair; MacArthur, Daniel G; et al. (Eur J Hum Genet, 2019)
We establish autosomal recessive DES variants p.(Leu190Pro) and a deep intronic splice variant causing inclusion of a frameshift-inducing artificial exon/intronic fragment, as the likely cause of myopathy with cardiac involvement in female siblings. Both sisters presented in their twenties with slowly progressive limb girdle weakness, severe systolic dysfunction, and progressive, severe respiratory weakness. Desmin is an intermediate filament protein typically associated with autosomal dominant myofibrillar myopathy with cardiac involvement. However a few rare cases of autosomal recessive desminopathy are reported. In this family, a paternal missense p.(Leu190Pro) variant was viewed unlikely to be causative of autosomal dominant desminopathy, as the father and brothers carrying this variant were clinically unaffected. Clinical fit with a DES-related myopathy encouraged closer scrutiny of all DES variants, identifying a maternal deep intronic variant within intron-7, predicted to create a cryptic splice site, which segregated with disease. RNA sequencing and studies of muscle cDNA confirmed the deep intronic variant caused aberrant splicing of an artificial exon/intronic fragment into maternal DES mRNA transcripts, encoding a premature termination codon, and potently activating nonsense-mediate decay (92% paternal DES transcripts, 8% maternal). Western blot showed 60-75% reduction in desmin levels, likely comprised only of missense p.(Leu190Pro) desmin. Biopsy showed fibre size variation with increased central nuclei. Electron microscopy showed extensive myofibrillar disarray, duplication of the basal lamina, but no inclusions or aggregates. This study expands the phenotypic spectrum of recessive DES cardio/myopathy, and emphasizes the continuing importance of muscle biopsy for functional genomics pursuit of 'tricky' variants in neuromuscular conditions.

A recurrent COL6A1 pseudoexon insertion causes muscular dystrophy and is effectively targeted by splice-correction therapies. - Bolduc, Veronique; Foley, A Reghan; Solomon-Degefa, Herimela; Sarathy, Apurva; Donkervoort, Sandra; Hu, Ying; Chen, Grace S; Sizov, Katherine; Nalls, Matthew; Zhou, Haiyan; Aguti, Sara; Cummings, Beryl B; et al. (JCI Insight, 2019)
The clinical application of advanced next-generation sequencing technologies is increasingly uncovering novel classes of mutations that may serve as potential targets for precision medicine therapeutics. Here, we show that a deep intronic splice defect in the COL6A1 gene, originally discovered by applying muscle RNA sequencing in patients with clinical findings of collagen VI-related dystrophy (COL6-RD), inserts an in-frame pseudoexon into COL6A1 mRNA, encodes a mutant collagen α1(VI) protein that exerts a dominant-negative effect on collagen VI matrix assembly, and provides a unique opportunity for splice-correction approaches aimed at restoring normal gene expression. Using splice-modulating antisense oligomers, we efficiently skipped the pseudoexon in patient-derived fibroblast cultures and restored a wild-type matrix. Similarly, we used CRISPR/Cas9 to precisely delete an intronic sequence containing the pseudoexon and efficiently abolish its inclusion while preserving wild-type splicing. Considering that this splice defect is emerging as one of the single most frequent mutations in COL6-RD, the design of specific and effective splice-correction therapies offers a promising path for clinical translation.

Redefining the Etiologic Landscape of Cerebellar Malformations. - Aldinger, Kimberly A; Timms, Andrew E; Thomson, Zachary; Mirzaa, Ghayda M; Bennett, James T; Rosenberg, Alexander B; Roco, Charles M; Hirano, Matthew; Abidi, Fatima; Haldipur, Parthiv; Cheng, Chi V; Collins, Sarah; et al. (Am J Hum Genet, 2019)
Cerebellar malformations are diverse congenital anomalies frequently associated with developmental disability. Although genetic and prenatal non-genetic causes have been described, no systematic analysis has been performed. Here, we present a large-exome sequencing study of Dandy-Walker malformation (DWM) and cerebellar hypoplasia (CBLH). We performed exome sequencing in 282 individuals from 100 families with DWM or CBLH, and we established a molecular diagnosis in 36 of 100 families, with a significantly higher yield for CBLH (51%) than for DWM (16%). The 41 variants impact 27 neurodevelopmental-disorder-associated genes, thus demonstrating that CBLH and DWM are often features of monogenic neurodevelopmental disorders. Though only seven monogenic causes (19%) were identified in more than one individual, neuroimaging review of 131 additional individuals confirmed cerebellar abnormalities in 23 of 27 genetic disorders (85%). Prenatal risk factors were frequently found among individuals without a genetic diagnosis (30 of 64 individuals [47%]). Single-cell RNA sequencing of prenatal human cerebellar tissue revealed gene enrichment in neuronal and vascular cell types; this suggests that defective vasculogenesis may disrupt cerebellar development. Further, de novo gain-of-function variants in PDGFRB, a tyrosine kinase receptor essential for vascular progenitor signaling, were associated with CBLH, and this discovery links genetic and non-genetic etiologies. Our results suggest that genetic defects impact specific cerebellar cell types and implicate abnormal vascular development as a mechanism for cerebellar malformations. We also confirmed a major contribution for non-genetic prenatal factors in individuals with cerebellar abnormalities, substantially influencing diagnostic evaluation and counseling regarding recurrence risk and prognosis.

ROBO4 variants predispose individuals to bicuspid aortic valve and thoracic aortic aneurysm. - Gould, Russell A; Aziz, Hamza; Woods, Courtney E; Seman-Senderos, Manuel Alejandro; Sparks, Elizabeth; Preuss, Christoph; Wünnemann, Florian; Bedja, Djahida; Moats, Cassandra R; McClymont, Sarah A; Rose, Rebecca; Sobreira, Nara; et al. (Nat Genet, 2019)
Bicuspid aortic valve (BAV) is a common congenital heart defect (population incidence, 1-2%) that frequently presents with ascending aortic aneurysm (AscAA). BAV/AscAA shows autosomal dominant inheritance with incomplete penetrance and male predominance. Causative gene mutations (for example, NOTCH1, SMAD6) are known for ≤1% of nonsyndromic BAV cases with and without AscAA, impeding mechanistic insight and development of therapeutic strategies. Here, we report the identification of variants in ROBO4 (which encodes a factor known to contribute to endothelial performance) that segregate with disease in two families. Targeted sequencing of ROBO4 showed enrichment for rare variants in BAV/AscAA probands compared with controls. Targeted silencing of ROBO4 or mutant ROBO4 expression in endothelial cell lines results in impaired barrier function and a synthetic repertoire suggestive of endothelial-to-mesenchymal transition. This is consistent with BAV/AscAA-associated findings in patients and in animal models deficient for ROBO4. These data identify a novel endothelial etiology for this common human disease phenotype.
Keywords: Animals; Aortic Aneurysm, Thoracic; Aortic Valve; Cells, Cultured; Disease Models, Animal; Endothelial Cells; Female; Heart Valve Diseases; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Receptors, Cell Surface; Zebrafish

Spatially clustering de novo variants in CYFIP2, encoding the cytoplasmic FMRP interacting protein 2, cause intellectual disability and seizures. - Zweier, Markus; Begemann, Anaïs; McWalter, Kirsty; Cho, Megan T; Abela, Lucia; Banka, Siddharth; Behring, Bettina; Berger, Andrea; Brown, Chester W; Carneiro, Maryline; Chen, Jiani; Cooper, Gregory M; et al. (Eur J Hum Genet, 2019)
CYFIP2, encoding the evolutionary highly conserved cytoplasmic FMRP interacting protein 2, has previously been proposed as a candidate gene for intellectual disability and autism because of its important role linking FMRP-dependent transcription regulation and actin polymerization via the WAVE regulatory complex (WRC). Recently, de novo variants affecting the amino acid p.Arg87 of CYFIP2 were reported in four individuals with epileptic encephalopathy. We here report 12 independent patients harboring a variety of de novo variants in CYFIP2 broadening the molecular and clinical spectrum of a novel CYFIP2-related neurodevelopmental disorder. Using trio whole-exome or -genome sequencing, we identified 12 independent patients carrying a total of eight distinct de novo variants in CYFIP2 with a shared phenotype of intellectual disability, seizures, and muscular hypotonia. We detected seven different missense variants, of which two occurred recurrently (p.(Arg87Cys) and p.(Ile664Met)), and a splice donor variant in the last intron for which we showed exon skipping in the transcript. The latter is expected to escape nonsense-mediated mRNA decay resulting in a truncated protein. Despite the large spacing in the primary structure, the variants spatially cluster in the tertiary structure and are all predicted to weaken the interaction with WAVE1 or NCKAP1 of the actin polymerization regulating WRC-complex. Preliminary genotype-phenotype correlation indicates a profound phenotype in p.Arg87 substitutions and a more variable phenotype in other alterations. This study evidenced a variety of de novo variants in CYFIP2 as a novel cause of mostly severe intellectual disability with seizures and muscular hypotonia.

Targeted Treatment of Individuals With Psychosis Carrying a Copy Number Variant Containing a Genomic Triplication of the Glycine Decarboxylase Gene. - Bodkin, J Alexander; Coleman, Michael J; Godfrey, Laura J; Carvalho, Claudia M B; Morgan, Charity J; Suckow, Raymond F; Anderson, Thea; Öngür, Dost; Kaufman, Marc J; Lewandowski, Kathryn E; Siegel, Arthur J; Waldstreicher, Elliot; et al. (Biol Psychiatry, 2019)
BACKGROUND: The increased mutational burden for rare structural genomic variants in schizophrenia and other neurodevelopmental disorders has so far not yielded therapies targeting the biological effects of specific mutations. We identified two carriers (mother and son) of a triplication of the gene encoding glycine decarboxylase, GLDC, presumably resulting in reduced availability of the N-methyl-D-aspartate receptor coagonists glycine and D-serine and N-methyl-D-aspartate receptor hypofunction. Both carriers had a diagnosis of a psychotic disorder. METHODS: We carried out two double-blind, placebo-controlled clinical trials of N-methyl-D-aspartate receptor augmentation of psychotropic drug treatment in these two individuals. Glycine was used in the first clinical trial, and D-cycloserine was used in the second one. RESULTS: Glycine or D-cycloserine augmentation of psychotropic drug treatment each improved psychotic and mood symptoms in placebo-controlled trials. CONCLUSIONS: These results provide two independent proof-of-principle demonstrations of symptom relief by targeting a specific genotype and explicitly link an individual mutation to the pathophysiology of psychosis and treatment response.

TBX6 compound inheritance leads to congenital vertebral malformations in humans and mice. - Yang, Nan; Wu, Nan; Zhang, Ling; Zhao, Yanxue; Liu, Jiaqi; Liang, Xiangyu; Ren, Xiaojun; Li, Weiyu; Chen, Weisheng; Dong, Shuangshuang; Zhao, Sen; Lin, Jiachen; et al. (Hum Mol Genet, 2019)
Congenital vertebral malformations (CVMs) are associated with human TBX6 compound inheritance that combines a rare null allele and a common hypomorphic allele at the TBX6 locus. Our previous in vitro evidence suggested that this compound inheritance resulted in a TBX6 gene dosage of less than haploinsufficiency (i.e. <50%) as a potential mechanism of TBX6-associated CVMs. To further investigate this pathogenetic model, we ascertained and collected 108 Chinese CVM cases and found that 10 (9.3%) of them carried TBX6 null mutations in combination with common hypomorphic variants at the second TBX6 allele. For in vivo functional verification and genetic analysis of TBX6 compound inheritance, we generated both null and hypomorphic mutations in mouse Tbx6 using the CRISPR-Cas9 method. These Tbx6 mutants are not identical to the patient variants at the DNA sequence level, but instead functionally mimic disease-associated TBX6 variants. Intriguingly, as anticipated by the compound inheritance model, a high penetrance of CVM phenotype was only observed in the mice with combined null and hypomorphic alleles of Tbx6. These findings are consistent with our experimental observations in humans and supported the dosage effect of TBX6 in CVM etiology. In conclusion, our findings in the newly collected human CVM subjects and Tbx6 mouse models consistently support the contention that TBX6 compound inheritance causes CVMs, potentially via a gene dosage-dependent mechanism. Furthermore, mouse Tbx6 mutants mimicking human CVM-associated variants will be useful models for further mechanistic investigations of CVM pathogenesis in the cases associated with TBX6.
Keywords: Adolescent; Alleles; Animals; Child; Child, Preschool; Congenital Abnormalities; CRISPR-Cas Systems; Disease Models, Animal; Female; Haploinsufficiency; Humans; Infant; Male; Mice; Mutation; Phenotype; Scoliosis; Spine; T-Box Domain Proteins

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.

Whole-Exome Sequencing Enables a Precision Medicine Approach for Kidney Transplant Recipients. - Mann, Nina; Braun, Daniela A; Amann, Kassaundra; Tan, Weizhen; Shril, Shirlee; Connaughton, Dervla M; Nakayama, Makiko; Schneider, Ronen; Kitzler, Thomas M; van der Ven, Amelie T; Chen, Jing; Ityel, Hadas; et al. (J Am Soc Nephrol, 2019)
BACKGROUND: Whole-exome sequencing (WES) finds a CKD-related mutation in approximately 20% of patients presenting with CKD before 25 years of age. Although provision of a molecular diagnosis could have important implications for clinical management, evidence is lacking on the diagnostic yield and clinical utility of WES for pediatric renal transplant recipients. METHODS: To determine the diagnostic yield of WES in pediatric kidney transplant recipients, we recruited 104 patients who had received a transplant at Boston Children's Hospital from 2007 through 2017, performed WES, and analyzed results for likely deleterious variants in approximately 400 genes known to cause CKD. RESULTS: By WES, we identified a genetic cause of CKD in 34 out of 104 (32.7%) transplant recipients. The likelihood of detecting a molecular genetic diagnosis was highest for patients with urinary stone disease (three out of three individuals), followed by renal cystic ciliopathies (seven out of nine individuals), steroid-resistant nephrotic syndrome (nine out of 21 individuals), congenital anomalies of the kidney and urinary tract (ten out of 55 individuals), and chronic glomerulonephritis (one out of seven individuals). WES also yielded a molecular diagnosis for four out of nine individuals with ESRD of unknown etiology. The WES-related molecular genetic diagnosis had implications for clinical care for five patients. CONCLUSIONS: Nearly one third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES. Knowledge of this genetic information can help guide management of both transplant patients and potential living related donors.
Keywords: Adolescent; Boston; Child; Child, Preschool; Cohort Studies; Female; Genetic Predisposition to Disease; Genetic Testing; Graft Rejection; Graft Survival; Hospitals, Pediatric; Humans; Kidney Transplantation; Male; Precision Medicine; Prognosis; Renal Insufficiency, Chronic; Retrospective Studies; Risk Assessment; Severity of Illness Index; Survival Analysis; Transplant Recipients; Treatment Outcome; Whole Exome Sequencing

ZMIZ1 Variants Cause a Syndromic Neurodevelopmental Disorder. - Carapito, Raphael; Ivanova, Ekaterina L; Morlon, Aurore; Meng, Linyan; Molitor, Anne; Erdmann, Eva; Kieffer, Bruno; Pichot, Angélique; Naegely, Lydie; Kolmer, Aline; Paul, Nicodème; Hanauer, Antoine; et al. (Am J Hum Genet, 2019)
ZMIZ1 is a coactivator of several transcription factors, including p53, the androgen receptor, and NOTCH1. Here, we report 19 subjects with intellectual disability and developmental delay carrying variants in ZMIZ1. The associated features include growth failure, feeding difficulties, microcephaly, facial dysmorphism, and various other congenital malformations. Of these 19, 14 unrelated subjects carried de novo heterozygous single-nucleotide variants (SNVs) or single-base insertions/deletions, 3 siblings harbored a heterozygous single-base insertion, and 2 subjects had a balanced translocation disrupting ZMIZ1 or involving a regulatory region of ZMIZ1. In total, we identified 13 point mutations that affect key protein regions, including a SUMO acceptor site, a central disordered alanine-rich motif, a proline-rich domain, and a transactivation domain. All identified variants were absent from all available exome and genome databases. In vitro, ZMIZ1 showed impaired coactivation of the androgen receptor. In vivo, overexpression of ZMIZ1 mutant alleles in developing mouse brains using in utero electroporation resulted in abnormal pyramidal neuron morphology, polarization, and positioning, underscoring the importance of ZMIZ1 in neural development and supporting mutations in ZMIZ1 as the cause of a rare neurodevelopmental syndrome.
Keywords: Alleles; Animals; Child; Child, Preschool; Developmental Disabilities; Female; Humans; Infant; Intellectual Disability; Male; Mice; Point Mutation; Syndrome; Transcription Factors

and Mutations Implicate RAB5 Regulation in Nephrotic Syndrome. - Hermle, Tobias; Schneider, Ronen; Schapiro, David; Braun, Daniela A; van der Ven, Amelie T; Warejko, Jillian K; Daga, Ankana; Widmeier, Eugen; Nakayama, Makiko; Jobst-Schwan, Tilman; Majmundar, Amar J; Ashraf, Shazia; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of CKD. The discovery of monogenic causes of SRNS has revealed specific pathogenetic pathways, but these monogenic causes do not explain all cases of SRNS. METHODS: To identify novel monogenic causes of SRNS, we screened 665 patients by whole-exome sequencing. We then evaluated the functional significance of two genes and the mutations therein that we discovered through this sequencing and conducted complementary studies in podocyte-like nephrocytes. RESULTS: We identified conserved, homozygous missense mutations of in two families with early-onset NS and a homozygous missense mutation of in two siblings with SRNS. GAPVD1 and ANKFY1 interact with the endosomal regulator RAB5. Coimmunoprecipitation assays indicated interaction between GAPVD1 and ANKFY1 proteins, which also colocalized when expressed in HEK293T cells. Silencing either protein diminished the podocyte migration rate. Compared with wild-type GAPVD1 and ANKFY1, the mutated proteins produced upon ectopic expression of or bearing the patient-derived mutations exhibited altered binding affinity for active RAB5 and reduced ability to rescue the knockout-induced defect in podocyte migration. Coimmunoprecipitation assays further demonstrated a physical interaction between nephrin and GAPVD1, and immunofluorescence revealed partial colocalization of these proteins in rat glomeruli. The patient-derived mutations reduced nephrin-GAPVD1 binding affinity. In , silencing impaired endocytosis and caused mistrafficking of the nephrin ortholog. CONCLUSIONS: Mutations in and probably in are novel monogenic causes of NS. The discovery of these genes implicates RAB5 regulation in the pathogenesis of human NS.

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Doddapaneni, Harsha; Hu, Jianhong; Muzny, Donna M; Guven, Yeliz; Aktoren, Oya; Kayserili, Hülya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface; Whole Exome Sequencing

Biallelic variants in KIF14 cause intellectual disability with microcephaly. - Makrythanasis, Periklis; Maroofian, Reza; Stray-Pedersen, Asbjørg; Musaev, Damir; Zaki, Maha S; Mahmoud, Iman G; Selim, Laila; Elbadawy, Amera; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Gambin, Tomasz; Sorte, Hanne S; et al. (Eur J Hum Genet, 2018)
Kinesin proteins are critical for various cellular functions such as intracellular transport and cell division, and many members of the family have been linked to monogenic disorders and cancer. We report eight individuals with intellectual disability and microcephaly from four unrelated families with parental consanguinity. In the affected individuals of each family, homozygosity for likely pathogenic variants in KIF14 were detected; two loss-of-function (p.Asn83Ilefs*3 and p.Ser1478fs), and two missense substitutions (p.Ser841Phe and p.Gly459Arg). KIF14 is a mitotic motor protein that is required for spindle localization of the mitotic citron rho-interacting kinase, CIT, also mutated in microcephaly. Our results demonstrate the involvement of KIF14 in development and reveal a wide phenotypic variability ranging from fetal lethality to moderate developmental delay and microcephaly.
Keywords: Child; Child, Preschool; Female; Humans; Intellectual Disability; Kinesin; Loss of Function Mutation; Microcephaly; Mutation, Missense; Oncogene Proteins; Pedigree; Phenotype; Protein Domains; Syndrome

CLCN2 chloride channel mutations in familial hyperaldosteronism type II. - Scholl, Ute I; Stölting, Gabriel; Schewe, Julia; Thiel, Anne; Tan, Hua; Nelson-Williams, Carol; Vichot, Alfred A; Jin, Sheng Chih; Loring, Erin; Untiet, Verena; Yoo, Taekyeong; Choi, Jungmin; et al. (Nat Genet, 2018)
Primary aldosteronism, a common cause of severe hypertension , features constitutive production of the adrenal steroid aldosterone. We analyzed a multiplex family with familial hyperaldosteronism type II (FH-II) and 80 additional probands with unsolved early-onset primary aldosteronism. Eight probands had novel heterozygous variants in CLCN2, including two de novo mutations and four independent occurrences of a mutation encoding an identical p.Arg172Gln substitution; all relatives with early-onset primary aldosteronism carried the CLCN2 variant found in the proband. CLCN2 encodes a voltage-gated chloride channel expressed in adrenal glomerulosa that opens at hyperpolarized membrane potentials. Channel opening depolarizes glomerulosa cells and induces expression of aldosterone synthase, the rate-limiting enzyme for aldosterone biosynthesis. Mutant channels show gain of function, with higher open probabilities at the glomerulosa resting potential. These findings for the first time demonstrate a role of anion channels in glomerulosa membrane potential determination, aldosterone production and hypertension. They establish the cause of a substantial fraction of early-onset primary aldosteronism.

A comprehensive clinical and genetic study in 127 patients with ID in Kinshasa, DR Congo. - Lumaka, Aimé; Race, Valerie; Peeters, Hilde; Corveleyn, Anniek; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Song, Xiaofei; Mubungu, Gerrye; Posey, Jennifer; Lupski, James R; Vermeesch, Joris R; Lukusa, Prosper; et al. (Am J Med Genet A, 2018)
Pathogenic variants account for 4 to 41% of patients with intellectual disability (ID) or developmental delay (DD). In Sub-Saharan Africa, the prevalence of ID is thought to be higher, but data in Central Africa are limited to some case reports. In addition, clinical descriptions of some syndromes are not available for this population. This study aimed at providing an estimate for the fraction of ID/DD for which an underlying etiological genetic cause may be elucidated and provide insights into their clinical presentation in special institutions in a Central African country. A total of 127 patients (33 females and 94 males, mean age 10.03 ± 4.68 years), were recruited from six institutions across Kinshasa. A clinical diagnosis was achieved in 44 but molecular confirmation was achieved in 21 of the 22 patients with expected genetic defect (95% clinical sensitivity). Identified diseases included Down syndrome (15%), submicroscopic copy number variants (9%), aminoacylase deficiency (0.8%), Partington syndrome in one patient (0.8%) and his similarly affected brother, X-linked syndromic Mental Retardation type 33 (0.8%), and two conditions without clear underlying molecular genetic etiologies (Oculo-Auriculo-Vertebral and Amniotic Bands Sequence). We have shown that genetic etiologies, similar to those reported in Caucasian subjects, are a common etiologic cause of ID in African patients from Africa. We have confirmed the diagnostic utility of clinical characterization prior to genetic testing. Finally, our clinical descriptions provide insights into the presentation of these genetic diseases in African patients.

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

Confirmation of the Role of DHX38 in the Etiology of Early-Onset Retinitis Pigmentosa. - Latif, Zahid; Chakchouk, Imen; Schrauwen, Isabelle; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Abbe, Izoduwa; Acharya, Anushree; Jarral, Afeefa; Ali, Imran; Ullah, Ehsan; Khan, Muhammad Nasim; Ali, Ghazanfar; et al. (Invest Ophthalmol Vis Sci, 2018)
Purpose: Retinitis pigmentosa (RP) is a genetically heterogeneous trait with autosomal-recessive (ar) inheritance underlying 50% of genetic disease cases. Sixty-one arRP genes have been identified, and recently, DHX38 has been reported as a potential candidate gene for arRP with only a single family reported with a variant of unknown significance. We identified a missense variant in DHX38 that co-segregates with the arRP phenotype in two Pakistani families confirming the involvement of DHX38 in the etiology of early-onset RP. Methods: Exome sequencing was performed using two DNA samples from affected members of Pakistani families (MA88 and MA157) with early onset arRP. Sanger sequencing of DNA samples from all family members confirmed the segregation of candidate variant within both families. Results: A novel missense DHX38 variant c.971G>A; p.(Arg324Gln) was identified which segregates with the arRP phenotype and yielded a logarithm of the odds (LOD) score of 5.0 and 4.3 for families MA88 and MA157, respectively. This variant is predicted to be conserved and deleterious by several bioinformatics tools. Conclusions: We identified a second deleterious DHX38 variant that segregates with arRP in two families, providing additional evidence that DHX38 is involved in RP etiology. DHX38 encodes for pre-mRNA splicing factor PRP16, which is important in catalyzing pre-mRNA splicing.
Keywords: Adolescent; Adult; Cataract; Computational Biology; DEAD-box RNA Helicases; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; Humans; Male; Mutation, Missense; Nucleotide Mapping; Ophthalmoscopy; Pedigree; Retinitis Pigmentosa; RNA Splicing Factors; Sequence Analysis, DNA; Whole Exome Sequencing; Young Adult

Congenital Titinopathy: Comprehensive characterization and pathogenic insights. - Oates, Emily C; Jones, Kristi J; Donkervoort, Sandra; Charlton, Amanda; Brammah, Susan; Smith, John E; Ware, James S; Yau, Kyle S; Swanson, Lindsay C; Whiffin, Nicola; Peduto, Anthony J; Bournazos, Adam; et al. (Ann Neurol, 2018)
OBJECTIVE: Comprehensive clinical characterization of congenital titinopathy to facilitate diagnosis and management of this important emerging disorder. METHODS: Using massively parallel sequencing we identified 30 patients from 27 families with 2 pathogenic nonsense, frameshift and/or splice site TTN mutations in trans. We then undertook a detailed analysis of the clinical, histopathological and imaging features of these patients. RESULTS: All patients had prenatal or early onset hypotonia and/or congenital contractures. None had ophthalmoplegia. Scoliosis and respiratory insufficiency typically developed early and progressed rapidly, whereas limb weakness was often slowly progressive, and usually did not prevent independent walking. Cardiac involvement was present in 46% of patients. Relatives of 2 patients had dilated cardiomyopathy. Creatine kinase levels were normal to moderately elevated. Increased fiber size variation, internalized nuclei and cores were common histopathological abnormalities. Cap-like regions, whorled or ring fibers, and mitochondrial accumulations were also observed. Muscle magnetic resonance imaging showed gluteal, hamstring and calf muscle involvement. Western blot analysis showed a near-normal sized titin protein in all samples. The presence of 2 mutations predicted to impact both N2BA and N2B cardiac isoforms appeared to be associated with greatest risk of cardiac involvement. One-third of patients had 1 mutation predicted to impact exons present in fetal skeletal muscle, but not included within the mature skeletal muscle isoform transcript. This strongly suggests developmental isoforms are involved in the pathogenesis of this congenital/early onset disorder. INTERPRETATION: This detailed clinical reference dataset will greatly facilitate diagnostic confirmation and management of patients, and has provided important insights into disease pathogenesis. Ann Neurol 2018;83:1105-1124.

De Novo Variants in the F-Box Protein FBXO11 in 20 Individuals with a Variable Neurodevelopmental Disorder. - Gregor, Anne; Sadleir, Lynette G; Asadollahi, Reza; Azzarello-Burri, Silvia; Battaglia, Agatino; Ousager, Lilian Bomme; Boonsawat, Paranchai; Bruel, Ange-Line; Buchert, Rebecca; Calpena, Eduardo; Cogné, Benjamin; Dallapiccola, Bruno; et al. (Am J Hum Genet, 2018)
Next-generation sequencing combined with international data sharing has enormously facilitated identification of new disease-associated genes and mutations. This is particularly true for genetically extremely heterogeneous entities such as neurodevelopmental disorders (NDDs). Through exome sequencing and world-wide collaborations, we identified and assembled 20 individuals with de novo variants in FBXO11. They present with mild to severe developmental delay associated with a range of features including short (4/20) or tall (2/20) stature, obesity (5/20), microcephaly (4/19) or macrocephaly (2/19), behavioral problems (17/20), seizures (5/20), cleft lip or palate or bifid uvula (3/20), and minor skeletal anomalies. FBXO11 encodes a member of the F-Box protein family, constituting a subunit of an E3-ubiquitin ligase complex. This complex is involved in ubiquitination and proteasomal degradation and thus in controlling critical biological processes by regulating protein turnover. The identified de novo aberrations comprise two large deletions, ten likely gene disrupting variants, and eight missense variants distributed throughout FBXO11. Structural modeling for missense variants located in the CASH or the Zinc-finger UBR domains suggests destabilization of the protein. This, in combination with the observed spectrum and localization of identified variants and the lack of apparent genotype-phenotype correlations, is compatible with loss of function or haploinsufficiency as an underlying mechanism. We implicate de novo missense and likely gene disrupting variants in FBXO11 in a neurodevelopmental disorder with variable intellectual disability and various other features.

Detection of variants in dystroglycanopathy-associated genes through the application of targeted whole-exome sequencing analysis to a large cohort of patients with unexplained limb-girdle muscle weakness. - Johnson, Katherine; Bertoli, Marta; Phillips, Lauren; Topf, Ana; Van den Bergh, Peter; Vissing, John; Witting, Nanna; Nafissi, Shahriar; Jamal-Omidi, Shirin; Łusakowska, Anna; Kostera-Pruszczyk, Anna; Potulska-Chromik, Anna; et al. (Skelet Muscle, 2018)
BACKGROUND: Dystroglycanopathies are a clinically and genetically heterogeneous group of disorders that are typically characterised by limb-girdle muscle weakness. Mutations in 18 different genes have been associated with dystroglycanopathies, the encoded proteins of which typically modulate the binding of α-dystroglycan to extracellular matrix ligands by altering its glycosylation. This results in a disruption of the structural integrity of the myocyte, ultimately leading to muscle degeneration. METHODS: Deep phenotypic information was gathered using the PhenoTips online software for 1001 patients with unexplained limb-girdle muscle weakness from 43 different centres across 21 European and Middle Eastern countries. Whole-exome sequencing with at least 250 ng DNA was completed using an Illumina exome capture and a 38 Mb baited target. Genes known to be associated with dystroglycanopathies were analysed for disease-causing variants. RESULTS: Suspected pathogenic variants were detected in DPM3, ISPD, POMT1 and FKTN in one patient each, in POMK in two patients, in GMPPB in three patients, in FKRP in eight patients and in POMT2 in ten patients. This indicated a frequency of 2.7% for the disease group within the cohort of 1001 patients with unexplained limb-girdle muscle weakness. The phenotypes of the 27 patients were highly variable, yet with a fundamental presentation of proximal muscle weakness and elevated serum creatine kinase. CONCLUSIONS: Overall, we have identified 27 patients with suspected pathogenic variants in dystroglycanopathy-associated genes. We present evidence for the genetic and phenotypic diversity of the dystroglycanopathies as a disease group, while also highlighting the advantage of incorporating next-generation sequencing into the diagnostic pathway of rare diseases.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Dystroglycans; Female; Genetic Predisposition to Disease; Genetic Variation; Glycosylation; Heterozygote; Homozygote; Humans; Male; Middle Aged; Muscle Proteins; Muscular Dystrophies, Limb-Girdle; Mutation; Phenotype; Whole Exome Sequencing; Young Adult

Dissecting the Causal Mechanism of X-Linked Dystonia-Parkinsonism by Integrating Genome and Transcriptome Assembly. - Aneichyk, Tatsiana; Hendriks, William T; Yadav, Rachita; Shin, David; Gao, Dadi; Vaine, Christine A; Collins, Ryan L; Domingo, Aloysius; Currall, Benjamin; Stortchevoi, Alexei; Multhaupt-Buell, Trisha; Penney, Ellen B; et al. (Cell, 2018)
X-linked Dystonia-Parkinsonism (XDP) is a Mendelian neurodegenerative disease that is endemic to the Philippines and is associated with a founder haplotype. We integrated multiple genome and transcriptome assembly technologies to narrow the causal mutation to the TAF1 locus, which included a SINE-VNTR-Alu (SVA) retrotransposition into intron 32 of the gene. Transcriptome analyses identified decreased expression of the canonical cTAF1 transcript among XDP probands, and de novo assembly across multiple pluripotent stem-cell-derived neuronal lineages discovered aberrant TAF1 transcription that involved alternative splicing and intron retention (IR) in proximity to the SVA that was anti-correlated with overall TAF1 expression. CRISPR/Cas9 excision of the SVA rescued this XDP-specific transcriptional signature and normalized TAF1 expression in probands. These data suggest an SVA-mediated aberrant transcriptional mechanism associated with XDP and may provide a roadmap for layered technologies and integrated assembly-based analyses for other unsolved Mendelian disorders.
Keywords: Alternative Splicing; Alu Elements; Base Sequence; Cohort Studies; CRISPR-Cas Systems; Dystonic Disorders; Family; Female; Genetic Diseases, X-Linked; Genetic Loci; Genome, Human; Haplotypes; High-Throughput Nucleotide Sequencing; Histone Acetyltransferases; Humans; Induced Pluripotent Stem Cells; Introns; Male; Minisatellite Repeats; Models, Genetic; Nerve Degeneration; Neural Stem Cells; Neurons; RNA, Messenger; Short Interspersed Nucleotide Elements; TATA-Binding Protein Associated Factors; Transcription Factor TFIID; Transcriptome

Enrolling Genomics Research Participants through a Clinical Setting: the Impact of Existing Clinical Relationships on Informed Consent and Expectations for Return of Research Results. - Berrios, Courtney; James, Cynthia A; Raraigh, Karen; Bollinger, Juli; Murray, Brittney; Tichnell, Crystal; Applegate, Carolyn D; Bergner, Amanda L (J Genet Couns, 2018)
Genetic counselors working in a clinical setting may find themselves recruiting, enrolling, and returning results for genomic research, and existing clinical relationships with study participants may impact these research interactions. We present a qualitative study using semi-structured interviews of participants enrolled in a genome sequencing/exome sequencing (GS/ES) study at the same institution where they receive clinical care. Interviews were coded for motivations to participate and expectations of this research. The interviews revealed common motivations for participation, including altruism and hope for benefit for themselves, family members, and/or others with their condition. Additionally, themes emerged related to unintentional influence based on trust of the clinical provider that recruited them to the study. Participant trust in the enrolling provider at times appeared to extend to the study team to decide which research results to return and to do so in an appropriate format. Participants also based expectations for research results return on previous clinical genetic testing experiences, which may or may not be realistic depending on study design. It is imperative that genetic counselors enrolling patients into research studies be aware of the potential influence of their clinical relationship on potential subjects, be transparent about their role on the study team, and help set expectations about the study process, including results return.
Keywords: Base Sequence; Decision Making; Family; Female; Genetic Testing; Humans; Informed Consent; Male; Motivation; Qualitative Research; Research Design; Trust

FUT2 Variants Confer Susceptibility to Familial Otitis Media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Frank, Daniel N; Ryan, Allen F; Giese, Arnaud P J; Bootpetch Roberts, Tori; Daly, Kathleen A; Steritz, Matthew J; Szeremeta, Wasyl; Pedro, Melquiadesa; Pine, Harold; Yarza, Talitha Karisse L; et al. (Am J Hum Genet, 2018)
Non-secretor status due to homozygosity for the common FUT2 variant c.461G>A (p.Trp154) is associated with either risk for autoimmune diseases or protection against viral diarrhea and HIV. We determined the role of FUT2 in otitis media susceptibility by obtaining DNA samples from 609 multi-ethnic families and simplex case subjects with otitis media. Exome and Sanger sequencing, linkage analysis, and Fisher exact and transmission disequilibrium tests (TDT) were performed. The common FUT2 c.604C>T (p.Arg202) variant co-segregates with otitis media in a Filipino pedigree (LOD = 4.0). Additionally, a rare variant, c.412C>T (p.Arg138Cys), is associated with recurrent/chronic otitis media in European-American children (p = 1.2 × 10) and US trios (TDT p = 0.01). The c.461G>A (p.Trp154) variant was also over-transmitted in US trios (TDT p = 0.01) and was associated with shifts in middle ear microbiota composition (PERMANOVA p < 10) and increased biodiversity. When all missense and nonsense variants identified in multi-ethnic US trios with CADD > 20 were combined, FUT2 variants were over-transmitted in trios (TDT p = 0.001). Fut2 is transiently upregulated in mouse middle ear after inoculation with non-typeable Haemophilus influenzae. Four FUT2 variants-namely p.Ala104Val, p.Arg138Cys, p.Trp154, and p.Arg202-reduced A antigen in mutant-transfected COS-7 cells, while the nonsense variants also reduced FUT2 protein levels. Common and rare FUT2 variants confer susceptibility to otitis media, likely by modifying the middle ear microbiome through regulation of A antigen levels in epithelial cells. Our families demonstrate marked intra-familial genetic heterogeneity, suggesting that multiple combinations of common and rare variants plus environmental factors influence the individual otitis media phenotype as a complex trait.

Genetic and mechanistic diversity in pediatric hemophagocytic lymphohistiocytosis. - Chinn, Ivan K; Eckstein, Olive S; Peckham-Gregory, Erin C; Goldberg, Baruch R; Forbes, Lisa R; Nicholas, Sarah K; Mace, Emily M; Vogel, Tiphanie P; Abhyankar, Harshal A; Diaz, Maria I; Heslop, Helen E; Krance, Robert A; et al. (Blood, 2018)
The HLH-2004 criteria are used to diagnose hemophagocytic lymphohistiocytosis (HLH), yet concern exists for their misapplication, resulting in suboptimal treatment of some patients. We sought to define the genomic spectrum and associated outcomes of a diverse cohort of children who met the HLH-2004 criteria. Genetic testing was performed clinically or through research-based whole-exome sequencing. Clinical metrics were analyzed with respect to genomic results. Of 122 subjects enrolled over the course of 17 years, 101 subjects received genetic testing. Biallelic familial HLH (fHLH) gene defects were identified in only 19 (19%) and correlated with presentation at younger than 1 year of age ( < .0001). Digenic fHLH variants were observed but lacked statistical support for disease association. In 28 (58%) of 48 subjects, research whole-exome sequencing analyses successfully identified likely molecular explanations, including underlying primary immunodeficiency diseases, dysregulated immune activation and proliferation disorders, and potentially novel genetic conditions. Two-thirds of patients identified by the HLH-2004 criteria had underlying etiologies for HLH, including genetic defects, autoimmunity, and malignancy. Overall survival was 45%, and increased mortality correlated with HLH triggered by infection or malignancy ( < .05). Differences in survival did not correlate with genetic profile or extent of therapy. HLH should be conceptualized as a phenotype of critical illness characterized by toxic activation of immune cells from different underlying mechanisms. In most patients with HLH, targeted sequencing of fHLH genes remains insufficient for identifying pathogenic mechanisms. Whole-exome sequencing, however, may identify specific therapeutic opportunities and affect hematopoietic stem cell transplantation options for these patients.

Genetic variants in components of the NALCN-UNC80-UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies). - Bramswig, Nuria C; Bertoli-Avella, Aida M; Albrecht, Beate; Al Aqeel, Aida I; Alhashem, Amal; Al-Sannaa, Nouriya; Bah, Maissa; Bröhl, Katharina; Depienne, Christel; Dorison, Nathalie; Doummar, Diane; Ehmke, Nadja; et al. (Hum Genet, 2018)
NALCN is a conserved cation channel, which conducts a permanent sodium leak current and regulates resting membrane potential and neuronal excitability. It is part of a large ion channel complex, the "NALCN channelosome", consisting of multiple proteins including UNC80 and UNC79. The predominant neuronal expression pattern and its function suggest an important role in neuronal function and disease. So far, biallelic NALCN and UNC80 variants have been described in a small number of individuals leading to infantile hypotonia, psychomotor retardation, and characteristic facies 1 (IHPRF1, OMIM 615419) and 2 (IHPRF2, OMIM 616801), respectively. Heterozygous de novo NALCN missense variants in the S5/S6 pore-forming segments lead to congenital contractures of the limbs and face, hypotonia, and developmental delay (CLIFAHDD, OMIM 616266) with some clinical overlap. In this study, we present detailed clinical information of 16 novel individuals with biallelic NALCN variants, 1 individual with a heterozygous de novo NALCN missense variant and an interesting clinical phenotype without contractures, and 12 individuals with biallelic UNC80 variants. We report for the first time a missense NALCN variant located in the predicted S6 pore-forming unit inherited in an autosomal-recessive manner leading to mild IHPRF1. We show evidence of clinical variability, especially among IHPRF1-affected individuals, and discuss differences between the IHPRF1- and IHPRF2 phenotypes. In summary, we provide a comprehensive overview of IHPRF1 and IHPRF2 phenotypes based on the largest cohort of individuals reported so far and provide additional insights into the clinical phenotypes of these neurodevelopmental diseases to help improve counseling of affected families.
Keywords: Adolescent; Adult; Carrier Proteins; Channelopathies; Child; Child, Preschool; Developmental Disabilities; Female; Genetic Markers; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Phenotype; Sodium Channels; Young Adult

Heterozygous Truncating Variants in POMP Escape Nonsense-Mediated Decay and Cause a Unique Immune Dysregulatory Syndrome. - Poli, M Cecilia; Ebstein, Frédéric; Nicholas, Sarah K; de Guzman, Marietta M; Forbes, Lisa R; Chinn, Ivan K; Mace, Emily M; Vogel, Tiphanie P; Carisey, Alexandre F; Benavides, Felipe; Coban-Akdemir, Zeynep H; Gibbs, Richard A; et al. (Am J Hum Genet, 2018)
The proteasome processes proteins to facilitate immune recognition and host defense. When inherently defective, it can lead to aberrant immunity resulting in a dysregulated response that can cause autoimmunity and/or autoinflammation. Biallelic or digenic loss-of-function variants in some of the proteasome subunits have been described as causing a primary immunodeficiency disease that manifests as a severe dysregulatory syndrome: chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE). Proteasome maturation protein (POMP) is a chaperone for proteasome assembly and is critical for the incorporation of catalytic subunits into the proteasome. Here, we characterize and describe POMP-related autoinflammation and immune dysregulation disease (PRAID) discovered in two unrelated individuals with a unique constellation of early-onset combined immunodeficiency, inflammatory neutrophilic dermatosis, and autoimmunity. We also begin to delineate a complex genetic mechanism whereby de novo heterozygous frameshift variants in the penultimate exon of POMP escape nonsense-mediated mRNA decay (NMD) and result in a truncated protein that perturbs proteasome assembly by a dominant-negative mechanism. To our knowledge, this mechanism has not been reported in any primary immunodeficiencies, autoinflammatory syndromes, or autoimmune diseases. Here, we define a unique hypo- and hyper-immune phenotype and report an immune dysregulation syndrome caused by frameshift mutations that escape NMD.
Keywords: Base Sequence; Cell Line; Endoplasmic Reticulum Stress; Exons; Family; Frameshift Mutation; Genetic Predisposition to Disease; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Infant, Newborn; Inflammation; Interferon Type I; Male; Molecular Chaperones; Mutant Proteins; Mutation; Nonsense Mediated mRNA Decay; Phenotype; Proteasome Endopeptidase Complex; RNA, Messenger; Syndrome; Unfolded Protein Response

A homozygous founder mutation in associates with a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features. - Marin-Valencia, Isaac; Novarino, Gaia; Johansen, Anide; Rosti, Basak; Issa, Mahmoud Y; Musaev, Damir; Bhat, Gifty; Scott, Eric; Silhavy, Jennifer L; Stanley, Valentina; Rosti, Rasim O; Gleeson, Jeremy W; et al. (J Med Genet, 2018)
BACKGROUND: Transport protein particle (TRAPP) is a multisubunit complex that regulates membrane trafficking through the Golgi apparatus. The clinical phenotype associated with mutations in various TRAPP subunits has allowed elucidation of their functions in specific tissues. The role of some subunits in human disease, however, has not been fully established, and their functions remain uncertain. OBJECTIVE: We aimed to expand the range of neurodevelopmental disorders associated with mutations in TRAPP subunits by exome sequencing of consanguineous families. METHODS: Linkage and homozygosity mapping and candidate gene analysis were used to identify homozygous mutations in families. Patient fibroblasts were used to study splicing defect and zebrafish to model the disease. RESULTS: We identified six individuals from three unrelated families with a founder homozygous splice mutation in , encoding a core subunit of the complex TRAPP I. Patients manifested a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features, and showed splicing defect. Zebrafish morphants replicated the human phenotype, displaying decreased head size and neuronal hyperexcitability, leading to a lower seizure threshold. CONCLUSION: This study provides clinical and functional evidence of the role of in brain development and function.
Keywords: Animals; Autistic Disorder; Epilepsy; Founder Effect; Genetic Association Studies; Homozygote; Humans; Microcephaly; Mutation; Neurodevelopmental Disorders; Phenotype; Vesicular Transport Proteins; Zebrafish

Identification of a pathogenic PMP2 variant in a multi-generational family with CMT type 1: Clinical gene panels versus genome-wide approaches to molecular diagnosis. - Punetha, Jaya; Mackay-Loder, Loren; Harel, Tamar; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Gibbs, Richard A; Lee, Ian; Terespolsky, Deborah; Lupski, James R; Posey, Jennifer E (Mol Genet Metab, 2018)
Charcot-Marie-Tooth (CMT) disease type 1 is an inherited peripheral neuropathy characterized by demyelination and reduced nerve conduction velocities. We present a multi-generational family with peripheral neuropathy in whom clinical CMT panel testing failed to conclude a molecular diagnosis. We found a PMP2 pathogenic variant c.155T > C, p.(Ile52Thr) that segregates with disease suggesting that PMP2 variants should be considered in patients with neuropathy and that it may be prudent to include in clinical CMT gene panels.

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hülya; Petty, Lauren E; Muzny, Donna M; Below, Jennifer E; Boerwinkle, Eric; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Identifying Genes Whose Mutant Transcripts Cause Dominant Disease Traits by Potential Gain-of-Function Alleles. - Coban-Akdemir, Zeynep; White, Janson J; Song, Xiaofei; Jhangiani, Shalini N; Fatih, Jawid M; Gambin, Tomasz; Bayram, Yavuz; Chinn, Ivan K; Karaca, Ender; Punetha, Jaya; Poli, Cecilia; Boerwinkle, Eric; et al. (Am J Hum Genet, 2018)
Premature termination codon (PTC)-bearing transcripts are often degraded by nonsense-mediated decay (NMD) resulting in loss-of-function (LoF) alleles. However, not all PTCs result in LoF mutations, i.e., some such transcripts escape NMD and are translated to truncated peptide products that result in disease due to gain-of-function (GoF) effects. Since the location of the PTC is a major factor determining transcript fate, we hypothesized that depletion of protein-truncating variants (PTVs) within the gene region predicted to escape NMD in control databases could provide a rank for genic susceptibility for disease through GoF versus LoF. We developed an NMD escape intolerance score to rank genes based on the depletion of PTVs that would render them able to escape NMD using the Atherosclerosis Risk in Communities Study (ARIC) and the Exome Aggregation Consortium (ExAC) control databases, which was further used to screen the Baylor-Center for Mendelian Genomics disease database. This analysis revealed 1,996 genes significantly depleted for PTVs that are predicted to escape from NMD, i.e., PTVesc; further studies provided evidence that revealed a subset as candidate genes underlying Mendelian phenotypes. Importantly, these genes have characteristically low pLI scores, which can cause them to be overlooked as candidates for dominant diseases. Collectively, we demonstrate that this NMD escape intolerance score is an effective and efficient tool for gene discovery in Mendelian diseases due to production of truncated or altered proteins. More importantly, we provide a complementary analytical tool to aid identification of genes associated with dominant traits through a mechanism distinct from LoF.

Loss of tubulin deglutamylase CCP1 causes infantile-onset neurodegeneration. - Shashi, Vandana; Magiera, Maria M; Klein, Dennis; Zaki, Maha; Schoch, Kelly; Rudnik-Schöneborn, Sabine; Norman, Andrew; Lopes Abath Neto, Osorio; Dusl, Marina; Yuan, Xidi; Bartesaghi, Luca; De Marco, Patrizia; et al. (EMBO J, 2018)
A set of glutamylases and deglutamylases controls levels of tubulin polyglutamylation, a prominent post-translational modification of neuronal microtubules. Defective tubulin polyglutamylation was first linked to neurodegeneration in the () mouse, which lacks deglutamylase CCP1, displays massive cerebellar atrophy, and accumulates abnormally glutamylated tubulin in degenerating neurons. We found biallelic rare and damaging variants in the gene encoding CCP1 in 13 individuals with infantile-onset neurodegeneration and confirmed the absence of functional CCP1 along with dysregulated tubulin polyglutamylation. The human disease mainly affected the cerebellum, spinal motor neurons, and peripheral nerves. We also demonstrate previously unrecognized peripheral nerve and spinal motor neuron degeneration in mice, which thus recapitulated key features of the human disease. Our findings link human neurodegeneration to tubulin polyglutamylation, entailing this post-translational modification as a potential target for drug development for neurodegenerative disorders.

matchbox: An open-source tool for patient matching via the Matchmaker Exchange. - Arachchi, Harindra; Wojcik, Monica H; Weisburd, Benjamin; Jacobsen, Julius O B; Valkanas, Elise; Baxter, Samantha; Byrne, Alicia B; O'Donnell-Luria, Anne H; Haendel, Melissa; Smedley, Damian; MacArthur, Daniel G; Philippakis, Anthony A; et al. (Hum Mutat, 2018)
Rare disease investigators constantly face challenges in identifying additional cases to build evidence for gene-disease causality. The Matchmaker Exchange (MME) addresses this limitation by providing a mechanism for matching patients across genomic centers via a federated network. The MME has revolutionized searching for additional cases by making it possible to query across institutional boundaries, so that what was once a laborious and manual process of contacting researchers is now automated and computable. However, while the MME network is beginning to scale, the growth of additional nodes is limited by the lack of easy-to-use solutions that can be implemented by any rare disease database owner, even one without significant software engineering resources. Here, we describe matchbox, which is an open-source, platform-independent, portable bridge between any given rare disease genomic center and the MME network, which has already led to novel gene discoveries. We also describe how matchbox greatly reduces the barrier to participation by overcoming challenges for new databases to join the MME.

Monoallelic Mutations to DNAJB11 Cause Atypical Autosomal-Dominant Polycystic Kidney Disease. - Cornec-Le Gall, Emilie; Olson, Rory J; Besse, Whitney; Heyer, Christina M; Gainullin, Vladimir G; Smith, Jessica M; Audrézet, Marie-Pierre; Hopp, Katharina; Porath, Binu; Shi, Beili; Baheti, Saurabh; Senum, Sarah R; et al. (Am J Hum Genet, 2018)
Autosomal-dominant polycystic kidney disease (ADPKD) is characterized by the progressive development of kidney cysts, often resulting in end-stage renal disease (ESRD). This disorder is genetically heterogeneous with ∼7% of families genetically unresolved. We performed whole-exome sequencing (WES) in two multiplex ADPKD-like pedigrees, and we analyzed a further 591 genetically unresolved, phenotypically similar families by targeted next-generation sequencing of 65 candidate genes. WES identified a DNAJB11 missense variant (p.Pro54Arg) in two family members presenting with non-enlarged polycystic kidneys and a frameshifting change (c.166_167insTT) in a second family with small renal and liver cysts. DNAJB11 is a co-factor of BiP, a key chaperone in the endoplasmic reticulum controlling folding, trafficking, and degradation of secreted and membrane proteins. Five additional multigenerational families carrying DNAJB11 mutations were identified by the targeted analysis. The clinical phenotype was consistent in the 23 affected members, with non-enlarged cystic kidneys that often evolved to kidney atrophy; 7 subjects reached ESRD from 59 to 89 years. The lack of kidney enlargement, histologically evident interstitial fibrosis in non-cystic parenchyma, and recurring episodes of gout (one family) suggested partial phenotypic overlap with autosomal-dominant tubulointerstitial diseases (ADTKD). Characterization of DNAJB11-null cells and kidney samples from affected individuals revealed a pathogenesis associated with maturation and trafficking defects involving the ADPKD protein, PC1, and ADTKD proteins, such as UMOD. DNAJB11-associated disease is a phenotypic hybrid of ADPKD and ADTKD, characterized by normal-sized cystic kidneys and progressive interstitial fibrosis resulting in late-onset ESRD.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Amino Acid Sequence; Base Sequence; Epithelial Cells; Family; Female; HSP40 Heat-Shock Proteins; Humans; Loop of Henle; Male; Middle Aged; Mutation; Pedigree; Polycystic Kidney, Autosomal Dominant; TRPP Cation Channels; Uromodulin; Whole Exome Sequencing; Young Adult

Mutation in the intracellular chloride channel CLCC1 associated with autosomal recessive retinitis pigmentosa. - Li, Lin; Jiao, Xiaodong; D'Atri, Ilaria; Ono, Fumihito; Nelson, Ralph; Chan, Chi-Chao; Nakaya, Naoki; Ma, Zhiwei; Ma, Yan; Cai, Xiaoying; Zhang, Longhua; Lin, Siying; et al. (PLoS Genet, 2018)
We identified a homozygous missense alteration (c.75C>A, p.D25E) in CLCC1, encoding a presumptive intracellular chloride channel highly expressed in the retina, associated with autosomal recessive retinitis pigmentosa (arRP) in eight consanguineous families of Pakistani descent. The p.D25E alteration decreased CLCC1 channel function accompanied by accumulation of mutant protein in granules within the ER lumen, while siRNA knockdown of CLCC1 mRNA induced apoptosis in cultured ARPE-19 cells. TALEN KO in zebrafish was lethal 11 days post fertilization. The depressed electroretinogram (ERG) cone response and cone spectral sensitivity of 5 dpf KO zebrafish and reduced eye size, retinal thickness, and expression of rod and cone opsins could be rescued by injection of wild type CLCC1 mRNA. Clcc1+/- KO mice showed decreased ERGs and photoreceptor number. Together these results strongly suggest that intracellular chloride transport by CLCC1 is a critical process in maintaining retinal integrity, and CLCC1 is crucial for survival and function of retinal cells.
Keywords: Animals; Asian Continental Ancestry Group; Cell Line; Chloride Channels; Cytoplasm; Eye Proteins; HEK293 Cells; Homozygote; Humans; Mice; Mice, Knockout; Mutation, Missense; Pakistan; Retina; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Zebrafish

Mutations in LNPK, Encoding the Endoplasmic Reticulum Junction Stabilizer Lunapark, Cause a Recessive Neurodevelopmental Syndrome. - Breuss, Martin W; Nguyen, An; Song, Qiong; Nguyen, Thai; Stanley, Valentina; James, Kiely N; Musaev, Damir; Chai, Guoliang; Wirth, Sara A; Anzenberg, Paula; George, Renee D; Johansen, Anide; et al. (Am J Hum Genet, 2018)
The dynamic shape of the endoplasmic reticulum (ER) is a reflection of its wide variety of critical cell biological functions. Consequently, perturbation of ER-shaping proteins can cause a range of human phenotypes. Here, we describe three affected children (from two consanguineous families) who carry homozygous loss-of-function mutations in LNPK (previously known as KIAA1715); this gene encodes lunapark, which is proposed to serve as a curvature-stabilizing protein within tubular three-way junctions of the ER. All individuals presented with severe psychomotor delay, intellectual disability, hypotonia, epilepsy, and corpus callosum hypoplasia, and two of three showed mild cerebellar hypoplasia and atrophy. Consistent with a proposed role in neurodevelopmental disease, LNPK was expressed during brain development in humans and mice and was present in neurite-like processes in differentiating human neural progenitor cells. Affected cells showed the absence of full-length lunapark, aberrant ER structures, and increased luminal mass density. Together, our results implicate the ER junction stabilizer lunapark in establishing the corpus callosum.

Mutations in multiple components of the nuclear pore complex cause nephrotic syndrome. - Braun, Daniela A; Lovric, Svjetlana; Schapiro, David; Schneider, Ronen; Marquez, Jonathan; Asif, Maria; Hussain, Muhammad Sajid; Daga, Ankana; Widmeier, Eugen; Rao, Jia; Ashraf, Shazia; Tan, Weizhen; et al. (J Clin Invest, 2018)
Steroid-resistant nephrotic syndrome (SRNS) almost invariably progresses to end-stage renal disease. Although more than 50 monogenic causes of SRNS have been described, a large proportion of SRNS remains unexplained. Recently, it was discovered that mutations of NUP93 and NUP205, encoding 2 proteins of the inner ring subunit of the nuclear pore complex (NPC), cause SRNS. Here, we describe mutations in genes encoding 4 components of the outer rings of the NPC, namely NUP107, NUP85, NUP133, and NUP160, in 13 families with SRNS. Using coimmunoprecipitation experiments, we showed that certain pathogenic alleles weakened the interaction between neighboring NPC subunits. We demonstrated that morpholino knockdown of nup107, nup85, or nup133 in Xenopus disrupted glomerulogenesis. Re-expression of WT mRNA, but not of mRNA reflecting mutations from SRNS patients, mitigated this phenotype. We furthermore found that CRISPR/Cas9 knockout of NUP107, NUP85, or NUP133 in podocytes activated Cdc42, an important effector of SRNS pathogenesis. CRISPR/Cas9 knockout of nup107 or nup85 in zebrafish caused developmental anomalies and early lethality. In contrast, an in-frame mutation of nup107 did not affect survival, thus mimicking the allelic effects seen in humans. In conclusion, we discovered here that mutations in 4 genes encoding components of the outer ring subunits of the NPC cause SRNS and thereby provide further evidence that specific hypomorphic mutations in these essential genes cause a distinct, organ-specific phenotype.

Mutations in PI3K110δ cause impaired natural killer cell function partially rescued by rapamycin treatment. - Ruiz-García, Raquel; Vargas-Hernandez, Alexander; Chinn, Ivan K; Angelo, Laura S; Cao, Tram N; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Meng, Qingchang; Forbes, Lisa R; Muzny, Donna M; Allende, Luis M; Ehlayel, Mohammed S; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Heterozygous gain-of-function mutations in PI3K110δ lead to lymphadenopathy, lymphoid hyperplasia, EBV and cytomegalovirus viremia, and sinopulmonary infections. OBJECTIVE: The known role of natural killer (NK) cell function in the control of EBV and cytomegalovirus prompted us to investigate the functional and phenotypic effects of PI3K110δ mutations on NK cell subsets and cytotoxic function. METHODS: Mutations in patients were identified by using whole-exome or targeted sequencing. We performed NK cell phenotyping and functional analysis of patients' cells using flow cytometry, standard Cr cytotoxicity assays, and quantitative confocal microscopy. RESULTS: PI3K110δ mutations led to an altered NK cell developmental phenotype and cytotoxic dysfunction. Impaired NK cell cytotoxicity was due to decreased conjugate formation with susceptible target cells and abrogated activation of cell machinery required for target cell killing. These defects were restored partially after initiation of treatment with rapamycin in 3 patients. CONCLUSION: We describe novel NK cell functional deficiency caused by PI3K110δ mutation, which is a likely contributor to the severe viremia observed in these patients. Rapamycin treatment partially restores NK cell function, providing a further rationale for its use in patients with this disease.

Mutations in the mitochondrial ribosomal protein MRPS22 lead to primary ovarian insufficiency. - Chen, Anlu; Tiosano, Dov; Guran, Tulay; Baris, Hagit N; Bayram, Yavuz; Mory, Adi; Shapiro-Kulnane, Laura; Hodges, Craig A; Akdemir, Zeynep C; Turan, Serap; Jhangiani, Shalini N; van den Akker, Focco; et al. (Hum Mol Genet, 2018)
Primary ovarian insufficiency (POI) is characterized by amenorrhea and loss or dysfunction of ovarian follicles prior to the age of 40. POI has been associated with autosomal recessive mutations in genes involving hormonal signaling and folliculogenesis, however, the genetic etiology of POI most often remains unknown. Here we report MRPS22 homozygous missense variants c.404G>A (p.R135Q) and c.605G>A (p.R202H) identified in four females from two independent consanguineous families as a novel genetic cause of POI in adolescents. Both missense mutations identified in MRPS22 are rare, occurred in highly evolutionarily conserved residues, and are predicted to be deleterious to protein function. In contrast to prior reports of mutations in MRPS22 associated with severe mitochondrial disease, the POI phenotype is far less severe. Consistent with this genotype-phenotype correlation, mitochondrial defects in oxidative phosphorylation or rRNA levels were not detected in fibroblasts derived from the POI patients, suggesting a non-bioenergetic or tissue-specific mitochondrial defect. Furthermore, we demonstrate in a Drosophila model that mRpS22 deficiency specifically in somatic cells of the ovary had no effect on fertility, whereas flies with mRpS22 deficiency specifically in germ cells were infertile and agametic, demonstrating a cell autonomous requirement for mRpS22 in germ cell development. These findings collectively identify that MRPS22, a component of the small mitochondrial ribosome subunit, is critical for ovarian development and may therefore provide insight into the pathophysiology and treatment of ovarian dysfunction.
Keywords: Adolescent; Adult; Amenorrhea; Animals; Disease Models, Animal; Drosophila; Drosophila Proteins; Female; Fertility; Homozygote; Humans; Menopause, Premature; Mitochondrial Proteins; Mutation, Missense; Ovarian Follicle; Primary Ovarian Insufficiency; Ribosomal Proteins; Young Adult

Mutations in WDR4 as a new cause of Galloway-Mowat syndrome. - Braun, Daniela A; Shril, Shirlee; Sinha, Aditi; Schneider, Ronen; Tan, Weizhen; Ashraf, Shazia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J; Daga, Ankana; Warejko, Jillian K; et al. (Am J Med Genet A, 2018)
Galloway-Mowat syndrome (GAMOS) is a phenotypically heterogeneous disorder characterized by neurodevelopmental defects combined with renal-glomerular disease, manifesting with proteinuria. To identify additional monogenic disease causes, we here performed whole exome sequencing (WES), linkage analysis, and homozygosity mapping in three affected siblings of an Indian family with GAMOS. Applying established criteria for variant filtering, we identify a novel homozygous splice site mutation in the gene WDR4 as the likely disease-causing mutation in this family. In line with previous reports, we observe growth deficiency, microcephaly, developmental delay, and intellectual disability as phenotypic features resulting from WDR4 mutations. However, the newly identified allele additionally gives rise to proteinuria and nephrotic syndrome, a phenotype that was never reported in patients with WDR4 mutations. Our data thus expand the phenotypic spectrum of WDR4 mutations by demonstrating that, depending on the specific mutated allele, a renal phenotype may be present. This finding suggests that GAMOS may occupy a phenotypic spectrum with other microcephalic diseases. Furthermore, WDR4 is an additional example of a gene that encodes a tRNA modifying enzyme and gives rise to GAMOS, if mutated. Our findings thereby support the recent observation that, like neurons, podocytes of the renal glomerulus are particularly vulnerable to cellular defects resulting from altered tRNA modifications.

Nemaline myopathy and distal arthrogryposis associated with an autosomal recessive TNNT3 splice variant. - Sandaradura, Sarah A; Bournazos, Adam; Mallawaarachchi, Amali; Cummings, Beryl B; Waddell, Leigh B; Jones, Kristi J; Troedson, Christopher; Sudarsanam, Annapurna; Nash, Benjamin M; Peters, Gregory B; Algar, Elizabeth M; MacArthur, Daniel G; et al. (Hum Mutat, 2018)
A male neonate presented with severe weakness, hypotonia, contractures and congenital scoliosis. Skeletal muscle specimens showed marked atrophy and degeneration of fast fibers with striking nemaline rods and hypertrophy of slow fibers that were ultrastructurally normal. A neuromuscular gene panel identified a homozygous essential splice variant in TNNT3 (chr11:1956150G > A, NM_006757.3:c.681+1G > A). TNNT3 encodes skeletal troponin-T and is associated with autosomal dominant distal arthrogryposis. TNNT3 has not previously been associated with nemaline myopathy (NM), a rare congenital myopathy linked to defects in proteins associated with thin filament structure and regulation. cDNA studies confirmed pathogenic consequences of the splice variant, eliciting exon-skipping and intron retention events leading to a frameshift. Western blot showed deficiency of troponin-T protein with secondary loss of troponin-I . We establish a homozygous splice variant in TNNT3 as the likely cause of severe congenital NM with distal arthrogryposis, characterized by specific involvement of Type-2 fibers and deficiency of troponin-T .
Keywords: Arthrogryposis; Genes, Recessive; Humans; Infant; Infant, Newborn; Male; Myopathies, Nemaline; RNA Splice Sites; RNA Splicing; RNA, Messenger; Troponin T

A novel NAA10 variant with impaired acetyltransferase activity causes developmental delay, intellectual disability, and hypertrophic cardiomyopathy. - Støve, Svein Isungset; Blenski, Marina; Stray-Pedersen, Asbjørg; Wierenga, Klaas J; Jhangiani, Shalini N; Akdemir, Zeynep Coban; Crawford, David; McTiernan, Nina; Myklebust, Line M; Purcarin, Gabriela; McNall-Knapp, Rene; Wadley, Alexandrea; et al. (Eur J Hum Genet, 2018)
The NAA10-NAA15 complex (NatA) is an N-terminal acetyltransferase that catalyzes N-terminal acetylation of ~40% of all human proteins. N-terminal acetylation has several different roles in the cell, including altering protein stability and degradation, protein localization and protein-protein interactions. In recent years several X-linked NAA10 variants have been associated with genetic disorders. We have identified a previously undescribed NAA10 c.215T>C p.(Ile72Thr) variant in three boys from two unrelated families with a milder phenotypic spectrum in comparison to most of the previously described patients with NAA10 variants. These boys have development delay, intellectual disability, and cardiac abnormalities as overlapping phenotypes. Functional studies reveal that NAA10 Ile72Thr is destabilized, while binding to NAA15 most likely is intact. Surprisingly, the NatA activity of NAA10 Ile72Thr appears normal while its monomeric activity is decreased. This study further broadens the phenotypic spectrum associated with NAA10 deficiency, and adds to the evidence that genotype-phenotype correlations for NAA10 variants are much more complex than initially anticipated.
Keywords: Cardiomyopathy, Hypertrophic; Child, Preschool; Developmental Disabilities; Enzyme Stability; HeLa Cells; Humans; Infant; Intellectual Disability; Male; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Phenotype; Protein Binding; Syndrome

Novel STAT1 Gain-of-Function Mutation Presenting as Combined Immunodeficiency. - Hartono, Stella P; Vargas-Hernandez, Alexander; Ponsford, Mark J; Chinn, Ivan K; Jolles, Stephen; Wilson, Keith; Forbes, Lisa R (J Clin Immunol, 2018)

Phenotypic expansion illuminates multilocus pathogenic variation. - Karaca, Ender; Posey, Jennifer E; Coban Akdemir, Zeynep; Pehlivan, Davut; Harel, Tamar; Jhangiani, Shalini N; Bayram, Yavuz; Song, Xiaofei; Bahrambeigi, Vahid; Yuregir, Ozge Ozalp; Bozdogan, Sevcan; Yesil, Gözde; et al. (Genet Med, 2018)
PURPOSE: Multilocus variation-pathogenic variants in two or more disease genes-can potentially explain the underlying genetic basis for apparent phenotypic expansion in cases for which the observed clinical features extend beyond those reported in association with a "known" disease gene. METHODS: Analyses focused on 106 patients, 19 for whom apparent phenotypic expansion was previously attributed to variation at known disease genes. We performed a retrospective computational reanalysis of whole-exome sequencing data using stringent Variant Call File filtering criteria to determine whether molecular diagnoses involving additional disease loci might explain the observed expanded phenotypes. RESULTS: Multilocus variation was identified in 31.6% (6/19) of families with phenotypic expansion and 2.3% (2/87) without phenotypic expansion. Intrafamilial clinical variability within two families was explained by multilocus variation identified in the more severely affected sibling. CONCLUSION: Our findings underscore the role of multiple rare variants at different loci in the etiology of genetically and clinically heterogeneous cohorts. Intrafamilial phenotypic and genotypic variability allowed a dissection of genotype-phenotype relationships in two families. Our data emphasize the critical role of the clinician in diagnostic genomic analyses and demonstrate that apparent phenotypic expansion may represent blended phenotypes resulting from pathogenic variation at more than one locus.

Phenotypic expansion in - a common cause of intellectual disability in females. - Wang, Xia; Posey, Jennifer E; Rosenfeld, Jill A; Bacino, Carlos A; Scaglia, Fernando; Immken, LaDonna; Harris, Jill M; Hickey, Scott E; Mosher, Theresa M; Slavotinek, Anne; Zhang, Jing; Beuten, Joke; et al. (Ann Clin Transl Neurol, 2018)
De variants in account for 1-3% of unexplained intellectual disability (ID) cases and are amongst the most common causes of ID especially in females. Forty-seven patients (44 females, 3 males) have been described. We identified 31 additional individuals carrying 29 unique variants, including 30 postnatal individuals with complex clinical presentations of developmental delay or ID, and one fetus with abnormal ultrasound findings. Rare or novel phenotypes observed include respiratory problems, congenital heart disease, skeletal muscle mitochondrial DNA depletion, and late-onset neurologic decline. Our findings expand the spectrum of DNA variants and phenotypes associated with disorders.

The phenotypic spectrum of Xia-Gibbs syndrome. - Jiang, Yunyun; Wangler, Michael F; McGuire, Amy L; Lupski, James R; Posey, Jennifer E; Khayat, Michael M; Murdock, David R; Sanchez-Pulido, Luis; Ponting, Chris P; Xia, Fan; Hunter, Jill V; Meng, Qingchang; et al. (Am J Med Genet A, 2018)
Xia-Gibbs syndrome (XGS: OMIM # 615829) results from de novo truncating mutations within the AT-Hook DNA Binding Motif Containing 1 gene (AHDC1). To further define the phenotypic and molecular spectrum of this disorder, we established an XGS Registry and recruited patients from a worldwide pool of approximately 60 probands. Additional de novo truncating mutations were observed among 25 individuals, extending both the known number of mutation sites and the range of positions within the coding region that were sensitive to alteration. Detailed phenotypic examination of 20 of these patients via clinical records review and data collection from additional surveys showed a wider age range than previously described. Data from developmental milestones showed evidence for delayed speech and that males were more severely affected. Neuroimaging from six available patients showed an associated thinning of the corpus callosum and posterior fossa cysts. An increased risk of both scoliosis and seizures relative to the population burden was also observed. Data from a modified autism screening tool revealed that XGS shares significant overlap with autism spectrum disorders. These details of the phenotypic heterogeneity of XGS implicate specific genotype/phenotype correlations and suggest potential clinical management guidelines.

Plain-language medical vocabulary for precision diagnosis. - Vasilevsky, Nicole A; Foster, Erin D; Engelstad, Mark E; Carmody, Leigh; Might, Matt; Chambers, Chip; Dawkins, Hugh J S; Lewis, Janine; Della Rocca, Maria G; Snyder, Michelle; Boerkoel, Cornelius F; Rath, Ana; et al. (Nat Genet, 2018)

Prioritization of Candidate Genes for Congenital Diaphragmatic Hernia in a Critical Region on Chromosome 4p16 using a Machine-Learning Algorithm. - Callaway, Danielle A; Campbell, Ian M; Stover, Samantha R; Hernandez-Garcia, Andres; Jhangiani, Shalini N; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Muzny, Donna; Lally, Kevin P; Lupski, James R; Shaw, Chad A; et al. (J Pediatr Genet, 2018)
Wolf-Hirschhorn syndrome (WHS) is caused by partial deletion of the short arm of chromosome 4 and is characterized by dysmorphic facies, congenital heart defects, intellectual/developmental disability, and increased risk for congenital diaphragmatic hernia (CDH). In this report, we describe a stillborn girl with WHS and a large CDH. A literature review revealed 15 cases of WHS with CDH, which overlap a 2.3-Mb CDH critical region. We applied a machine-learning algorithm that integrates large-scale genomic knowledge to genes within the 4p16.3 CDH critical region and identified , , , , , , , and as genes whose haploinsufficiency may contribute to the development of CDH.

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

SYT1-associated neurodevelopmental disorder: a case series. - Baker, Kate; Gordon, Sarah L; Melland, Holly; Bumbak, Fabian; Scott, Daniel J; Jiang, Tess J; Owen, David; Turner, Bradley J; Boyd, Stewart G; Rossi, Mari; Al-Raqad, Mohammed; Elpeleg, Orly; et al. (Brain, 2018)
Synaptotagmin 1 (SYT1) is a critical mediator of fast, synchronous, calcium-dependent neurotransmitter release and also modulates synaptic vesicle endocytosis. This paper describes 11 patients with de novo heterozygous missense mutations in SYT1. All mutations alter highly conserved residues, and cluster in two regions of the SYT1 C2B domain at positions Met303 (M303K), Asp304 (D304G), Asp366 (D366E), Ile368 (I368T) and Asn371 (N371K). Phenotypic features include infantile hypotonia, congenital ophthalmic abnormalities, childhood-onset hyperkinetic movement disorders, motor stereotypies, and developmental delay varying in severity from moderate to profound. Behavioural characteristics include sleep disturbance and episodic agitation. Absence of epileptic seizures and normal orbitofrontal head circumference are important negative features. Structural MRI is unremarkable but EEG disturbance is universal, characterized by intermittent low frequency high amplitude oscillations. The functional impact of these five de novo SYT1 mutations has been assessed by expressing rat SYT1 protein containing the equivalent human variants in wild-type mouse primary hippocampal cultures. All mutant forms of SYT1 were expressed at levels approximately equal to endogenous wild-type protein, and correctly localized to nerve terminals at rest, except for SYT1M303K, which was expressed at a lower level and failed to localize at nerve terminals. Following stimulation, SYT1I368T and SYT1N371K relocalized to nerve terminals at least as efficiently as wild-type SYT1. However, SYT1D304G and SYT1D366E failed to relocalize to nerve terminals following stimulation, indicative of impairments in endocytic retrieval and trafficking of SYT1. In addition, the presence of SYT1 variants at nerve terminals induced a slowing of exocytic rate following sustained action potential stimulation. The extent of disturbance to synaptic vesicle kinetics is mirrored by the severity of the affected individuals' phenotypes, suggesting that the efficiency of SYT1-mediated neurotransmitter release is critical to cognitive development. In summary, de novo dominant SYT1 missense mutations are associated with a recognizable neurodevelopmental syndrome, and further cases can now be diagnosed based on clinical features, electrophysiological signature and mutation characteristics. Variation in phenotype severity may reflect mutation-specific impact on the diverse physiological functions of SYT1.

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

Tuberculosis and impaired IL-23-dependent IFN-γ immunity in humans homozygous for a common missense variant. - Boisson-Dupuis, Stéphanie; Ramirez-Alejo, Noe; Li, Zhi; Patin, Etienne; Rao, Geetha; Kerner, Gaspard; Lim, Che Kang; Krementsov, Dimitry N; Hernandez, Nicholas; Ma, Cindy S; Zhang, Qian; Markle, Janet; et al. (Sci Immunol, 2018)
Inherited IL-12Rβ1 and TYK2 deficiencies impair both IL-12- and IL-23-dependent IFN-γ immunity and are rare monogenic causes of tuberculosis, each found in less than 1/600,000 individuals. We show that homozygosity for the common P1104A allele, which is found in about 1/600 Europeans and between 1/1000 and 1/10,000 individuals in regions other than East Asia, is more frequent in a cohort of patients with tuberculosis from endemic areas than in ethnicity-adjusted controls ( = 8.37 × 10; odds ratio, 89.31; 95% CI, 14.7 to 1725). Moreover, the frequency of P1104A in Europeans has decreased, from about 9% to 4.2%, over the past 4000 years, consistent with purging of this variant by endemic tuberculosis. Surprisingly, we also show that TYK2 P1104A impairs cellular responses to IL-23, but not to IFN-α, IL-10, or even IL-12, which, like IL-23, induces IFN-γ via activation of TYK2 and JAK2. Moreover, TYK2 P1104A is properly docked on cytokine receptors and can be phosphorylated by the proximal JAK, but lacks catalytic activity. Last, we show that the catalytic activity of TYK2 is essential for IL-23, but not IL-12, responses in cells expressing wild-type JAK2. In contrast, the catalytic activity of JAK2 is redundant for both IL-12 and IL-23 responses, because the catalytically inactive P1057A JAK2, which is also docked and phosphorylated, rescues signaling in cells expressing wild-type TYK2. In conclusion, homozygosity for the catalytically inactive P1104A missense variant of selectively disrupts the induction of IFN-γ by IL-23 and is a common monogenic etiology of tuberculosis.

A variant in LMX1A causes autosomal recessive severe-to-profound hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Liaqat, Khurram; Jan, Abid; Nasir, Abdul; Hussain, Shabir; Nickerson, Deborah A; Bamshad, Michael J; Ullah, Asmat; Ahmad, Wasim; Leal, Suzanne M (Hum Genet, 2018)
Hereditary hearing impairment is a common sensory disorder that is genetically and phenotypically heterogeneous. In this study, we used a homozygosity mapping and exome sequencing strategy to study a consanguineous Pakistani family with autosomal recessive severe-to-profound hearing impairment. This led to the identification of a missense variant (p.Ile369Thr) in the LMX1A gene affecting a conserved residue in the C-terminus of the protein, which was predicted damaging by an in silico bioinformatics analysis. The p.Ile369Thr variant disrupts several C-terminal and homeodomain residue interactions, including an interaction with homeodomain residue p.Val241 that was previously found to be involved in autosomal dominant progressive HI. LIM-homeodomain factor Lmx1a is expressed in the inner ear through development, shows a progressive restriction to non-sensory epithelia, and is important in the separation of the sensory and non-sensory domains in the inner ear. Homozygous Lmx1a mutant mice (Dreher) are deaf with dysmorphic ears with an abnormal morphogenesis and fused and misshapen sensory organs; however, computed tomography performed on a hearing-impaired family member did not reveal any cochleovestibular malformations. Our results suggest that LMX1A is involved in both human autosomal recessive and dominant sensorineural hearing impairment.
Keywords: Adolescent; Adult; Animals; Child; Disease Models, Animal; Ear, Inner; Female; Genes, Dominant; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; LIM-Homeodomain Proteins; Male; Mice; Mutation, Missense; Pedigree; Transcription Factors; Whole Exome Sequencing

Whole exome sequencing frequently detects a monogenic cause in early onset nephrolithiasis and nephrocalcinosis. - Daga, Ankana; Majmundar, Amar J; Braun, Daniela A; Gee, Heon Yung; Lawson, Jennifer A; Shril, Shirlee; Jobst-Schwan, Tilman; Vivante, Asaf; Schapiro, David; Tan, Weizhen; Warejko, Jillian K; Widmeier, Eugen; et al. (Kidney Int, 2018)
The incidence of nephrolithiasis continues to rise. Previously, we showed that a monogenic cause could be detected in 11.4% of individuals with adult-onset nephrolithiasis or nephrocalcinosis and in 16.7-20.8% of individuals with onset before 18 years of age, using gene panel sequencing of 30 genes known to cause nephrolithiasis/nephrocalcinosis. To overcome the limitations of panel sequencing, we utilized whole exome sequencing in 51 families, who presented before age 25 years with at least one renal stone or with a renal ultrasound finding of nephrocalcinosis to identify the underlying molecular genetic cause of disease. In 15 of 51 families, we detected a monogenic causative mutation by whole exome sequencing. A mutation in seven recessive genes (AGXT, ATP6V1B1, CLDN16, CLDN19, GRHPR, SLC3A1, SLC12A1), in one dominant gene (SLC9A3R1), and in one gene (SLC34A1) with both recessive and dominant inheritance was detected. Seven of the 19 different mutations were not previously described as disease-causing. In one family, a causative mutation in one of 117 genes that may represent phenocopies of nephrolithiasis-causing genes was detected. In nine of 15 families, the genetic diagnosis may have specific implications for stone management and prevention. Several factors that correlated with the higher detection rate in our cohort were younger age at onset of nephrolithiasis/nephrocalcinosis, presence of multiple affected members in a family, and presence of consanguinity. Thus, we established whole exome sequencing as an efficient approach toward a molecular genetic diagnosis in individuals with nephrolithiasis/nephrocalcinosis who manifest before age 25 years.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Disease Progression; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Heredity; Humans; Infant; Male; Mutation; Nephrocalcinosis; Nephrolithiasis; Pedigree; Phenotype; Predictive Value of Tests; Prognosis; Risk Factors; Tomography, X-Ray Computed; Ultrasonography; Whole Exome Sequencing; Young Adult

Whole Exome Sequencing of Patients with Steroid-Resistant Nephrotic Syndrome. - Warejko, Jillian K; Tan, Weizhen; Daga, Ankana; Schapiro, David; Lawson, Jennifer A; Shril, Shirlee; Lovric, Svjetlana; Ashraf, Shazia; Rao, Jia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; et al. (Clin J Am Soc Nephrol, 2018)
BACKGROUND AND OBJECTIVES: Steroid-resistant nephrotic syndrome overwhelmingly progresses to ESRD. More than 30 monogenic genes have been identified to cause steroid-resistant nephrotic syndrome. We previously detected causative mutations using targeted panel sequencing in 30% of patients with steroid-resistant nephrotic syndrome. Panel sequencing has a number of limitations when compared with whole exome sequencing. We employed whole exome sequencing to detect monogenic causes of steroid-resistant nephrotic syndrome in an international cohort of 300 families. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Three hundred thirty-five individuals with steroid-resistant nephrotic syndrome from 300 families were recruited from April of 1998 to June of 2016. Age of onset was restricted to <25 years of age. Exome data were evaluated for 33 known monogenic steroid-resistant nephrotic syndrome genes. RESULTS: In 74 of 300 families (25%), we identified a causative mutation in one of 20 genes known to cause steroid-resistant nephrotic syndrome. In 11 families (3.7%), we detected a mutation in a gene that causes a phenocopy of steroid-resistant nephrotic syndrome. This is consistent with our previously published identification of mutations using a panel approach. We detected a causative mutation in a known steroid-resistant nephrotic syndrome gene in 38% of consanguineous families and in 13% of nonconsanguineous families, and 48% of children with congenital nephrotic syndrome. A total of 68 different mutations were detected in 20 of 33 steroid-resistant nephrotic syndrome genes. Fifteen of these mutations were novel. , , , and were the most common genes in which we detected a mutation. In another 28% of families, we detected mutations in one or more candidate genes for steroid-resistant nephrotic syndrome. CONCLUSIONS: Whole exome sequencing is a sensitive approach toward diagnosis of monogenic causes of steroid-resistant nephrotic syndrome. A molecular genetic diagnosis of steroid-resistant nephrotic syndrome may have important consequences for the management of treatment and kidney transplantation in steroid-resistant nephrotic syndrome.

Whole-Exome Sequencing Identifies Causative Mutations in Families with Congenital Anomalies of the Kidney and Urinary Tract. - van der Ven, Amelie T; Connaughton, Dervla M; Ityel, Hadas; Mann, Nina; Nakayama, Makiko; Chen, Jing; Vivante, Asaf; Hwang, Daw-Yang; Schulz, Julian; Braun, Daniela A; Schmidt, Johanna Magdalena; Schapiro, David; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most prevalent cause of kidney disease in the first three decades of life. Previous gene panel studies showed monogenic causation in up to 12% of patients with CAKUT. METHODS: We applied whole-exome sequencing to analyze the genotypes of individuals from 232 families with CAKUT, evaluating for mutations in single genes known to cause human CAKUT and genes known to cause CAKUT in mice. In consanguineous or multiplex families, we additionally performed a search for novel monogenic causes of CAKUT. RESULTS: In 29 families (13%), we detected a causative mutation in a known gene for isolated or syndromic CAKUT that sufficiently explained the patient's CAKUT phenotype. In three families (1%), we detected a mutation in a gene reported to cause a phenocopy of CAKUT. In 15 of 155 families with isolated CAKUT, we detected deleterious mutations in syndromic CAKUT genes. Our additional search for novel monogenic causes of CAKUT in consanguineous and multiplex families revealed a potential single, novel monogenic CAKUT gene in 19 of 232 families (8%). CONCLUSIONS: We identified monogenic mutations in a known human CAKUT gene or CAKUT phenocopy gene as the cause of disease in 14% of the CAKUT families in this study. Whole-exome sequencing provides an etiologic diagnosis in a high fraction of patients with CAKUT and will provide a new basis for the mechanistic understanding of CAKUT.

Whole-Exome Sequencing Identifies Novel Variants for Tooth Agenesis. - Dinckan, N; Du, R; Petty, L E; Coban-Akdemir, Z; Jhangiani, S N; Paine, I; Baugh, E H; Erdem, A P; Kayserili, H; Doddapaneni, H; Hu, J; Muzny, D M; et al. (J Dent Res, 2018)
Tooth agenesis is a common craniofacial abnormality in humans and represents failure to develop 1 or more permanent teeth. Tooth agenesis is complex, and variations in about a dozen genes have been reported as contributing to the etiology. Here, we combined whole-exome sequencing, array-based genotyping, and linkage analysis to identify putative pathogenic variants in candidate disease genes for tooth agenesis in 10 multiplex Turkish families. Novel homozygous and heterozygous variants in LRP6, DKK1, LAMA3, and COL17A1 genes, as well as known variants in WNT10A, were identified as likely pathogenic in isolated tooth agenesis. Novel variants in KREMEN1 were identified as likely pathogenic in 2 families with suspected syndromic tooth agenesis. Variants in more than 1 gene were identified segregating with tooth agenesis in 2 families, suggesting oligogenic inheritance. Structural modeling of missense variants suggests deleterious effects to the encoded proteins. Functional analysis of an indel variant (c.3607+3_6del) in LRP6 suggested that the predicted resulting mRNA is subject to nonsense-mediated decay. Our results support a major role for WNT pathways genes in the etiology of tooth agenesis while revealing new candidate genes. Moreover, oligogenic cosegregation was suggestive for complex inheritance and potentially complex gene product interactions during development, contributing to improved understanding of the genetic etiology of familial tooth agenesis.
Keywords: Anodontia; Female; Genetic Linkage; Genetic Variation; Humans; Intercellular Signaling Peptides and Proteins; Laminin; Low Density Lipoprotein Receptor-Related Protein-6; Male; Membrane Proteins; Mutation, Missense; Pedigree; Real-Time Polymerase Chain Reaction; Turkey; Whole Exome Sequencing; Wnt Proteins

WNT Signaling Perturbations Underlie the Genetic Heterogeneity of Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Coban-Akdemir, Zeynep; Bayram, Yavuz; Bahrambeigi, Vahid; Hoischen, Alexander; van Bon, Bregje W M; Gezdirici, Alper; Gulec, Elif Yilmaz; Ramond, Francis; Touraine, Renaud; Thevenon, Julien; et al. (Am J Hum Genet, 2018)
Locus heterogeneity characterizes a variety of skeletal dysplasias often due to interacting or overlapping signaling pathways. Robinow syndrome is a skeletal disorder historically refractory to molecular diagnosis, potentially stemming from substantial genetic heterogeneity. All current known pathogenic variants reside in genes within the noncanonical Wnt signaling pathway including ROR2, WNT5A, and more recently, DVL1 and DVL3. However, ∼70% of autosomal-dominant Robinow syndrome cases remain molecularly unsolved. To investigate this missing heritability, we recruited 21 families with at least one family member clinically diagnosed with Robinow or Robinow-like phenotypes and performed genetic and genomic studies. In total, four families with variants in FZD2 were identified as well as three individuals from two families with biallelic variants in NXN that co-segregate with the phenotype. Importantly, both FZD2 and NXN are relevant protein partners in the WNT5A interactome, supporting their role in skeletal development. In addition to confirming that clustered -1 frameshifting variants in DVL1 and DVL3 are the main contributors to dominant Robinow syndrome, we also found likely pathogenic variants in candidate genes GPC4 and RAC3, both linked to the Wnt signaling pathway. These data support an initial hypothesis that Robinow syndrome results from perturbation of the Wnt/PCP pathway, suggest specific relevant domains of the proteins involved, and reveal key contributors in this signaling cascade during human embryonic development. Contrary to the view that non-allelic genetic heterogeneity hampers gene discovery, this study demonstrates the utility of rare disease genomic studies to parse gene function in human developmental pathways.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Chromosome Segregation; Craniofacial Abnormalities; Diagnosis, Differential; Dwarfism; Female; Genes, Dominant; Genetic Association Studies; Genetic Heterogeneity; Humans; Limb Deformities, Congenital; Male; Middle Aged; Mutation, Missense; Phenotype; Urogenital Abnormalities; Wnt Signaling Pathway

Advillin acts upstream of phospholipase C ϵ1 in steroid-resistant nephrotic syndrome. - Rao, Jia; Ashraf, Shazia; Tan, Weizhen; van der Ven, Amelie T; Gee, Heon Yung; Braun, Daniela A; Fehér, Krisztina; George, Sudeep P; Esmaeilniakooshkghazi, Amin; Choi, Won-Il; Jobst-Schwan, Tilman; Schneider, Ronen; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of chronic kidney disease. Here, we identified recessive mutations in the gene encoding the actin-binding protein advillin (AVIL) in 3 unrelated families with SRNS. While all AVIL mutations resulted in a marked loss of its actin-bundling ability, truncation of AVIL also disrupted colocalization with F-actin, thereby leading to impaired actin binding and severing. Additionally, AVIL colocalized and interacted with the phospholipase enzyme PLCE1 and with the ARP2/3 actin-modulating complex. Knockdown of AVIL in human podocytes reduced actin stress fibers at the cell periphery, prevented recruitment of PLCE1 to the ARP3-rich lamellipodia, blocked EGF-induced generation of diacylglycerol (DAG) by PLCE1, and attenuated the podocyte migration rate (PMR). These effects were reversed by overexpression of WT AVIL but not by overexpression of any of the 3 patient-derived AVIL mutants. The PMR was increased by overexpression of WT Avil or PLCE1, or by EGF stimulation; however, this increased PMR was ameliorated by inhibition of the ARP2/3 complex, indicating that ARP-dependent lamellipodia formation occurs downstream of AVIL and PLCE1 function. Together, these results delineate a comprehensive pathogenic axis of SRNS that integrates loss of AVIL function with alterations in the action of PLCE1, an established SRNS protein.
Keywords: Actin-Related Protein 2-3 Complex; Cell Movement; Diglycerides; Female; Humans; Male; Microfilament Proteins; Mutation; Nephrotic Syndrome; Phosphoinositide Phospholipase C; Podocytes; Pseudopodia

Asprosin is a centrally acting orexigenic hormone. - Duerrschmid, Clemens; He, Yanlin; Wang, Chunmei; Li, Chia; Bournat, Juan C; Romere, Chase; Saha, Pradip K; Lee, Mark E; Phillips, Kevin J; Jain, Mahim; Jia, Peilin; Zhao, Zhongming; et al. (Nat Med, 2017)
Asprosin is a recently discovered fasting-induced hormone that promotes hepatic glucose production. Here we demonstrate that asprosin in the circulation crosses the blood-brain barrier and directly activates orexigenic AgRP neurons via a cAMP-dependent pathway. This signaling results in inhibition of downstream anorexigenic proopiomelanocortin (POMC)-positive neurons in a GABA-dependent manner, which then leads to appetite stimulation and a drive to accumulate adiposity and body weight. In humans, a genetic deficiency in asprosin causes a syndrome characterized by low appetite and extreme leanness; this is phenocopied by mice carrying similar mutations and can be fully rescued by asprosin. Furthermore, we found that obese humans and mice had pathologically elevated concentrations of circulating asprosin, and neutralization of asprosin in the blood with a monoclonal antibody reduced appetite and body weight in obese mice, in addition to improving their glycemic profile. Thus, in addition to performing a glucogenic function, asprosin is a centrally acting orexigenic hormone that is a potential therapeutic target in the treatment of both obesity and diabetes.
Keywords: Adolescent; Adult; Animals; Appetite Depressants; Appetite Regulation; Female; Humans; Hypothalamus; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microfilament Proteins; Neurons; Peptide Fragments; Peptide Hormones; Rats; Signal Transduction; Young Adult

Biallelic mutations in IRF8 impair human NK cell maturation and function. - Mace, Emily M; Bigley, Venetia; Gunesch, Justin T; Chinn, Ivan K; Angelo, Laura S; Care, Matthew A; Maisuria, Sheetal; Keller, Michael D; Togi, Sumihito; Watkin, Levi B; LaRosa, David F; Jhangiani, Shalini N; et al. (J Clin Invest, 2017)
Human NK cell deficiencies are rare yet result in severe and often fatal disease, particularly as a result of viral susceptibility. NK cells develop from hematopoietic stem cells, and few monogenic errors that specifically interrupt NK cell development have been reported. Here we have described biallelic mutations in IRF8, which encodes an interferon regulatory factor, as a cause of familial NK cell deficiency that results in fatal and severe viral disease. Compound heterozygous or homozygous mutations in IRF8 in 3 unrelated families resulted in a paucity of mature CD56dim NK cells and an increase in the frequency of the immature CD56bright NK cells, and this impairment in terminal maturation was also observed in Irf8-/-, but not Irf8+/-, mice. We then determined that impaired maturation was NK cell intrinsic, and gene expression analysis of human NK cell developmental subsets showed that multiple genes were dysregulated by IRF8 mutation. The phenotype was accompanied by deficient NK cell function and was stable over time. Together, these data indicate that human NK cells require IRF8 for development and functional maturation and that dysregulation of this function results in severe human disease, thereby emphasizing a critical role for NK cells in human antiviral defense.
Keywords: Alleles; Animals; CD56 Antigen; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Humans; Interferon Regulatory Factors; Killer Cells, Natural; Male; Mice; Mice, Knockout; Mutation; Virus Diseases

Choices for return of primary and secondary genomic research results of 790 members of families with Mendelian disease. - Fiallos, Katie; Applegate, Carolyn; Mathews, Debra Jh; Bollinger, Juli; Bergner, Amanda L; James, Cynthia A (Eur J Hum Genet, 2017)
Although consensus is building that primary (PR) and secondary findings (SF) from genomic research should be offered to participants under some circumstances, data describing (1) actual choices of study participants and (2) factors associated with these choices are limited, hampering study planning. We conducted a cross-sectional analysis of choices made for return of PR and SF during informed consent by members of the first 247 families (790 individuals) enrolled in the Baylor-Hopkins Center for Mendelian Genomics, a genome sequencing study. Most (619; 78.3%) chose to receive SF and PR, 66 (8.4%) chose PR only, 65 (8.2%) wanted no results, and 40 (5.1%) chose SF only. Choosing SF was associated with an established clinical diagnosis in the proband (87.8 vs 79%, P=0.009) and European ancestry (EA) (87.7 vs 73%, P<0.008). Participants of non-European ancestry (NEA) were as likely as those of EA to choose SF when consented by a genetic counselor (GC) (82% NEA vs 88.3% EA, P=0.09) but significantly less likely when consented by a physician (67.4% NEA vs 85.4% EA, P=0.001). Controlling for proband diagnosis, individuals of NEA were 2.13-fold (95% CI: 1.11-4.08) more likely to choose SF when consented by a GC rather than a physician. Participants of NEA were 3-fold more likely than those of EA to decline all study results (14.7% NEA vs 5.4% EA, P<0.008). In this ethnically diverse population, whereas most participants desired PR and SF, more than 20% declined some or all results, highlighting the importance of research participant choice.
Keywords: Databases, Genetic; Female; Genetic Diseases, Inborn; Genome, Human; Genome-Wide Association Study; Humans; Male; Pedigree; Research Subjects

Congenital heart defects and left ventricular non-compaction in males with loss-of-function variants in NONO. - Scott, Daryl A; Hernandez-Garcia, Andres; Azamian, Mahshid S; Jordan, Valerie K; Kim, Bum Jun; Starkovich, Molly; Zhang, Jinglan; Wong, Lee-Jun; Darilek, Sandra A; Breman, Amy M; Yang, Yaping; Lupski, James R; et al. (J Med Genet, 2017)
BACKGROUND: The non-POU domain containing octamer-binding gene (NONO) is located on chromosome Xq13.1 and encodes a member of a small family of RNA-binding and DNA-binding proteins that perform a variety of tasks involved in RNA synthesis, transcriptional regulation and DNA repair. Loss-of-function variants in NONO have been described as a cause of intellectual disability in males but have not been described in association with congenital heart defects or cardiomyopathy. In this article, we seek to further define the phenotypic consequences of NONO depletion in human subjects. METHODS: We searched a clinical database of over 6000 individuals referred for exome sequencing and over 60 000 individuals referred for CNV analysis. RESULTS: We identified two males with atrial and ventricular septal defects, left ventricular non-compaction (LVNC), developmental delay and intellectual disability, who harboured de novo, loss-of-function variants in NONO. We also identified a male infant with developmental delay, congenital brain anomalies and severe LVNC requiring cardiac transplantation, who inherited a single-gene deletion of NONO from his asymptomatic mother. CONCLUSIONS: We conclude that in addition to global developmental delay and intellectual disability, males with loss-of-function variants in NONO may also be predisposed to developing congenital heart defects and LVNC with the penetrance of these cardiac-related problems being influenced by genetic, epigenetic, environmental or stochastic factors. Brain imaging of males with NONO deficiency may reveal structural defects with abnormalities of the corpus callosum being the most common. Although dysmorphic features vary between affected individuals, relative macrocephaly is a common feature.
Keywords: Child; Child, Preschool; Developmental Disabilities; DNA-Binding Proteins; Exome; Heart Defects, Congenital; Heart Ventricles; Humans; Infant; Male; Nuclear Matrix-Associated Proteins; Octamer Transcription Factors; RNA-Binding Proteins

Contribution of rare inherited and de novo variants in 2,871 congenital heart disease probands. - Jin, Sheng Chih; Homsy, Jason; Zaidi, Samir; Lu, Qiongshi; Morton, Sarah; DePalma, Steven R; Zeng, Xue; Qi, Hongjian; Chang, Weni; Sierant, Michael C; Hung, Wei-Chien; Haider, Shozeb; et al. (Nat Genet, 2017)
Congenital heart disease (CHD) is the leading cause of mortality from birth defects. Here, exome sequencing of a single cohort of 2,871 CHD probands, including 2,645 parent-offspring trios, implicated rare inherited mutations in 1.8%, including a recessive founder mutation in GDF1 accounting for ∼5% of severe CHD in Ashkenazim, recessive genotypes in MYH6 accounting for ∼11% of Shone complex, and dominant FLT4 mutations accounting for 2.3% of Tetralogy of Fallot. De novo mutations (DNMs) accounted for 8% of cases, including ∼3% of isolated CHD patients and ∼28% with both neurodevelopmental and extra-cardiac congenital anomalies. Seven genes surpassed thresholds for genome-wide significance, and 12 genes not previously implicated in CHD had >70% probability of being disease related. DNMs in ∼440 genes were inferred to contribute to CHD. Striking overlap between genes with damaging DNMs in probands with CHD and autism was also found.
Keywords: Adult; Autistic Disorder; Cardiac Myosins; Case-Control Studies; Child; Exome; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Growth Differentiation Factor 1; Heart Defects, Congenital; Heterozygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Mutation; Myosin Heavy Chains; Pedigree; Risk; Vascular Endothelial Growth Factor Receptor-3

Corner fracture type spondylometaphyseal dysplasia: Overlap with type II collagenopathies. - Machol, Keren; Jain, Mahim; Almannai, Mohammed; Orand, Thibault; Lu, James T; Tran, Alyssa; Chen, Yuqing; Schlesinger, Alan; Gibbs, Richard; Bonafe, Luisa; Campos-Xavier, Ana Belinda; Unger, Sheila; et al. (Am J Med Genet A, 2017)
Spondylometaphyseal dysplasia (SMD) corner fracture type (also known as SMD "Sutcliffe" type, MIM 184255) is a rare skeletal dysplasia that presents with mild to moderate short stature, developmental coxa vara, mild platyspondyly, corner fracture-like lesions, and metaphyseal abnormalities with sparing of the epiphyses. The molecular basis for this disorder has yet to be clarified. We describe two patients with SMD corner fracture type and heterozygous pathogenic variants in COL2A1. These two cases together with a third case of SMD corner fracture type with a heterozygous COL2A1 pathogenic variant previously described suggest that this disorder overlaps with type II collagenopathies. The finding of one of the pathogenic variants in a previously reported case of spondyloepimetaphyseal dysplasia (SEMD) Strudwick type and the significant clinical similarity suggest an overlap between SMD corner fracture and SEMD Strudwick types. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Amino Acid Substitution; Bone Diseases, Developmental; Child, Preschool; Collagen Type II; Diagnosis, Differential; Exome; Genetic Association Studies; Genotype; Growth Disorders; High-Throughput Nucleotide Sequencing; Hip Joint; Humans; Infant; Male; Mutation; Osteochondrodysplasias; Phenotype; Radiography; Tibial Fractures

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

A defect in myoblast fusion underlies Carey-Fineman-Ziter syndrome. - Di Gioia, Silvio Alessandro; Connors, Samantha; Matsunami, Norisada; Cannavino, Jessica; Rose, Matthew F; Gilette, Nicole M; Artoni, Pietro; de Macena Sobreira, Nara Lygia; Chan, Wai-Man; Webb, Bryn D; Robson, Caroline D; Cheng, Long; et al. (Nat Commun, 2017)
Multinucleate cellular syncytial formation is a hallmark of skeletal muscle differentiation. Myomaker, encoded by Mymk (Tmem8c), is a well-conserved plasma membrane protein required for myoblast fusion to form multinucleated myotubes in mouse, chick, and zebrafish. Here, we report that autosomal recessive mutations in MYMK (OMIM 615345) cause Carey-Fineman-Ziter syndrome in humans (CFZS; OMIM 254940) by reducing but not eliminating MYMK function. We characterize MYMK-CFZS as a congenital myopathy with marked facial weakness and additional clinical and pathologic features that distinguish it from other congenital neuromuscular syndromes. We show that a heterologous cell fusion assay in vitro and allelic complementation experiments in mymk knockdown and mymk zebrafish in vivo can differentiate between MYMK wild type, hypomorphic and null alleles. Collectively, these data establish that MYMK activity is necessary for normal muscle development and maintenance in humans, and expand the spectrum of congenital myopathies to include cell-cell fusion deficits.
Keywords: Adult; Amino Acid Sequence; Animals; Cell Fusion; Child; Disease Models, Animal; Embryo, Nonmammalian; Female; Gene Expression; Genes, Recessive; Genetic Complementation Test; Humans; Infant; Male; Membrane Proteins; Mobius Syndrome; Morphogenesis; Muscle Proteins; Muscle, Skeletal; Muscular Diseases; Mutation; Myoblasts; Pedigree; Pierre Robin Syndrome; Sequence Alignment; Sequence Homology, Amino Acid; Zebrafish; Zebrafish Proteins

Dual molecular diagnosis contributes to atypical Prader-Willi phenotype in monozygotic twins. - Jehee, Fernanda S; de Oliveira, Valdirene T; Gurgel-Giannetti, Juliana; Pietra, Rafaella X; Rubatino, Fernando V M; Carobin, Natália V; Vianna, Gabrielle S; de Freitas, Mariana L; Fernandes, Karla S; Ribeiro, Beatriz S V; Brüggenwirth, Hennie T; Ali-Amin, Roza; et al. (Am J Med Genet A, 2017)
We describe monozygotic twin girls with genetic variation at two separate loci resulting in a blended phenotype of Prader-Willi syndrome and Pitt-Hopkins syndrome. These girls were diagnosed in early infancy with Prader-Willi syndrome, but developed an atypical phenotype, with apparent intellectual deficiency and lack of obesity. Array-comparative genomic hybridization confirmed a de novo paternal deletion of the 15q11.2q13 region and exome sequencing identified a second mutational event in both girls, which was a novel variant c.145+1G>A affecting a TCF4 canonical splicing site inherited from the mosaic mother. RNA studies showed that the variant abolished the donor splicing site, which was accompanied by activation of an alternative non-canonical splicing-site which then predicts a premature stop codon in the following exon. Clinical re-evaluation of the twins indicated that both variants are likely contributing to the more severe phenotypic presentation. Our data show that atypical clinical presentations may actually be the expression of blended clinical phenotypes arising from independent pathogenic events at two loci.
Keywords: Adolescent; Base Sequence; Child; Chromosome Deletion; Chromosomes, Human, Pair 15; Comparative Genomic Hybridization; Exome; Facies; Female; Humans; Hyperventilation; Intellectual Disability; Obesity; Pathology, Molecular; Phenotype; Prader-Willi Syndrome; Transcription Factor 4; Twins, Monozygotic

Efficient CNV breakpoint analysis reveals unexpected structural complexity and correlation of dosage-sensitive genes with clinical severity in genomic disorders. - Zhang, Ling; Wang, Jingmin; Zhang, Cheng; Li, Dongxiao; Carvalho, Claudia M B; Ji, Haoran; Xiao, Jianqiu; Wu, Ye; Zhou, Weichen; Wang, Hongyan; Jin, Li; Luo, Yang; et al. (Hum Mol Genet, 2017)
Genomic disorders are the clinical conditions manifested by submicroscopic genomic rearrangements including copy number variants (CNVs). The CNVs can be identified by array-based comparative genomic hybridization (aCGH), the most commonly used technology for molecular diagnostics of genomic disorders. However, clinical aCGH only informs CNVs in the probe-interrogated regions. Neither orientational information nor the resulting genomic rearrangement structure is provided, which is a key to uncovering mutational and pathogenic mechanisms underlying genomic disorders. Long-range polymerase chain reaction (PCR) is a traditional approach to obtain CNV breakpoint junction, but this method is inefficient when challenged by structural complexity such as often found at the PLP1 locus in association with Pelizaeus-Merzbacher disease (PMD). Here we introduced 'capture and single-molecule real-time sequencing' (cap-SMRT-seq) and newly developed 'asymmetry linker-mediated nested PCR walking' (ALN-walking) for CNV breakpoint sequencing in 49 subjects with PMD-associated CNVs. Remarkably, 29 (94%) of the 31 CNV breakpoint junctions unobtainable by conventional long-range PCR were resolved by cap-SMRT-seq and ALN-walking. Notably, unexpected CNV complexities, including inter-chromosomal rearrangements that cannot be resolved by aCGH, were revealed by efficient breakpoint sequencing. These sequence-based structures of PMD-associated CNVs further support the role of DNA replicative mechanisms in CNV mutagenesis, and facilitate genotype-phenotype correlation studies. Intriguingly, the lengths of gained segments by CNVs are strongly correlated with clinical severity in PMD, potentially reflecting the functional contribution of other dosage-sensitive genes besides PLP1. Our study provides new efficient experimental approaches (especially ALN-walking) for CNV breakpoint sequencing and highlights their importance in uncovering CNV mutagenesis and pathogenesis in genomic disorders.
Keywords: Base Sequence; Comparative Genomic Hybridization; DNA Copy Number Variations; DNA Replication; Female; Gene Dosage; Gene Duplication; Gene Rearrangement; Genetic Association Studies; Genome, Human; Genomics; Humans; Male; Mutation; Pelizaeus-Merzbacher Disease; Sequence Analysis, DNA

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Rett Syndrome; Whole Exome Sequencing

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin; Whole Exome Sequencing

Exome-wide Association Study Identifies GREB1L Mutations in Congenital Kidney Malformations. - Sanna-Cherchi, Simone; Khan, Kamal; Westland, Rik; Krithivasan, Priya; Fievet, Lorraine; Rasouly, Hila Milo; Ionita-Laza, Iuliana; Capone, Valentina P; Fasel, David A; Kiryluk, Krzysztof; Kamalakaran, Sitharthan; Bodria, Monica; et al. (Am J Hum Genet, 2017)
Renal agenesis and hypodysplasia (RHD) are major causes of pediatric chronic kidney disease and are highly genetically heterogeneous. We conducted whole-exome sequencing in 202 case subjects with RHD and identified diagnostic mutations in genes known to be associated with RHD in 7/202 case subjects. In an additional affected individual with RHD and a congenital heart defect, we found a homozygous loss-of-function (LOF) variant in SLIT3, recapitulating phenotypes reported with Slit3 inactivation in the mouse. To identify genes associated with RHD, we performed an exome-wide association study with 195 unresolved case subjects and 6,905 control subjects. The top signal resided in GREB1L, a gene implicated previously in Hoxb1 and Shha signaling in zebrafish. The significance of the association, which was p = 2.0 × 10 for novel LOF, increased to p = 4.1 × 10 for LOF and deleterious missense variants combined, and augmented further after accounting for segregation and de novo inheritance of rare variants (joint p = 2.3 × 10). Finally, CRISPR/Cas9 disruption or knockdown of greb1l in zebrafish caused specific pronephric defects, which were rescued by wild-type human GREB1L mRNA, but not mRNA containing alleles identified in case subjects. Together, our study provides insight into the genetic landscape of kidney malformations in humans, presents multiple candidates, and identifies SLIT3 and GREB1L as genes implicated in the pathogenesis of RHD.
Keywords: Alleles; Animals; Case-Control Studies; Clustered Regularly Interspaced Short Palindromic Repeats; Congenital Abnormalities; Exome; Female; Genetic Heterogeneity; Genome-Wide Association Study; Genotype; Heredity; Homozygote; Humans; Kidney; Kidney Diseases; Male; Membrane Proteins; Mice; Mutation; Neoplasm Proteins; Phenotype; RNA, Long Noncoding; Urinary Tract; Urogenital Abnormalities; Zebrafish

First Case of Deficiency in Ecuador, Diagnosed after Whole Exome Sequencing in a Patient with Severe Cutaneous Histoplasmosis. - Pedroza, Luis Alberto; Guerrero, Nina; Stray-Pedersen, Asbjørg; Tafur, Cristina; Macias, Roque; Muñoz, Greta; Akdemir, Zeynep Coban; Jhangiani, Shalini N; Watkin, Levi B; Chinn, Ivan K; Lupski, James R; Orange, Jordan S (Front Pediatr, 2017)
Severe infections with are commonly observed in patient with secondary immunodeficiency disorders. We report a two and a half years old boy previously healthy with disseminated cutaneous histoplasmosis. Using whole exome sequencing, we found an mutation at the gene, suggesting a diagnosis of hyper-IgM (HIGM) syndrome, even in the absence of the usual features for the disease. Interestingly, the patient lives in a region endemic for histoplasmosis. The unusual infections in our case suggest that in children with severe histoplasmosis and resident in endemic areas, HIGM syndrome should be considered as a diagnosis.

Genetic Drivers of Kidney Defects in the DiGeorge Syndrome. - Lopez-Rivera, Esther; Liu, Yangfan P; Verbitsky, Miguel; Anderson, Blair R; Capone, Valentina P; Otto, Edgar A; Yan, Zhonghai; Mitrotti, Adele; Martino, Jeremiah; Steers, Nicholas J; Fasel, David A; Vukojevic, Katarina; et al. (N Engl J Med, 2017)
BACKGROUND: The DiGeorge syndrome, the most common of the microdeletion syndromes, affects multiple organs, including the heart, the nervous system, and the kidney. It is caused by deletions on chromosome 22q11.2; the genetic driver of the kidney defects is unknown. METHODS: We conducted a genomewide search for structural variants in two cohorts: 2080 patients with congenital kidney and urinary tract anomalies and 22,094 controls. We performed exome and targeted resequencing in samples obtained from 586 additional patients with congenital kidney anomalies. We also carried out functional studies using zebrafish and mice. RESULTS: We identified heterozygous deletions of 22q11.2 in 1.1% of the patients with congenital kidney anomalies and in 0.01% of population controls (odds ratio, 81.5; P=4.5×10). We localized the main drivers of renal disease in the DiGeorge syndrome to a 370-kb region containing nine genes. In zebrafish embryos, an induced loss of function in snap29, aifm3, and crkl resulted in renal defects; the loss of crkl alone was sufficient to induce defects. Five of 586 patients with congenital urinary anomalies had newly identified, heterozygous protein-altering variants, including a premature termination codon, in CRKL. The inactivation of Crkl in the mouse model induced developmental defects similar to those observed in patients with congenital urinary anomalies. CONCLUSIONS: We identified a recurrent 370-kb deletion at the 22q11.2 locus as a driver of kidney defects in the DiGeorge syndrome and in sporadic congenital kidney and urinary tract anomalies. Of the nine genes at this locus, SNAP29, AIFM3, and CRKL appear to be critical to the phenotype, with haploinsufficiency of CRKL emerging as the main genetic driver. (Funded by the National Institutes of Health and others.).
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Animals; Child; Chromosome Deletion; Chromosomes, Human, Pair 22; DiGeorge Syndrome; Exome; Female; Haploinsufficiency; Heterozygote; Humans; Infant; Infant, Newborn; Kidney; Male; Mice; Models, Animal; Nuclear Proteins; Sequence Analysis, DNA; Urinary Tract; Young Adult; Zebrafish

Heterozygous variants in ACTL6A, encoding a component of the BAF complex, are associated with intellectual disability. - Marom, Ronit; Jain, Mahim; Burrage, Lindsay C; Song, I-Wen; Graham, Brett H; Brown, Chester W; Stevens, Servi J C; Stegmann, Alexander P A; Gunter, Andrew T; Kaplan, Julie D; Gavrilova, Ralitza H; Shinawi, Marwan; et al. (Hum Mutat, 2017)
Pathogenic variants in genes encoding components of the BRG1-associated factor (BAF) chromatin remodeling complex have been associated with intellectual disability syndromes. We identified heterozygous, novel variants in ACTL6A, a gene encoding a component of the BAF complex, in three subjects with varying degrees of intellectual disability. Two subjects have missense variants affecting highly conserved amino acid residues within the actin-like domain. Missense mutations in the homologous region in yeast actin were previously reported to be dominant lethal and were associated with impaired binding of the human ACTL6A to β-actin and BRG1. A third subject has a splicing variant that creates an in-frame deletion. Our findings suggest that the variants identified in our subjects may have a deleterious effect on the function of the protein by disturbing the integrity of the BAF complex. Thus, ACTL6A gene mutation analysis should be considered in patients with intellectual disability, learning disabilities, or developmental language disorder.
Keywords: Actins; Adolescent; Child; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; DNA Helicases; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Multiprotein Complexes; Mutation, Missense; Nuclear Proteins; Protein Binding; Transcription Factors

High Rate of Recurrent De Novo Mutations in Developmental and Epileptic Encephalopathies. - Hamdan, Fadi F; Myers, Candace T; Cossette, Patrick; Lemay, Philippe; Spiegelman, Dan; Laporte, Alexandre Dionne; Nassif, Christina; Diallo, Ousmane; Monlong, Jean; Cadieux-Dion, Maxime; Dobrzeniecka, Sylvia; Meloche, Caroline; et al. (Am J Hum Genet, 2017)
Developmental and epileptic encephalopathy (DEE) is a group of conditions characterized by the co-occurrence of epilepsy and intellectual disability (ID), typically with developmental plateauing or regression associated with frequent epileptiform activity. The cause of DEE remains unknown in the majority of cases. We performed whole-genome sequencing (WGS) in 197 individuals with unexplained DEE and pharmaco-resistant seizures and in their unaffected parents. We focused our attention on de novo mutations (DNMs) and identified candidate genes containing such variants. We sought to identify additional subjects with DNMs in these genes by performing targeted sequencing in another series of individuals with DEE and by mining various sequencing datasets. We also performed meta-analyses to document enrichment of DNMs in candidate genes by leveraging our WGS dataset with those of several DEE and ID series. By combining these strategies, we were able to provide a causal link between DEE and the following genes: NTRK2, GABRB2, CLTC, DHDDS, NUS1, RAB11A, GABBR2, and SNAP25. Overall, we established a molecular diagnosis in 63/197 (32%) individuals in our WGS series. The main cause of DEE in these individuals was de novo point mutations (53/63 solved cases), followed by inherited mutations (6/63 solved cases) and de novo CNVs (4/63 solved cases). De novo missense variants explained a larger proportion of individuals in our series than in other series that were primarily ascertained because of ID. Moreover, these DNMs were more frequently recurrent than those identified in ID series. These observations indicate that the genetic landscape of DEE might be different from that of ID without epilepsy.
Keywords: Brain Diseases; Child; Child, Preschool; Epilepsy; Female; Genome, Human; Genome-Wide Association Study; Humans; Intellectual Disability; Male; Mutation; Recurrence; Seizures

Homozygous and hemizygous CNV detection from exome sequencing data in a Mendelian disease cohort. - Gambin, Tomasz; Akdemir, Zeynep C; Yuan, Bo; Gu, Shen; Chiang, Theodore; Carvalho, Claudia M B; Shaw, Chad; Jhangiani, Shalini; Boone, Philip M; Eldomery, Mohammad K; Karaca, Ender; Bayram, Yavuz; et al. (Nucleic Acids Res, 2017)
We developed an algorithm, HMZDelFinder, that uses whole exome sequencing (WES) data to identify rare and intragenic homozygous and hemizygous (HMZ) deletions that may represent complete loss-of-function of the indicated gene. HMZDelFinder was applied to 4866 samples in the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) cohort and detected 773 HMZ deletion calls (567 homozygous or 206 hemizygous) with an estimated sensitivity of 86.5% (82% for single-exonic and 88% for multi-exonic calls) and precision of 78% (53% single-exonic and 96% for multi-exonic calls). Out of 773 HMZDelFinder-detected deletion calls, 82 were subjected to array comparative genomic hybridization (aCGH) and/or breakpoint PCR and 64 were confirmed. These include 18 single-exon deletions out of which 8 were exclusively detected by HMZDelFinder and not by any of seven other CNV detection tools examined. Further investigation of the 64 validated deletion calls revealed at least 15 pathogenic HMZ deletions. Of those, 7 accounted for 17-50% of pathogenic CNVs in different disease cohorts where 7.1-11% of the molecular diagnosis solved rate was attributed to CNVs. In summary, we present an algorithm to detect rare, intragenic, single-exon deletion CNVs using WES data; this tool can be useful for disease gene discovery efforts and clinical WES analyses.
Keywords: Algorithms; Alternative Splicing; Cohort Studies; Computational Biology; Consanguinity; Datasets as Topic; DNA Copy Number Variations; Exome; Genetic Diseases, Inborn; Hemizygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Inheritance Patterns; Models, Genetic; Pedigree; Reproducibility of Results; Sequence Deletion; Workflow

Identification of GAA variants through whole exome sequencing targeted to a cohort of 606 patients with unexplained limb-girdle muscle weakness. - Johnson, Katherine; Topf, Ana; Bertoli, Marta; Phillips, Lauren; Claeys, Kristl G; Stojanovic, Vidosava Rakocevic; Perić, Stojan; Hahn, Andreas; Maddison, Paul; Akay, Ela; Bastian, Alexandra E; Łusakowska, Anna; et al. (Orphanet J Rare Dis, 2017)
BACKGROUND: Late-onset Pompe disease is a rare genetic neuromuscular disorder caused by a primary deficiency of α-glucosidase and the associated accumulation of glycogen in lysosomal vacuoles. The deficiency of α-glucosidase can often be detected using an inexpensive and readily accessible dried blood spot test when Pompe disease is suspected. Like several neuromuscular disorders, Pompe disease typically presents with progressive weakness of limb-girdle muscles and respiratory insufficiency. Due to the phenotypic heterogeneity of these disorders, however, it is often difficult for clinicians to reach a diagnosis for patients with Pompe disease. Six hundred and six patients from a European population were recruited onto our study. Inclusion criteria stipulated that index cases must present with limb-girdle weakness or elevated serum creatine kinase activity. Whole exome sequencing with at least 250 ng DNA was completed using an Illumina exome capture and a 38 Mb baited target. A panel of 169 candidate genes for limb-girdle weakness was analysed for disease-causing variants. RESULTS: A total of 35 variants within GAA were detected. Ten distinct variants in eight unrelated index cases (and four siblings not sequenced in our study) were considered disease-causing, with the patients presenting with heterogeneous phenotypes. The eight unrelated individuals were compound heterozygotes for two variants. Six patients carried the intronic splice site c.-13 T > G transversion and two of the six patients also carried the exonic p.Glu176ArgfsTer45 frameshift. Four of the ten variants were novel in their association with Pompe disease. CONCLUSIONS: Here, we highlight the advantage of using whole exome sequencing as a tool for detecting, diagnosing and treating patients with rare, clinically variable genetic disorders.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; alpha-Glucosidases; Child; Child, Preschool; Cohort Studies; Female; Genetic Variation; Glycogen Storage Disease Type II; Humans; Male; Middle Aged; Muscle Weakness; Muscular Dystrophies, Limb-Girdle; Whole Exome Sequencing; Young Adult

Identification of STAC3 variants in non-Native American families with overlapping features of Carey-Fineman-Ziter syndrome and Moebius syndrome. - Telegrafi, Aida; Webb, Bryn D; Robbins, Sarah M; Speck-Martins, Carlos E; FitzPatrick, David; Fleming, Leah; Redett, Richard; Dufke, Andreas; Houge, Gunnar; van Harssel, Jeske J T; Verloes, Alain; Robles, Angela; et al. (Am J Med Genet A, 2017)
Horstick et al. (2013) previously reported a homozygous p.Trp284Ser variant in STAC3 as the cause of Native American myopathy (NAM) in 5 Lumbee Native American families with congenital hypotonia and weakness, cleft palate, short stature, ptosis, kyphoscoliosis, talipes deformities, and susceptibility to malignant hyperthermia (MH). Here we present two non-Native American families, who were found to have STAC3 pathogenic variants. The first proband and her affected older sister are from a consanguineous Qatari family with a suspected clinical diagnosis of Carey-Fineman-Ziter syndrome (CFZS) based on features of hypotonia, myopathic facies with generalized weakness, ptosis, normal extraocular movements, cleft palate, growth delay, and kyphoscoliosis. We identified the homozygous c.851G>C;p.Trp284Ser variant in STAC3 in both sisters. The second proband and his affected sister are from a non-consanguineous, Puerto Rican family who was evaluated for a possible diagnosis of Moebius syndrome (MBS). His features included facial and generalized weakness, minimal limitation of horizontal gaze, cleft palate, and hypotonia, and he has a history of MH. The siblings were identified to be compound heterozygous for STAC3 variants c.851G>C;p.Trp284Ser and c.763_766delCTCT;p.Leu255IlefsX58. Given the phenotypic overlap of individuals with CFZS, MBS, and NAM, we screened STAC3 in 12 individuals diagnosed with CFZS and in 50 individuals diagnosed with MBS or a congenital facial weakness disorder. We did not identify any rare coding variants in STAC3. NAM should be considered in patients presenting with facial and generalized weakness, normal or mildly abnormal extraocular movement, hypotonia, cleft palate, and scoliosis, particularly if there is a history of MH.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Child; Female; Humans; Male; Mobius Syndrome; Muscular Diseases; Mutation; Pedigree; Pierre Robin Syndrome; Prognosis; Young Adult

Improving genetic diagnosis in Mendelian disease with transcriptome sequencing. - Cummings, Beryl B; Marshall, Jamie L; Tukiainen, Taru; Lek, Monkol; Donkervoort, Sandra; Foley, A Reghan; Bolduc, Veronique; Waddell, Leigh B; Sandaradura, Sarah A; O'Grady, Gina L; Estrella, Elicia; Reddy, Hemakumar M; et al. (Sci Transl Med, 2017)
Exome and whole-genome sequencing are becoming increasingly routine approaches in Mendelian disease diagnosis. Despite their success, the current diagnostic rate for genomic analyses across a variety of rare diseases is approximately 25 to 50%. We explore the utility of transcriptome sequencing [RNA sequencing (RNA-seq)] as a complementary diagnostic tool in a cohort of 50 patients with genetically undiagnosed rare muscle disorders. We describe an integrated approach to analyze patient muscle RNA-seq, leveraging an analysis framework focused on the detection of transcript-level changes that are unique to the patient compared to more than 180 control skeletal muscle samples. We demonstrate the power of RNA-seq to validate candidate splice-disrupting mutations and to identify splice-altering variants in both exonic and deep intronic regions, yielding an overall diagnosis rate of 35%. We also report the discovery of a highly recurrent de novo intronic mutation in that results in a dominantly acting splice-gain event, disrupting the critical glycine repeat motif of the triple helical domain. We identify this pathogenic variant in a total of 27 genetically unsolved patients in an external collagen VI-like dystrophy cohort, thus explaining approximately 25% of patients clinically suggestive of having collagen VI dystrophy in whom prior genetic analysis is negative. Overall, this study represents a large systematic application of transcriptome sequencing to rare disease diagnosis and highlights its utility for the detection and interpretation of variants missed by current standard diagnostic approaches.
Keywords: Collagen Type VI; High-Throughput Nucleotide Sequencing; Humans; Muscular Diseases; Mutation; Transcriptome

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

Matchmaker Exchange. - Sobreira, Nara L M; Arachchi, Harindra; Buske, Orion J; Chong, Jessica X; Hutton, Ben; Foreman, Julia; Schiettecatte, François; Groza, Tudor; Jacobsen, Julius O B; Haendel, Melissa A; Boycott, Kym M; Hamosh, Ada; et al. (Curr Protoc Hum Genet, 2017)
In well over half of the individuals with rare disease who undergo clinical or research next-generation sequencing, the responsible gene cannot be determined. Some reasons for this relatively low yield include unappreciated phenotypic heterogeneity; locus heterogeneity; somatic and germline mosaicism; variants of uncertain functional significance; technically inaccessible areas of the genome; incorrect mode of inheritance investigated; and inadequate communication between clinicians and basic scientists with knowledge of particular genes, proteins, or biological systems. To facilitate such communication and improve the search for patients or model organisms with similar phenotypes and variants in specific candidate genes, we have developed the Matchmaker Exchange (MME). MME was created to establish a federated network connecting databases of genomic and phenotypic data using a common application programming interface (API). To date, seven databases can exchange data using the API (GeneMatcher, PhenomeCentral, DECIPHER, MyGene2, matchbox, Australian Genomics Health Alliance Patient Archive, and Monarch Initiative; the latter included for model organism matching). This article guides usage of the MME for rare disease gene discovery. © 2017 by John Wiley & Sons, Inc.
Keywords: Animals; Computational Biology; Databases, Genetic; Genetic Association Studies; Genetic Predisposition to Disease; Genomics; Humans; Rare Diseases; Software; Web Browser

Multilevel analyses of SCN5A mutations in arrhythmogenic right ventricular dysplasia/cardiomyopathy suggest non-canonical mechanisms for disease pathogenesis. - Te Riele, Anneline S J M; Agullo-Pascual, Esperanza; James, Cynthia A; Leo-Macias, Alejandra; Cerrone, Marina; Zhang, Mingliang; Lin, Xianming; Lin, Bin; Sobreira, Nara L; Amat-Alarcon, Nuria; Marsman, Roos F; Murray, Brittney; et al. (Cardiovasc Res, 2017)
AIMS: Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy (ARVD/C) is often associated with desmosomal mutations. Recent studies suggest an interaction between the desmosome and sodium channel protein Na1.5. We aimed to determine the prevalence and biophysical properties of mutations in SCN5A (the gene encoding Na1.5) in ARVD/C. METHODS AND RESULTS: We performed whole-exome sequencing in six ARVD/C patients (33% male, 38.2 ± 12.1 years) without a desmosomal mutation. We found a rare missense variant (p.Arg1898His; R1898H) in SCN5A in one patient. We generated induced pluripotent stem cell-derived cardiomyocytes (hIPSC-CMs) from the patient's peripheral blood mononuclear cells. The variant was then corrected (R1898R) using Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 technology, allowing us to study the impact of the R1898H substitution in the same cellular background. Whole-cell patch clamping revealed a 36% reduction in peak sodium current (P = 0.002); super-resolution fluorescence microscopy showed reduced abundance of Na1.5 (P = 0.005) and N-Cadherin (P = 0.026) clusters at the intercalated disc. Subsequently, we sequenced SCN5A in an additional 281 ARVD/C patients (60% male, 34.8 ± 13.7 years, 52% desmosomal mutation-carriers). Five (1.8%) subjects harboured a putatively pathogenic SCN5A variant (p.Tyr416Cys, p.Leu729del, p.Arg1623Ter, p.Ser1787Asn, and p.Val2016Met). SCN5A variants were associated with prolonged QRS duration (119 ± 15 vs. 94 ± 14 ms, P < 0.01) and all SCN5A variant carriers had major structural abnormalities on cardiac imaging. CONCLUSIONS: Almost 2% of ARVD/C patients harbour rare SCN5A variants. For one of these variants, we demonstrated reduced sodium current, Na1.5 and N-Cadherin clusters at junctional sites. This suggests that Na1.5 is in a functional complex with adhesion molecules, and reveals potential non-canonical mechanisms by which Na1.5 dysfunction causes cardiomyopathy.
Keywords: Adult; Antigens, CD; Arrhythmogenic Right Ventricular Dysplasia; Cadherins; Cell Differentiation; CRISPR-Cas Systems; DNA Mutational Analysis; Electrocardiography; Exome; Female; Gene Editing; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Magnetic Resonance Imaging; Male; Membrane Potentials; Middle Aged; Multilevel Analysis; Mutation, Missense; Myocytes, Cardiac; NAV1.5 Voltage-Gated Sodium Channel; Netherlands; Phenotype; Sodium; Transfection; United States; Young Adult

Mutations in EBF3 Disturb Transcriptional Profiles and Cause Intellectual Disability, Ataxia, and Facial Dysmorphism. - Harms, Frederike Leonie; Girisha, Katta M; Hardigan, Andrew A; Kortüm, Fanny; Shukla, Anju; Alawi, Malik; Dalal, Ashwin; Brady, Lauren; Tarnopolsky, Mark; Bird, Lynne M; Ceulemans, Sophia; Bebin, Martina; et al. (Am J Hum Genet, 2017)
From a GeneMatcher-enabled international collaboration, we identified ten individuals affected by intellectual disability, speech delay, ataxia, and facial dysmorphism and carrying a deleterious EBF3 variant detected by whole-exome sequencing. One 9-bp duplication and one splice-site, five missense, and two nonsense variants in EBF3 were found; the mutations occurred de novo in eight individuals, and the missense variant c.625C>T (p.Arg209Trp) was inherited by two affected siblings from their healthy mother, who is mosaic. EBF3 belongs to the early B cell factor family (also known as Olf, COE, or O/E) and is a transcription factor involved in neuronal differentiation and maturation. Structural assessment predicted that the five amino acid substitutions have damaging effects on DNA binding of EBF3. Transient expression of EBF3 mutant proteins in HEK293T cells revealed mislocalization of all but one mutant in the cytoplasm, as well as nuclear localization. By transactivation assays, all EBF3 mutants showed significantly reduced or no ability to activate transcription of the reporter gene CDKN1A, and in situ subcellular fractionation experiments demonstrated that EBF3 mutant proteins were less tightly associated with chromatin. Finally, in RNA-seq and ChIP-seq experiments, EBF3 acted as a transcriptional regulator, and mutant EBF3 had reduced genome-wide DNA binding and gene-regulatory activity. Our findings demonstrate that variants disrupting EBF3-mediated transcriptional regulation cause intellectual disability and developmental delay and are present in ∼0.1% of individuals with unexplained neurodevelopmental disorders.
Keywords: Adolescent; Adult; Amino Acid Substitution; Ataxia; Child; Child, Preschool; Chromatin; Cyclin-Dependent Kinase Inhibitor p21; Developmental Disabilities; Exome; Face; Female; Gene Expression Regulation; Genes, Reporter; HEK293 Cells; Humans; Intellectual Disability; Language Development Disorders; Male; Models, Molecular; Mosaicism; Mutation; Neurodevelopmental Disorders; Protein Transport; Syndrome; Transcription Factors; Transcription, Genetic

Mutations in GPAA1, Encoding a GPI Transamidase Complex Protein, Cause Developmental Delay, Epilepsy, Cerebellar Atrophy, and Osteopenia. - Nguyen, Thi Tuyet Mai; Murakami, Yoshiko; Sheridan, Eamonn; Ehresmann, Sophie; Rousseau, Justine; St-Denis, Anik; Chai, Guoliang; Ajeawung, Norbert F; Fairbrother, Laura; Reimschisel, Tyler; Bateman, Alexandra; Berry-Kravis, Elizabeth; et al. (Am J Hum Genet, 2017)
Approximately one in every 200 mammalian proteins is anchored to the cell membrane through a glycosylphosphatidylinositol (GPI) anchor. These proteins play important roles notably in neurological development and function. To date, more than 20 genes have been implicated in the biogenesis of GPI-anchored proteins. GPAA1 (glycosylphosphatidylinositol anchor attachment 1) is an essential component of the transamidase complex along with PIGK, PIGS, PIGT, and PIGU (phosphatidylinositol-glycan biosynthesis classes K, S, T, and U, respectively). This complex orchestrates the attachment of the GPI anchor to the C terminus of precursor proteins in the endoplasmic reticulum. Here, we report bi-allelic mutations in GPAA1 in ten individuals from five families. Using whole-exome sequencing, we identified two frameshift mutations (c.981_993del [p.Gln327Hisfs102] and c.920delG [p.Gly307Alafs11]), one intronic splicing mutation (c.1164+5C>T), and six missense mutations (c.152C>T [p.Ser51Leu], c.160_161delinsAA [p.Ala54Asn], c.527G>C [p.Trp176Ser], c.869T>C [p.Leu290Pro], c.872T>C [p.Leu291Pro], and c.1165G>C [p.Ala389Pro]). Most individuals presented with global developmental delay, hypotonia, early-onset seizures, cerebellar atrophy, and osteopenia. The splicing mutation was found to decrease GPAA1 mRNA. Moreover, flow-cytometry analysis of five available individual samples showed that several GPI-anchored proteins had decreased cell-surface abundance in leukocytes (FLAER, CD16, and CD59) or fibroblasts (CD73 and CD109). Transduction of fibroblasts with a lentivirus encoding the wild-type protein partially rescued the deficiency of GPI-anchored proteins. These findings highlight the role of the transamidase complex in the development and function of the cerebellum and the skeletal system.
Keywords: Acyltransferases; Adolescent; Adult; Alleles; Atrophy; Bone Diseases, Metabolic; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Epilepsy; Exome; Female; Fibroblasts; Glycosylphosphatidylinositols; Humans; Male; Membrane Glycoproteins; Muscle Hypotonia; Mutation; Pedigree; RNA, Messenger; Seizures

Mutations in IFT-A satellite core component genes and produce short rib polydactyly syndrome with distinctive campomelia. - Duran, Ivan; Taylor, S Paige; Zhang, Wenjuan; Martin, Jorge; Qureshi, Faisal; Jacques, Suzanne M; Wallerstein, Robert; Lachman, Ralph S; Nickerson, Deborah A; Bamshad, Michael; Cohn, Daniel H; Krakow, Deborah (Cilia, 2017)
BACKGROUND: Skeletal ciliopathies comprise a spectrum of ciliary malfunction disorders that have a profound effect on the skeleton. Most common among these disorders is short rib polydactyly syndrome (SRPS), a recessively inherited perinatal lethal condition characterized by a long narrow chest, markedly shortened long bones, polydactyly and, often, multi-organ system involvement. SRPS shows extensive locus heterogeneity with mutations in genes encoding proteins that participate in cilia formation and/or function. RESULTS: Herein we describe mutations in , a satellite member of the retrograde IFT-A complex, that produce a form of SRPS with unusual bending of the ribs and appendicular bones. These newly described mutations disrupted cilia formation, produced abnormalities in cartilage growth plate architecture thus contributing to altered endochondral ossification. We further show that the SRPS phenotype is similar to SRPS resulting from mutations in the gene encoding IFT121 (WDR35), a direct interactor with IFT43. CONCLUSIONS: This study defines a new -associated phenotype, identifying an additional locus for SRPS. The data demonstrate that IFT43 is essential for ciliogenesis and that the mutations disrupted the orderly proliferation and differentiation of growth plate chondrocytes, resulting in a severe effect on endochondral ossification and mineralization. Phenotypic similarities with SRPS cases resulting from mutations in the gene encoding the IFT43 direct interacting protein IFT121 suggests that similar mechanisms may be disrupted by defects in these two IFT-A satellite interactors.

Mutations in KEOPS-complex genes cause nephrotic syndrome with primary microcephaly. - Braun, Daniela A; Rao, Jia; Mollet, Geraldine; Schapiro, David; Daugeron, Marie-Claire; Tan, Weizhen; Gribouval, Olivier; Boyer, Olivia; Revy, Patrick; Jobst-Schwan, Tilman; Schmidt, Johanna Magdalena; Lawson, Jennifer A; et al. (Nat Genet, 2017)
Galloway-Mowat syndrome (GAMOS) is an autosomal-recessive disease characterized by the combination of early-onset nephrotic syndrome (SRNS) and microcephaly with brain anomalies. Here we identified recessive mutations in OSGEP, TP53RK, TPRKB, and LAGE3, genes encoding the four subunits of the KEOPS complex, in 37 individuals from 32 families with GAMOS. CRISPR-Cas9 knockout in zebrafish and mice recapitulated the human phenotype of primary microcephaly and resulted in early lethality. Knockdown of OSGEP, TP53RK, or TPRKB inhibited cell proliferation, which human mutations did not rescue. Furthermore, knockdown of these genes impaired protein translation, caused endoplasmic reticulum stress, activated DNA-damage-response signaling, and ultimately induced apoptosis. Knockdown of OSGEP or TP53RK induced defects in the actin cytoskeleton and decreased the migration rate of human podocytes, an established intermediate phenotype of SRNS. We thus identified four new monogenic causes of GAMOS, describe a link between KEOPS function and human disease, and delineate potential pathogenic mechanisms.
Keywords: Animals; Apoptosis; Carrier Proteins; Cell Movement; CRISPR-Cas Systems; Cytoskeleton; DNA Repair; Endoplasmic Reticulum Stress; Gene Knockout Techniques; Hernia, Hiatal; Humans; Intracellular Signaling Peptides and Proteins; Metalloendopeptidases; Mice; Microcephaly; Models, Molecular; Multiprotein Complexes; Mutation; Nephrosis; Nephrotic Syndrome; Podocytes; Protein Conformation; Protein-Serine-Threonine Kinases; RNA Processing, Post-Transcriptional; RNA, Transfer; Telomere Homeostasis; Zebrafish; Zebrafish Proteins

Mutations in sphingosine-1-phosphate lyase cause nephrosis with ichthyosis and adrenal insufficiency. - Lovric, Svjetlana; Goncalves, Sara; Gee, Heon Yung; Oskouian, Babak; Srinivas, Honnappa; Choi, Won-Il; Shril, Shirlee; Ashraf, Shazia; Tan, Weizhen; Rao, Jia; Airik, Merlin; Schapiro, David; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease cases. A mutation in 1 of over 40 monogenic genes can be detected in approximately 30% of individuals with SRNS whose symptoms manifest before 25 years of age. However, in many patients, the genetic etiology remains unknown. Here, we have performed whole exome sequencing to identify recessive causes of SRNS. In 7 families with SRNS and facultative ichthyosis, adrenal insufficiency, immunodeficiency, and neurological defects, we identified 9 different recessive mutations in SGPL1, which encodes sphingosine-1-phosphate (S1P) lyase. All mutations resulted in reduced or absent SGPL1 protein and/or enzyme activity. Overexpression of cDNA representing SGPL1 mutations resulted in subcellular mislocalization of SGPL1. Furthermore, expression of WT human SGPL1 rescued growth of SGPL1-deficient dpl1Δ yeast strains, whereas expression of disease-associated variants did not. Immunofluorescence revealed SGPL1 expression in mouse podocytes and mesangial cells. Knockdown of Sgpl1 in rat mesangial cells inhibited cell migration, which was partially rescued by VPC23109, an S1P receptor antagonist. In Drosophila, Sply mutants, which lack SGPL1, displayed a phenotype reminiscent of nephrotic syndrome in nephrocytes. WT Sply, but not the disease-associated variants, rescued this phenotype. Together, these results indicate that SGPL1 mutations cause a syndromic form of SRNS.
Keywords: Aldehyde-Lyases; Animals; Cell Line; Cell Movement; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Ichthyosis, Lamellar; Male; Mesangial Cells; Mice; Mice, Knockout; Mutation; Nephrotic Syndrome; Protein Transport; Rats

My46: a Web-based tool for self-guided management of genomic test results in research and clinical settings. - Tabor, Holly K; Jamal, Seema M; Yu, Joon-Ho; Crouch, Julia M; Shankar, Aditi G; Dent, Karin M; Anderson, Nick; Miller, Damon A; Futral, Brett T; Bamshad, Michael J (Genet Med, 2017)
A major challenge to implementing precision medicine is the need for an efficient and cost-effective strategy for returning individual genomic test results that is easily scalable and can be incorporated into multiple models of clinical practice. My46 is a Web-based tool for managing the return of genetic results that was designed and developed to support a wide range of approaches to disclosing results, ranging from traditional face-to-face disclosure to self-guided models. My46 has five key functions: set and modify results-return preferences, return results, educate, manage the return of results, and assess the return of results. These key functions are supported by six distinct modules and a suite of features that enhance the user experience, ease site navigation, facilitate knowledge sharing, and enable results-return tracking. My46 is a potentially effective solution for returning results and supports current trends toward shared decision making between patients and providers and patient-driven health management.Genet Med 19 4, 467-475.
Keywords: Biomedical Research; Computational Biology; Decision Making; Genomics; Humans; Internet; Medical Informatics; Patient Access to Records; Precision Medicine

Neonatal fractures as a presenting feature of LMOD3-associated congenital myopathy. - Abbott, Megan; Jain, Mahim; Pferdehirt, Rachel; Chen, Yuqing; Tran, Alyssa; Duz, Mehmet B; Seven, Mehmet; Gibbs, Richard A; Muzny, Donna; Lee, Brendan; Marom, Ronit; Burrage, Lindsay C (Am J Med Genet A, 2017)
Nemaline myopathy is a rare inherited disorder characterized by weakness, hypotonia, and depressed deep tendon reflexes. It is clinically and genetically heterogeneous, with the most severe phenotype presenting as perinatal akinesia, severe muscle weakness, feeding difficulties and respiratory failure, leading to early mortality. Pathogenic variants in 12 genes, encoding components of the sarcomere or factors related to myogenesis, have been reported in patients affected with the disorder. Here, we describe an early, lethal presentation of decreased fetal movements, hypotonia, muscle weakness, and neonatal respiratory failure requiring ventilator support in three siblings from a consanguineous family. All exhibited perinatal fractures, and thus, a skeletal dysplasia was considered as possibly contributing to the phenotype. However, whole exome sequencing revealed a homozygous, loss-of-function pathogenic variant in LMOD3, which has recently been associated with nemaline myopathy and, in a subset of patients, perinatal fractures. This case demonstrates the importance of considering congenital neuromuscular disorders in the differential diagnosis of perinatal fractures.
Keywords: Female; Fractures, Bone; Homozygote; Humans; Infant, Newborn; Male; Muscle Proteins; Mutation; Myopathies, Structural, Congenital; Pedigree

Novel Genetic Triggers and Genotype-Phenotype Correlations in Patients With Left Ventricular Noncompaction. - Miszalski-Jamka, Karol; Jefferies, John L; Mazur, Wojciech; Głowacki, Jan; Hu, Jianhong; Lazar, Monika; Gibbs, Richard A; Liczko, Jacek; Kłyś, Jan; Venner, Eric; Muzny, Donna M; Rycaj, Jarosław; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Left ventricular noncompaction (LVNC) is a genetically and phenotypically heterogeneous disease and, although increasingly recognized in clinical practice, there is a lack of widely accepted diagnostic criteria. We sought to identify novel genetic causes of LVNC and describe genotype-phenotype correlations. METHODS AND RESULTS: A total of 190 patients from 174 families with left ventricular hypertrabeculation (LVHT) or LVNC were referred for cardiac magnetic resonance and whole-exome sequencing. A total of 425 control individuals were included to identify variants of interest (VOIs). We found an excess of 138 VOIs in 102 (59%) unrelated patients in 54 previously identified LVNC or other known cardiomyopathy genes. VOIs were found in 68 of 90 probands with LVNC and 34 of 84 probands with LVHT (76% and 40%, respectively; <0.001). We identified 0, 1, and ≥2 VOIs in 72, 74, and 28 probands, respectively. We found increasing number of VOIs in a patient strongly correlated with several markers of disease severity, including ratio of noncompacted to compacted myocardium (<0.001) and left ventricular ejection fraction (=0.01). The presence of sarcomeric gene mutations was associated with increased occurrence of late gadolinium enhancement (=0.004). CONCLUSIONS: LVHT and LVNC likely represent a continuum of genotypic disease with differences in severity and variable phenotype explained, in part, by the number of VOIs and whether mutations are present in sarcomeric or nonsarcomeric genes. Presence of VOIs is common in patients with LVHT. Our findings expand the current clinical and genetic diagnostic approaches for patients with LVHT and LVNC.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Aged; Cardiac Myosins; Carrier Proteins; Child; Connectin; Female; Genetic Association Studies; Genetic Variation; Heart Ventricles; Humans; LIM Domain Proteins; Magnetic Resonance Imaging, Cine; Male; Middle Aged; Muscle Proteins; Myocardium; Myosin Heavy Chains; Prospective Studies; Severity of Illness Index; Tropomyosin; Ventricular Dysfunction, Left; Young Adult

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Yuan, Bo; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Yuan, Bo; Jhangiani, Shalini N; Muzny, Donna M; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

A Recurrent De Novo Variant in NACC1 Causes a Syndrome Characterized by Infantile Epilepsy, Cataracts, and Profound Developmental Delay. - Schoch, Kelly; Meng, Linyan; Szelinger, Szabolcs; Bearden, David R; Stray-Pedersen, Asbjorg; Busk, Oyvind L; Stong, Nicholas; Liston, Eriskay; Cohn, Ronald D; Scaglia, Fernando; Rosenfeld, Jill A; Tarpinian, Jennifer; et al. (Am J Hum Genet, 2017)
Whole-exome sequencing (WES) has increasingly enabled new pathogenic gene variant identification for undiagnosed neurodevelopmental disorders and provided insights into both gene function and disease biology. Here, we describe seven children with a neurodevelopmental disorder characterized by microcephaly, profound developmental delays and/or intellectual disability, cataracts, severe epilepsy including infantile spasms, irritability, failure to thrive, and stereotypic hand movements. Brain imaging in these individuals reveals delay in myelination and cerebral atrophy. We observe an identical recurrent de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in seven affected individuals. One of the seven individuals is mosaic for this variant. NACC1 encodes a transcriptional repressor implicated in gene expression and has not previously been associated with germline disorders. The probability of finding the same missense NACC1 variant by chance in 7 out of 17,228 individuals who underwent WES for diagnoses of neurodevelopmental phenotypes is extremely small and achieves genome-wide significance (p = 1.25 × 10). Selective constraint against missense variants in NACC1 makes this excess of an identical missense variant in all seven individuals more remarkable. Our findings are consistent with a germline recurrent mutational hotspot associated with an allele-specific neurodevelopmental phenotype in NACC1.
Keywords: Alleles; Amino Acid Sequence; Brain; Cataract; Child; Child, Preschool; Female; Genetic Variation; Genome-Wide Association Study; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Microcephaly; Mutation, Missense; Neoplasm Proteins; Pedigree; Phenotype; Repressor Proteins; Spasms, Infantile

Resolution of Disease Phenotypes Resulting from Multilocus Genomic Variation. - Posey, Jennifer E; Harel, Tamar; Liu, Pengfei; Rosenfeld, Jill A; James, Regis A; Coban Akdemir, Zeynep H; Walkiewicz, Magdalena; Bi, Weimin; Xiao, Rui; Ding, Yan; Xia, Fan; Beaudet, Arthur L; et al. (N Engl J Med, 2017)
BACKGROUND: Whole-exome sequencing can provide insight into the relationship between observed clinical phenotypes and underlying genotypes. METHODS: We conducted a retrospective analysis of data from a series of 7374 consecutive unrelated patients who had been referred to a clinical diagnostic laboratory for whole-exome sequencing; our goal was to determine the frequency and clinical characteristics of patients for whom more than one molecular diagnosis was reported. The phenotypic similarity between molecularly diagnosed pairs of diseases was calculated with the use of terms from the Human Phenotype Ontology. RESULTS: A molecular diagnosis was rendered for 2076 of 7374 patients (28.2%); among these patients, 101 (4.9%) had diagnoses that involved two or more disease loci. We also analyzed parental samples, when available, and found that de novo variants accounted for 67.8% (61 of 90) of pathogenic variants in autosomal dominant disease genes and 51.7% (15 of 29) of pathogenic variants in X-linked disease genes; both variants were de novo in 44.7% (17 of 38) of patients with two monoallelic variants. Causal copy-number variants were found in 12 patients (11.9%) with multiple diagnoses. Phenotypic similarity scores were significantly lower among patients in whom the phenotype resulted from two distinct mendelian disorders that affected different organ systems (50 patients) than among patients with disorders that had overlapping phenotypic features (30 patients) (median score, 0.21 vs. 0.36; P=1.77×10). CONCLUSIONS: In our study, we found multiple molecular diagnoses in 4.9% of cases in which whole-exome sequencing was informative. Our results show that structured clinical ontologies can be used to determine the degree of overlap between two mendelian diseases in the same patient; the diseases can be distinct or overlapping. Distinct disease phenotypes affect different organ systems, whereas overlapping disease phenotypes are more likely to be caused by two genes encoding proteins that interact within the same pathway. (Funded by the National Institutes of Health and the Ting Tsung and Wei Fong Chao Foundation.).
Keywords: Exome; Genetic Diseases, Inborn; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Phenotype; Retrospective Studies; Sequence Analysis, DNA

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis. - Bayram, Yavuz; White, Janson J; Elcioglu, Nursel; Cho, Megan T; Zadeh, Neda; Gedikbasi, Asuman; Palanduz, Sukru; Ozturk, Sukru; Cefle, Kivanc; Kasapcopur, Ozgur; Coban Akdemir, Zeynep; Pehlivan, Davut; et al. (Am J Hum Genet, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exon-truncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Adolescent; Base Sequence; Chromosome Segregation; Exons; Family; Female; Fibromatosis, Gingival; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Repressor Proteins

The sensitivity of exome sequencing in identifying pathogenic mutations for LGMD in the United States. - Reddy, Hemakumar M; Cho, Kyung-Ah; Lek, Monkol; Estrella, Elicia; Valkanas, Elise; Jones, Michael D; Mitsuhashi, Satomi; Darras, Basil T; Amato, Anthony A; Lidov, Hart Gw; Brownstein, Catherine A; Margulies, David M; et al. (J Hum Genet, 2017)
The current study characterizes a cohort of limb-girdle muscular dystrophy (LGMD) in the United States using whole-exome sequencing. Fifty-five families affected by LGMD were recruited using an institutionally approved protocol. Exome sequencing was performed on probands and selected parental samples. Pathogenic mutations and cosegregation patterns were confirmed by Sanger sequencing. Twenty-two families (40%) had novel and previously reported pathogenic mutations, primarily in LGMD genes, and also in genes for Duchenne muscular dystrophy, facioscapulohumeral muscular dystrophy, congenital myopathy, myofibrillar myopathy, inclusion body myopathy and Pompe disease. One family was diagnosed via clinical testing. Dominant mutations were identified in COL6A1, COL6A3, FLNC, LMNA, RYR1, SMCHD1 and VCP, recessive mutations in ANO5, CAPN3, GAA, LAMA2, SGCA and SGCG, and X-linked mutations in DMD. A previously reported variant in DMD was confirmed to be benign. Exome sequencing is a powerful diagnostic tool for LGMD. Despite careful phenotypic screening, pathogenic mutations were found in other muscle disease genes, largely accounting for the increased sensitivity of exome sequencing. Our experience suggests that broad sequencing panels are useful for these analyses because of the phenotypic overlap of many neuromuscular conditions. The confirmation of a benign DMD variant illustrates the potential of exome sequencing to help determine pathogenicity.
Keywords: Base Sequence; Distal Myopathies; Exome; Female; Genetic Testing; Glycogen Storage Disease Type II; Humans; Male; Muscular Dystrophies, Limb-Girdle; Muscular Dystrophy, Duchenne; Muscular Dystrophy, Facioscapulohumeral; Mutation; Myopathies, Structural, Congenital; Sequence Analysis, DNA; United States

Sequence variants in nine different genes underlying rare skin disorders in 10 consanguineous families. - Shah, Khadim; Mehmood, Sabba; Jan, Abid; Abbe, Izoduwa; Hussain Ali, Raja; Khan, Anwar; Chishti, Muhammad S; Lee, Kwanghyuk; Ahmad, Farooq; Ansar, Muhammad; Shahzad, Shaheen; Nickerson, Deborah A; et al. (Int J Dermatol, 2017)
BACKGROUND: Genodermatoses represent genetic anomalies of skin tissues including hair follicles, sebaceous glands, eccrine glands, nails, and teeth. Ten consanguineous families segregating various genodermatosis phenotypes were investigated in the present study. METHODS: Homozygosity mapping, exome, and Sanger sequencing were employed to search for the disease-causing variants in the 10 families. RESULTS: Exome sequencing identified seven homozygous sequence variants in different families, including: c.27delT in FERMT1; c.836delA in ABHD5; c.2453C>T in ERCC5; c.5314C>T in COL7A1; c.1630C>T in ALOXE3; c.502C>T in PPOX; and c.10G>T in ALDH3A2. Sanger sequencing revealed three homozygous variants: c.1718 + 2A>G in FERMT1; c.10459A>T in FLG; and c.92delT in the KRT14 genes as the underlying genetic cause of skin phenotypes. CONCLUSION: This study supports the use of exome sequencing as a powerful, efficient tool for identifying genes that underlie rare monogenic skin disorders.
Keywords: 1-Acylglycerol-3-Phosphate O-Acyltransferase; Aldehyde Oxidoreductases; Blister; Collagen Type VII; Consanguinity; DNA Mutational Analysis; DNA-Binding Proteins; Endonucleases; Epidermolysis Bullosa; Epidermolysis Bullosa Dystrophica; Epidermolysis Bullosa Simplex; Exome; Female; Flavoproteins; Homozygote; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis Vulgaris; Ichthyosis, Lamellar; INDEL Mutation; Intermediate Filament Proteins; Keratin-14; Lipid Metabolism, Inborn Errors; Lipoxygenase; Male; Membrane Proteins; Mitochondrial Proteins; Muscular Diseases; Neoplasm Proteins; Nuclear Proteins; Pedigree; Periodontal Diseases; Phenotype; Photosensitivity Disorders; Porphyria, Variegate; Protoporphyrinogen Oxidase; Rare Diseases; Sjogren-Larsson Syndrome; Skin Diseases, Genetic; Transcription Factors; Xeroderma Pigmentosum

Sequencing of sporadic Attention-Deficit Hyperactivity Disorder (ADHD) identifies novel and potentially pathogenic de novo variants and excludes overlap with genes associated with autism spectrum disorder. - Kim, Daniel Seung; Burt, Amber A; Ranchalis, Jane E; Wilmot, Beth; Smith, Joshua D; Patterson, Karynne E; Coe, Bradley P; Li, Yatong K; Bamshad, Michael J; Nikolas, Molly; Eichler, Evan E; Swanson, James M; et al. (Am J Med Genet B Neuropsychiatr Genet, 2017)
Attention-Deficit Hyperactivity Disorder (ADHD) has high heritability; however, studies of common variation account for <5% of ADHD variance. Using data from affected participants without a family history of ADHD, we sought to identify de novo variants that could account for sporadic ADHD. Considering a total of 128 families, two analyses were conducted in parallel: first, in 11 unaffected parent/affected proband trios (or quads with the addition of an unaffected sibling) we completed exome sequencing. Six de novo missense variants at highly conserved bases were identified and validated from four of the 11 families: the brain-expressed genes TBC1D9, DAGLA, QARS, CSMD2, TRPM2, and WDR83. Separately, in 117 unrelated probands with sporadic ADHD, we sequenced a panel of 26 genes implicated in intellectual disability (ID) and autism spectrum disorder (ASD) to evaluate whether variation in ASD/ID-associated genes were also present in participants with ADHD. Only one putative deleterious variant (Gln600STOP) in CHD1L was identified; this was found in a single proband. Notably, no other nonsense, splice, frameshift, or highly conserved missense variants in the 26 gene panel were identified and validated. These data suggest that de novo variant analysis in families with independently adjudicated sporadic ADHD diagnosis can identify novel genes implicated in ADHD pathogenesis. Moreover, that only one of the 128 cases (0.8%, 11 exome, and 117 MIP sequenced participants) had putative deleterious variants within our data in 26 genes related to ID and ASD suggests significant independence in the genetic pathogenesis of ADHD as compared to ASD and ID phenotypes. © 2017 Wiley Periodicals, Inc.
Keywords: Adult; Attention Deficit Disorder with Hyperactivity; Autism Spectrum Disorder; Biomarkers; Child; Exome; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation, Missense; Phenotype

SLC13A5 is the second gene associated with Kohlschütter-Tönz syndrome. - Schossig, Anna; Bloch-Zupan, Agnès; Lussi, Adrian; Wolf, Nicole I; Raskin, Salmo; Cohen, Monika; Giuliano, Fabienne; Jurgens, Julie; Krabichler, Birgit; Koolen, David A; de Macena Sobreira, Nara Lygia; Maurer, Elisabeth; et al. (J Med Genet, 2017)
BACKGROUND: Kohlschütter-Tönz syndrome (KTZS) is a rare autosomal-recessive disease characterised by epileptic encephalopathy, intellectual disability and amelogenesis imperfecta (AI). It is frequently caused by biallelic mutations in ROGDI. Here, we report on individuals with ROGDI-negative KTZS carrying biallelic SLC13A5 mutations. METHODS: In the present cohort study, nine individuals from four families with the clinical diagnosis of KTZS and absence of ROGDI mutations as well as one patient with unexplained epileptic encephalopathy were investigated by clinical and dental evaluation, parametric linkage analysis (one family), and exome and/or Sanger sequencing. Dental histological investigations were performed on teeth from individuals with SLC13A5-associated and ROGDI-associated KTZS. RESULTS: Biallelic mutations in SLC13A5 were identified in 10 affected individuals. Epileptic encephalopathy usually presents in the neonatal and (less frequently) early infantile period. Yellowish to orange discolouration of both deciduous and permanent teeth, as well as wide interdental spaces and abnormal crown forms are major clinical signs of individuals with biallelic SLC13A5 mutations. Histological dental investigations confirmed the clinical diagnosis of hypoplastic AI. In comparison, the histological evaluation of a molar assessed from an individual with ROGDI-associated KTZS revealed hypocalcified AI. CONCLUSIONS: We conclude that SLC13A5 is the second major gene associated with the clinical diagnosis of KTZS, characterised by neonatal epileptic encephalopathy and hypoplastic AI. Careful clinical and dental delineation provides clues whether ROGDI or SLC13A5 is the causative gene. Hypersensitivity of teeth as well as high caries risk requires individual dental prophylaxis and attentive dental management.
Keywords: Alleles; Amelogenesis Imperfecta; Brain Diseases; Cohort Studies; Dementia; Epilepsy; Exome; Female; Genetic Linkage; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Mutation; Nuclear Proteins; Pedigree; Symporters; Tooth

SMCHD1 mutations associated with a rare muscular dystrophy can also cause isolated arhinia and Bosma arhinia microphthalmia syndrome. - Shaw, Natalie D; Brand, Harrison; Kupchinsky, Zachary A; Bengani, Hemant; Plummer, Lacey; Jones, Takako I; Erdin, Serkan; Williamson, Kathleen A; Rainger, Joe; Stortchevoi, Alexei; Samocha, Kaitlin; Currall, Benjamin B; et al. (Nat Genet, 2017)
Arhinia, or absence of the nose, is a rare malformation of unknown etiology that is often accompanied by ocular and reproductive defects. Sequencing of 40 people with arhinia revealed that 84% of probands harbor a missense mutation localized to a constrained region of SMCHD1 encompassing the ATPase domain. SMCHD1 mutations cause facioscapulohumeral muscular dystrophy type 2 (FSHD2) via a trans-acting loss-of-function epigenetic mechanism. We discovered shared mutations and comparable DNA hypomethylation patterning between these distinct disorders. CRISPR/Cas9-mediated alteration of smchd1 in zebrafish yielded arhinia-relevant phenotypes. Transcriptome and protein analyses in arhinia probands and controls showed no differences in SMCHD1 mRNA or protein abundance but revealed regulatory changes in genes and pathways associated with craniofacial patterning. Mutations in SMCHD1 thus contribute to distinct phenotypic spectra, from craniofacial malformation and reproductive disorders to muscular dystrophy, which we speculate to be consistent with oligogenic mechanisms resulting in pleiotropic outcomes.
Keywords: Adolescent; Child; Child, Preschool; Choanal Atresia; Chromosomal Proteins, Non-Histone; Female; Genetic Predisposition to Disease; Humans; Infant; Male; Microphthalmos; Muscular Dystrophies; Mutation; Nose; Phenotype

Unraveling genetic predisposition to familial or early onset gastric cancer using germline whole-exome sequencing. - Vogelaar, Ingrid P; van der Post, Rachel S; van Krieken, J Han Jm; Spruijt, Liesbeth; van Zelst-Stams, Wendy Ag; Kets, C Marleen; Lubinski, Jan; Jakubowska, Anna; Teodorczyk, Urszula; Aalfs, Cora M; van Hest, Liselotte P; Pinheiro, Hugo; et al. (Eur J Hum Genet, 2017)
Recognition of individuals with a genetic predisposition to gastric cancer (GC) enables preventive measures. However, the underlying cause of genetic susceptibility to gastric cancer remains largely unexplained. We performed germline whole-exome sequencing on leukocyte DNA of 54 patients from 53 families with genetically unexplained diffuse-type and intestinal-type GC to identify novel GC-predisposing candidate genes. As young age at diagnosis and familial clustering are hallmarks of genetic tumor susceptibility, we selected patients that were diagnosed below the age of 35, patients from families with two cases of GC at or below age 60 and patients from families with three GC cases at or below age 70. All included individuals were tested negative for germline CDH1 mutations before or during the study. Variants that were possibly deleterious according to in silico predictions were filtered using several independent approaches that were based on gene function and gene mutation burden in controls. Despite a rigorous search, no obvious candidate GC predisposition genes were identified. This negative result stresses the importance of future research studies in large, homogeneous cohorts.
Keywords: Adult; Aged; Antigens, CD; Cadherins; Early Detection of Cancer; Exome; Female; Genetic Predisposition to Disease; Genetic Testing; Germ-Line Mutation; Humans; Male; Middle Aged; Sequence Analysis, DNA; Stomach Neoplasms

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Muzny, Donna; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male; Whole Exome Sequencing

Whole-exome sequencing in the molecular diagnosis of individuals with congenital anomalies of the kidney and urinary tract and identification of a new causative gene. - Bekheirnia, Mir Reza; Bekheirnia, Nasim; Bainbridge, Matthew N; Gu, Shen; Coban Akdemir, Zeynep Hande; Gambin, Tomek; Janzen, Nicolette K; Jhangiani, Shalini N; Muzny, Donna M; Michael, Mini; Brewer, Eileen D; Elenberg, Ewa; et al. (Genet Med, 2017)
PURPOSE: To investigate the utility of whole-exome sequencing (WES) to define a molecular diagnosis for patients clinically diagnosed with congenital anomalies of kidney and urinary tract (CAKUT). METHODS: WES was performed in 62 families with CAKUT. WES data were analyzed for single-nucleotide variants (SNVs) in 35 known CAKUT genes, putatively deleterious sequence changes in new candidate genes, and potentially disease-associated copy-number variants (CNVs). RESULTS: In approximately 5% of families, pathogenic SNVs were identified in PAX2, HNF1B, and EYA1. Observed phenotypes in these families expand the current understanding about the role of these genes in CAKUT. Four pathogenic CNVs were also identified using two CNV detection tools. In addition, we found one deleterious de novo SNV in FOXP1 among the 62 families with CAKUT. The clinical database of the Baylor Miraca Genetics laboratory was queried and seven additional unrelated individuals with novel de novo SNVs in FOXP1 were identified. Six of these eight individuals with FOXP1 SNVs have syndromic urinary tract defects, implicating this gene in urinary tract development. CONCLUSION: We conclude that WES can be used to identify molecular etiology (SNVs, CNVs) in a subset of individuals with CAKUT. WES can also help identify novel CAKUT genes.Genet Med 19 4, 412-420.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-beta; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Nuclear Proteins; PAX2 Transcription Factor; Pedigree; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases; Repressor Proteins; Urogenital Abnormalities; Vesico-Ureteral Reflux; Young Adult

ACOX2 deficiency: A disorder of bile acid synthesis with transaminase elevation, liver fibrosis, ataxia, and cognitive impairment. - Vilarinho, Sílvia; Sari, Sinan; Mazzacuva, Francesca; Bilguvar, Kaya; Esendagli-Yilmaz, Güldal; Jain, Dhanpat; Akyol, Gülen; Dalgiç, Buket; Günel, Murat; Clayton, Peter T; Lifton, Richard P (Proc Natl Acad Sci U S A, 2016)
Acyl CoA Oxidase 2 (ACOX2) encodes branched-chain acyl-CoA oxidase, a peroxisomal enzyme believed to be involved in the metabolism of branched-chain fatty acids and bile acid intermediates. Deficiency of this enzyme has not been described previously. We report an 8-y-old male with intermittently elevated transaminase levels, liver fibrosis, mild ataxia, and cognitive impairment. Exome sequencing revealed a previously unidentified homozygous premature termination mutation (p.Y69*) in ACOX2 Immunohistochemistry confirmed the absence of ACOX2 expression in the patient's liver, and biochemical analysis showed marked elevation of intermediate bile acids upstream of ACOX2. These findings define a potentially treatable inborn error of bile acid biosynthesis caused by ACOX2 deficiency.
Keywords: Ataxia; Bile Acids and Salts; Child; Cognitive Dysfunction; Homozygote; Humans; Infant; Infant, Newborn; Liver; Liver Cirrhosis; Loss of Function Mutation; Male; Mutation; Oxidation-Reduction; Oxidoreductases; Transaminases

Aggressive tumor growth and clinical evolution in a patient with X-linked acro-gigantism syndrome. - Naves, Luciana A; Daly, Adrian F; Dias, Luiz Augusto; Yuan, Bo; Zakir, Juliano Coelho Oliveira; Barra, Gustavo Barcellos; Palmeira, Leonor; Villa, Chiara; Trivellin, Giampaolo; Júnior, Armindo Jreige; Neto, Florêncio Figueiredo Cavalcante; Liu, Pengfei; et al. (Endocrine, 2016)
X-linked acro-gigantism (X-LAG) syndrome is a newly described disease caused by microduplications on chromosome Xq26.3 leading to copy number gain of GPR101. We describe the clinical progress of a sporadic male X-LAG syndrome patient with an Xq26.3 microduplication, highlighting the aggressive natural history of pituitary tumor growth in the absence of treatment. The patient first presented elsewhere aged 5 years 8 months with a history of excessive growth for >2 years. His height was 163 cm, his weight was 36 kg, and he had markedly elevated GH and IGF-1. MRI showed a non-invasive sellar mass measuring 32.5 × 23.9 × 29.1 mm. Treatment was declined and the family was lost to follow-up. At the age of 10 years and 7 months, he presented again with headaches, seizures, and visual disturbance. His height had increased to 197 cm. MRI showed an invasive mass measuring 56.2 × 58.1 × 45.0 mm, with compression of optic chiasma, bilateral cavernous sinus invasion, and hydrocephalus. His thyrotrope, corticotrope, and gonadotrope axes were deficient. Surgery, somatostatin analogs, and cabergoline did not control vertical growth and pegvisomant was added, although vertical growth continues (currently 207 cm at 11 years 7 months of age). X-LAG syndrome is a new genomic disorder in which early-onset pituitary tumorigenesis can lead to marked overgrowth and gigantism. This case illustrates the aggressive nature of tumor evolution and the challenging clinical management in X-LAG syndrome.
Keywords: Adenoma; Child; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Pituitary Neoplasms; Treatment Outcome

ALG1-CDG: Clinical and Molecular Characterization of 39 Unreported Patients. - Ng, Bobby G; Shiryaev, Sergey A; Rymen, Daisy; Eklund, Erik A; Raymond, Kimiyo; Kircher, Martin; Abdenur, Jose E; Alehan, Fusun; Midro, Alina T; Bamshad, Michael J; Barone, Rita; Berry, Gerard T; et al. (Hum Mutat, 2016)
Congenital disorders of glycosylation (CDG) arise from pathogenic mutations in over 100 genes leading to impaired protein or lipid glycosylation. ALG1 encodes a β1,4 mannosyltransferase that catalyzes the addition of the first of nine mannose moieties to form a dolichol-lipid linked oligosaccharide intermediate required for proper N-linked glycosylation. ALG1 mutations cause a rare autosomal recessive disorder termed ALG1-CDG. To date 13 mutations in 18 patients from 14 families have been described with varying degrees of clinical severity. We identified and characterized 39 previously unreported cases of ALG1-CDG from 32 families and add 26 new mutations. Pathogenicity of each mutation was confirmed based on its inability to rescue impaired growth or hypoglycosylation of a standard biomarker in an alg1-deficient yeast strain. Using this approach we could not establish a rank order comparison of biomarker glycosylation and patient phenotype, but we identified mutations with a lethal outcome in the first two years of life. The recently identified protein-linked xeno-tetrasaccharide biomarker, NeuAc-Gal-GlcNAc2 , was seen in all 27 patients tested. Our study triples the number of known patients and expands the molecular and clinical correlates of this disorder.
Keywords: Biomarkers; Congenital Disorders of Glycosylation; Female; Genes, Lethal; Glycosylation; Humans; Male; Mannosyltransferases; Mutation; Polysaccharides; Sequence Analysis, DNA; Survival Analysis

Asprosin, a Fasting-Induced Glucogenic Protein Hormone. - Romere, Chase; Duerrschmid, Clemens; Bournat, Juan; Constable, Petra; Jain, Mahim; Xia, Fan; Saha, Pradip K; Del Solar, Maria; Zhu, Bokai; York, Brian; Sarkar, Poonam; Rendon, David A; et al. (Cell, 2016)
Hepatic glucose release into the circulation is vital for brain function and survival during periods of fasting and is modulated by an array of hormones that precisely regulate plasma glucose levels. We have identified a fasting-induced protein hormone that modulates hepatic glucose release. It is the C-terminal cleavage product of profibrillin, and we name it Asprosin. Asprosin is secreted by white adipose, circulates at nanomolar levels, and is recruited to the liver, where it activates the G protein-cAMP-PKA pathway, resulting in rapid glucose release into the circulation. Humans and mice with insulin resistance show pathologically elevated plasma asprosin, and its loss of function via immunologic or genetic means has a profound glucose- and insulin-lowering effect secondary to reduced hepatic glucose release. Asprosin represents a glucogenic protein hormone, and therapeutically targeting it may be beneficial in type II diabetes and metabolic syndrome.
Keywords: Adipose Tissue, White; Amino Acid Sequence; Animals; Antibodies; Circadian Rhythm; Cyclic AMP; Cyclic AMP-Dependent Protein Kinases; Fasting; Female; Fetal Growth Retardation; Glucose; Humans; Insulin; Liver; Male; Mice; Mice, Inbred C57BL; Mice, Obese; Microfilament Proteins; Molecular Sequence Data; Peptide Fragments; Peptide Hormones; Progeria; Recombinant Proteins; Sequence Alignment

Association Between Absolute Neutrophil Count and Variation at TCIRG1: The NHLBI Exome Sequencing Project. - Rosenthal, Elisabeth A; Makaryan, Vahagn; Burt, Amber A; Crosslin, David R; Kim, Daniel Seung; Smith, Joshua D; Nickerson, Deborah A; Reiner, Alex P; Rich, Stephen S; Jackson, Rebecca D; Ganesh, Santhi K; Polfus, Linda M; et al. (Genet Epidemiol, 2016)
Neutrophils are a key component of innate immunity. Individuals with low neutrophil count are susceptible to frequent infections. Linkage and association between congenital neutropenia and a single rare missense variant in TCIRG1 have been reported in a single family. Here, we report on nine rare missense variants at evolutionarily conserved sites in TCIRG1 that are associated with lower absolute neutrophil count (ANC; p = 0.005) in 1,058 participants from three cohorts: Atherosclerosis Risk in Communities (ARIC), Coronary Artery Risk Development in Young Adults (CARDIA), and Jackson Heart Study (JHS) of the NHLBI Grand Opportunity Exome Sequencing Project (GO ESP). These results validate the effects of TCIRG1 coding variation on ANC and suggest that this gene may be associated with a spectrum of mild to severe effects on ANC.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Cohort Studies; Female; Gene Frequency; Genotype; High-Throughput Nucleotide Sequencing; Humans; Leukocyte Count; Male; Middle Aged; Mutation, Missense; National Heart, Lung, and Blood Institute (U.S.); Neutropenia; Neutrophils; Sequence Analysis, DNA; United States; Vacuolar Proton-Translocating ATPases

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Bi-allelic Mutations in PKD1L1 Are Associated with Laterality Defects in Humans. - Vetrini, Francesco; D'Alessandro, Lisa C A; Akdemir, Zeynep C; Braxton, Alicia; Azamian, Mahshid S; Eldomery, Mohammad K; Miller, Kathryn; Kois, Chelsea; Sack, Virginia; Shur, Natasha; Rijhsinghani, Asha; Chandarana, Jignesh; et al. (Am J Hum Genet, 2016)
Disruption of the establishment of left-right (L-R) asymmetry leads to situs anomalies ranging from situs inversus totalis (SIT) to situs ambiguus (heterotaxy). The genetic causes of laterality defects in humans are highly heterogeneous. Via whole-exome sequencing (WES), we identified homozygous mutations in PKD1L1 from three affected individuals in two unrelated families. PKD1L1 encodes a polycystin-1-like protein and its loss of function is known to cause laterality defects in mouse and medaka fish models. Family 1 had one fetus and one deceased child with heterotaxy and complex congenital heart malformations. WES identified a homozygous splicing mutation, c.6473+2_6473+3delTG, which disrupts the invariant splice donor site in intron 42, in both affected individuals. In the second family, a homozygous c.5072G>C (p.Cys1691Ser) missense mutation was detected in an individual with SIT and congenital heart disease. The p.Cys1691Ser substitution affects a highly conserved cysteine residue and is predicted by molecular modeling to disrupt a disulfide bridge essential for the proper folding of the G protein-coupled receptor proteolytic site (GPS) motif. Damaging effects associated with substitutions of this conserved cysteine residue in the GPS motif have also been reported in other genes, namely GPR56, BAI3, and PKD1 in human and lat-1 in C. elegans, further supporting the likely pathogenicity of p.Cys1691Ser in PKD1L1. The identification of bi-allelic PKD1L1 mutations recapitulates previous findings regarding phenotypic consequences of loss of function of the orthologous genes in mice and medaka fish and further expands our understanding of genetic contributions to laterality defects in humans.
Keywords: Alleles; Amino Acid Motifs; Amino Acid Sequence; Animals; Caenorhabditis elegans; Cysteine; Exome; Female; Fetal Diseases; Functional Laterality; Heart Defects, Congenital; Heterotaxy Syndrome; Homozygote; Humans; Infant, Newborn; Introns; Male; Membrane Proteins; Mice; Middle Aged; Models, Molecular; Mutation; Mutation, Missense; Oryzias; Pedigree; RNA Splicing; Situs Inversus

Biallelic Mutations in TMTC3, Encoding a Transmembrane and TPR-Containing Protein, Lead to Cobblestone Lissencephaly. - Jerber, Julie; Zaki, Maha S; Al-Aama, Jumana Y; Rosti, Rasim Ozgur; Ben-Omran, Tawfeg; Dikoglu, Esra; Silhavy, Jennifer L; Caglar, Caner; Musaev, Damir; Albrecht, Beate; Campbell, Kevin P; Willer, Tobias; et al. (Am J Hum Genet, 2016)
Cobblestone lissencephaly (COB) is a severe brain malformation in which overmigration of neurons and glial cells into the arachnoid space results in the formation of cortical dysplasia. COB occurs in a wide range of genetic disorders known as dystroglycanopathies, which are congenital muscular dystrophies associated with brain and eye anomalies and range from Walker-Warburg syndrome to Fukuyama congenital muscular dystrophy. Each of these conditions has been associated with alpha-dystroglycan defects or with mutations in genes encoding basement membrane components, which are known to interact with alpha-dystroglycan. Our screening of a cohort of 25 families with recessive forms of COB identified six families affected by biallelic mutations in TMTC3 (encoding transmembrane and tetratricopeptide repeat containing 3), a gene without obvious functional connections to alpha-dystroglycan. Most affected individuals showed brainstem and cerebellum hypoplasia, as well as ventriculomegaly. However, the minority of the affected individuals had eye defects or elevated muscle creatine phosphokinase, separating the TMTC3 COB phenotype from typical congenital muscular dystrophies. Our data suggest that loss of TMTC3 causes COB with minimal eye or muscle involvement.
Keywords: Alleles; Amino Acid Sequence; Basement Membrane; Brain; Carrier Proteins; Cerebellum; Cobblestone Lissencephaly; Developmental Disabilities; Dystroglycans; Eye Abnormalities; Female; Humans; Infant; Male; Membrane Proteins; Mutation; Nervous System Malformations; Neuroglia; Neurons; Pedigree; Phenotype

Biallelic Mutations in UNC80 Cause Persistent Hypotonia, Encephalopathy, Growth Retardation, and Severe Intellectual Disability. - Stray-Pedersen, Asbjørg; Cobben, Jan-Maarten; Prescott, Trine E; Lee, Sora; Cang, Chunlei; Aranda, Kimberly; Ahmed, Sohnee; Alders, Marielle; Gerstner, Thorsten; Aslaksen, Kathinka; Tétreault, Martine; Qin, Wen; et al. (Am J Hum Genet, 2016)
Ion channel proteins are required for both the establishment of resting membrane potentials and the generation of action potentials. Hundreds of mutations in genes encoding voltage-gated ion channels responsible for action potential generation have been found to cause severe neurological diseases. In contrast, the roles of voltage-independent "leak" channels, important for the establishment and maintenance of resting membrane potentials upon which action potentials are generated, are not well established in human disease. UNC80 is a large component of the NALCN sodium-leak channel complex that regulates the basal excitability of the nervous system. Loss-of-function mutations of NALCN cause infantile hypotonia with psychomotor retardation and characteristic facies (IHPRF). We report four individuals from three unrelated families who have homozygous missense or compound heterozygous truncating mutations in UNC80 and persistent hypotonia, encephalopathy, growth failure, and severe intellectual disability. Compared to control cells, HEK293T cells transfected with an expression plasmid containing the c.5098C>T (p.Pro1700Ser) UNC80 mutation found in one individual showed markedly decreased NALCN channel currents. Our findings demonstrate the fundamental significance of UNC80 and basal ionic conductance to human health.
Keywords: Adolescent; Alleles; Brain Diseases; Carrier Proteins; Child; Child, Preschool; Female; Growth Disorders; Humans; Intellectual Disability; Membrane Proteins; Muscle Hypotonia; Mutation; Severity of Illness Index

The ciliopathy-associated CPLANE proteins direct basal body recruitment of intraflagellar transport machinery. - Toriyama, Michinori; Lee, Chanjae; Taylor, S Paige; Duran, Ivan; Cohn, Daniel H; Bruel, Ange-Line; Tabler, Jacqueline M; Drew, Kevin; Kelly, Marcus R; Kim, Sukyoung; Park, Tae Joo; Braun, Daniela A; et al. (Nat Genet, 2016)
Cilia use microtubule-based intraflagellar transport (IFT) to organize intercellular signaling. Ciliopathies are a spectrum of human diseases resulting from defects in cilia structure or function. The mechanisms regulating the assembly of ciliary multiprotein complexes and the transport of these complexes to the base of cilia remain largely unknown. Combining proteomics, in vivo imaging and genetic analysis of proteins linked to planar cell polarity (Inturned, Fuzzy and Wdpcp), we identified and characterized a new genetic module, which we term CPLANE (ciliogenesis and planar polarity effector), and an extensive associated protein network. CPLANE proteins physically and functionally interact with the poorly understood ciliopathy-associated protein Jbts17 at basal bodies, where they act to recruit a specific subset of IFT-A proteins. In the absence of CPLANE, defective IFT-A particles enter the axoneme and IFT-B trafficking is severely perturbed. Accordingly, mutation of CPLANE genes elicits specific ciliopathy phenotypes in mouse models and is associated with ciliopathies in human patients.
Keywords: Animals; Ciliopathies; Flagella; Humans; Mice; Mutation; Phenotype; Protein Binding; Protein Transport; Proteins

Collapsing glomerulopathy in a young woman with APOL1 risk alleles following acute parvovirus B19 infection: a case report investigation. - Besse, Whitney; Mansour, Sherry; Jatwani, Karan; Nast, Cynthia C; Brewster, Ursula C (BMC Nephrol, 2016)
BACKGROUND: Collapsing Glomerulopathy (CG), also known as the collapsing variant of Focal Segmental Glomerulosclerosis (FSGS), is distinct in both its clinical severity and its pathophysiologic characteristics from other forms of FSGS. This lesion occurs disproportionally in patients carrying two APOL1 risk alleles, and is the classic histologic lesion resulting from Human Immunodeficiency Virus (HIV) infection of podocytes. Other viral infections, including parvovirus B19, and drugs such as interferon that perturb the immune system, have also been associated with CG. Despite significant advances, explaining such genetic and immune/infectious associations with causative mechanisms and supporting evidence has proven challenging. CASE PRESENTATION: We report the case of a healthy (HIV-negative) pregnant 36 year-old Caribbean-American woman who presented with nephrotic syndrome and fetal demise in the setting of acute parvovirus B19 infection. A series of three renal biopsies and rapid clinical course showed progression from significant podocyte injury with mild light microscopy findings to classic viral-associated CG to ESRD in less than 3 months. Genetic analysis revealed two APOL1 G1 risk alleles. CONCLUSIONS: This is the first published case report of CG in the setting of acute parvovirus infection in a patient with two APOL1 risk allelles, and parvoviral proteins identified in renal epithelium on kidney biopsy. These findings support the causative role of parvovirus B19 infection in the development of CG on the background of APOL1 genetic risk.
Keywords: Acute Disease; Adult; Alleles; Apolipoprotein L1; Female; Glomerulosclerosis, Focal Segmental; Humans; Kidney Failure, Chronic; Parvoviridae Infections; Parvovirus B19, Human; Pregnancy; Pregnancy Complications, Infectious

Comparison of Short-Wavelength Reduced-Illuminance and Conventional Autofluorescence Imaging in Stargardt Macular Dystrophy. - Strauss, Rupert W; Muñoz, Beatriz; Jha, Anamika; Ho, Alexander; Cideciyan, Artur V; Kasilian, Melissa L; Wolfson, Yulia; Sadda, SriniVas; West, Sheila; Scholl, Hendrik P N; Michaelides, Michel (Am J Ophthalmol, 2016)
PURPOSE: To compare grading results between short-wavelength reduced-illuminance and conventional autofluorescence imaging in Stargardt macular dystrophy. DESIGN: Reliability study. METHODS: setting: Moorfields Eye Hospital, London (United Kingdom). PATIENTS: Eighteen patients (18 eyes) with Stargardt macular dystrophy. OBSERVATION PROCEDURES: A series of 3 fundus autofluorescence images using 3 different acquisition parameters on a custom-patched device were obtained: (1) 25% laser power and total sensitivity 87; (2) 25% laser power and freely adjusted sensitivity; and (3) 100% laser power and freely adjusted total sensitivity (conventional). The total area of 2 hypoautofluorescent lesion types (definitely decreased autofluorescence and poorly demarcated questionably decreased autofluorescence) was measured. MAIN OUTCOME MEASURES: Agreement in grading between the 3 imaging methods was assessed by kappa coefficients (κ) and intraclass correlation coefficients. RESULTS: The mean ± standard deviation area for images acquired with 25% laser power and freely adjusted total sensitivity was 2.04 ± 1.87 mm(2) for definitely decreased autofluorescence (n = 15) and 1.86 ± 2.14 mm(2) for poorly demarcated questionably decreased autofluorescence (n = 12). The intraclass correlation coefficient (95% confidence interval) was 0.964 (0.929, 0.999) for definitely decreased autofluorescence and 0.268 (0.000, 0.730) for poorly demarcated questionably decreased autofluorescence. CONCLUSIONS: Short-wavelength reduced-illuminance and conventional fundus autofluorescence imaging showed good concordance in assessing areas of definitely decreased autofluorescence. However, there was significantly higher variability between imaging modalities for assessing areas of poorly demarcated questionably decreased autofluorescence.
Keywords: Adult; Female; Fluorescein Angiography; Fundus Oculi; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Ophthalmoscopy; Optical Imaging; Reproducibility of Results; Stargardt Disease

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease. - Ma, Lijiang; Bayram, Yavuz; McLaughlin, Heather M; Cho, Megan T; Krokosky, Alyson; Turner, Clesson E; Lindstrom, Kristin; Bupp, Caleb P; Mayberry, Katey; Mu, Weiyi; Bodurtha, Joann; Weinstein, Veronique; et al. (Hum Genet, 2016)
Intellectual disabilities are genetically heterogeneous and can be associated with congenital anomalies. Using whole-exome sequencing (WES), we identified five different de novo missense variants in the protein phosphatase-1 catalytic subunit beta (PPP1CB) gene in eight unrelated individuals who share an overlapping phenotype of dysmorphic features, macrocephaly, developmental delay or intellectual disability (ID), congenital heart disease, short stature, and skeletal and connective tissue abnormalities. Protein phosphatase-1 (PP1) is a serine/threonine-specific protein phosphatase involved in the dephosphorylation of a variety of proteins. The PPP1CB gene encodes a PP1 subunit that regulates the level of protein phosphorylation. All five altered amino acids we observed are highly conserved among the PP1 subunit family, and all are predicted to disrupt PP1 subunit binding and impair dephosphorylation. Our data suggest that our heterozygous de novo PPP1CB pathogenic variants are associated with syndromic intellectual disability.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Intellectual Disability; Male; Mutation, Missense; Phosphorylation; Protein Phosphatase 1

De Novo Mutations in SON Disrupt RNA Splicing of Genes Essential for Brain Development and Metabolism, Causing an Intellectual-Disability Syndrome. - Kim, Jung-Hyun; Shinde, Deepali N; Reijnders, Margot R F; Hauser, Natalie S; Belmonte, Rebecca L; Wilson, Gregory R; Bosch, Daniëlle G M; Bubulya, Paula A; Shashi, Vandana; Petrovski, Slavé; Stone, Joshua K; Park, Eun Young; et al. (Am J Hum Genet, 2016)
The overall understanding of the molecular etiologies of intellectual disability (ID) and developmental delay (DD) is increasing as next-generation sequencing technologies identify genetic variants in individuals with such disorders. However, detailed analyses conclusively confirming these variants, as well as the underlying molecular mechanisms explaining the diseases, are often lacking. Here, we report on an ID syndrome caused by de novo heterozygous loss-of-function (LoF) mutations in SON. The syndrome is characterized by ID and/or DD, malformations of the cerebral cortex, epilepsy, vision problems, musculoskeletal abnormalities, and congenital malformations. Knockdown of son in zebrafish resulted in severe malformation of the spine, brain, and eyes. Importantly, analyses of RNA from affected individuals revealed that genes critical for neuronal migration and cortex organization (TUBG1, FLNA, PNKP, WDR62, PSMD3, and HDAC6) and metabolism (PCK2, PFKL, IDH2, ACY1, and ADA) are significantly downregulated because of the accumulation of mis-spliced transcripts resulting from erroneous SON-mediated RNA splicing. Our data highlight SON as a master regulator governing neurodevelopment and demonstrate the importance of SON-mediated RNA splicing in human development.
Keywords: Animals; Brain; Developmental Disabilities; DNA-Binding Proteins; Eye Abnormalities; Female; Genes, Essential; Haploinsufficiency; Head; Heterozygote; Humans; Intellectual Disability; Male; Metabolic Diseases; Minor Histocompatibility Antigens; Mutation; Pedigree; RNA Splicing; RNA, Messenger; Spine; Syndrome; Zebrafish

Digenic mutations of human paralogs in Dent's disease type 2 associated with Chiari I malformation. - Duran, Daniel; Jin, Sheng Chih; DeSpenza, Tyrone; Nelson-Williams, Carol; Cogal, Andrea G; Abrash, Elizabeth W; Harris, Peter C; Lieske, John C; Shimshak, Serena Je; Mane, Shrikant; Bilguvar, Kaya; DiLuna, Michael L; et al. (Hum Genome Var, 2016)
and its paralog encode phosphatidylinositol 5-phosphatases that localize to the primary cilium and have roles in ciliogenesis. Mutations in cause the X-linked Dent disease type 2 (DD2; OMIM# 300555), characterized by low-molecular weight proteinuria, hypercalciuria, and the variable presence of cataracts, glaucoma and intellectual disability without structural brain anomalies. Disease-causing mutations in have not been described in humans. Here, we report the case of an 11-year-old boy with short stature and an above-average IQ; severe proteinuria, hypercalciuria and osteopenia resulting in a vertebral compression fracture; and Chiari I malformation with cervico-thoracic syringohydromyelia requiring suboccipital decompression. Sequencing revealed a novel, DD2-causing 462 bp deletion disrupting exon 3 of and a maternally inherited, extremely rare (ExAC allele frequency 8.4×10) damaging missense mutation in (p.A51V). This mutation substitutes an evolutionarily conserved amino acid in the protein's critical PH domain. analyses of mutation impact predicted by SIFT, PolyPhen2, MetaSVM and CADD algorithms were all highly deleterious. Together, our findings report a novel association of DD2 with Chiari I malformation and syringohydromyelia, and document the effects of digenic mutation of human paralogs. These findings lend genetic support to the hypothesis that impaired ciliogenesis may contribute to the development of Chiari I malformation, and implicates OCRL-dependent PIP metabolism in this mechanism.

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

Exome sequencing in mostly consanguineous Arab families with neurologic disease provides a high potential molecular diagnosis rate. - Charng, Wu-Lin; Karaca, Ender; Coban Akdemir, Zeynep; Gambin, Tomasz; Atik, Mehmed M; Gu, Shen; Posey, Jennifer E; Jhangiani, Shalini N; Muzny, Donna M; Doddapaneni, Harsha; Hu, Jianhong; Boerwinkle, Eric; et al. (BMC Med Genomics, 2016)
BACKGROUND: Neurodevelopment is orchestrated by a wide range of genes, and the genetic causes of neurodevelopmental disorders are thus heterogeneous. We applied whole exome sequencing (WES) for molecular diagnosis and in silico analysis to identify novel disease gene candidates in a cohort from Saudi Arabia with primarily Mendelian neurologic diseases. METHODS: We performed WES in 31 mostly consanguineous Arab families and analyzed both single nucleotide and copy number variants (CNVs) from WES data. Interaction/expression network and pathway analyses, as well as paralog studies were utilized to investigate potential pathogenicity and disease association of novel candidate genes. Additional cases for candidate genes were identified through the clinical WES database at Baylor Miraca Genetics Laboratories and GeneMatcher. RESULTS: We found known pathogenic or novel variants in known disease genes with phenotypic expansion in 6 families, disease-associated CNVs in 2 families, and 12 novel disease gene candidates in 11 families, including KIF5B, GRM7, FOXP4, MLLT1, and KDM2B. Overall, a potential molecular diagnosis was provided by variants in known disease genes in 17 families (54.8 %) and by novel candidate disease genes in an additional 11 families, making the potential molecular diagnostic rate ~90 %. CONCLUSIONS: Molecular diagnostic rate from WES is improved by exome-predicted CNVs. Novel candidate disease gene discovery is facilitated by paralog studies and through the use of informatics tools and available databases to identify additional evidence for pathogenicity. TRIAL REGISTRATION: Not applicable.
Keywords: Arabs; Cohort Studies; Consanguinity; Data Mining; Databases, Genetic; DNA Copy Number Variations; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Diagnostic Techniques; Nervous System Diseases; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Expansion of the spectrum of ITGB6-related disorders to adolescent alopecia, dentogingival abnormalities and intellectual disability. - Ansar, Muhammad; Jan, Abid; Santos-Cortez, Regie Lyn P; Wang, Xin; Suliman, Muhammad; Acharya, Anushree; Habib, Rabia; Abbe, Izoduwa; Ali, Ghazanfar; Lee, Kwanghyuk; Smith, Joshua D; Nickerson, Deborah A; et al. (Eur J Hum Genet, 2016)
Alopecia with mental retardation (APMR) is a very rare disorder. In this study, we report on a consanguineous Pakistani family (AP91) with mild-to-moderate intellectual disability, adolescent alopecia and dentogingival abnormalities. Using homozygosity mapping, linkage analysis and exome sequencing, we identified a novel rare missense variant c.898G>A (p.(Glu300Lys)) in ITGB6, which co-segregates with the phenotype within the family and is predicted to be deleterious. Structural modeling shows that Glu300 lies in the β-propeller domain, and is surrounded by several residues that are important for heterodimerization with α integrin. Previous studies showed that ITGB6 variants can cause amelogenesis imperfecta in humans, but patients from family AP91 who are homozygous for the c.898G>A variant present with neurological and dermatological features, indicating a role for ITGB6 beyond enamel formation. Our study demonstrates that a rare deleterious variant within ITGB6 causes not only dentogingival anomalies but also intellectual disability and alopecia.
Keywords: Adolescent; Adult; Alopecia; Child; Female; Humans; Integrin beta Chains; Intellectual Disability; Male; Mutation, Missense; Pedigree; Phenotype; Protein Domains; Syndrome; Tooth Abnormalities

FOXE3 mutations predispose to thoracic aortic aneurysms and dissections. - Kuang, Shao-Qing; Medina-Martinez, Olga; Guo, Dong-Chuan; Gong, Limin; Regalado, Ellen S; Reynolds, Corey L; Boileau, Catherine; Jondeau, Guillaume; Prakash, Siddharth K; Kwartler, Callie S; Zhu, Lawrence Yang; Peters, Andrew M; et al. (J Clin Invest, 2016)
The ascending thoracic aorta is designed to withstand biomechanical forces from pulsatile blood. Thoracic aortic aneurysms and acute aortic dissections (TAADs) occur as a result of genetically triggered defects in aortic structure and a dysfunctional response to these forces. Here, we describe mutations in the forkhead transcription factor FOXE3 that predispose mutation-bearing individuals to TAAD. We performed exome sequencing of a large family with multiple members with TAADs and identified a rare variant in FOXE3 with an altered amino acid in the DNA-binding domain (p.Asp153His) that segregated with disease in this family. Additional pathogenic FOXE3 variants were identified in unrelated TAAD families. In mice, Foxe3 deficiency reduced smooth muscle cell (SMC) density and impaired SMC differentiation in the ascending aorta. Foxe3 expression was induced in aortic SMCs after transverse aortic constriction, and Foxe3 deficiency increased SMC apoptosis and ascending aortic rupture with increased aortic pressure. These phenotypes were rescued by inhibiting p53 activity, either by administration of a p53 inhibitor (pifithrin-α), or by crossing Foxe3-/- mice with p53-/- mice. Our data demonstrate that FOXE3 mutations lead to a reduced number of aortic SMCs during development and increased SMC apoptosis in the ascending aorta in response to increased biomechanical forces, thus defining an additional molecular pathway that leads to familial thoracic aortic disease.
Keywords: Adult; Aneurysm, Dissecting; Animals; Aorta; Aortic Aneurysm, Thoracic; Apoptosis; Cells, Cultured; Cyclin-Dependent Kinase Inhibitor p21; Female; Forkhead Transcription Factors; Gene Expression; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Mice, Inbred C57BL; Mice, Knockout; Middle Aged; Muscle, Smooth, Vascular; Mutation, Missense; Myocytes, Smooth Muscle; Pedigree; Tumor Suppressor Protein p53; Vascular Remodeling; Zebrafish

Gene discovery for Mendelian conditions via social networking: de novo variants in KDM1A cause developmental delay and distinctive facial features. - Chong, Jessica X; Yu, Joon-Ho; Lorentzen, Peter; Park, Karen M; Jamal, Seema M; Tabor, Holly K; Rauch, Anita; Saenz, Margarita Sifuentes; Boltshauser, Eugen; Patterson, Karynne E; Nickerson, Deborah A; Bamshad, Michael J (Genet Med, 2016)
PURPOSE: The pace of Mendelian gene discovery is slowed by the "n-of-1 problem"-the difficulty of establishing the causality of a putatively pathogenic variant in a single person or family. Identification of an unrelated person with an overlapping phenotype and suspected pathogenic variant in the same gene can overcome this barrier, but it is often impeded by lack of a convenient or widely available way to share data on candidate variants/genes among families, clinicians, and researchers. METHODS: Social networking among families, clinicians, and researchers was used to identify three children with variants of unknown significance in KDM1A and similar phenotypes. RESULTS: De novo variants in KDM1A underlie a new syndrome characterized by developmental delay and distinctive facial features. CONCLUSION: Social networking is a potentially powerful strategy to discover genes for rare Mendelian conditions, particularly those with nonspecific phenotypic features. To facilitate the efforts of families to share phenotypic and genomic information with each other, clinicians, and researchers, we developed the Repository for Mendelian Genomics Family Portal (RMD-FP; http://uwcmg.org/#/family). Design and development of MyGene2 (http://www.mygene2.org), a Web-based tool that enables families, clinicians, and researchers to search for gene matches based on analysis of phenotype and exome data deposited into the RMD-FP, is under way.Genet Med 18 8, 788-795.
Keywords: Child; Child, Preschool; Databases, Factual; Developmental Disabilities; Female; Genetic Association Studies; Histone Demethylases; Humans; Information Dissemination; Male; Mutation, Missense; Phenotype; Social Networking; Web Browser

A genome-wide association study of congenital cardiovascular left-sided lesions shows association with a locus on chromosome 20. - Hanchard, Neil A; Swaminathan, Shanker; Bucasas, Kristine; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid S; Wang, Xueqing; Lewin, Mark; Towbin, Jeffrey A; D'Alessandro, Lisa C A; Morris, Shaine A; Dreyer, William; et al. (Hum Mol Genet, 2016)
Congenital heart defects involving left-sided lesions (LSLs) are relatively common birth defects with substantial morbidity and mortality. Previous studies have suggested a high heritability with a complex genetic architecture, such that only a few LSL loci have been identified. We performed a genome-wide case-control association study to address the role of common variants using a discovery cohort of 778 cases and 2756 controls. We identified a genome-wide significant association mapping to a 200 kb region on chromosome 20q11 [P= 1.72 × 10 for rs3746446; imputed Single Nucleotide Polymorphism (SNP) rs6088703 P= 3.01 × 10, odds ratio (OR)= 1.6 for both]. This result was supported by transmission disequilibrium analyses using a subset of 541 case families (lowest P in region= 4.51 × 10, OR= 1.5). Replication in a cohort of 367 LSL cases and 5159 controls showed nominal association (P= 0.03 for rs3746446) resulting in P= 9.49 × 10 for rs3746446 upon meta-analysis of the combined cohorts. In addition, a group of seven SNPs on chromosome 1q21.3 met threshold for suggestive association (lowest P= 9.35 × 10 for rs12045807). Both regions include genes involved in cardiac development-MYH7B/miR499A on chromosome 20 and CTSK, CTSS and ARNT on chromosome 1. Genome-wide heritability analysis using case-control genotyped SNPs suggested that the mean heritability of LSLs attributable to common variants is moderately high ([Formula: see text] range= 0.26-0.34) and consistent with previous assertions. These results provide evidence for the role of common variation in LSLs, proffer new genes as potential biological candidates, and give further insight to the complex genetic architecture of congenital heart disease.
Keywords: Chromosome Mapping; Chromosomes, Human, Pair 20; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Defects, Congenital; Heart Ventricles; Humans; Male; Polymorphism, Single Nucleotide

Germline or somatic GPR101 duplication leads to X-linked acrogigantism: a clinico-pathological and genetic study. - Iacovazzo, Donato; Caswell, Richard; Bunce, Benjamin; Jose, Sian; Yuan, Bo; Hernández-Ramírez, Laura C; Kapur, Sonal; Caimari, Francisca; Evanson, Jane; Ferraù, Francesco; Dang, Mary N; Gabrovska, Plamena; et al. (Acta Neuropathol Commun, 2016)
Non-syndromic pituitary gigantism can result from AIP mutations or the recently identified Xq26.3 microduplication causing X-linked acrogigantism (XLAG). Within Xq26.3, GPR101 is believed to be the causative gene, and the c.924G > C (p.E308D) variant in this orphan G protein-coupled receptor has been suggested to play a role in the pathogenesis of acromegaly.We studied 153 patients (58 females and 95 males) with pituitary gigantism. AIP mutation-negative cases were screened for GPR101 duplication through copy number variation droplet digital PCR and high-density aCGH. The genetic, clinical and histopathological features of XLAG patients were studied in detail. 395 peripheral blood and 193 pituitary tumor DNA samples from acromegaly patients were tested for GPR101 variants.We identified 12 patients (10 females and 2 males; 7.8 %) with XLAG. In one subject, the duplicated region only contained GPR101, but not the other three genes in found to be duplicated in the previously reported patients, defining a new smallest region of overlap of duplications. While females presented with germline mutations, the two male patients harbored the mutation in a mosaic state. Nine patients had pituitary adenomas, while three had hyperplasia. The comparison of the features of XLAG, AIP-positive and GPR101&AIP-negative patients revealed significant differences in sex distribution, age at onset, height, prolactin co-secretion and histological features. The pathological features of XLAG-related adenomas were remarkably similar. These tumors had a sinusoidal and lobular architecture. Sparsely and densely granulated somatotrophs were admixed with lactotrophs; follicle-like structures and calcifications were commonly observed. Patients with sporadic of familial acromegaly did not have an increased prevalence of the c.924G > C (p.E308D) GPR101 variant compared to public databases.In conclusion, XLAG can result from germline or somatic duplication of GPR101. Duplication of GPR101 alone is sufficient for the development of XLAG, implicating it as the causative gene within the Xq26.3 region. The pathological features of XLAG-associated pituitary adenomas are typical and, together with the clinical phenotype, should prompt genetic testing.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Female; Gene Duplication; Germ-Line Mutation; Gigantism; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Pituitary Neoplasms; Receptors, G-Protein-Coupled; Treatment Outcome; Young Adult

Gonadal mosaicism in ARID1B gene causes intellectual disability and dysmorphic features in three siblings. - Ben-Salem, Salma; Sobreira, Nara; Akawi, Nadia A; Al-Shamsi, Aisha M; John, Anne; Pramathan, Thachillath; Valle, David; Ali, Bassam R; Al-Gazali, Lihadh (Am J Med Genet A, 2016)
The gene encoding the AT-rich interaction domain-containing protein 1B (ARID1B) has recently been shown to be one of the most frequently mutated genes in patients with intellectual disability (ID). The phenotypic spectrums associated with variants in this gene vary widely ranging for mild to severe non-specific ID to Coffin-Siris syndrome. In this study, we evaluated three children from a consanguineous Emirati family affected with ID and dysmorphic features. Genomic DNA from all affected siblings was analyzed using CGH array and whole-exome sequencing (WES). Based on a recessive mode of inheritance, homozygous or compound heterozygous variants shared among all three affected children could not be identified. However, further analysis revealed a heterozygous variant (c.4318C>T; p.Q1440*) in the three affected children in an autosomal dominant ID causing gene, ARID1B. This variant was absent in peripheral blood samples obtained from both parents and unaffected siblings. Therefore, we propose that the most likely explanation for this situation is that one of the parents is a gonadal mosaic for the variant. To the best of our knowledge, this is the first report of a gonadal mosaicism inheritance of an ARID1B variant leading to familial ID recurrence.
Keywords: Abnormalities, Multiple; Adolescent; Child; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Mosaicism; Mutation; Neck; Pedigree; Siblings; Transcription Factors

Hutterite-type cataract maps to chromosome 6p21.32-p21.31, cosegregates with a homozygous mutation in LEMD2, and is associated with sudden cardiac death. - Boone, Philip M; Yuan, Bo; Gu, Shen; Ma, Zhiwei; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Jain, Mahim; Murdock, Todd J; White, Janson J; Jhangiani, Shalini N; Walker, Kimberly; Wang, Qiaoyan; et al. (Mol Genet Genomic Med, 2016)
BACKGROUND: Juvenile-onset cataracts are known among the Hutterites of North America. Despite being identified over 30 years ago, this autosomal recessive condition has not been mapped, and the disease gene is unknown. METHODS: We performed whole exome sequencing of three Hutterite-type cataract trios and follow-up genotyping and mapping in four extended kindreds. RESULTS: Trio exomes enabled genome-wide autozygosity mapping, which localized the disease gene to a 9.5-Mb region on chromosome 6p. This region contained two candidate variants, LEMD2 c.T38G and MUC21 c.665delC. Extended pedigrees recruited for variant genotyping revealed multiple additional relatives with juvenile-onset cataract, as well as six deceased relatives with both cataracts and sudden cardiac death. The candidate variants were genotyped in 84 family members, including 17 with cataracts; only the variant in LEMD2 cosegregated with cataracts (LOD = 9.62). SNP-based fine mapping within the 9.5 Mb linked region supported this finding by refining the cataract locus to a 0.5- to 2.9-Mb subregion (6p21.32-p21.31) containing LEMD2 but not MUC21. LEMD2 is expressed in mouse and human lenses and encodes a LEM domain-containing protein; the c.T38G missense mutation is predicted to mutate a highly conserved residue within this domain (p.Leu13Arg). CONCLUSION: We performed a genetic and genomic study of Hutterite-type cataract and found evidence for an association of this phenotype with sudden cardiac death. Using combined genetic and genomic approaches, we mapped cataracts to a small portion of chromosome 6 and propose that they result from a homozygous missense mutation in LEMD2.

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

Identification of Intellectual Disability Genes in Female Patients with a Skewed X-Inactivation Pattern. - Fieremans, Nathalie; Van Esch, Hilde; Holvoet, Maureen; Van Goethem, Gert; Devriendt, Koenraad; Rosello, Monica; Mayo, Sonia; Martinez, Francisco; Jhangiani, Shalini; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; et al. (Hum Mutat, 2016)
Intellectual disability (ID) is a heterogeneous disorder with an unknown molecular etiology in many cases. Previously, X-linked ID (XLID) studies focused on males because of the hemizygous state of their X chromosome. Carrier females are generally unaffected because of the presence of a second normal allele, or inactivation of the mutant X chromosome in most of their cells (skewing). However, in female ID patients, we hypothesized that the presence of skewing of X-inactivation would be an indicator for an X chromosomal ID cause. We analyzed the X-inactivation patterns of 288 females with ID, and found that 22 (7.6%) had extreme skewing (>90%), which is significantly higher than observed in the general population (3.6%; P = 0.029). Whole-exome sequencing of 19 females with extreme skewing revealed causal variants in six females in the XLID genes DDX3X, NHS, WDR45, MECP2, and SMC1A. Interestingly, variants in genes escaping X-inactivation presumably cause both XLID and skewing of X-inactivation in three of these patients. Moreover, variants likely accounting for skewing only were detected in MED12, HDAC8, and TAF9B. All tested candidate causative variants were de novo events. Hence, extreme skewing is a good indicator for the presence of X-linked variants in female patients.
Keywords: Carrier Proteins; Cell Cycle Proteins; Chromosomal Proteins, Non-Histone; DEAD-box RNA Helicases; Exome; Female; Genetic Variation; Humans; Intellectual Disability; Methyl-CpG-Binding Protein 2; Nuclear Proteins; Sequence Analysis, DNA; X Chromosome Inactivation

Impaired Amino Acid Transport at the Blood Brain Barrier Is a Cause of Autism Spectrum Disorder. - Tărlungeanu, Dora C; Deliu, Elena; Dotter, Christoph P; Kara, Majdi; Janiesch, Philipp Christoph; Scalise, Mariafrancesca; Galluccio, Michele; Tesulov, Mateja; Morelli, Emanuela; Sonmez, Fatma Mujgan; Bilguvar, Kaya; Ohgaki, Ryuichi; et al. (Cell, 2016)
Autism spectrum disorders (ASD) are a group of genetic disorders often overlapping with other neurological conditions. We previously described abnormalities in the branched-chain amino acid (BCAA) catabolic pathway as a cause of ASD. Here, we show that the solute carrier transporter 7a5 (SLC7A5), a large neutral amino acid transporter localized at the blood brain barrier (BBB), has an essential role in maintaining normal levels of brain BCAAs. In mice, deletion of Slc7a5 from the endothelial cells of the BBB leads to atypical brain amino acid profile, abnormal mRNA translation, and severe neurological abnormalities. Furthermore, we identified several patients with autistic traits and motor delay carrying deleterious homozygous mutations in the SLC7A5 gene. Finally, we demonstrate that BCAA intracerebroventricular administration ameliorates abnormal behaviors in adult mutant mice. Our data elucidate a neurological syndrome defined by SLC7A5 mutations and support an essential role for the BCAA in human brain function.
Keywords: Amino Acids; Animals; Autism Spectrum Disorder; Blood-Brain Barrier; Brain; Female; Humans; Infant; Infant, Newborn; Large Neutral Amino Acid-Transporter 1; Male; Mice; Mice, Knockout; Mutation; Pedigree; Protein Biosynthesis; Receptor, TIE-2

An inactivating mutation in intestinal cell kinase, ICK, impairs hedgehog signalling and causes short rib-polydactyly syndrome. - Paige Taylor, S; Kunova Bosakova, Michaela; Varecha, Miroslav; Balek, Lukas; Barta, Tomas; Trantirek, Lukas; Jelinkova, Iva; Duran, Ivan; Vesela, Iva; Forlenza, Kimberly N; Martin, Jorge H; Hampl, Ales; et al. (Hum Mol Genet, 2016)
The short rib polydactyly syndromes (SRPS) are a group of recessively inherited, perinatal-lethal skeletal disorders primarily characterized by short ribs, shortened long bones, varying types of polydactyly and concomitant visceral abnormalities. Mutations in several genes affecting cilia function cause SRPS, revealing a role for cilia function in skeletal development. To identify additional SRPS genes and discover novel ciliary molecules required for normal skeletogenesis, we performed exome sequencing in a cohort of patients and identified homozygosity for a missense mutation, p.E80K, in Intestinal Cell Kinase, ICK, in one SRPS family. The p.E80K mutation abolished serine/threonine kinase activity, resulting in altered ICK subcellular and ciliary localization, increased cilia length, aberrant cartilage growth plate structure, defective Hedgehog and altered ERK signalling. These data identify ICK as an SRPS-associated gene and reveal that abnormalities in signalling pathways contribute to defective skeletogenesis.
Keywords: Abnormalities, Multiple; Cilia; Exome; Female; Hedgehog Proteins; Humans; Infant; MAP Kinase Signaling System; Pedigree; Pregnancy; Protein-Serine-Threonine Kinases; Sequence Analysis, DNA; Short Rib-Polydactyly Syndrome; Signal Transduction; Skeleton

Loss-of-Function Mutations in FRRS1L Lead to an Epileptic-Dyskinetic Encephalopathy. - Madeo, Marianna; Stewart, Michelle; Sun, Yuyang; Sahir, Nadia; Wiethoff, Sarah; Chandrasekar, Indra; Yarrow, Anna; Rosenfeld, Jill A; Yang, Yaping; Cordeiro, Dawn; McCormick, Elizabeth M; Muraresku, Colleen C; et al. (Am J Hum Genet, 2016)
Glutamatergic neurotransmission governs excitatory signaling in the mammalian brain, and abnormalities of glutamate signaling have been shown to contribute to both epilepsy and hyperkinetic movement disorders. The etiology of many severe childhood movement disorders and epilepsies remains uncharacterized. We describe a neurological disorder with epilepsy and prominent choreoathetosis caused by biallelic pathogenic variants in FRRS1L, which encodes an AMPA receptor outer-core protein. Loss of FRRS1L function attenuates AMPA-mediated currents, implicating chronic abnormalities of glutamatergic neurotransmission in this monogenic neurological disease of childhood.
Keywords: alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; Brain Diseases; Electrophysiology; Epilepsy; Female; Humans; Hyperkinesis; Infant; Male; Membrane Proteins; Mutation; Nerve Tissue Proteins; Pedigree; Synaptic Transmission

LOX Mutations Predispose to Thoracic Aortic Aneurysms and Dissections. - Guo, Dong-Chuan; Regalado, Ellen S; Gong, Limin; Duan, Xueyan; Santos-Cortez, Regie Lyn P; Arnaud, Pauline; Ren, Zhao; Cai, Bo; Hostetler, Ellen M; Moran, Rocio; Liang, David; Estrera, Anthony; et al. (Circ Res, 2016)
RATIONALE: Mutations in several genes have been identified that are responsible for 25% of families with familial thoracic aortic aneurysms and dissections. However, the causative gene remains unknown in 75% of families. OBJECTIVES: To identify the causative mutation in families with autosomal dominant inheritance of thoracic aortic aneurysms and dissections. METHODS AND RESULTS: Exome sequencing was used to identify the mutation responsible for a large family with thoracic aortic aneurysms and dissections. A heterozygous rare variant, c.839G>T (p.Ser280Arg), was identified in LOX, encoding a lysyl oxidase, that segregated with disease in the family. Sanger and exome sequencing was used to investigate mutations in LOX in an additional 410 probands from unrelated families. Additional LOX rare variants that segregated with disease in families were identified, including c.125G>A (p.Trp42*), c.604G>T (p.Gly202*), c.743C>T (p.Thr248Ile), c.800A>C (p.Gln267Pro), and c.1044T>A (p.Ser348Arg). The altered amino acids cause haploinsufficiency for LOX or are located at a highly conserved LOX catalytic domain, which is relatively invariant in the population. Expression of the LOX variants p.Ser280Arg and p.Ser348Arg resulted in significantly lower lysyl oxidase activity when compared with the wild-type protein. Individuals with LOX variants had fusiform enlargement of the root and ascending thoracic aorta, leading to ascending aortic dissections. CONCLUSIONS: These data, along with previous studies showing that the deficiency of LOX in mice or inhibition of lysyl oxidases in turkeys and rats causes aortic dissections, support the conclusion that rare genetic variants in LOX predispose to thoracic aortic disease.
Keywords: Adult; Aged; Amino Acid Sequence; Aneurysm, Dissecting; Aortic Aneurysm, Thoracic; Female; Genetic Variation; Humans; Male; Middle Aged; Molecular Sequence Data; Mutation; Pedigree; Protein-Lysine 6-Oxidase

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Molecular etiology of arthrogryposis in multiple families of mostly Turkish origin. - Bayram, Yavuz; Karaca, Ender; Coban Akdemir, Zeynep; Yilmaz, Elif Ozdamar; Tayfun, Gulsen Akay; Aydin, Hatip; Torun, Deniz; Bozdogan, Sevcan Tug; Gezdirici, Alper; Isikay, Sedat; Atik, Mehmed M; Gambin, Tomasz; et al. (J Clin Invest, 2016)
BACKGROUND: Arthrogryposis, defined as congenital joint contractures in 2 or more body areas, is a clinical sign rather than a specific disease diagnosis. To date, more than 400 different disorders have been described that present with arthrogryposis, and variants of more than 220 genes have been associated with these disorders; however, the underlying molecular etiology remains unknown in the considerable majority of these cases. METHODS: We performed whole exome sequencing (WES) of 52 patients with clinical presentation of arthrogryposis from 48 different families. RESULTS: Affected individuals from 17 families (35.4%) had variants in known arthrogryposis-associated genes, including homozygous variants of cholinergic γ nicotinic receptor (CHRNG, 6 subjects) and endothelin converting enzyme-like 1 (ECEL1, 4 subjects). Deleterious variants in candidate arthrogryposis-causing genes (fibrillin 3 [FBN3], myosin IXA [MYO9A], and pleckstrin and Sec7 domain containing 3 [PSD3]) were identified in 3 families (6.2%). Moreover, in 8 families with a homozygous mutation in an arthrogryposis-associated gene, we identified a second locus with either a homozygous or compound heterozygous variant in a candidate gene (myosin binding protein C, fast type [MYBPC2] and vacuolar protein sorting 8 [VPS8], 2 families, 4.2%) or in another disease-associated genes (6 families, 12.5%), indicating a potential mutational burden contributing to disease expression. CONCLUSION: In 58.3% of families, the arthrogryposis manifestation could be explained by a molecular diagnosis; however, the molecular etiology in subjects from 20 families remained unsolved by WES. Only 5 of these 20 unrelated subjects had a clinical presentation consistent with amyoplasia; a phenotype not thought to be of genetic origin. Our results indicate that increased use of genome-wide technologies will provide opportunities to better understand genetic models for diseases and molecular mechanisms of genetically heterogeneous disorders, such as arthrogryposis. FUNDING: This work was supported in part by US National Human Genome Research Institute (NHGRI)/National Heart, Lung, and Blood Institute (NHLBI) grant U54HG006542 to the Baylor-Hopkins Center for Mendelian Genomics, and US National Institute of Neurological Disorders and Stroke (NINDS) grant R01NS058529 to J.R. Lupski.
Keywords: Arthrogryposis; Exome; Family; Female; Genome-Wide Association Study; Humans; Male; Turkey

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gözde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Mosaic Activating Mutations in FGFR1 Cause Encephalocraniocutaneous Lipomatosis. - Bennett, James T; Tan, Tiong Yang; Alcantara, Diana; Tétrault, Martine; Timms, Andrew E; Jensen, Dana; Collins, Sarah; Nowaczyk, Malgorzata J M; Lindhurst, Marjorie J; Christensen, Katherine M; Braddock, Stephen R; Brandling-Bennett, Heather; et al. (Am J Hum Genet, 2016)
Encephalocraniocutaneous lipomatosis (ECCL) is a sporadic condition characterized by ocular, cutaneous, and central nervous system anomalies. Key clinical features include a well-demarcated hairless fatty nevus on the scalp, benign ocular tumors, and central nervous system lipomas. Seizures, spasticity, and intellectual disability can be present, although affected individuals without seizures and with normal intellect have also been reported. Given the patchy and asymmetric nature of the malformations, ECCL has been hypothesized to be due to a post-zygotic, mosaic mutation. Despite phenotypic overlap with several other disorders associated with mutations in the RAS-MAPK and PI3K-AKT pathways, the molecular etiology of ECCL remains unknown. Using exome sequencing of DNA from multiple affected tissues from five unrelated individuals with ECCL, we identified two mosaic mutations, c.1638C>A (p.Asn546Lys) and c.1966A>G (p.Lys656Glu) within the tyrosine kinase domain of FGFR1, in two affected individuals each. These two residues are the most commonly mutated residues in FGFR1 in human cancers and are associated primarily with CNS tumors. Targeted resequencing of FGFR1 in multiple tissues from an independent cohort of individuals with ECCL identified one additional individual with a c.1638C>A (p.Asn546Lys) mutation in FGFR1. Functional studies of ECCL fibroblast cell lines show increased levels of phosphorylated FGFRs and phosphorylated FRS2, a direct substrate of FGFR1, as well as constitutive activation of RAS-MAPK signaling. In addition to identifying the molecular etiology of ECCL, our results support the emerging overlap between mosaic developmental disorders and tumorigenesis.
Keywords: Adolescent; Cell Line, Tumor; Central Nervous System Neoplasms; Child, Preschool; Exome; Eye; Eye Diseases; Female; Humans; Infant; Lipomatosis; Male; Mutation; Mutation, Missense; Neurocutaneous Syndromes; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; Receptor, Fibroblast Growth Factor, Type 1; Seizures; Sequence Analysis, DNA

Multiallelic Positions in the Human Genome: Challenges for Genetic Analyses. - Campbell, Ian M; Gambin, Tomasz; Jhangiani, Shalini; Grove, Megan L; Veeraraghavan, Narayanan; Muzny, Donna M; Shaw, Chad A; Gibbs, Richard A; Boerwinkle, Eric; Yu, Fuli; Lupski, James R (Hum Mutat, 2016)
As the amount of human genomic sequence available from personal genomes and exomes has increased, so too has the observation of genomic positions having two or more alternative alleles, so-called multiallelic sites. For portions of the haploid genome that are present in more than one copy, including segmental duplications, variation at such multisite variant positions becomes even more complex. Despite the frequency of multiallelic variants, a number of commonly used resources and tools in genomic research and diagnostics do not support these multiallelic variants all together or require special modifications. Here, we explore the frequency of multiallelic sites in large samples with whole exome sequencing and discuss potential outcomes of failing to account for multiple variant alleles. We also briefly discuss some commonly utilized resources that fully support multiallelic sites.
Keywords: Alleles; Exome; Genome, Human; Humans

Mutations in MBOAT7, Encoding Lysophosphatidylinositol Acyltransferase I, Lead to Intellectual Disability Accompanied by Epilepsy and Autistic Features. - Johansen, Anide; Rosti, Rasim O; Musaev, Damir; Sticca, Evan; Harripaul, Ricardo; Zaki, Maha; Çağlayan, Ahmet Okay; Azam, Matloob; Sultan, Tipu; Froukh, Tawfiq; Reis, André; Popp, Bernt; et al. (Am J Hum Genet, 2016)
The risk of epilepsy among individuals with intellectual disability (ID) is approximately ten times that of the general population. From a cohort of >5,000 families affected by neurodevelopmental disorders, we identified six consanguineous families harboring homozygous inactivating variants in MBOAT7, encoding lysophosphatidylinositol acyltransferase (LPIAT1). Subjects presented with ID frequently accompanied by epilepsy and autistic features. LPIAT1 is a membrane-bound phospholipid-remodeling enzyme that transfers arachidonic acid (AA) to lysophosphatidylinositol to produce AA-containing phosphatidylinositol. This study suggests a role for AA-containing phosphatidylinositols in the development of ID accompanied by epilepsy and autistic features.
Keywords: Acyltransferases; Arachidonic Acid; Autistic Disorder; Child; Child, Preschool; Consanguinity; Epilepsy; Female; Homozygote; Humans; Infant; Intellectual Disability; Lysophospholipids; Male; Membrane Proteins; Mutation; Pedigree; Phosphatidylinositols

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis. - Gomez-Ospina, Natalia; Potter, Carol J; Xiao, Rui; Manickam, Kandamurugu; Kim, Mi-Sun; Kim, Kang Ho; Shneider, Benjamin L; Picarsic, Jennifer L; Jacobson, Theodora A; Zhang, Jing; He, Weimin; Liu, Pengfei; et al. (Nat Commun, 2016)
Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, persistent NR1H4-related cholestasis include neonatal onset with rapid progression to end-stage liver disease, vitamin K-independent coagulopathy, low-to-normal serum gamma-glutamyl transferase activity, elevated serum alpha-fetoprotein and undetectable liver bile salt export pump (ABCB11) expression. Our findings demonstrate a pivotal function for FXR in bile acid homeostasis and liver protection.
Keywords: ATP Binding Cassette Transporter, Subfamily B, Member 11; ATP-Binding Cassette Transporters; Bile Acids and Salts; Cholestasis, Intrahepatic; Female; Humans; Male; Mutation; Receptors, Cytoplasmic and Nuclear; Young Adult

Novel genetic causes for cerebral visual impairment. - Bosch, Daniëlle G M; Boonstra, F Nienke; de Leeuw, Nicole; Pfundt, Rolph; Nillesen, Willy M; de Ligt, Joep; Gilissen, Christian; Jhangiani, Shalini; Lupski, James R; Cremers, Frans P M; de Vries, Bert B A (Eur J Hum Genet, 2016)
Cerebral visual impairment (CVI) is a major cause of low vision in children due to impairment in projection and/or interpretation of the visual input in the brain. Although acquired causes for CVI are well known, genetic causes underlying CVI are largely unidentified. DNAs of 25 patients with CVI and intellectual disability, but without acquired (eg, perinatal) damage, were investigated by whole-exome sequencing. The data were analyzed for de novo, autosomal-recessive, and X-linked variants, and subsequently classified into known, candidate, or unlikely to be associated with CVI. This classification was based on the Online Mendelian Inheritance in Man database, literature reports, variant characteristics, and functional relevance of the gene. After classification, variants in four genes known to be associated with CVI (AHDC1, NGLY1, NR2F1, PGAP1) in 5 patients (20%) were identified, establishing a conclusive genetic diagnosis for CVI. In addition, in 11 patients (44%) with CVI, variants in one or more candidate genes were identified (ACP6, AMOT, ARHGEF10L, ATP6V1A, DCAF6, DLG4, GABRB2, GRIN1, GRIN2B, KCNQ3, KCTD19, RERE, SLC1A1, SLC25A16, SLC35A2, SOX5, UFSP2, UHMK1, ZFP30). Our findings show that diverse genetic causes underlie CVI, some of which will provide insight into the biology underlying this disease process.
Keywords: Adolescent; Blindness, Cortical; Child; Child, Preschool; Female; Genetic Loci; Humans; Male; Polymorphism, Single Nucleotide; Young Adult

Novel mutations in LRP6 highlight the role of WNT signaling in tooth agenesis. - Ockeloen, Charlotte W; Khandelwal, Kriti D; Dreesen, Karoline; Ludwig, Kerstin U; Sullivan, Robert; van Rooij, Iris A L M; Thonissen, Michelle; Swinnen, Steven; Phan, Milien; Conte, Federica; Ishorst, Nina; Gilissen, Christian; et al. (Genet Med, 2016)
PURPOSE: We aimed to identify a novel genetic cause of tooth agenesis (TA) and/or orofacial clefting (OFC) by combining whole-exome sequencing (WES) and targeted resequencing in a large cohort of TA and OFC patients. METHODS: WES was performed in two unrelated patients: one with severe TA and OFC and another with severe TA only. After deleterious mutations were identified in a gene encoding low-density lipoprotein receptor-related protein 6 (LRP6), all its exons were resequenced with molecular inversion probes in 67 patients with TA, 1,072 patients with OFC, and 706 controls. RESULTS: We identified a frameshift (c.4594delG, p.Cys1532fs) and a canonical splice-site mutation (c.3398-2A>C, p.?) in LRP6, respectively, in the patient with TA and OFC and in the patient with severe TA only. The targeted resequencing showed significant enrichment of unique LRP6 variants in TA patients but not in nonsyndromic OFC patients. Of the five variants in patients with TA, two affected the canonical splice site and three were missense variants; all variants segregated with the dominant phenotype, and in one case the missense mutation occurred de novo. CONCLUSION: Mutations in LRP6 cause TA in humans.Genet Med 18 11, 1158-1162.
Keywords: Adolescent; Anodontia; Child; Exome; Female; Frameshift Mutation; Genetic Predisposition to Disease; Humans; Low Density Lipoprotein Receptor-Related Protein-6; Male; Mutation, Missense; Pedigree; Sequence Analysis, DNA; Wnt Signaling Pathway

PADRE: Pedigree-Aware Distant-Relationship Estimation. - Staples, Jeffrey; Witherspoon, David J; Jorde, Lynn B; Nickerson, Deborah A; Below, Jennifer E; Huff, Chad D (Am J Hum Genet, 2016)
Accurate estimation of shared ancestry is an important component of many genetic studies; current prediction tools accurately estimate pairwise genetic relationships up to the ninth degree. Pedigree-aware distant-relationship estimation (PADRE) combines relationship likelihoods generated by estimation of recent shared ancestry (ERSA) with likelihoods from family networks reconstructed by pedigree reconstruction and identification of a maximum unrelated set (PRIMUS), improving the power to detect distant relationships between pedigrees. Using PADRE, we estimated relationships from simulated pedigrees and three extended pedigrees, correctly predicting 20% more fourth- through ninth-degree simulated relationships than when using ERSA alone. By leveraging pedigree information, PADRE can even identify genealogical relationships between individuals who are genetically unrelated. For example, although 95% of 13(th)-degree relatives are genetically unrelated, in simulations, PADRE correctly predicted 50% of 13(th)-degree relationships to within one degree of relatedness. The improvement in prediction accuracy was consistent between simulated and actual pedigrees. We also applied PADRE to the HapMap3 CEU samples and report new cryptic relationships and validation of previously described relationships between families. PADRE greatly expands the range of relationships that can be estimated by using genetic data in pedigrees.
Keywords: Algorithms; Female; Haplotypes; Humans; Male; Models, Genetic; Pedigree; Reproducibility of Results

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins. - Szafranski, Przemyslaw; Gambin, Tomasz; Dharmadhikari, Avinash V; Akdemir, Kadir Caner; Jhangiani, Shalini N; Schuette, Jennifer; Godiwala, Nihal; Yatsenko, Svetlana A; Sebastian, Jessica; Madan-Khetarpal, Suneeta; Surti, Urvashi; Abellar, Rosanna G; et al. (Hum Genet, 2016)
Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a lethal lung developmental disorder caused by heterozygous point mutations or genomic deletion copy-number variants (CNVs) of FOXF1 or its upstream enhancer involving fetal lung-expressed long noncoding RNA genes LINC01081 and LINC01082. Using custom-designed array comparative genomic hybridization, Sanger sequencing, whole exome sequencing (WES), and bioinformatic analyses, we studied 22 new unrelated families (20 postnatal and two prenatal) with clinically diagnosed ACDMPV. We describe novel deletion CNVs at the FOXF1 locus in 13 unrelated ACDMPV patients. Together with the previously reported cases, all 31 genomic deletions in 16q24.1, pathogenic for ACDMPV, for which parental origin was determined, arose de novo with 30 of them occurring on the maternally inherited chromosome 16, strongly implicating genomic imprinting of the FOXF1 locus in human lungs. Surprisingly, we have also identified four ACDMPV families with the pathogenic variants in the FOXF1 locus that arose on paternal chromosome 16. Interestingly, a combination of the severe cardiac defects, including hypoplastic left heart, and single umbilical artery were observed only in children with deletion CNVs involving FOXF1 and its upstream enhancer. Our data demonstrate that genomic imprinting at 16q24.1 plays an important role in variable ACDMPV manifestation likely through long-range regulation of FOXF1 expression, and may be also responsible for key phenotypic features of maternal uniparental disomy 16. Moreover, in one family, WES revealed a de novo missense variant in ESRP1, potentially implicating FGF signaling in the etiology of ACDMPV.
Keywords: Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Female; Forkhead Transcription Factors; Genes, Lethal; Genome, Human; Genomic Imprinting; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Pedigree; Persistent Fetal Circulation Syndrome; Pulmonary Alveoli; Pulmonary Veins; Sequence Deletion

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Muzny, Donna M; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Boerwinkle, Eric; Gibbs, Richard A; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

Phenotypic Expansion of Congenital Disorder of Glycosylation Due to SRD5A3 Null Mutation. - Tuysuz, Beyhan; Pehlivan, Davut; Özkök, Ahmet; Jhangiani, Shalini; Yalcinkaya, Cengiz; Zeybek, Çiğdem Aktuğlu; Muzny, Donna Marie; Lupski, James R; Gibbs, Richard; Jaeken, Jaak (JIMD Rep, 2016)
We present a boy, admitted at 4 months, with facial dysmorphism, hypertrichosis, loose skin, bilateral inguinal hernia, severe hypotonia, psychomotor disability, seizures with hypsarrhythmia (West syndrome), hepatosplenomegaly, increased serum transaminases, iris coloboma, glaucoma, corneal clouding and bilateral dilated lateral ventricles, and extra-axial post-cerebellar space. Serum transferrin isoelectrofocusing (IEF) showed a type 1 pattern. Whole-exome genotyping showed a previously reported homozygous nonsense mutation c.320G>A; p.Trp107X in SRD5A3. Epilepsy and glaucoma have been reported only once in the 19 described SRD5A3-congenital glycosylation defect patients, and corneal clouding not at all.

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

PYCR2 Mutations cause a lethal syndrome of microcephaly and failure to thrive. - Zaki, Maha S; Bhat, Gifty; Sultan, Tipu; Issa, Mahmoud; Jung, Hea-Jin; Dikoglu, Esra; Selim, Laila; G Mahmoud, Imam; Abdel-Hamid, Mohamed S; Abdel-Salam, Ghada; Marin-Valencia, Isaac; Gleeson, Joseph G (Ann Neurol, 2016)
OBJECTIVE: A study was undertaken to characterize the clinical features of the newly described hypomyelinating leukodystrophy type 10 with microcephaly. This is an autosomal recessive disorder mapped to chromosome 1q42.12 due to mutations in the PYCR2 gene, encoding an enzyme involved in proline synthesis in mitochondria. METHODS: From several international clinics, 11 consanguineous families were identified with PYCR2 mutations by whole exome or targeted sequencing, with detailed clinical and radiological phenotyping. Selective mutations from patients were tested for effect on protein function. RESULTS: The characteristic clinical presentation of patients with PYCR2 mutations included failure to thrive, microcephaly, craniofacial dysmorphism, progressive psychomotor disability, hyperkinetic movements, and axial hypotonia with variable appendicular spasticity. Patients did not survive beyond the first decade of life. Brain magnetic resonance imaging showed global brain atrophy and white matter T2 hyperintensities. Routine serum metabolic profiles were unremarkable. Both nonsense and missense mutations were identified, which impaired protein multimerization. INTERPRETATION: PYCR2-related syndrome represents a clinically recognizable condition in which PYCR2 mutations lead to protein dysfunction, not detectable on routine biochemical assessments. Mutations predict a poor outcome, probably as a result of impaired mitochondrial function. Ann Neurol 2016;80:59-70.
Keywords: Adolescent; Child; Child, Preschool; Codon, Nonsense; Exome; Failure to Thrive; Female; Fibroblasts; Gene Expression; Genetic Predisposition to Disease; Genotype; Humans; Infant; Male; Microcephaly; Mutation, Missense; Phenotype; Primary Cell Culture; Pyrroline Carboxylate Reductases; Syndrome; Transfection; Young Adult

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; European Continental Ancestry Group; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic Americans; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis

Recurrent recessive mutation in deoxyguanosine kinase causes idiopathic noncirrhotic portal hypertension. - Vilarinho, Sílvia; Sari, Sinan; Yilmaz, Güldal; Stiegler, Amy L; Boggon, Titus J; Jain, Dhanpat; Akyol, Gülen; Dalgiç, Buket; Günel, Murat; Lifton, Richard P (Hepatology, 2016)
UNLABELLED: Despite advances in the diagnosis and management of idiopathic noncirrhotic portal hypertension, its pathogenesis remains elusive. Insight may be gained from study of early-onset familial idiopathic noncirrhotic portal hypertension, in which Mendelian mutations may account for disease. We performed exome sequencing of eight subjects from six kindreds with onset of portal hypertension of indeterminate etiology during infancy or childhood. Three subjects from two consanguineous families shared the identical rare homozygous p.N46S mutation in DGUOK, a deoxyguanosine kinase required for mitochondrial DNA replication; haplotype sharing demonstrated that the mutation in the two families was inherited from a remote common ancestor. All three affected subjects had stable portal hypertension with noncirrhotic liver disease for 6-16 years of follow-up. This mutation impairs adenosine triphosphate binding and reduces catalytic activity. Loss-of-function mutations in DGUOK have previously been implicated in cirrhosis and liver failure but not in isolated portal hypertension. Interestingly, treatment of patients with human immunodeficiency viral infection with the nucleoside analogue didanosine is known to cause portal hypertension in a subset of patients and lowers deoxyguanosine kinase levels in vitro; the current findings implicate these effects on deoxyguanosine kinase in the causal mechanism. CONCLUSION: Our findings provide new insight into the mechanisms mediating inherited and acquired noncirrhotic portal hypertension, expand the phenotypic spectrum of DGUOK deficiency, and provide a new genetic test for a specific cause of idiopathic noncirrhotic portal hypertension. (Hepatology 2016;63:1977-1986).
Keywords: Adolescent; Amino Acid Sequence; Animals; Cattle; Child; Child, Preschool; DNA Mutational Analysis; Dogs; Female; Genes, Recessive; Homozygote; Humans; Hypertension, Portal; Infant; Liver Failure; Male; Molecular Sequence Data; Pedigree; Phosphotransferases (Alcohol Group Acceptor); Principal Component Analysis; Rats; Young Adult

The role of combined SNV and CNV burden in patients with distal symmetric polyneuropathy. - Pehlivan, Davut; Beck, Christine R; Okamoto, Yuji; Harel, Tamar; Akdemir, Zeynep H C; Jhangiani, Shalini N; Withers, Marjorie A; Goksungur, Meryem Tuba; Carvalho, Claudia M B; Czesnik, Dirk; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; et al. (Genet Med, 2016)
PURPOSE: Charcot-Marie-Tooth (CMT) disease is a heterogeneous group of genetic disorders of the peripheral nervous system. Copy-number variants (CNVs) contribute significantly to CMT, as duplication of PMP22 underlies the majority of CMT1 cases. We hypothesized that CNVs and/or single-nucleotide variants (SNVs) might exist in patients with CMT with an unknown molecular genetic etiology. METHODS: Two hundred patients with CMT, negative for both SNV mutations in several CMT genes and for CNVs involving PMP22, were screened for CNVs by high-resolution oligonucleotide array comparative genomic hybridization. Whole-exome sequencing was conducted on individuals with rare, potentially pathogenic CNVs. RESULTS: Putatively causative CNVs were identified in five subjects (~2.5%); four of the five map to known neuropathy genes. Breakpoint sequencing revealed Alu-Alu-mediated junctions as a predominant contributor. Exome sequencing identified MFN2 SNVs in two of the individuals. CONCLUSION: Neuropathy-associated CNV outside of the PMP22 locus is rare in CMT. Nevertheless, there is potential clinical utility in testing for CNVs and exome sequencing in CMT cases negative for the CMT1A duplication. These findings suggest that complex phenotypes including neuropathy can potentially be caused by a combination of SNVs and CNVs affecting more than one disease-associated locus and contributing to a mutational burden.Genet Med 18 5, 443-451.
Keywords: Adult; Age of Onset; Charcot-Marie-Tooth Disease; Child, Preschool; Comparative Genomic Hybridization; DNA Copy Number Variations; Exome; Female; Genetic Predisposition to Disease; GTP Phosphohydrolases; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Motor Neurons; Myelin P0 Protein; Myelin Proteins; Neural Conduction; Polymorphism, Single Nucleotide; Polyneuropathies

Somatic mosaicism underlies X-linked acrogigantism syndrome in sporadic male subjects. - Daly, Adrian F; Yuan, Bo; Fina, Frederic; Caberg, Jean-Hubert; Trivellin, Giampaolo; Rostomyan, Liliya; de Herder, Wouter W; Naves, Luciana A; Metzger, Daniel; Cuny, Thomas; Rabl, Wolfgang; Shah, Nalini; et al. (Endocr Relat Cancer, 2016)
Somatic mosaicism has been implicated as a causative mechanism in a number of genetic and genomic disorders. X-linked acrogigantism (XLAG) syndrome is a recently characterized genomic form of pediatric gigantism due to aggressive pituitary tumors that is caused by submicroscopic chromosome Xq26.3 duplications that include GPR101 We studied XLAG syndrome patients (n= 18) to determine if somatic mosaicism contributed to the genomic pathophysiology. Eighteen subjects with XLAG syndrome caused by Xq26.3 duplications were identified using high-definition array comparative genomic hybridization (HD-aCGH). We noted that males with XLAG had a decreased log2ratio (LR) compared with expected values, suggesting potential mosaicism, whereas females showed no such decrease. Compared with familial male XLAG cases, sporadic males had more marked evidence for mosaicism, with levels of Xq26.3 duplication between 16.1 and 53.8%. These characteristics were replicated using a novel, personalized breakpoint junction-specific quantification droplet digital polymerase chain reaction (ddPCR) technique. Using a separate ddPCR technique, we studied the feasibility of identifying XLAG syndrome cases in a distinct patient population of 64 unrelated subjects with acromegaly/gigantism, and identified one female gigantism patient who had had increased copy number variation (CNV) threshold for GPR101 that was subsequently diagnosed as having XLAG syndrome on HD-aCGH. Employing a combination of HD-aCGH and novel ddPCR approaches, we have demonstrated, for the first time, that XLAG syndrome can be caused by variable degrees of somatic mosaicism for duplications at chromosome Xq26.3. Somatic mosaicism was shown to occur in sporadic males but not in females with XLAG syndrome, although the clinical characteristics of the disease were similarly severe in both sexes.
Keywords: Adult; Female; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Middle Aged; Mosaicism; Polymerase Chain Reaction; Syndrome; Young Adult

A Syndromic Intellectual Disability Disorder Caused by Variants in TELO2, a Gene Encoding a Component of the TTT Complex. - You, Jing; Sobreira, Nara L; Gable, Dustin L; Jurgens, Julie; Grange, Dorothy K; Belnap, Newell; Siniard, Ashley; Szelinger, Szabolcs; Schrauwen, Isabelle; Richholt, Ryan F; Vallee, Stephanie E; Dinulos, Mary Beth P; et al. (Am J Hum Genet, 2016)
The proteins encoded by TELO2, TTI1, and TTI2 interact to form the TTT complex, a co-chaperone for maturation of the phosphatidylinositol 3-kinase-related protein kinases (PIKKs). Here we report six affected individuals from four families with intellectual disability (ID) and neurological and other congenital abnormalities associated with compound heterozygous variants in TELO2. Although their fibroblasts showed reduced steady-state levels of TELO2 and the other components of the TTT complex, PIKK functions were normal in cellular assays. Our results suggest that these TELO2 missense variants result in loss of function, perturb TTT complex stability, and cause an autosomal-recessive syndromic form of ID.
Keywords: Adolescent; Carrier Proteins; Child; Female; Humans; Intellectual Disability; Male; Molecular Chaperones; Pedigree; Phosphatidylinositol 3-Kinases; Protein-Serine-Threonine Kinases; Telomere-Binding Proteins

Variants in SKP1, PROB1, and IL17B genes at keratoconus 5q31.1-q35.3 susceptibility locus identified by whole-exome sequencing. - Karolak, Justyna A; Gambin, Tomasz; Pitarque, Jose A; Molinari, Andrea; Jhangiani, Shalini; Stankiewicz, Pawel; Lupski, James R; Gajecka, Marzena (Eur J Hum Genet, 2016)
Keratoconus (KTCN) is a protrusion and thinning of the cornea, resulting in impairment of visual function. The extreme genetic heterogeneity makes it difficult to discover factors unambiguously influencing the KTCN phenotype. In this study, we used whole-exome sequencing (WES) and Sanger sequencing to reduce the number of candidate genes at the 5q31.1-q35.3 locus and to prioritize other potentially relevant variants in an Ecuadorian family with KTCN. We applied WES in two affected KTCN individuals from the Ecuadorian family that showed a suggestive linkage between the KTCN phenotype and the 5q31.1-q35.3 locus. Putative variants identified by WES were further evaluated in this family using Sanger sequencing. Exome capture discovered a total of 173 rare (minor allele frequency <0.001 in control population) nonsynonymous variants in both affected individuals. Among them, 16 SNVs were selected for further evaluation. Segregation analysis revealed that variants c.475T>G in SKP1, c.671G>A in PROB1, and c.527G>A in IL17B in the 5q31.1-q35.3 linkage region, and c.850G>A in HKDC1 in the 10q22 locus completely segregated with the phenotype in the studied KTCN family. We demonstrate that a combination of various techniques significantly narrowed the studied genomic region and reduced the list of the putative exonic variants. Moreover, since this locus overlapped two other chromosomal regions previously recognized in distinct KTCN studies, our findings suggest that this 5q31.1-q35.3 locus might be linked with KTCN.
Keywords: Chromosomes, Human, Pair 5; Exome; Female; Gene Frequency; Genetic Linkage; Genetic Predisposition to Disease; Genome, Human; Hexokinase; High-Throughput Nucleotide Sequencing; Humans; Interleukin-17; Keratoconus; Male; Pedigree; Phenotype; Proteins; S-Phase Kinase-Associated Proteins

Variants in the Oxidoreductase PYROXD1 Cause Early-Onset Myopathy with Internalized Nuclei and Myofibrillar Disorganization. - O'Grady, Gina L; Best, Heather A; Sztal, Tamar E; Schartner, Vanessa; Sanjuan-Vazquez, Myriam; Donkervoort, Sandra; Abath Neto, Osorio; Sutton, Roger Bryan; Ilkovski, Biljana; Romero, Norma Beatriz; Stojkovic, Tanya; Dastgir, Jahannaz; et al. (Am J Hum Genet, 2016)
This study establishes PYROXD1 variants as a cause of early-onset myopathy and uses biospecimens and cell lines, yeast, and zebrafish models to elucidate the fundamental role of PYROXD1 in skeletal muscle. Exome sequencing identified recessive variants in PYROXD1 in nine probands from five families. Affected individuals presented in infancy or childhood with slowly progressive proximal and distal weakness, facial weakness, nasal speech, swallowing difficulties, and normal to moderately elevated creatine kinase. Distinctive histopathology showed abundant internalized nuclei, myofibrillar disorganization, desmin-positive inclusions, and thickened Z-bands. PYROXD1 is a nuclear-cytoplasmic pyridine nucleotide-disulphide reductase (PNDR). PNDRs are flavoproteins (FAD-binding) and catalyze pyridine-nucleotide-dependent (NAD/NADH) reduction of thiol residues in other proteins. Complementation experiments in yeast lacking glutathione reductase glr1 show that human PYROXD1 has reductase activity that is strongly impaired by the disease-associated missense mutations. Immunolocalization studies in human muscle and zebrafish myofibers demonstrate that PYROXD1 localizes to the nucleus and to striated sarcomeric compartments. Zebrafish with ryroxD1 knock-down recapitulate features of PYROXD1 myopathy with sarcomeric disorganization, myofibrillar aggregates, and marked swimming defect. We characterize variants in the oxidoreductase PYROXD1 as a cause of early-onset myopathy with distinctive histopathology and introduce altered redox regulation as a primary cause of congenital muscle disease.
Keywords: Amino Acid Sequence; Animals; Cell Nucleus; Cercopithecus aethiops; Cohort Studies; COS Cells; Creatine Kinase; Cytoplasm; Distal Myopathies; ELAV-Like Protein 4; Female; Flavoproteins; Gene Deletion; Genetic Variation; Genome-Wide Association Study; Glutathione Reductase; HEK293 Cells; Humans; Male; Muscle, Skeletal; Mutation, Missense; Myopathies, Structural, Congenital; Oxidoreductases; Pedigree; Protein Conformation; Saccharomyces cerevisiae Proteins; Zebrafish

A visual and curatorial approach to clinical variant prioritization and disease gene discovery in genome-wide diagnostics. - James, Regis A; Campbell, Ian M; Chen, Edward S; Boone, Philip M; Rao, Mitchell A; Bainbridge, Matthew N; Lupski, James R; Yang, Yaping; Eng, Christine M; Posey, Jennifer E; Shaw, Chad A (Genome Med, 2016)
BACKGROUND: Genome-wide data are increasingly important in the clinical evaluation of human disease. However, the large number of variants observed in individual patients challenges the efficiency and accuracy of diagnostic review. Recent work has shown that systematic integration of clinical phenotype data with genotype information can improve diagnostic workflows and prioritization of filtered rare variants. We have developed visually interactive, analytically transparent analysis software that leverages existing disease catalogs, such as the Online Mendelian Inheritance in Man database (OMIM) and the Human Phenotype Ontology (HPO), to integrate patient phenotype and variant data into ranked diagnostic alternatives. METHODS: Our tool, "OMIM Explorer" ( http://www.omimexplorer.com ), extends the biomedical application of semantic similarity methods beyond those reported in previous studies. The tool also provides a simple interface for translating free-text clinical notes into HPO terms, enabling clinical providers and geneticists to contribute phenotypes to the diagnostic process. The visual approach uses semantic similarity with multidimensional scaling to collapse high-dimensional phenotype and genotype data from an individual into a graphical format that contextualizes the patient within a low-dimensional disease map. The map proposes a differential diagnosis and algorithmically suggests potential alternatives for phenotype queries--in essence, generating a computationally assisted differential diagnosis informed by the individual's personal genome. Visual interactivity allows the user to filter and update variant rankings by interacting with intermediate results. The tool also implements an adaptive approach for disease gene discovery based on patient phenotypes. RESULTS: We retrospectively analyzed pilot cohort data from the Baylor Miraca Genetics Laboratory, demonstrating performance of the tool and workflow in the re-analysis of clinical exomes. Our tool assigned to clinically reported variants a median rank of 2, placing causal variants in the top 1 % of filtered candidates across the 47 cohort cases with reported molecular diagnoses of exome variants in OMIM Morbidmap genes. Our tool outperformed Phen-Gen, eXtasy, PhenIX, PHIVE, and hiPHIVE in the prioritization of these clinically reported variants. CONCLUSIONS: Our integrative paradigm can improve efficiency and, potentially, the quality of genomic medicine by more effectively utilizing available phenotype information, catalog data, and genomic knowledge.
Keywords: Computational Biology; Diagnosis, Differential; Disease; Genetic Variation; Genome-Wide Association Study; Humans; Phenotype; Pilot Projects; Retrospective Studies; Software

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Boerwinkle, Eric; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Gibbs, Richard A; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Absence of heterozygosity due to template switching during replicative rearrangements. - Carvalho, Claudia M B; Pfundt, Rolph; King, Daniel A; Lindsay, Sarah J; Zuccherato, Luciana W; Macville, Merryn V E; Liu, Pengfei; Johnson, Diana; Stankiewicz, Pawel; Brown, Chester W; Shaw, Chad A; Hurles, Matthew E; et al. (Am J Hum Genet, 2015)
We investigated complex genomic rearrangements (CGRs) consisting of triplication copy-number variants (CNVs) that were accompanied by extended regions of copy-number-neutral absence of heterozygosity (AOH) in subjects with multiple congenital abnormalities. Molecular analyses provided observational evidence that in humans, post-zygotically generated CGRs can lead to regional uniparental disomy (UPD) due to template switches between homologs versus sister chromatids by using microhomology to prime DNA replication-a prediction of the replicative repair model, MMBIR. Our findings suggest that replication-based mechanisms might underlie the formation of diverse types of genomic alterations (CGRs and AOH) implicated in constitutional disorders.
Keywords: Base Sequence; DNA Copy Number Variations; DNA Repair; DNA Replication; Gene Rearrangement; Humans; In Situ Hybridization, Fluorescence; Loss of Heterozygosity; Models, Genetic; Molecular Sequence Data; Netherlands; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Uniparental Disomy

Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2. - Zazo Seco, Celia; Serrão de Castro, Luciana; van Nierop, Josephine W; Morín, Matías; Jhangiani, Shalini; Verver, Eva J J; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (Am J Hum Genet, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mutation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlying WS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.
Keywords: Alleles; Animals; Female; Fluorescent Antibody Technique; Genetic Linkage; Hearing Loss, Unilateral; Humans; Male; Mice; Mutation; NIH 3T3 Cells; Pedigree; Phenotype; Prognosis; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stem Cell Factor; Waardenburg Syndrome

Assessment of incidental findings in 232 whole-exome sequences from the Baylor-Hopkins Center for Mendelian Genomics. - Jurgens, Julie; Ling, Hua; Hetrick, Kurt; Pugh, Elizabeth; Schiettecatte, François; Doheny, Kimberly; Hamosh, Ada; Avramopoulos, Dimitri; Valle, David; Sobreira, Nara (Genet Med, 2015)
PURPOSE: In March 2013 the American College of Medical Genetics and Genomics published a list of 56 genes with the recommendation that pathogenic and likely pathogenic variants detected incidentally by clinical sequencing be reported to patients. As an initial step in determining the practical consequences of this recommendation in the research setting, we searched for variants in these genes in 232 whole-exome sequences from the Baylor-Hopkins Center for Mendelian Genomics. METHODS: We identified rare, nonsynonymous, and splicing single-nucleotide variants and insertions/deletions and assessed variant classification using the Human Gene Mutation, Emory, and ClinVar databases. We analyzed the burden of mutation in each of the 56 genes and determined which variants should be reported to patients. RESULTS: Our filtering resulted in 249 distinct variants, with a mean of 1.69 variants per individual. Half of these were novel missense mutations not classified by any of the three reference databases. Of 101 variants listed in the Human Gene Mutation Database, 48 were also in ClinVar and 3 were also in Emory; half of these shared variants were classified discordantly between databases. Some genes consistently had greater variation than others. In total, 0.86% of individuals had a reportable incidental variant. CONCLUSION: These observations demonstrate some current challenges of assessing phenotypic consequences of incidental variants for counseling patients.
Keywords: Databases, Nucleic Acid; Exome; Female; Genetic Diseases, Inborn; Genomics; High-Throughput Nucleotide Sequencing; Humans; Incidental Findings; Male; Mutation; Polymorphism, Single Nucleotide

Autosomal-Dominant Multiple Pterygium Syndrome Is Caused by Mutations in MYH3. - Chong, Jessica X; Burrage, Lindsay C; Beck, Anita E; Marvin, Colby T; McMillin, Margaret J; Shively, Kathryn M; Harrell, Tanya M; Buckingham, Kati J; Bacino, Carlos A; Jain, Mahim; Alanay, Yasemin; Berry, Susan A; et al. (Am J Hum Genet, 2015)
Multiple pterygium syndrome (MPS) is a phenotypically and genetically heterogeneous group of rare Mendelian conditions characterized by multiple pterygia, scoliosis, and congenital contractures of the limbs. MPS typically segregates as an autosomal-recessive disorder, but rare instances of autosomal-dominant transmission have been reported. Whereas several mutations causing recessive MPS have been identified, the genetic basis of dominant MPS remains unknown. We identified four families affected by dominantly transmitted MPS characterized by pterygia, camptodactyly of the hands, vertebral fusions, and scoliosis. Exome sequencing identified predicted protein-altering mutations in embryonic myosin heavy chain (MYH3) in three families. MYH3 mutations underlie distal arthrogryposis types 1, 2A, and 2B, but all mutations reported to date occur in the head and neck domains. In contrast, two of the mutations found to cause MPS in this study occurred in the tail domain. The phenotypic overlap among persons with MPS, coupled with physical findings distinct from other conditions caused by mutations in MYH3, suggests that the developmental mechanism underlying MPS differs from that of other conditions and/or that certain functions of embryonic myosin might be perturbed by disruption of specific residues and/or domains. Moreover, the vertebral fusions in persons with MPS, coupled with evidence of MYH3 expression in bone, suggest that embryonic myosin plays a role in skeletal development.
Keywords: Arthrogryposis; Cytoskeletal Proteins; Exome; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Mutation; Myosins; Osteogenesis

Cerebral visual impairment and intellectual disability caused by PGAP1 variants. - Bosch, Daniëlle G M; Boonstra, F Nienke; Kinoshita, Taroh; Jhangiani, Shalini; de Ligt, Joep; Cremers, Frans P M; Lupski, James R; Murakami, Yoshiko; de Vries, Bert B A (Eur J Hum Genet, 2015)
Homozygous variants in PGAP1 (post-GPI attachment to proteins 1) have recently been identified in two families with developmental delay, seizures and/or spasticity. PGAP1 is a member of the glycosylphosphatidylinositol anchor biosynthesis and remodeling pathway and defects in this pathway are a subclass of congenital disorders of glycosylation. Here we performed whole-exome sequencing in an individual with cerebral visual impairment (CVI), intellectual disability (ID), and factor XII deficiency and revealed compound heterozygous variants in PGAP1, c.274_276del (p.(Pro92del)) and c.921_925del (p.(Lys308Asnfs*25)). Subsequently, PGAP1-deficient Chinese hamster ovary (CHO)-cell lines were transfected with either mutant or wild-type constructs and their sensitivity to phosphatidylinositol-specific phospholipase C (PI-PLC) treatment was measured. The mutant constructs could not rescue the PGAP1-deficient CHO cell lines resistance to PI-PLC treatment. In addition, lymphoblastoid cell lines (LCLs) of the affected individual showed no sensitivity to PI-PLC treatment, whereas the LCLs of the heterozygous carrier parents were partially resistant. In conclusion, we report novel PGAP1 variants in a boy with CVI and ID and a proven functional loss of PGAP1 and show, to our knowledge, for the first time this genetic association with CVI.
Keywords: Animals; Cell Line, Tumor; Child; CHO Cells; Cricetinae; Cricetulus; Humans; Intellectual Disability; Male; Membrane Proteins; Mutation; Phosphoinositide Phospholipase C; Phosphoric Monoester Hydrolases; Syndrome; Vision Disorders; Visual Perception

Challenges and solutions for gene identification in the presence of familial locus heterogeneity. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Drummond, Meghan C; Shahzad, Mohsin; Lee, Kwanghyuk; Morell, Robert J; Ansar, Muhammad; Jan, Abid; Wang, Xin; Aziz, Abdul; Riazuddin, Saima; Smith, Joshua D; et al. (Eur J Hum Genet, 2015)
Next-generation sequencing (NGS) of exomes and genomes has accelerated the identification of genes involved in Mendelian phenotypes. However, many NGS studies fall short of identifying causal variants, with estimates for success rates as low as 25% for uncovering the pathological variant underlying disease etiology. An important reason for such failures is familial locus heterogeneity, where within a single pedigree causal variants in two or more genes underlie Mendelian trait etiology. As examples of intra- and inter-sibship familial locus heterogeneity, we present 10 consanguineous Pakistani families segregating hearing impairment due to homozygous variants in two different hearing impairment genes and a European-American pedigree in which hearing impairment is caused by four variants in three different genes. We have identified 41 additional pedigrees with syndromic and nonsyndromic hearing impairment for which a single previously reported hearing impairment gene has been identified but only segregates with the phenotype in a subset of affected pedigree members. We estimate that locus heterogeneity occurs in 15.3% (95% confidence interval: 11.9%, 19.9%) of the families in our collection. We demonstrate novel approaches to apply linkage analysis and homozygosity mapping (for autosomal recessive consanguineous pedigrees), which can be used to detect locus heterogeneity using either NGS or SNP array data. Results from linkage analysis and homozygosity mapping can also be used to group sibships or individuals most likely to be segregating the same causal variants and thereby increase the success rate of gene identification.
Keywords: Asian Continental Ancestry Group; Calcium-Binding Proteins; Chromosome Mapping; Connexin 26; Connexins; Consanguinity; European Continental Ancestry Group; Female; Genes, Recessive; Genetic Heterogeneity; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genotype; Hearing Loss; Hepatocyte Growth Factor; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Membrane Transport Proteins; Mutation; Pedigree; Phenotype; Sulfate Transporters

CNV instability associated with DNA replication dynamics: evidence for replicative mechanisms in CNV mutagenesis. - Chen, Lu; Zhou, Weichen; Zhang, Cheng; Lupski, James R; Jin, Li; Zhang, Feng (Hum Mol Genet, 2015)
Copy number variation (CNV) in the human genome is of vital importance to human health and evolution of our species. However, much of the molecular basis of CNV mutagenesis remains to be elucidated. Considering the DNA replication model of 'fork stalling and template switching' for CNV formation, we hypothesized that replication fork progression could be important for CNV mutagenesis. However, molecular assays of replication fork progression at the genome level are technically challenging. Instead, we conducted an estimation of DNA replication dynamics, as the statistic R, using the readily available data of replication timing. Small R-values can reflect 'slowed' replication, which could result from less fork initiation, reduced fork speed or fork barriers. We generated genome-wide profiles of R in the genomes of human, mouse and Drosophila. Intriguingly, the CNV breakpoints in all three genomes showed significantly biased distributions toward the genomic regions with small R-values, suggesting potential replication stress-induced CNV instability. Notably, among the human CNVs with distinct breakpoint junction characteristics, the homology-mediated and VNTR-mediated CNVs contribute the most to the correlation between CNV instability and the statistic R, consistent with the recent findings in the C. elegans and yeast genomes of repeat-induced DNA replication error and consequent CNV formation. The statistic R may reflect both replication stress and the effect of local genome architecture on fork progression. Our concordant observations suggest an important role for DNA replicative mechanisms in CNV mutagenesis and genome instability.
Keywords: Animals; DNA Copy Number Variations; DNA Replication; Drosophila; Genome; Genomic Instability; Humans; Mice

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

DVL1 frameshift mutations clustering in the penultimate exon cause autosomal-dominant Robinow syndrome. - White, Janson; Mazzeu, Juliana F; Hoischen, Alexander; Jhangiani, Shalini N; Gambin, Tomasz; Alcino, Michele Calijorne; Penney, Samantha; Saraiva, Jorge M; Hove, Hanne; Skovby, Flemming; Kayserili, Hülya; Estrella, Elicia; et al. (Am J Hum Genet, 2015)
Robinow syndrome is a genetically heterogeneous disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features and for which both autosomal-recessive and autosomal-dominant inheritance patterns have been described. Causative variants in the non-canonical signaling gene WNT5A underlie a subset of autosomal-dominant Robinow syndrome (DRS) cases, but most individuals with DRS remain without a molecular diagnosis. We performed whole-exome sequencing in four unrelated DRS-affected individuals without coding mutations in WNT5A and found heterozygous DVL1 exon 14 mutations in three of them. Targeted Sanger sequencing in additional subjects with DRS uncovered DVL1 exon 14 mutations in five individuals, including a pair of monozygotic twins. In total, six distinct frameshift mutations were found in eight subjects, and all were heterozygous truncating variants within the penultimate exon of DVL1. In five families in which samples from unaffected parents were available, the variants were demonstrated to represent de novo mutations. All variant alleles are predicted to result in a premature termination codon within the last exon, escape nonsense-mediated decay (NMD), and most likely generate a C-terminally truncated protein with a distinct -1 reading-frame terminus. Study of the transcripts extracted from affected subjects' leukocytes confirmed expression of both wild-type and variant alleles, supporting the hypothesis that mutant mRNA escapes NMD. Genomic variants identified in our study suggest that truncation of the C-terminal domain of DVL1, a protein hypothesized to have a downstream role in the Wnt-5a non-canonical pathway, is a common cause of DRS.
Keywords: Adaptor Proteins, Signal Transducing; Amino Acid Sequence; Base Sequence; Craniofacial Abnormalities; Dishevelled Proteins; DNA Primers; Dwarfism; Exome; Exons; Frameshift Mutation; Gene Components; Humans; Limb Deformities, Congenital; Molecular Sequence Data; Phosphoproteins; Sequence Analysis, DNA; Urogenital Abnormalities

Exome analysis of a family with Wolff-Parkinson-White syndrome identifies a novel disease locus. - Bowles, Neil E; Jou, Chuanchau J; Arrington, Cammon B; Kennedy, Brett J; Earl, Aubree; Matsunami, Norisada; Meyers, Lindsay L; Etheridge, Susan P; Saarel, Elizabeth V; Bleyl, Steven B; Yost, H Joseph; Yandell, Mark; et al. (Am J Med Genet A, 2015)
Wolff-Parkinson-White (WPW) syndrome is a common cause of supraventricular tachycardia that carries a risk of sudden cardiac death. To date, mutations in only one gene, PRKAG2, which encodes the 5'-AMP-activated protein kinase subunit γ-2, have been identified as causative for WPW. DNA samples from five members of a family with WPW were analyzed by exome sequencing. We applied recently designed prioritization strategies (VAAST/pedigree VAAST) coupled with an ontology-based algorithm (Phevor) that reduced the number of potentially damaging variants to 10: a variant in KCNE2 previously associated with Long QT syndrome was also identified. Of these 11 variants, only MYH6 p.E1885K segregated with the WPW phenotype in all affected individuals and was absent in 10 unaffected family members. This variant was predicted to be damaging by in silico methods and is not present in the 1,000 genome and NHLBI exome sequencing project databases. Screening of a replication cohort of 47 unrelated WPW patients did not identify other likely causative variants in PRKAG2 or MYH6. MYH6 variants have been identified in patients with atrial septal defects, cardiomyopathies, and sick sinus syndrome. Our data highlight the pleiotropic nature of phenotypes associated with defects in this gene.
Keywords: Adult; AMP-Activated Protein Kinases; Cardiac Myosins; Exome; Female; Genetic Loci; Humans; Male; Myosin Heavy Chains; Pedigree; Potassium Channels, Voltage-Gated; Wolff-Parkinson-White Syndrome

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

Exome sequencing identifies a homozygous C5orf42 variant in a Turkish kindred with oral-facial-digital syndrome type VI. - Bayram, Yavuz; Aydin, Hatip; Gambin, Tomasz; Akdemir, Zeynep Coban; Atik, Mehmed M; Karaca, Ender; Karaman, Ali; Pehlivan, Davut; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Am J Med Genet A, 2015)
Oral-facial-digital syndrome type VI (OFDVI) is a rare ciliopathy in the spectrum of Joubert syndrome (JS) and distinguished from other oral-facial-digital syndromes by metacarpal abnormalities with central polydactyly and by a molar tooth sign on cranial MRI. Additional characteristic features include short stature, micrognathia, posteriorly rotated low-set ears, hypertelorism, epicanthal folds, broad nasal tip, tongue hamartoma, upper lip notch, intraoral frenula, cleft lip/palate, and renal anomalies. Recently, novel mutations in C5orf42 were identified in 9 out of 11 OFDVI families. In a subsequent study C5orf42 was found to be mutated in only 2 out of 17 OFDVI probands while 28 patients with a pure JS phenotype also had pathogenic mutations of C5orf42. We report on two affected cousins diagnosed with OFDVI who were born from first degree cousin marriages. Whole exome sequencing (WES) identified a homozygous predicted damaging missense mutation (c.4034A > G; p.Gln1345Arg) in the C5orf42 gene. Our data contribute to the evidence that C5orf42 is one of the causative genes for OFDVI.
Keywords: Abnormalities, Multiple; Cerebellar Diseases; Cerebellum; Child; Cleft Palate; Exome; Eye Abnormalities; Female; Genetic Predisposition to Disease; Hamartoma; Homozygote; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Mutation; Orofaciodigital Syndromes; Phenotype; Retina; Turkey

Exome sequencing links mutations in PARN and RTEL1 with familial pulmonary fibrosis and telomere shortening. - Stuart, Bridget D; Choi, Jungmin; Zaidi, Samir; Xing, Chao; Holohan, Brody; Chen, Rui; Choi, Mihwa; Dharwadkar, Pooja; Torres, Fernando; Girod, Carlos E; Weissler, Jonathan; Fitzgerald, John; et al. (Nat Genet, 2015)
Idiopathic pulmonary fibrosis (IPF) is an age-related disease featuring progressive lung scarring. To elucidate the molecular basis of IPF, we performed exome sequencing of familial kindreds with pulmonary fibrosis. Gene burden analysis comparing 78 European cases and 2,816 controls implicated PARN, an exoribonuclease with no previous connection to telomere biology or disease, with five new heterozygous damaging mutations in unrelated cases and none in controls (P = 1.3 × 10(-8)); mutations were shared by all affected relatives (odds in favor of linkage = 4,096:1). RTEL1, an established locus for dyskeratosis congenita, harbored significantly more new damaging and missense variants at conserved residues in cases than in controls (P = 1.6 × 10(-6)). PARN and RTEL1 mutation carriers had shortened leukocyte telomere lengths, and we observed epigenetic inheritance of short telomeres in family members. Together, these genes explain ~7% of familial pulmonary fibrosis and strengthen the link between lung fibrosis and telomere dysfunction.
Keywords: Adult; Aged; Aged, 80 and over; Amino Acid Sequence; Case-Control Studies; Cells, Cultured; DNA Helicases; DNA Mutational Analysis; Exome; Exoribonucleases; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Idiopathic Pulmonary Fibrosis; Leukocytes; Lod Score; Male; Middle Aged; Molecular Sequence Data; Pedigree; Telomere; Telomere Shortening

Exome sequencing reveals homozygous TRIM2 mutation in a patient with early onset CMT and bilateral vocal cord paralysis. - Pehlivan, Davut; Coban Akdemir, Zeynep; Karaca, Ender; Bayram, Yavuz; Jhangiani, Shalini; Yildiz, Edibe Pembegul; Muzny, Donna; Uluc, Kayihan; Gibbs, Richard A; Elcioglu, Nursel; Lupski, James R; Harel, Tamar (Hum Genet, 2015)
Charcot-Marie-Tooth disease is a heterogeneous group of inherited distal symmetric polyneuropathies associated with mutations in genes encoding components essential for normal functioning of the Schwann cell and axon. TRIM2, encoding a ligase that ubiquitinates the neurofilament light chain, was recently associated with early-onset neuropathy in a single patient. We report a TRIM2 homozygous missense mutation (c.2000A>C; p.D667A) in a patient with peripheral neuropathy and bilateral vocal cord paralysis, allowing for further delineation of the associated phenotypic spectrum.
Keywords: Adult; Charcot-Marie-Tooth Disease; Exome; Female; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant, Newborn; Male; Mutation, Missense; Nuclear Proteins; Vocal Cord Paralysis

Expanding the Molecular and Clinical Phenotype of SSR4-CDG. - Ng, Bobby G; Raymond, Kimiyo; Kircher, Martin; Buckingham, Kati J; Wood, Tim; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Wong, Jonathan T S; Monteiro, Fabiola Paoli; Graham, Brett H; Jackson, Sheryl; et al. (Hum Mutat, 2015)
Congenital disorders of glycosylation (CDG) are a group of mostly autosomal recessive disorders primarily characterized by neurological abnormalities. Recently, we described a single CDG patient with a de novo mutation in the X-linked gene, Signal Sequence Receptor 4 (SSR4). We performed whole-exome sequencing to identify causal variants in several affected individuals who had either an undifferentiated neurological disorder or unsolved CDG of unknown etiology based on abnormal transferrin glycosylation. We now report eight affected males with either de novo (4) or inherited (4) loss of function mutations in SSR4. Western blot analysis revealed that the mutations caused a complete loss of SSR4 protein. In nearly all cases, the abnormal glycosylation of serum transferrin was only slightly above the accepted normal cutoff range.
Keywords: Calcium-Binding Proteins; Congenital Disorders of Glycosylation; DNA Mutational Analysis; Exome; Gene Order; Genes, X-Linked; Genetic Loci; Humans; Male; Membrane Glycoproteins; Mutation; Phenotype; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Functional genome-wide siRNA screen identifies KIAA0586 as mutated in Joubert syndrome. - Roosing, Susanne; Hofree, Matan; Kim, Sehyun; Scott, Eric; Copeland, Brett; Romani, Marta; Silhavy, Jennifer L; Rosti, Rasim O; Schroth, Jana; Mazza, Tommaso; Miccinilli, Elide; Zaki, Maha S; et al. (Elife, 2015)
Defective primary ciliogenesis or cilium stability forms the basis of human ciliopathies, including Joubert syndrome (JS), with defective cerebellar vermis development. We performed a high-content genome-wide small interfering RNA (siRNA) screen to identify genes regulating ciliogenesis as candidates for JS. We analyzed results with a supervised-learning approach, using SYSCILIA gold standard, Cildb3.0, a centriole siRNA screen and the GTex project, identifying 591 likely candidates. Intersection of this data with whole exome results from 145 individuals with unexplained JS identified six families with predominantly compound heterozygous mutations in KIAA0586. A c.428del base deletion in 0.1% of the general population was found in trans with a second mutation in an additional set of 9 of 163 unexplained JS patients. KIAA0586 is an orthologue of chick Talpid3, required for ciliogenesis and Sonic hedgehog signaling. Our results uncover a relatively high frequency cause for JS and contribute a list of candidates for future gene discoveries in ciliopathies.
Keywords: Abnormalities, Multiple; Cell Cycle Proteins; Cerebellum; Eye Abnormalities; Gene Frequency; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Heterozygote; Humans; Kidney Diseases, Cystic; Mutant Proteins; Retina; RNA, Small Interfering

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

Global transcriptional disturbances underlie Cornelia de Lange syndrome and related phenotypes. - Yuan, Bo; Pehlivan, Davut; Karaca, Ender; Patel, Nisha; Charng, Wu-Lin; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Sutton, V Reid; Yesil, Gözde; Bozdogan, Sevcan Tug; Tos, Tulay; Koparir, Asuman; et al. (J Clin Invest, 2015)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder that presents with extensive phenotypic variability, including facial dysmorphism, developmental delay/intellectual disability (DD/ID), abnormal extremities, and hirsutism. About 65% of patients harbor mutations in genes that encode subunits or regulators of the cohesin complex, including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. Wiedemann-Steiner syndrome (WDSTS), which shares CdLS phenotypic features, is caused by mutations in lysine-specific methyltransferase 2A (KMT2A). Here, we performed whole-exome sequencing (WES) of 2 male siblings clinically diagnosed with WDSTS; this revealed a hemizygous, missense mutation in SMC1A that was predicted to be deleterious. Extensive clinical evaluation and WES of 32 Turkish patients clinically diagnosed with CdLS revealed the presence of a de novo heterozygous nonsense KMT2A mutation in 1 patient without characteristic WDSTS features. We also identified de novo heterozygous mutations in SMC3 or SMC1A that affected RNA splicing in 2 independent patients with combined CdLS and WDSTS features. Furthermore, in families from 2 separate world populations segregating an autosomal-recessive disorder with CdLS-like features, we identified homozygous mutations in TAF6, which encodes a core transcriptional regulatory pathway component. Together, our data, along with recent transcriptome studies, suggest that CdLS and related phenotypes may be "transcriptomopathies" rather than cohesinopathies.
Keywords: Adolescent; Adult; Cell Cycle Proteins; Child; Child, Preschool; Chondroitin Sulfate Proteoglycans; Chromosomal Proteins, Non-Histone; Codon, Nonsense; De Lange Syndrome; Exome; Exonucleases; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Heterozygote; Histone Deacetylases; Histone-Lysine N-Methyltransferase; Humans; Infant; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Proteins; Repressor Proteins; Transcriptome

Homozygous loss-of-function mutations in SOHLH1 in patients with nonsyndromic hypergonadotropic hypogonadism. - Bayram, Yavuz; Gulsuner, Suleyman; Guran, Tulay; Abaci, Ayhan; Yesil, Gözde; Gulsuner, Hilal Unal; Atay, Zeynep; Pierce, Sarah B; Gambin, Tomasz; Lee, Ming; Turan, Serap; Bober, Ece; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Hypergonadotropic hypogonadism presents in females with delayed or arrested puberty, primary or secondary amenorrhea due to gonadal dysfunction, and is further characterized by elevated gonadotropins and low sex steroids. Chromosomal aberrations and various specific gene defects can lead to hypergonadotropic hypogonadism. Responsible genes include those with roles in gonadal development or maintenance, sex steroid synthesis, or end-organ resistance to gonadotropins. Identification of novel causative genes in this disorder will contribute to our understanding of the regulation of human reproductive function. OBJECTIVES: The aim of this study was to identify and report the gene responsible for autosomal-recessive hypergonadotropic hypogonadism in two unrelated families. DESIGN AND PARTICIPANTS: Clinical evaluation and whole-exome sequencing were performed in two pairs of sisters with nonsyndromic hypergonadotropic hypogonadism from two unrelated families. RESULTS: Exome sequencing analysis revealed two different truncating mutations in the same gene: SOHLH1 c.705delT (p.Pro235fs*4) and SOHLH1 c.27C>G (p.Tyr9stop). Both mutations were unique to the families and segregation was consistent with Mendelian expectations for an autosomal-recessive mode of inheritance. CONCLUSIONS: Sohlh1 was known from previous mouse studies to be a transcriptional regulator that functions in the maintenance and survival of primordial ovarian follicles, but loss-of-function mutations in human females have not been reported. Our results provide evidence that homozygous-truncating mutations in SOHLH1 cause female nonsyndromic hypergonadotropic hypogonadism.
Keywords: Adolescent; Basic Helix-Loop-Helix Transcription Factors; Child; Exome; Female; Homozygote; Humans; Hypogonadism; Mutation

Identification and functional characterization of natural human melanocortin 1 receptor mutant alleles in Pakistani population. - Shahzad, Mohsin; Sires Campos, Julia; Tariq, Nabeela; Herraiz Serrano, Cecilia; Yousaf, Rizwan; Jiménez-Cervantes, Celia; Yousaf, Sairah; Waryah, Yar M; Dad, Haseeb A; Blue, Elizabeth M; Sobreira, Nara; López-Giráldez, Francesc; et al. (Pigment Cell Melanoma Res, 2015)
Melanocortin 1 receptor (MC1R), a Gs protein-coupled receptor of the melanocyte's plasma membrane, is a major determinant of skin pigmentation and phototype. Upon activation by α-melanocyte stimulating hormone, MC1R triggers the cAMP cascade to stimulate eumelanogenesis. We used whole-exome sequencing to identify causative alleles in Pakistani families with skin and hair hypopigmentation. Six MC1R mutations segregated with the phenotype in seven families, including a p.Val174del in-frame deletion and a p.Tyr298* nonsense mutation, that were analyzed for function in heterologous HEK293 cells. p.Tyr298* MC1R showed no agonist-induced signaling to the cAMP or ERK pathways, nor detectable agonist binding. Conversely, signaling was comparable for p.Val174del and wild-type in HEK cells overexpressing the proteins, but binding analysis suggested impaired cell surface expression. Flow cytometry and confocal imaging studies revealed reduced plasma membrane expression of p.Val174del and p.Tyr298*. Therefore, p.Tyr298* was a total loss-of-function (LOF) allele, while p.Val174del displayed a partial LOF attribute.
Keywords: Alleles; Family; Female; Humans; Hypopigmentation; Male; Mutation; Pakistan; Pedigree; Phenotype; Receptor, Melanocortin, Type 1

Mutations in COL27A1 cause Steel syndrome and suggest a founder mutation effect in the Puerto Rican population. - Gonzaga-Jauregui, Claudia; Gamble, Candace N; Yuan, Bo; Penney, Samantha; Jhangiani, Shalini; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Hecht, Jacqueline T (Eur J Hum Genet, 2015)
Osteochondrodysplasias represent a large group of developmental structural disorders that can be caused by mutations in a variety of genes responsible for chondrocyte development, differentiation, mineralization and early ossification. The application of whole-exome sequencing to disorders apparently segregating as Mendelian traits has proven to be an effective approach to disease gene identification for conditions with unknown molecular etiology. We identified a homozygous missense variant p.(Gly697Arg) in COL27A1, in a family with Steel syndrome and no consanguinity. Interestingly, the identified variant seems to have arisen as a founder mutation in the Puerto Rican population.
Keywords: Amino Acid Sequence; Child, Preschool; Comparative Genomic Hybridization; Exome; Female; Fibrillar Collagens; Follow-Up Studies; Founder Effect; Genotype; Hispanic Americans; Humans; Infant; Male; Molecular Sequence Data; Mutation; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Prostaglandins F; Puerto Rico; Sequence Alignment

Mutations in SPATA5 Are Associated with Microcephaly, Intellectual Disability, Seizures, and Hearing Loss. - Tanaka, Akemi J; Cho, Megan T; Millan, Francisca; Juusola, Jane; Retterer, Kyle; Joshi, Charuta; Niyazov, Dmitriy; Garnica, Adolfo; Gratz, Edward; Deardorff, Matthew; Wilkins, Alisha; Ortiz-Gonzalez, Xilma; et al. (Am J Hum Genet, 2015)
Using whole-exome sequencing, we have identified in ten families 14 individuals with microcephaly, developmental delay, intellectual disability, hypotonia, spasticity, seizures, sensorineural hearing loss, cortical visual impairment, and rare autosomal-recessive predicted pathogenic variants in spermatogenesis-associated protein 5 (SPATA5). SPATA5 encodes a ubiquitously expressed member of the ATPase associated with diverse activities (AAA) protein family and is involved in mitochondrial morphogenesis during early spermatogenesis. It might also play a role in post-translational modification during cell differentiation in neuronal development. Mutations in SPATA5 might affect brain development and function, resulting in microcephaly, developmental delay, and intellectual disability.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Base Sequence; Exome; Female; Gene Frequency; Genes, Recessive; Hearing Loss; Homeodomain Proteins; Humans; Intellectual Disability; Male; Microcephaly; Molecular Sequence Data; Mutation; Seizures; Sequence Alignment; Sequence Analysis, DNA

Mutations in TBX18 Cause Dominant Urinary Tract Malformations via Transcriptional Dysregulation of Ureter Development. - Vivante, Asaf; Kleppa, Marc-Jens; Schulz, Julian; Kohl, Stefan; Sharma, Amita; Chen, Jing; Shril, Shirlee; Hwang, Daw-Yang; Weiss, Anna-Carina; Kaminski, Michael M; Shukrun, Rachel; Kemper, Markus J; et al. (Am J Hum Genet, 2015)
Congenital anomalies of the kidneys and urinary tract (CAKUT) are the most common cause of chronic kidney disease in the first three decades of life. Identification of single-gene mutations that cause CAKUT permits the first insights into related disease mechanisms. However, for most cases the underlying defect remains elusive. We identified a kindred with an autosomal-dominant form of CAKUT with predominant ureteropelvic junction obstruction. By whole exome sequencing, we identified a heterozygous truncating mutation (c.1010delG) of T-Box transcription factor 18 (TBX18) in seven affected members of the large kindred. A screen of additional families with CAKUT identified three families harboring two heterozygous TBX18 mutations (c.1570C>T and c.487A>G). TBX18 is essential for developmental specification of the ureteric mesenchyme and ureteric smooth muscle cells. We found that all three TBX18 altered proteins still dimerized with the wild-type protein but had prolonged protein half life and exhibited reduced transcriptional repression activity compared to wild-type TBX18. The p.Lys163Glu substitution altered an amino acid residue critical for TBX18-DNA interaction, resulting in impaired TBX18-DNA binding. These data indicate that dominant-negative TBX18 mutations cause human CAKUT by interference with TBX18 transcriptional repression, thus implicating ureter smooth muscle cell development in the pathogenesis of human CAKUT.
Keywords: Base Sequence; Electrophoretic Mobility Shift Assay; Exome; Gene Expression Regulation, Developmental; Genes, Dominant; HEK293 Cells; Humans; Immunohistochemistry; Immunoprecipitation; Microscopy, Fluorescence; Molecular Sequence Data; Muscle, Smooth; Mutation; Pedigree; Sequence Analysis, DNA; T-Box Domain Proteins; Ureter; Urinary Tract

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Muzny, Donna; Yuan, Bo; Boerwinkle, Eric; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic Americans; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

Novel COL2A1 variant (c.619G>A, p.Gly207Arg) manifesting as a phenotype similar to progressive pseudorheumatoid dysplasia and spondyloepiphyseal dysplasia, Stanescu type. - Jurgens, Julie; Sobreira, Nara; Modaff, Peggy; Reiser, Catherine A; Seo, Soo Hyun; Seong, Moon-Woo; Park, Sung Sup; Kim, Ok Hwa; Cho, Tae-Joon; Pauli, Richard M (Hum Mutat, 2015)
Progressive pseudorheumatoid dysplasia (PPRD) is a rare, autosomal-recessive condition characterized by mild spondyloepiphyseal dysplasia (SED) and severe, progressive, early-onset arthritis due to WISP3 mutations. SED, Stanescu type, is a vaguely delineated autosomal-dominant dysplasia of unknown genetic etiology. Here, we report three individuals from two unrelated families with radiological features similar to PPRD and SED, Stanescu type who share the same novel COL2A1 variant and were matched following discussion at an academic conference. In the first family, we performed whole-exome sequencing on three family members, two of whom have a PPRD-like phenotype, and identified a heterozygous variant (c.619G>A, p.Gly207Arg) in both affected individuals. Independently, targeted sequencing of the COL2A1 gene in an unrelated proband with a similar phenotype identified the same heterozygous variant. We suggest that the p.Gly207Arg variant causes a distinct type II collagenopathy with features of PPRD and SED, Stanescu type.
Keywords: Adolescent; Adult; Child; Collagen Type II; Exome; Female; Humans; Joint Diseases; Male; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Radiography; Sequence Analysis, DNA

Rare variants in the notch signaling pathway describe a novel type of autosomal recessive Klippel-Feil syndrome. - Karaca, Ender; Yuregir, Ozge O; Bozdogan, Sevcan T; Aslan, Huseyin; Pehlivan, Davut; Jhangiani, Shalini N; Akdemir, Zeynep C; Gambin, Tomasz; Bayram, Yavuz; Atik, Mehmed M; Erdin, Serkan; Muzny, Donna; et al. (Am J Med Genet A, 2015)
Klippel-Feil syndrome is a rare disorder represented by a subgroup of segmentation defects of the vertebrae and characterized by fusion of the cervical vertebrae, low posterior hairline, and short neck with limited motion. Both autosomal dominant and recessive inheritance patterns were reported in families with Klippel-Feil. Mutated genes for both dominant (GDF6 and GDF3) and recessive (MEOX1) forms of Klippel-Feil syndrome have been shown to be involved in somite development via transcription regulation and signaling pathways. Heterotaxy arises from defects in proteins that function in the development of left-right asymmetry of the developing embryo. We describe a consanguineous family with a male proband who presents with classical Klippel-Feil syndrome together with heterotaxy (situs inversus totalis). The present patient also had Sprengel's deformity, deformity of the sternum, and a solitary kidney. Using exome sequencing, we identified a homozygous frameshift mutation (c.299delT; p.L100fs) in RIPPLY2, a gene shown to play a crucial role in somitogenesis and participate in the Notch signaling pathway via negatively regulating Tbx6. Our data confirm RIPPLY2 as a novel gene for autosomal recessive Klippel-Feil syndrome, and in addition-from a mechanistic standpoint-suggest the possibility that mutations in RIPPLY2 could also lead to heterotaxy. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescent; Base Sequence; Female; Humans; Klippel-Feil Syndrome; Male; Molecular Sequence Data; Mutation; Pedigree; Radiography; Receptors, Notch; Signal Transduction; Spine

Recurrent gain of function mutation in calcium channel CACNA1H causes early-onset hypertension with primary aldosteronism. - Scholl, Ute I; Stölting, Gabriel; Nelson-Williams, Carol; Vichot, Alfred A; Choi, Murim; Loring, Erin; Prasad, Manju L; Goh, Gerald; Carling, Tobias; Juhlin, C Christofer; Quack, Ivo; Rump, Lars C; et al. (Elife, 2015)
Many Mendelian traits are likely unrecognized owing to absence of traditional segregation patterns in families due to causation by de novo mutations, incomplete penetrance, and/or variable expressivity. Genome-level sequencing can overcome these complications. Extreme childhood phenotypes are promising candidates for new Mendelian traits. One example is early onset hypertension, a rare form of a global cause of morbidity and mortality. We performed exome sequencing of 40 unrelated subjects with hypertension due to primary aldosteronism by age 10. Five subjects (12.5%) shared the identical, previously unidentified, heterozygous CACNA1H(M1549V) mutation. Two mutations were demonstrated to be de novo events, and all mutations occurred independently. CACNA1H encodes a voltage-gated calcium channel (CaV3.2) expressed in adrenal glomerulosa. CACNA1H(M1549V) showed drastically impaired channel inactivation and activation at more hyperpolarized potentials, producing increased intracellular Ca(2+), the signal for aldosterone production. This mutation explains disease pathogenesis and provides new insight into mechanisms mediating aldosterone production and hypertension.
Keywords: Adolescent; Adult; Age of Onset; Aldosterone; Amino Acid Sequence; Calcium; Calcium Channels, T-Type; Calcium Signaling; Child; Child, Preschool; Female; Gene Expression; Genotype; Heterozygote; Humans; Hyperaldosteronism; Hypertension; Infant; Male; Membrane Potentials; Middle Aged; Molecular Sequence Data; Mutation; Phenotype; Recurrence; Sequence Alignment; Zona Glomerulosa

Secondary findings and carrier test frequencies in a large multiethnic sample. - Gambin, Tomasz; Jhangiani, Shalini N; Below, Jennifer E; Campbell, Ian M; Wiszniewski, Wojciech; Muzny, Donna M; Staples, Jeffrey; Morrison, Alanna C; Bainbridge, Matthew N; Penney, Samantha; McGuire, Amy L; Gibbs, Richard A; et al. (Genome Med, 2015)
BACKGROUND: Besides its growing importance in clinical diagnostics and understanding the genetic basis of Mendelian and complex diseases, whole exome sequencing (WES) is a rich source of additional information of potential clinical utility for physicians, patients and their families. We analyzed the frequency and nature of single nucleotide variants (SNVs) considered secondary findings and recessive disease allele carrier status in the exomes of 8554 individuals from a large, randomly sampled cohort study and 2514 patients from a study of presumed Mendelian disease having undergone WES. METHODS: We used the same sequencing platform and data processing pipeline to analyze all samples and characterized the distributions of reported pathogenic (ClinVar, Human Gene Mutation Database (HGMD)) and predicted deleterious variants in the pre-specified American College of Medical Genetics and Genomics (ACMG) secondary findings and recessive disease genes in different ethnic groups. RESULTS: In the 56 ACMG secondary findings genes, the average number of predicted deleterious variants per individual was 0.74, and the mean number of ClinVar reported pathogenic variants was 0.06. We observed an average of 10 deleterious and 0.78 ClinVar reported pathogenic variants per individual in 1423 autosomal recessive disease genes. By repeatedly sampling pairs of exomes, 0.5 % of the randomly generated couples were at 25 % risk of having an affected offspring for an autosomal recessive disorder based on the ClinVar variants. CONCLUSIONS: By investigating reported pathogenic and novel, predicted deleterious variants we estimated the lower and upper limits of the population fraction for which exome sequencing may reveal additional medically relevant information. We suggest that the observed wide range for the lower and upper limits of these frequency numbers will be gradually reduced due to improvement in classification databases and prediction algorithms.

An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes. - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A; Szymanska, Katarzyna; Nguyen, Thanh-Minh T; Racher, Hilary; Phelps, Ian G; Toedt, Grischa; Kennedy, Julie; Wunderlich, Kirsten A; Sorusch, Nasrin; Abdelhamed, Zakia A; et al. (Nat Cell Biol, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
Keywords: Abnormalities, Multiple; Animals; Caenorhabditis elegans; Cerebellar Diseases; Cerebellum; Cilia; Ciliary Motility Disorders; Databases, Genetic; Ellis-Van Creveld Syndrome; Eye Abnormalities; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Genomics; HEK293 Cells; High-Throughput Nucleotide Sequencing; Humans; Kidney Diseases, Cystic; Membrane Proteins; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Photoreceptor Cells; Pregnancy Proteins; Proteins; Reproducibility of Results; Retina; RNA Interference; Suppressor Factors, Immunologic; Transfection; Zebrafish

TBX6 null variants and a common hypomorphic allele in congenital scoliosis. - Wu, N; Ming, X; Xiao, J; Wu, Z; Chen, X; Shinawi, M; Shen, Y; Yu, G; Liu, J; Xie, H; Gucev, Z S; Liu, S; et al. (N Engl J Med, 2015)
BACKGROUND: Congenital scoliosis is a common type of vertebral malformation. Genetic susceptibility has been implicated in congenital scoliosis. METHODS: We evaluated 161 Han Chinese persons with sporadic congenital scoliosis, 166 Han Chinese controls, and 2 pedigrees, family members of which had a 16p11.2 deletion, using comparative genomic hybridization, quantitative polymerase-chain-reaction analysis, and DNA sequencing. We carried out tests of replication using an additional series of 76 Han Chinese persons with congenital scoliosis and a multicenter series of 42 persons with 16p11.2 deletions. RESULTS: We identified a total of 17 heterozygous TBX6 null mutations in the 161 persons with sporadic congenital scoliosis (11%); we did not observe any null mutations in TBX6 in 166 controls (P<3.8×10(-6)). These null alleles include copy-number variants (12 instances of a 16p11.2 deletion affecting TBX6) and single-nucleotide variants (1 nonsense and 4 frame-shift mutations). However, the discordant intrafamilial phenotypes of 16p11.2 deletion carriers suggest that heterozygous TBX6 null mutation is insufficient to cause congenital scoliosis. We went on to identify a common TBX6 haplotype as the second risk allele in all 17 carriers of TBX6 null mutations (P<1.1×10(-6)). Replication studies involving additional persons with congenital scoliosis who carried a deletion affecting TBX6 confirmed this compound inheritance model. In vitro functional assays suggested that the risk haplotype is a hypomorphic allele. Hemivertebrae are characteristic of TBX6-associated congenital scoliosis. CONCLUSIONS: Compound inheritance of a rare null mutation and a hypomorphic allele of TBX6 accounted for up to 11% of congenital scoliosis cases in the series that we analyzed. (Funded by the National Basic Research Program of China and others.).
Keywords: Adolescent; Asian Continental Ancestry Group; Child; Child, Preschool; Chromosomes, Human, Pair 16; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genotype; Humans; Male; Mutation; Pedigree; Phenotype; Radiography; Scoliosis; Sequence Deletion; Spine; T-Box Domain Proteins

Whole Exome Sequencing Identifies an Adult-Onset Case of Methylmalonic Aciduria and Homocystinuria Type C (cblC) with Non-Syndromic Bull's Eye Maculopathy. - Collison, Frederick T; Xie, Yajing Angela; Gambin, Tomasz; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Fishman, Gerald A; Allikmets, Rando (Ophthalmic Genet, 2015)
BACKGROUND: Methylmalonic aciduria and homocystinuria type C (cblC), a disorder of vitamin B12 (cobalamin) metabolism caused by mutations in the MMACHC gene, presents with many systemic symptoms, including neurological, cognitive, psychiatric, and thromboembolic events. Retinal phenotypes, including maculopathy, pigmentary retinopathy, and optic atrophy are common in early onset form of the disease but are rare in adult onset forms. MATERIALS AND METHODS: An adult Hispanic female presented with decreased central vision, bilateral pericentral ring scotomas and bull's eye-appearing macular lesions at 28 years of age. Her medical history was otherwise unremarkable except for iron deficiency anemia and both urinary tract and kidney infections. Screening of the ABCA4 gene, mutations in which frequently cause bull's eye maculopathy, was negative. Subsequently, analysis with whole exome sequencing was performed. RESULTS: Whole exome sequencing discovered compound heterozygous mutations in MMACHC, c.G482A:p.Arg161Gln and c.270_271insA:p.Arg91Lysfs*14, which segregated with the disease in the family. The genetic diagnosis was confirmed by biochemical laboratory testing, showing highly elevated urine methylmalonic acid/creatinine and homocysteine levels, and suggesting disease management with hydroxycobalamin injections and carnitine supplementation. CONCLUSIONS: In summary, a unique case of an adult patient with bull's eye macular lesions and no clinically relevant systemic symptoms was diagnosed with cblC by genetic screening and follow-up biochemical laboratory tests.
Keywords: Adult; Carrier Proteins; Electroretinography; Exome; Female; Genetic Testing; Heterozygote; Homocystinuria; Humans; Macular Degeneration; Mutation; Pedigree; Scotoma; Sequence Analysis, DNA; Tomography, Optical Coherence; Visual Acuity; Visual Fields; Vitamin B 12; Vitamin B 12 Deficiency; Vitamin B Complex

Whole-exome sequencing identifies homozygous GPR161 mutation in a family with pituitary stalk interruption syndrome. - Karaca, Ender; Buyukkaya, Ramazan; Pehlivan, Davut; Charng, Wu-Lin; Yaykasli, Kursat O; Bayram, Yavuz; Gambin, Tomasz; Withers, Marjorie; Atik, Mehmed M; Arslanoglu, Ilknur; Bolu, Semih; Erdin, Serkan; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Pituitary stalk interruption syndrome (PSIS) is a rare, congenital anomaly of the pituitary gland characterized by pituitary gland insufficiency, thin or discontinuous pituitary stalk, anterior pituitary hypoplasia, and ectopic positioning of the posterior pituitary gland (neurohypophysis). The clinical presentation of patients with PSIS varies from isolated growth hormone (GH) deficiency to combined pituitary insufficiency and accompanying extrapituitary findings. Mutations in HESX1, LHX4, OTX2, SOX3, and PROKR2 have been associated with PSIS in less than 5% of cases; thus, the underlying genetic etiology for the vast majority of cases remains to be determined. OBJECTIVE: We applied whole-exome sequencing (WES) to a consanguineous family with two affected siblings who have pituitary gland insufficiency and radiographic findings of hypoplastic (thin) pituitary gland, empty sella, ectopic neurohypophysis, and interrupted pitiutary stalk-characteristic clinical diagnostic findings of PSIS. DESIGN AND PARTICIPANTS: WES was applied to two affected and one unaffected siblings. RESULTS: WES of two affected and one unaffected sibling revealed a unique homozygous missense mutation in GPR161, which encodes the orphan G protein-coupled receptor 161, a protein responsible for transducing extracellular signals across the plasma membrane into the cell. CONCLUSION: Mutations of GPR161 may be implicated as a potential novel cause of PSIS.
Keywords: Adolescent; Child, Preschool; Exome; Female; Genome-Wide Association Study; Humans; Hypopituitarism; Mutation; Pituitary Gland; Receptors, G-Protein-Coupled

Whole-exome sequencing identifies novel homozygous mutation in NPAS2 in family with nonobstructive azoospermia. - Ramasamy, Ranjith; Bakırcıoğlu, M Emre; Cengiz, Cenk; Karaca, Ender; Scovell, Jason; Jhangiani, Shalini N; Akdemir, Zeynep C; Bainbridge, Matthew; Yu, Yao; Huff, Chad; Gibbs, Richard A; Lupski, James R; et al. (Fertil Steril, 2015)
OBJECTIVE: To investigate the genetic cause of nonobstructive azoospermia (NOA) in a consanguineous Turkish family through homozygosity mapping followed by targeted exon/whole-exome sequencing to identify genetic variations. DESIGN: Whole-exome sequencing (WES). SETTING: Research laboratory. PATIENT(S): Two siblings in a consanguineous family with NOA. INTERVENTION(S): Validating all variants passing filter criteria with Sanger sequencing to confirm familial segregation and absence in the control population. MAIN OUTCOME MEASURE(S): Discovery of a mutation that could potentially cause NOA. RESULT(S): A novel nonsynonymous mutation in the neuronal PAS-2 domain (NPAS2) was identified in a consanguineous family from Turkey. This mutation in exon 14 (chr2: 101592000 C>G) of NPAS2 is likely a disease-causing mutation as it is predicted to be damaging, it is a novel variant, and it segregates with the disease. Family segregation of the variants showed the presence of the homozygous mutation in the three brothers with NOA and a heterozygous mutation in the mother as well as one brother and one sister who were both fertile. The mutation is not found in the single-nucleotide polymorphism database, the 1000 Genomes Project, the Baylor College of Medicine cohort of 500 Turkish patients (not a population-specific polymorphism), or the matching 50 fertile controls. CONCLUSION(S): With the use of WES we identified a novel homozygous mutation in NPAS2 as a likely disease-causing variant in a Turkish family diagnosed with NOA. Our data reinforce the clinical role of WES in the molecular diagnosis of highly heterogeneous genetic diseases for which conventional genetic approaches have previously failed to find a molecular diagnosis.
Keywords: Adult; Azoospermia; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Exome; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Nerve Tissue Proteins; Pedigree

X-linked acrogigantism syndrome: clinical profile and therapeutic responses. - Beckers, Albert; Lodish, Maya Beth; Trivellin, Giampaolo; Rostomyan, Liliya; Lee, Misu; Faucz, Fabio R; Yuan, Bo; Choong, Catherine S; Caberg, Jean-Hubert; Verrua, Elisa; Naves, Luciana Ansaneli; Cheetham, Tim D; et al. (Endocr Relat Cancer, 2015)
X-linked acrogigantism (X-LAG) is a new syndrome of pituitary gigantism, caused by microduplications on chromosome Xq26.3, encompassing the gene GPR101, which is highly upregulated in pituitary tumors. We conducted this study to explore the clinical, radiological, and hormonal phenotype and responses to therapy in patients with X-LAG syndrome. The study included 18 patients (13 sporadic) with X-LAG and microduplication of chromosome Xq26.3. All sporadic cases had unique duplications and the inheritance pattern in two families was dominant, with all Xq26.3 duplication carriers being affected. Patients began to grow rapidly as early as 2-3 months of age (median 12 months). At diagnosis (median delay 27 months), patients had a median height and weight standard deviation scores (SDS) of >+3.9 SDS. Apart from the increased overall body size, the children had acromegalic symptoms including acral enlargement and facial coarsening. More than a third of cases had increased appetite. Patients had marked hypersecretion of GH/IGF1 and usually prolactin, due to a pituitary macroadenoma or hyperplasia. Primary neurosurgical control was achieved with extensive anterior pituitary resection, but postoperative hypopituitarism was frequent. Control with somatostatin analogs was not readily achieved despite moderate to high levels of expression of somatostatin receptor subtype-2 in tumor tissue. Postoperative use of adjuvant pegvisomant resulted in control of IGF1 in all five cases where it was employed. X-LAG is a new infant-onset gigantism syndrome that has a severe clinical phenotype leading to challenging disease management.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Chromosomes, Human, X; Female; Gigantism; Humans; Infant; Male; Pituitary Neoplasms; Young Adult

Attitudes of genetics professionals toward the return of incidental results from exome and whole-genome sequencing. - Yu, Joon-Ho; Harrell, Tanya M; Jamal, Seema M; Tabor, Holly K; Bamshad, Michael J (Am J Hum Genet, 2014)
Professional recommendations for the return of results from exome and whole-genome sequencing (ES/WGS) have been controversial. The lack of clear guidance about whether and, if so, how to return ES/WGS incidental results limits the extent to which individuals and families might benefit from ES/WGS. The perspectives of genetics professionals, particularly those at the forefront of using ES/WGS in clinics, are largely unknown. Data on stakeholder perspectives could help clarify how to weigh expert positions and recommendations. We conducted an online survey of 9,857 genetics professionals to learn their attitudes on the return of incidental results from ES/WGS and the recent American College of Medical Genetic and Genomics Recommendations for Reporting of Incidental Findings in Clinical Exome and Genome Sequencing. Of the 847 respondents, 760 completed the survey. The overwhelming majority of respondents thought that incidental ES/WGS results should be offered to adult patients (85%), healthy adults (75%), and the parents of a child with a medical condition (74%). The majority thought that incidental results about adult-onset conditions (62%) and carrier status (62%) should be offered to the parents of a child with a medical condition. About half thought that offered results should not be limited to those deemed clinically actionable. The vast majority (81%) thought that individual preferences should guide return. Genetics professionals' perspectives on the return of ES/WGS results differed substantially from current recommendations, underscoring the need to establish clear purpose for recommendations on the return of incidental ES/WGS results as professional societies grapple with developing and updating recommendations.
Keywords: Adult; Attitude of Health Personnel; Child; Exome; Genetics, Medical; Genome, Human; Humans; Incidental Findings; Workforce

Attitudes of non-African American focus group participants toward return of results from exome and whole genome sequencing. - Yu, Joon-Ho; Crouch, Julia; Jamal, Seema M; Bamshad, Michael J; Tabor, Holly K (Am J Med Genet A, 2014)
Exome sequencing and whole genome sequencing (ES/WGS) present individuals with the opportunity to benefit from a broad scope of genetic results of clinical and personal utility. Yet, it is unclear which genetic results people want to receive (i.e., what type of genetic information they want to learn about themselves) or conversely not receive, and how they want to receive or manage results over time. Very little is known about whether and how attitudes toward receiving individual results from ES/WGS vary among racial/ethnic populations. We conducted 13 focus groups with a racially and ethnically diverse parent population (n = 76) to investigate attitudes toward return of individual results from WGS. We report on our findings for non-African American (non-AA) participants. Non-AA participants were primarily interested in genetic results on which they could act or "do something about." They defined "actionability" broadly to include individual medical treatment and disease prevention. The ability to plan for the future was both a motivation for and an expected benefit of receiving results. Their concerns focused on the meaning of results, specifically the potential inaccuracy and uncertainty of results. Non-AA participants expected healthcare providers to be involved in results management by helping them interpret results in the context of their own health and by providing counseling support. We compare and contrast these themes with those we previously reported from our analysis of African American (AA) perspectives to highlight the importance of varying preferences for results, characterize the central role of temporal orientation in framing expectations about the possibility of receiving ES/WGS results, and identify potential avenues by which genomic healthcare disparities may be inadvertently perpetuated.
Keywords: Adult; African Americans; Aged; Attitude to Health; Exome; Female; Focus Groups; Genome, Human; Humans; Male; Middle Aged; Sequence Analysis, DNA

Biallelic truncating mutations in FMN2, encoding the actin-regulatory protein Formin 2, cause nonsyndromic autosomal-recessive intellectual disability. - Law, Rosalind; Dixon-Salazar, Tracy; Jerber, Julie; Cai, Na; Abbasi, Ansar A; Zaki, Maha S; Mittal, Kirti; Gabriel, Stacey B; Rafiq, Muhammad Arshad; Khan, Valeed; Nguyen, Maria; Ali, Ghazanfar; et al. (Am J Hum Genet, 2014)
Dendritic spines represent the major site of neuronal activity in the brain; they serve as the receiving point for neurotransmitters and undergo rapid activity-dependent morphological changes that correlate with learning and memory. Using a combination of homozygosity mapping and next-generation sequencing in two consanguineous families affected by nonsyndromic autosomal-recessive intellectual disability, we identified truncating mutations in formin 2 (FMN2), encoding a protein that belongs to the formin family of actin cytoskeleton nucleation factors and is highly expressed in the maturing brain. We found that FMN2 localizes to punctae along dendrites and that germline inactivation of mouse Fmn2 resulted in animals with decreased spine density; such mice were previously demonstrated to have a conditioned fear-learning defect. Furthermore, patient neural cells derived from induced pluripotent stem cells showed correlated decreased synaptic density. Thus, FMN2 mutations link intellectual disability either directly or indirectly to the regulation of actin-mediated synaptic spine density.
Keywords: Adolescent; Adult; Base Sequence; Chromosome Disorders; Cohort Studies; Consanguinity; Egypt; Exome; Female; Genes, Recessive; Genetic Linkage; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Intellectual Disability; Male; Microfilament Proteins; Molecular Sequence Data; Nuclear Proteins; Pakistan; Pedigree; Sequence Analysis, DNA; Sequence Deletion

Compound heterozygous CORO1A mutations in siblings with a mucocutaneous-immunodeficiency syndrome of epidermodysplasia verruciformis-HPV, molluscum contagiosum and granulomatous tuberculoid leprosy. - Stray-Pedersen, Asbjorg; Jouanguy, Emmanuelle; Crequer, Amandine; Bertuch, Alison A; Brown, Betty S; Jhangiani, Shalini N; Muzny, Donna M; Gambin, Tomasz; Sorte, Hanne; Sasa, Ghadir; Metry, Denise; Campbell, Judith; et al. (J Clin Immunol, 2014)
PURPOSE: Coronin-1A deficiency is a recently recognized autosomal recessive primary immunodeficiency caused by mutations in CORO1A (OMIM 605000) that results in T-cell lymphopenia and is classified as T(-)B(+)NK(+)severe combined immunodeficiency (SCID). Only two other CORO1A-kindred are known to date, thus the defining characteristics are not well delineated. We identified a unique CORO1A-kindred. METHODS: We captured a 10-year analysis of the immune-clinical phenotypes in two affected siblings from disease debut of age 7 years. Target-specific genetic studies were pursued but unrevealing. Telomere lengths were also assessed. Whole exome sequencing (WES) uncovered the molecular diagnosis and Western blot validated findings. RESULTS: We found the compound heterozygous CORO1A variants: c.248_249delCT (p.P83RfsX10) and a novel mutation c.1077delC (p.Q360RfsX44) (NM_007074.3) in two affected non-consanguineous siblings that manifested as absent CD4CD45RA(+) (naïve) T and memory B cells, low NK cells and abnormally increased double-negative (DN) ϒδ T-cells. Distinguishing characteristics were late clinical debut with an unusual mucocutaneous syndrome of epidermodysplasia verruciformis-human papilloma virus (EV-HPV), molluscum contagiosum and oral-cutaneous herpetic ulcers; the older female sibling also had a disfiguring granulomatous tuberculoid leprosy. Both had bilateral bronchiectasis and the female died of EBV+ lymphomas at age 16 years. The younger surviving male, without malignancy, had reproducibly very short telomere lengths, not before appreciated in CORO1A mutations. CONCLUSION: We reveal the third CORO1A-mutated kindred, with the immune phenotype of abnormal naïve CD4 and DN T-cells and newfound characteristics of a late/hypomorphic-like SCID of an EV-HPV mucocutaneous syndrome with also B and NK defects and shortened telomeres. Our findings contribute to the elucidation of the CORO1A-SCID-CID spectrum.
Keywords: Adolescent; B-Lymphocytes; CD4-Positive T-Lymphocytes; Child; DNA Mutational Analysis; Epidermodysplasia Verruciformis; Female; Genetic Predisposition to Disease; Granuloma; Heterozygote; Humans; Immunologic Memory; Killer Cells, Natural; Leprosy, Tuberculoid; Male; Microfilament Proteins; Molluscum Contagiosum; Mucous Membrane; Mutation; Papillomavirus Infections; Polymorphism, Genetic; Severe Combined Immunodeficiency; Siblings; Skin; Telomere Shortening

Diagnosis of ALG12-CDG by exome sequencing in a case of severe skeletal dysplasia. - Murali, Chaya; Lu, James T; Jain, Mahim; Liu, David S; Lachman, Ralph; Gibbs, Richard A; Lee, Brendan H; Cohn, Daniel; Campeau, Philippe M (Mol Genet Metab Rep, 2014)
Congenital Disorder of Glycosylation type Ig (ALG12-CDG) is part of a group of autosomal recessive conditions caused by deficiency of proteins involved in the assembly of dolichol-oligosaccharides used for protein N-glycosylation. In ALG12-CDG, the enzyme affected is encoded by the gene. Affected individuals present clinically with neurodevelopmental delay, growth retardation, immune deficiency, male genital hypoplasia, and cardiomyopathy. A total of six individuals have been reported in the literature. Here, we present an infant with rhizomelic short stature, talipes equinovarus, platyspondyly, and joint dislocations. The infant had marked underossification of the pubic bones. Exome sequencing was performed and two deletions, each resulting in frameshifts, were found in . A review of the literature revealed two infants with ALG12-CDG and a severe skeletal dysplasia, including under-ossification of cervical vertebrae, pubic bones, and knees; in addition to talipes equinovarus and rhizomelic short stature. The phenotype of the individual we describe resembles pseudodiastrophic dysplasia and we discuss similarities and differences between ALG12-CDG and pseudodiastrophic dysplasia. The differential diagnosis in selected undiagnosed skeletal dysplasias should include CDGs.

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

Exome sequencing identifies a recurrent de novo ZSWIM6 mutation associated with acromelic frontonasal dysostosis. - Smith, Joshua D; Hing, Anne V; Clarke, Christine M; Johnson, Nathan M; Perez, Francisco A; Park, Sarah S; Horst, Jeremy A; Mecham, Brig; Maves, Lisa; Nickerson, Deborah A; Cunningham, Michael L (Am J Hum Genet, 2014)
Acromelic frontonasal dysostosis (AFND) is a rare disorder characterized by distinct craniofacial, brain, and limb malformations, including frontonasal dysplasia, interhemispheric lipoma, agenesis of the corpus callosum, tibial hemimelia, preaxial polydactyly of the feet, and intellectual disability. Exome sequencing of one trio and two unrelated probands revealed the same heterozygous variant (c.3487C>T [p. Arg1163Trp]) in a highly conserved protein domain of ZSWIM6; this variant has not been seen in the 1000 Genomes data, dbSNP, or the Exome Sequencing Project. Sanger validation of the three trios confirmed that the variant was de novo and was also present in a fourth isolated proband. In situ hybridization of early zebrafish embryos at 24 hr postfertilization (hpf) demonstrated telencephalic expression of zswim6 and onset of midbrain, hindbrain, and retinal expression at 48 hpf. Immunohistochemistry of later-stage mouse embryos demonstrated tissue-specific expression in the derivatives of all three germ layers. qRT-PCR expression analysis of osteoblast and fibroblast cell lines available from two probands was suggestive of Hedgehog pathway activation, indicating that the ZSWIM6 mutation associated with AFND may lead to the craniofacial, brain and limb malformations through the disruption of Hedgehog signaling.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Craniofacial Abnormalities; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Face; Hedgehog Proteins; Humans; Intellectual Disability; Limb Deformities, Congenital; Mandibulofacial Dysostosis; Mice; Molecular Sequence Data; Mutation; Protein Structure, Tertiary; Zebrafish; Zinc Fingers

Exome sequencing links corticospinal motor neuron disease to common neurodegenerative disorders. - Novarino, Gaia; Fenstermaker, Ali G; Zaki, Maha S; Hofree, Matan; Silhavy, Jennifer L; Heiberg, Andrew D; Abdellateef, Mostafa; Rosti, Basak; Scott, Eric; Mansour, Lobna; Masri, Amira; Kayserili, Hülya; et al. (Science, 2014)
Hereditary spastic paraplegias (HSPs) are neurodegenerative motor neuron diseases characterized by progressive age-dependent loss of corticospinal motor tract function. Although the genetic basis is partly understood, only a fraction of cases can receive a genetic diagnosis, and a global view of HSP is lacking. By using whole-exome sequencing in combination with network analysis, we identified 18 previously unknown putative HSP genes and validated nearly all of these genes functionally or genetically. The pathways highlighted by these mutations link HSP to cellular transport, nucleotide metabolism, and synapse and axon development. Network analysis revealed a host of further candidate genes, of which three were mutated in our cohort. Our analysis links HSP to other neurodegenerative disorders and can facilitate gene discovery and mechanistic understanding of disease.
Keywords: Animals; Axons; Biological Transport; Cohort Studies; Exome; Gene Regulatory Networks; Genetic Association Studies; Humans; Motor Neuron Disease; Mutation; Neurons; Nucleotides; Pyramidal Tracts; Sequence Analysis, DNA; Spastic Paraplegia, Hereditary; Synapses; Transcriptome; Zebrafish

Expanding the phenotypic spectrum of ARID1B-mediated disorders and identification of altered cell-cycle dynamics due to ARID1B haploinsufficiency. - Sim, Joe C H; White, Susan M; Fitzpatrick, Elizabeth; Wilson, Gabrielle R; Gillies, Greta; Pope, Kate; Mountford, Hayley S; Torring, Pernille M; McKee, Shane; Vulto-van Silfhout, Anneke T; Jhangiani, Shalini N; Muzny, Donna M; et al. (Orphanet J Rare Dis, 2014)
BACKGROUND: Mutations in genes encoding components of the Brahma-associated factor (BAF) chromatin remodeling complex have recently been shown to contribute to multiple syndromes characterised by developmental delay and intellectual disability. ARID1B mutations have been identified as the predominant cause of Coffin-Siris syndrome and have also been shown to be a frequent cause of nonsyndromic intellectual disability. Here, we investigate the molecular basis of a patient with an overlapping but distinctive phenotype of intellectual disability, plantar fat pads and facial dysmorphism. METHODS/RESULTS: High density microarray analysis of the patient demonstrated a heterozygous deletion at 6q25.3, which resulted in the loss of four genes including AT Rich Interactive Domain 1B (ARID1B). Subsequent quantitative real-time PCR analysis revealed ARID1B haploinsufficiency in the patient. Analysis of both patient-derived and ARID1B knockdown fibroblasts after serum starvation demonstrated delayed cell cycle re-entry associated with reduced cell number in the S1 phase. Based on the patient's distinctive phenotype, we ascertained four additional patients and identified heterozygous de novo ARID1B frameshift or nonsense mutations in all of them. CONCLUSIONS: This study broadens the spectrum of ARID1B associated phenotypes by describing a distinctive phenotype including plantar fat pads but lacking the hypertrichosis or fifth nail hypoplasia associated with Coffin-Siris syndrome. We present the first direct evidence in patient-derived cells that alterations in cell cycle contribute to the underlying pathogenesis of syndromes associated with ARID1B haploinsufficiency.
Keywords: Abnormalities, Multiple; Cell Cycle; Chromatin Assembly and Disassembly; DNA-Binding Proteins; Face; Female; Hand Deformities, Congenital; Haploinsufficiency; Humans; Intellectual Disability; Male; Micrognathism; Neck; Transcription Factors

A general framework for estimating the relative pathogenicity of human genetic variants. - Kircher, Martin; Witten, Daniela M; Jain, Preti; O'Roak, Brian J; Cooper, Gregory M; Shendure, Jay (Nat Genet, 2014)
Current methods for annotating and interpreting human genetic variation tend to exploit a single information type (for example, conservation) and/or are restricted in scope (for example, to missense changes). Here we describe Combined Annotation-Dependent Depletion (CADD), a method for objectively integrating many diverse annotations into a single measure (C score) for each variant. We implement CADD as a support vector machine trained to differentiate 14.7 million high-frequency human-derived alleles from 14.7 million simulated variants. We precompute C scores for all 8.6 billion possible human single-nucleotide variants and enable scoring of short insertions-deletions. C scores correlate with allelic diversity, annotations of functionality, pathogenicity, disease severity, experimentally measured regulatory effects and complex trait associations, and they highly rank known pathogenic variants within individual genomes. The ability of CADD to prioritize functional, deleterious and pathogenic variants across many functional categories, effect sizes and genetic architectures is unmatched by any current single-annotation method.
Keywords: Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; INDEL Mutation; Models, Genetic; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Selection, Genetic; Support Vector Machine

Germ-line and somatic DICER1 mutations in pineoblastoma. - de Kock, Leanne; Sabbaghian, Nelly; Druker, Harriet; Weber, Evan; Hamel, Nancy; Miller, Suzanne; Choong, Catherine S; Gottardo, Nicholas G; Kees, Ursula R; Rednam, Surya P; van Hest, Liselotte P; Jongmans, Marjolijn C; et al. (Acta Neuropathol, 2014)
Germ-line RB-1 mutations predispose to pineoblastoma (PinB), but other predisposing genetic factors are not well established. We recently identified a germ-line DICER1 mutation in a child with a PinB. This was accompanied by loss of heterozygosity (LOH) of the wild-type allele within the tumour. We set out to establish the prevalence of DICER1 mutations in an opportunistically ascertained series of PinBs. Twenty-one PinB cases were studied: Eighteen cases had not undergone previous testing for DICER1 mutations; three patients were known carriers of germ-line DICER1 mutations. The eighteen PinBs were sequenced by Sanger and/or Fluidigm-based next-generation sequencing to identify DICER1 mutations in blood gDNA and/or tumour gDNA. Testing for somatic DICER1 mutations was also conducted on one case with a known germ-line DICER1 mutation. From the eighteen PinBs, we identified four deleterious DICER1 mutations, three of which were germ line in origin, and one for which a germ line versus somatic origin could not be determined; in all four, the second allele was also inactivated leading to complete loss of DICER1 protein. No somatic DICER1 RNase IIIb mutations were identified. One PinB arising in a germ-line DICER1 mutation carrier was found to have LOH. This study suggests that germ-line DICER1 mutations make a clinically significant contribution to PinB, establishing DICER1 as an important susceptibility gene for PinB and demonstrates PinB to be a manifestation of a germ-line DICER1 mutation. The means by which the second allele is inactivated may differ from other DICER1-related tumours.
Keywords: Adolescent; Brain Neoplasms; Child; Child, Preschool; DEAD-box RNA Helicases; DNA Mutational Analysis; Family Health; Female; Germ-Line Mutation; Humans; Infant; Male; Pineal Gland; Pinealoma; Ribonuclease III; Young Adult

Gigantism and acromegaly due to Xq26 microduplications and GPR101 mutation. - Trivellin, Giampaolo; Daly, Adrian F; Faucz, Fabio R; Yuan, Bo; Rostomyan, Liliya; Larco, Darwin O; Schernthaner-Reiter, Marie Helene; Szarek, Eva; Leal, Letícia F; Caberg, Jean-Hubert; Castermans, Emilie; Villa, Chiara; et al. (N Engl J Med, 2014)
BACKGROUND: Increased secretion of growth hormone leads to gigantism in children and acromegaly in adults; the genetic causes of gigantism and acromegaly are poorly understood. METHODS: We performed clinical and genetic studies of samples obtained from 43 patients with gigantism and then sequenced an implicated gene in samples from 248 patients with acromegaly. RESULTS: We observed microduplication on chromosome Xq26.3 in samples from 13 patients with gigantism; of these samples, 4 were obtained from members of two unrelated kindreds, and 9 were from patients with sporadic cases. All the patients had disease onset during early childhood. Of the patients with gigantism who did not carry an Xq26.3 microduplication, none presented before the age of 5 years. Genomic characterization of the Xq26.3 region suggests that the microduplications are generated during chromosome replication and that they contain four protein-coding genes. Only one of these genes, GPR101, which encodes a G-protein-coupled receptor, was overexpressed in patients' pituitary lesions. We identified a recurrent GPR101 mutation (p.E308D) in 11 of 248 patients with acromegaly, with the mutation found mostly in tumors. When the mutation was transfected into rat GH3 cells, it led to increased release of growth hormone and proliferation of growth hormone-producing cells. CONCLUSIONS: We describe a pediatric disorder (which we have termed X-linked acrogigantism [X-LAG]) that is caused by an Xq26.3 genomic duplication and is characterized by early-onset gigantism resulting from an excess of growth hormone. Duplication of GPR101 probably causes X-LAG. We also found a recurrent mutation in GPR101 in some adults with acromegaly. (Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development and others.).
Keywords: Acromegaly; Adolescent; Adult; Age of Onset; Child; Child, Preschool; Chromosome Duplication; Chromosomes, Human, X; Female; Gigantism; Human Growth Hormone; Humans; Infant; Male; Mutation; Phenotype; Protein Conformation; Receptors, G-Protein-Coupled

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; Transcription Factors

Individual exome analysis in diagnosis and management of paediatric liver failure of indeterminate aetiology. - Vilarinho, Sílvia; Choi, Murim; Jain, Dhanpat; Malhotra, Ajay; Kulkarni, Sanjay; Pashankar, Dinesh; Phatak, Uma; Patel, Mohini; Bale, Allen; Mane, Shrikant; Lifton, Richard P; Mistry, Pramod K (J Hepatol, 2014)
BACKGROUND & AIMS: In children with liver failure, as many as half remain of indeterminate aetiology. This hinders timely consideration of optimal treatment options. We posit that a significant subset of these children harbour known inherited metabolic liver diseases with atypical presentation or novel inborn errors of metabolism. We investigated the utility of whole-exome sequencing in three children with advanced liver disease of indeterminate aetiology. METHODS: Patient 1 was a 10 year-old female diagnosed with Wilson disease but no detectable ATP7B mutations, and decompensated liver cirrhosis who underwent liver transplant and subsequently developed onset of neurodegenerative disease. Patient 2 was a full-term 2 day-old male with fatal acute liver failure of indeterminate aetiology. Patient 3 was an 8 year-old female with progressive syndromic cholestasis of unknown aetiology since age 3 months. RESULTS: Unbiased whole-exome sequencing of germline DNA revealed homozygous mutations in MPV17 and SERAC1 as the disease causing genes in patient 1 and 2, respectively. This is the first demonstration of SERAC1 loss-of-function associated fatal acute liver failure. Patient 1 expands the phenotypic spectrum of the MPV17-related hepatocerebral mitochondrial DNA depletion syndrome. Patient 3 was found to have syndromic cholestasis due to bi-allelic NOTCH2 mutations. CONCLUSIONS: Our findings validate the application of whole-exome sequencing in the diagnosis and management of children with advanced liver disease of indeterminate aetiology, with the potential to enhance optimal selection of treatment options and adequate counselling of families. Moreover, whole-exome sequencing revealed a hitherto unrecognized phenotypic spectrum of inherited metabolic liver diseases.
Keywords: Amino Acid Sequence; Base Sequence; Carboxylic Ester Hydrolases; Child; Cholestasis; DNA Mutational Analysis; End Stage Liver Disease; Exome; Fatal Outcome; Female; Genes, Recessive; Hepatolenticular Degeneration; Heterozygote; Homozygote; Humans; Infant, Newborn; Liver Failure; Liver Failure, Acute; Male; Membrane Proteins; Mitochondrial Proteins; Molecular Sequence Data; Pedigree; Receptor, Notch2; RNA Splice Sites; Sequence Homology, Amino Acid

Informed consent for exome sequencing research in families with genetic disease: the emerging issue of incidental findings. - Bergner, Amanda L; Bollinger, Juli; Raraigh, Karen S; Tichnell, Crystal; Murray, Brittney; Blout, Carrie Lynn; Telegrafi, Aida Bytyci; James, Cynthia A (Am J Med Genet A, 2014)
Genomic sequencing technology is increasingly used in genetic research. Studies of informed consent for exome and genome sequencing (ES/GS) research have largely involved hypothetical scenarios or healthy individuals enrolling in population-based studies. Studies have yet to explore the consent experiences of adults with inherited disease. We conducted a qualitative interview study of 15 adults recently enrolled in a large-scale ES/GS study (11 affected adults, four parents of affected children). Our study had two goals: (1) to explore three theoretical barriers to consent for ES/GS research (interpretive/technical complexity, possibility of incidental findings, and risks of loss of privacy); and (2) to explore how interviewees experienced the consent process. Interviewees could articulate study goals and processes, describe incidental findings, discuss risks of privacy loss, and reflect on their consent experience. Few expected the study would identify the genetic cause of their condition. All elected to receive incidental findings. Interviewees acknowledged paying little attention to potential implications of incidental findings in light of more pressing goals of supporting research regarding their own medical conditions. Interviewees suggested that experience living with a genetic condition prepared them to adjust to incidental findings. Interviewees also expressed little concern about loss of confidentiality of study data. Some experienced the consent process as very long. None desired reconsent prior to return of study results. Families with inherited disease likely would benefit from a consent process in which study risks and benefits were discussed in the context of prior experiences with genetic research and genetic disease.
Keywords: Adolescent; Adult; Aged; Confidentiality; Ethics, Medical; Exome; Family; Female; Genetic Diseases, Inborn; Genetic Research; High-Throughput Nucleotide Sequencing; Humans; Incidental Findings; Informed Consent; Male; Middle Aged; Young Adult

Loss-of-function HDAC8 mutations cause a phenotypic spectrum of Cornelia de Lange syndrome-like features, ocular hypertelorism, large fontanelle and X-linked inheritance. - Kaiser, Frank J; Ansari, Morad; Braunholz, Diana; Concepción Gil-Rodríguez, María; Decroos, Christophe; Wilde, Jonathan J; Fincher, Christopher T; Kaur, Maninder; Bando, Masashige; Amor, David J; Atwal, Paldeep S; Bahlo, Melanie; et al. (Hum Mol Genet, 2014)
Cornelia de Lange syndrome (CdLS) is a multisystem genetic disorder with distinct facies, growth failure, intellectual disability, distal limb anomalies, gastrointestinal and neurological disease. Mutations in NIPBL, encoding a cohesin regulatory protein, account for >80% of cases with typical facies. Mutations in the core cohesin complex proteins, encoded by the SMC1A, SMC3 and RAD21 genes, together account for ∼5% of subjects, often with atypical CdLS features. Recently, we identified mutations in the X-linked gene HDAC8 as the cause of a small number of CdLS cases. Here, we report a cohort of 38 individuals with an emerging spectrum of features caused by HDAC8 mutations. For several individuals, the diagnosis of CdLS was not considered prior to genomic testing. Most mutations identified are missense and de novo. Many cases are heterozygous females, each with marked skewing of X-inactivation in peripheral blood DNA. We also identified eight hemizygous males who are more severely affected. The craniofacial appearance caused by HDAC8 mutations overlaps that of typical CdLS but often displays delayed anterior fontanelle closure, ocular hypertelorism, hooding of the eyelids, a broader nose and dental anomalies, which may be useful discriminating features. HDAC8 encodes the lysine deacetylase for the cohesin subunit SMC3 and analysis of the functional consequences of the missense mutations indicates that all cause a loss of enzymatic function. These data demonstrate that loss-of-function mutations in HDAC8 cause a range of overlapping human developmental phenotypes, including a phenotypically distinct subgroup of CdLS.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Cohort Studies; Cranial Fontanelles; De Lange Syndrome; Eye Abnormalities; Female; Genes, X-Linked; Histone Deacetylases; Humans; Hypertelorism; Infant; Male; Molecular Sequence Data; Mutation, Missense; Phenotype; Repressor Proteins; Sequence Alignment

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

Multilineage somatic activating mutations in HRAS and NRAS cause mosaic cutaneous and skeletal lesions, elevated FGF23 and hypophosphatemia. - Lim, Young H; Ovejero, Diana; Sugarman, Jeffrey S; Deklotz, Cynthia M C; Maruri, Ann; Eichenfield, Lawrence F; Kelley, Patrick K; Jüppner, Harald; Gottschalk, Michael; Tifft, Cynthia J; Gafni, Rachel I; Boyce, Alison M; et al. (Hum Mol Genet, 2014)
Pathologically elevated serum levels of fibroblast growth factor-23 (FGF23), a bone-derived hormone that regulates phosphorus homeostasis, result in renal phosphate wasting and lead to rickets or osteomalacia. Rarely, elevated serum FGF23 levels are found in association with mosaic cutaneous disorders that affect large proportions of the skin and appear in patterns corresponding to the migration of ectodermal progenitors. The cause and source of elevated serum FGF23 is unknown. In those conditions, such as epidermal and large congenital melanocytic nevi, skin lesions are variably associated with other abnormalities in the eye, brain and vasculature. The wide distribution of involved tissues and the appearance of multiple segmental skin and bone lesions suggest that these conditions result from early embryonic somatic mutations. We report five such cases with elevated serum FGF23 and bone lesions, four with large epidermal nevi and one with a giant congenital melanocytic nevus. Exome sequencing of blood and affected skin tissue identified somatic activating mutations of HRAS or NRAS in each case without recurrent secondary mutation, and we further found that the same mutation is present in dysplastic bone. Our finding of somatic activating RAS mutation in bone, the endogenous source of FGF23, provides the first evidence that elevated serum FGF23 levels, hypophosphatemia and osteomalacia are associated with pathologic Ras activation and may provide insight in the heretofore limited understanding of the regulation of FGF23.
Keywords: Adolescent; Child; Exome; Female; Fibroblast Growth Factors; Gene Expression Regulation, Developmental; GTP Phosphohydrolases; Humans; Hypophosphatemia; Male; Membrane Proteins; Mutation; Nevus; Nevus, Pigmented; Osteomalacia; Proto-Oncogene Proteins p21(ras); Sequence Analysis, DNA; Skin; Skin Neoplasms

Mutations in Alström protein impair terminal differentiation of cardiomyocytes. - Shenje, Lincoln T; Andersen, Peter; Halushka, Marc K; Lui, Cecillia; Fernandez, Laviel; Collin, Gayle B; Amat-Alarcon, Nuria; Meschino, Wendy; Cutz, Ernest; Chang, Kenneth; Yonescu, Raluca; Batista, Denise A S; et al. (Nat Commun, 2014)
Cardiomyocyte cell division and replication in mammals proceed through embryonic development and abruptly decline soon after birth. The process governing cardiomyocyte cell cycle arrest is poorly understood. Here we carry out whole-exome sequencing in an infant with evidence of persistent postnatal cardiomyocyte replication to determine the genetic risk factors. We identify compound heterozygous ALMS1 mutations in the proband, and confirm their presence in her affected sibling, one copy inherited from each heterozygous parent. Next, we recognize homozygous or compound heterozygous truncating mutations in ALMS1 in four other children with high levels of postnatal cardiomyocyte proliferation. Alms1 mRNA knockdown increases multiple markers of proliferation in cardiomyocytes, the percentage of cardiomyocytes in G2/M phases, and the number of cardiomyocytes by 10% in cultured cells. Homozygous Alms1-mutant mice have increased cardiomyocyte proliferation at 2 weeks postnatal compared with wild-type littermates. We conclude that deficiency of Alström protein impairs postnatal cardiomyocyte cell cycle arrest.
Keywords: Animals; Cell Cycle; Cell Differentiation; Cells, Cultured; DNA-Binding Proteins; Humans; Immunohistochemistry; Mice; Molecular Sequence Data; Mutation; Myocytes, Cardiac; Proteins; Reverse Transcriptase Polymerase Chain Reaction

Mutations in PCYT1A, encoding a key regulator of phosphatidylcholine metabolism, cause spondylometaphyseal dysplasia with cone-rod dystrophy. - Hoover-Fong, Julie; Sobreira, Nara; Jurgens, Julie; Modaff, Peggy; Blout, Carrie; Moser, Ann; Kim, Ok-Hwa; Cho, Tae-Joon; Cho, Sung Yoon; Kim, Sang Jin; Jin, Dong-Kyu; Kitoh, Hiroshi; et al. (Am J Hum Genet, 2014)
Keywords: Alleles; Child, Preschool; Choline-Phosphate Cytidylyltransferase; Female; Humans; Infant; Male; Middle Aged; Mutation, Missense; Osteochondrodysplasias; Pedigree; Phosphatidylcholines; Retinitis Pigmentosa

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Mutations in TJP2 cause progressive cholestatic liver disease. - Sambrotta, Melissa; Strautnieks, Sandra; Papouli, Efterpi; Rushton, Peter; Clark, Barnaby E; Parry, David A; Logan, Clare V; Newbury, Lucy J; Kamath, Binita M; Ling, Simon; Grammatikopoulos, Tassos; Wagner, Bart E; et al. (Nat Genet, 2014)
Elucidating genetic causes of cholestasis has proved to be important in understanding the physiology and pathophysiology of the liver. Here we show that protein-truncating mutations in the tight junction protein 2 gene (TJP2) cause failure of protein localization and disruption of tight-junction structure, leading to severe cholestatic liver disease. These findings contrast with those in the embryonic-lethal knockout mouse, highlighting differences in redundancy in junctional complexes between organs and species.
Keywords: Animals; Base Sequence; Cholestasis, Intrahepatic; High-Throughput Nucleotide Sequencing; Humans; Immunoblotting; Immunohistochemistry; Mice; Mice, Knockout; Microscopy, Electron, Transmission; Models, Biological; Molecular Sequence Data; Mutation; Pedigree; Real-Time Polymerase Chain Reaction; Sequence Alignment; Species Specificity; Tight Junctions; Zonula Occludens-2 Protein

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Muzny, Donna; Boerwinkle, Eric; Gibbs, Richard; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

Novel Deletion of SERPINF1 Causes Autosomal Recessive Osteogenesis Imperfecta Type VI in Two Brazilian Families. - Minillo, Renata Moldenhauer; Sobreira, Nara; de Faria Soares, Maria de Fatima; Jurgens, Julie; Ling, Hua; Hetrick, Kurt N; Doheny, Kimberly F; Valle, David; Brunoni, Decio; Perez, Ana B Alvarez (Mol Syndromol, 2014)
Autosomal recessive osteogenesis imperfecta (OI) accounts for 10% of all OI cases, and, currently, mutations in 10 genes (CRTAP, LEPRE1, PPIB, SERPINH1, FKBP10, SERPINF1, SP7, BMP1, TMEM38B, and WNT1) are known to be responsible for this form of the disease. PEDF is a secreted glycoprotein of the serpin superfamily that maintains bone homeostasis and regulates osteoid mineralization, and it is encoded by SERPINF1, currently associated with OI type VI (MIM 172860). Here, we report a consanguineous Brazilian family in which multiple individuals from at least 4 generations are affected with a severe form of OI, and we also report an unrelated individual from the same small city in Brazil with a similar but more severe phenotype. In both families the same homozygous SERPINF1 19-bp deletion was identified which is not known in the literature yet. We described intra- and interfamilial clinical and radiological phenotypic variability of OI type VI caused by the same homozygous SERPINF1 19-bp deletion and suggest a founder effect. Furthermore, the SERPINF1 genotypes/phenotypes reported so far in the literature are reviewed.

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Muzny, Donna M; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

Parent of origin, mosaicism, and recurrence risk: probabilistic modeling explains the broken symmetry of transmission genetics. - Campbell, Ian M; Stewart, Jonathan R; James, Regis A; Lupski, James R; Stankiewicz, Paweł; Olofsson, Peter; Shaw, Chad A (Am J Hum Genet, 2014)
Most new mutations are observed to arise in fathers, and increasing paternal age positively correlates with the risk of new variants. Interestingly, new mutations in X-linked recessive disease show elevated familial recurrence rates. In male offspring, these mutations must be inherited from mothers. We previously developed a simulation model to consider parental mosaicism as a source of transmitted mutations. In this paper, we extend and formalize the model to provide analytical results and flexible formulas. The results implicate parent of origin and parental mosaicism as central variables in recurrence risk. Consistent with empirical data, our model predicts that more transmitted mutations arise in fathers and that this tendency increases as fathers age. Notably, the lack of expansion later in the male germline determines relatively lower variance in the proportion of mutants, which decreases with paternal age. Subsequently, observation of a transmitted mutation has less impact on the expected risk for future offspring. Conversely, for the female germline, which arrests after clonal expansion in early development, variance in the mutant proportion is higher, and observation of a transmitted mutation dramatically increases the expected risk of recurrence in another pregnancy. Parental somatic mosaicism considerably elevates risk for both parents. These findings have important implications for genetic counseling and for understanding patterns of recurrence in transmission genetics. We provide a convenient online tool and source code implementing our analytical results. These tools permit varying the underlying parameters that influence recurrence risk and could be useful for analyzing risk in diverse family structures.
Keywords: Adult; Aged; Aged, 80 and over; Chromosome Aberrations; DNA Copy Number Variations; Fathers; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Inheritance Patterns; Male; Middle Aged; Models, Theoretical; Mosaicism; Mothers; Pregnancy; Recurrence; Risk Factors; Young Adult

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Somatic mutations in cerebral cortical malformations. - Jamuar, Saumya S; Lam, Anh-Thu N; Kircher, Martin; D'Gama, Alissa M; Wang, Jian; Barry, Brenda J; Zhang, Xiaochang; Hill, Robert Sean; Partlow, Jennifer N; Rozzo, Aldo; Servattalab, Sarah; Mehta, Bhaven K; et al. (N Engl J Med, 2014)
BACKGROUND: Although there is increasing recognition of the role of somatic mutations in genetic disorders, the prevalence of somatic mutations in neurodevelopmental disease and the optimal techniques to detect somatic mosaicism have not been systematically evaluated. METHODS: Using a customized panel of known and candidate genes associated with brain malformations, we applied targeted high-coverage sequencing (depth, ≥200×) to leukocyte-derived DNA samples from 158 persons with brain malformations, including the double-cortex syndrome (subcortical band heterotopia, 30 persons), polymicrogyria with megalencephaly (20), periventricular nodular heterotopia (61), and pachygyria (47). We validated candidate mutations with the use of Sanger sequencing and, for variants present at unequal read depths, subcloning followed by colony sequencing. RESULTS: Validated, causal mutations were found in 27 persons (17%; range, 10 to 30% for each phenotype). Mutations were somatic in 8 of the 27 (30%), predominantly in persons with the double-cortex syndrome (in whom we found mutations in DCX and LIS1), persons with periventricular nodular heterotopia (FLNA), and persons with pachygyria (TUBB2B). Of the somatic mutations we detected, 5 (63%) were undetectable with the use of traditional Sanger sequencing but were validated through subcloning and subsequent sequencing of the subcloned DNA. We found potentially causal mutations in the candidate genes DYNC1H1, KIF5C, and other kinesin genes in persons with pachygyria. CONCLUSIONS: Targeted sequencing was found to be useful for detecting somatic mutations in patients with brain malformations. High-coverage sequencing panels provide an important complement to whole-exome and whole-genome sequencing in the evaluation of somatic mutations in neuropsychiatric disease. (Funded by the National Institute of Neurological Disorders and Stroke and others.).
Keywords: Cerebral Cortex; Classical Lissencephalies and Subcortical Band Heterotopias; DNA Mutational Analysis; Humans; Lissencephaly; Magnetic Resonance Imaging; Malformations of Cortical Development; Mutation; Periventricular Nodular Heterotopia

Structural variation and missense mutation in SBDS associated with Shwachman-Diamond syndrome. - Carvalho, Claudia M B; Zuccherato, Luciana W; Williams, Christopher L; Neill, Nicholas J; Murdock, David R; Bainbridge, Matthew; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Ip, Wan; Guillerman, Robert Paul; Lupski, James R; et al. (BMC Med Genet, 2014)
BACKGROUND: Shwachman-Diamond syndrome (SDS) is an autosomal recessive ribosomopathy caused mainly by compound heterozygous mutations in SBDS. Structural variation (SV) involving the SBDS locus has been rarely reported in association with the disease. We aimed to determine whether an SV contributed to the pathogenesis of a case lacking biallelic SBDS point mutations. CASE PRESENTATION: Whole exome sequencing was performed in a patient with SDS lacking biallelic SBDS point mutations. Array comparative genomic hybridization and Southern blotting were used to seek SVs across the SBDS locus. Locus-specific polymerase chain reaction (PCR) encompassing flanking intronic sequence was also performed to investigate mutation within the locus. RNA expression and Western blotting were performed to analyze allele and protein expression. We found the child harbored a single missense mutation in SBDS (c.98A > C; p.K33T), inherited from the mother, and an SV in the SBDS locus, inherited from the father. The missense allele and SV segregated in accordance with Mendelian expectations for autosomal recessive SDS. Complementary DNA and western blotting analysis and locus specific PCR support the contention that the SV perturbed SBDS protein expression in the father and child. CONCLUSION: Our findings implicate genomic rearrangements in the pathogenesis of some cases of SDS and support patients lacking biallelic SBDS point mutations be tested for SV within the SBDS locus.
Keywords: Abdomen; Alleles; Bone Marrow Diseases; Cell Line, Transformed; Child, Preschool; Comparative Genomic Hybridization; DNA Mutational Analysis; Exocrine Pancreatic Insufficiency; Female; Gene Order; Humans; Lipomatosis; Mutagenesis, Insertional; Mutation; Mutation, Missense; Pedigree; Proteins; Radiography, Abdominal; Ultrasonography

TCIRG1-associated congenital neutropenia. - Makaryan, Vahagn; Rosenthal, Elisabeth A; Bolyard, Audrey Anna; Kelley, Merideth L; Below, Jennifer E; Bamshad, Michael J; Bofferding, Kathryn M; Smith, Joshua D; Buckingham, Kati; Boxer, Laurence A; Skokowa, Julia; Welte, Karl; et al. (Hum Mutat, 2014)
Severe congenital neutropenia (SCN) is a rare hematopoietic disorder, with estimated incidence of 1 in 200,000 individuals of European descent, many cases of which are inherited in an autosomal dominant pattern. Despite the fact that several causal genes have been identified, the genetic basis for >30% of cases remains unknown. We report a five-generation family segregating a novel single nucleotide variant (SNV) in TCIRG1. There is perfect cosegregation of the SNV with congenital neutropenia in this family; all 11 affected, but none of the unaffected, individuals carry this novel SNV. Western blot analysis show reduced levels of TCIRG1 protein in affected individuals, compared to healthy controls. Two unrelated patients with SCN, identified by independent investigators, are heterozygous for different, rare, highly conserved, coding variants in TCIRG1.
Keywords: DNA Mutational Analysis; Heterozygote; Humans; Mutation; Neutropenia; Pedigree; Vacuolar Proton-Translocating ATPases

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Muzny, Donna; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Whole-exome sequencing links TMCO1 defect syndrome with cerebro-facio-thoracic dysplasia. - Pehlivan, Davut; Karaca, Ender; Aydin, Hatip; Beck, Christine R; Gambin, Tomasz; Muzny, Donna M; Bilge Geckinli, B; Karaman, Ali; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Eur J Hum Genet, 2014)
Whole-exome sequencing (WES) is a type of disruptive technology that has tremendous influence on human and clinical genetics research. An efficient and cost-effective method, WES is now widely used as a diagnostic tool for identifying the molecular basis of genetic syndromes that are often challenging to diagnose. Here we report a patient with a clinical diagnosis of cerebro-facio-thoracic dysplasia (CFTD; MIM#213980) in whom we identified a homozygous splice-site mutation in the transmembrane and coiled-coil domains 1 (TMCO1) gene using WES. TMCO1 mutations cause craniofacial dysmorphism, skeletal anomalies characterized by multiple malformations of the vertebrae and ribs, and intellectual disability (MIM#614132). A retrospective review revealed that clinical manifestations of both syndromes are very similar and overlap remarkably. We propose that mutations of TMCO1 are not only responsible for craniofacial dysmorphism, skeletal anomalies and mental retardation syndrome but also for CFTD.
Keywords: Abnormalities, Multiple; Exome; Humans; Infant; Intellectual Disability; Male; Membrane Proteins; Mutation; Protein Isoforms

Whole-exome sequencing reveals GPIHBP1 mutations in infantile colitis with severe hypertriglyceridemia. - Gonzaga-Jauregui, Claudia; Mir, Sabina; Penney, Samantha; Jhangiani, Shalini; Midgen, Craig; Finegold, Milton; Muzny, Donna M; Wang, Min; Bacino, Carlos A; Gibbs, Richard A; Lupski, James R; Kellermayer, Richard; et al. (J Pediatr Gastroenterol Nutr, 2014)
Severe congenital hypertriglyceridemia (HTG) is a rare disorder caused by mutations in genes affecting lipoprotein lipase (LPL) activity. Here we report a 5-week-old Hispanic girl with severe HTG (12,031 mg/dL, normal limit 150 mg/dL) who presented with the unusual combination of lower gastrointestinal bleeding and milky plasma. Initial colonoscopy was consistent with colitis, which resolved with reduction of triglycerides. After negative sequencing of the LPL gene, whole-exome sequencing revealed novel compound heterozygous mutations in GPIHBP1. Our study broadens the phenotype of GPIHBP1-associated HTG, reinforces the effectiveness of whole-exome sequencing in Mendelian diagnoses, and implicates triglycerides in gastrointestinal mucosal injury.
Keywords: Colitis; DNA Mutational Analysis; Exome; Female; Humans; Hypertriglyceridemia; Infant; Receptors, Lipoprotein

Attitudes of African Americans toward return of results from exome and whole genome sequencing. - Yu, Joon-Ho; Crouch, Julia; Jamal, Seema M; Tabor, Holly K; Bamshad, Michael J (Am J Med Genet A, 2013)
Exome sequencing and whole genome sequencing (ES/WGS) present patients and research participants with the opportunity to benefit from a broad scope of genetic results of clinical and personal utility. Yet, this potential for benefit also risks disenfranchising populations such as African Americans (AAs) that are already underrepresented in genetic research and utilize genetic tests at lower rates than other populations. Understanding a diverse range of perspectives on consenting for ES/WGS and receiving ES/WGS results is necessary to ensure parity in genomic health care and research. We conducted a series of 13 focus groups (n = 76) to investigate if and how attitudes toward participation in ES/WGS research and return of results from ES/WGS differ between self-described AAs and non-AAs. The majority of both AAs and non-AAs were willing to participate in WGS studies and receive individual genetic results, but the fraction not interested in either was higher in AAs. This is due in part to different expectations of health benefits from ES/WGS and how results should be managed. Our results underscore the need to develop and test culturally tailored strategies for returning ES/WGS results to AAs.
Keywords: Adult; African Americans; Aged; Attitude; Exome; Female; Focus Groups; Genetic Research; Genome-Wide Association Study; Humans; Male; Middle Aged; Sequence Analysis, DNA; Surveys and Questionnaires; Washington

De novo mutations in histone-modifying genes in congenital heart disease. - Zaidi, Samir; Choi, Murim; Wakimoto, Hiroko; Ma, Lijiang; Jiang, Jianming; Overton, John D; Romano-Adesman, Angela; Bjornson, Robert D; Breitbart, Roger E; Brown, Kerry K; Carriero, Nicholas J; Cheung, Yee Him; et al. (Nature, 2013)
Congenital heart disease (CHD) is the most frequent birth defect, affecting 0.8% of live births. Many cases occur sporadically and impair reproductive fitness, suggesting a role for de novo mutations. Here we compare the incidence of de novo mutations in 362 severe CHD cases and 264 controls by analysing exome sequencing of parent-offspring trios. CHD cases show a significant excess of protein-altering de novo mutations in genes expressed in the developing heart, with an odds ratio of 7.5 for damaging (premature termination, frameshift, splice site) mutations. Similar odds ratios are seen across the main classes of severe CHD. We find a marked excess of de novo mutations in genes involved in the production, removal or reading of histone 3 lysine 4 (H3K4) methylation, or ubiquitination of H2BK120, which is required for H3K4 methylation. There are also two de novo mutations in SMAD2, which regulates H3K27 methylation in the embryonic left-right organizer. The combination of both activating (H3K4 methylation) and inactivating (H3K27 methylation) chromatin marks characterizes 'poised' promoters and enhancers, which regulate expression of key developmental genes. These findings implicate de novo point mutations in several hundreds of genes that collectively contribute to approximately 10% of severe CHD.
Keywords: Adult; Case-Control Studies; Child; Chromatin; DNA Mutational Analysis; Enhancer Elements, Genetic; Exome; Female; Genes, Developmental; Heart Diseases; Histones; Humans; Lysine; Male; Methylation; Mutation; Odds Ratio; Promoter Regions, Genetic

Exome sequencing resolves apparent incidental findings and reveals further complexity of SH3TC2 variant alleles causing Charcot-Marie-Tooth neuropathy. - Lupski, James R; Gonzaga-Jauregui, Claudia; Yang, Yaping; Bainbridge, Matthew N; Jhangiani, Shalini; Buhay, Christian J; Kovar, Christie L; Wang, Min; Hawes, Alicia C; Reid, Jeffrey G; Eng, Christine; Muzny, Donna M; et al. (Genome Med, 2013)
BACKGROUND: The debate regarding the relative merits of whole genome sequencing (WGS) versus exome sequencing (ES) centers around comparative cost, average depth of coverage for each interrogated base, and their relative efficiency in the identification of medically actionable variants from the myriad of variants identified by each approach. Nevertheless, few genomes have been subjected to both WGS and ES, using multiple next generation sequencing platforms. In addition, no personal genome has been so extensively analyzed using DNA derived from peripheral blood as opposed to DNA from transformed cell lines that may either accumulate mutations during propagation or clonally expand mosaic variants during cell transformation and propagation. METHODS: We investigated a genome that was studied previously by SOLiD chemistry using both ES and WGS, and now perform six independent ES assays (Illumina GAII (x2), Illumina HiSeq (x2), Life Technologies' Personal Genome Machine (PGM) and Proton), and one additional WGS (Illumina HiSeq). RESULTS: We compared the variants identified by the different methods and provide insights into the differences among variants identified between ES runs in the same technology platform and among different sequencing technologies. We resolved the true genotypes of medically actionable variants identified in the proband through orthogonal experimental approaches. Furthermore, ES identified an additional SH3TC2 variant (p.M1?) that likely contributes to the phenotype in the proband. CONCLUSIONS: ES identified additional medically actionable variant calls and helped resolve ambiguous single nucleotide variants (SNV) documenting the power of increased depth of coverage of the captured targeted regions. Comparative analyses of WGS and ES reveal that pseudogenes and segmental duplications may explain some instances of apparent disease mutations in unaffected individuals.

Mutations in ECEL1 cause distal arthrogryposis type 5D. - McMillin, Margaret J; Below, Jennifer E; Shively, Kathryn M; Beck, Anita E; Gildersleeve, Heidi I; Pinner, Jason; Gogola, Gloria R; Hecht, Jacqueline T; Grange, Dorothy K; Harris, David J; Earl, Dawn L; Jagadeesh, Sujatha; et al. (Am J Hum Genet, 2013)
Distal arthrogryposis (DA) syndromes are the most common of the heritable congenital-contracture disorders, and ~50% of cases are caused by mutations in genes that encode contractile proteins of skeletal myofibers. DA type 5D (DA5D) is a rare, autosomal-recessive DA previously defined by us and is characterized by congenital contractures of the hands and feet, along with distinctive facial features, including ptosis. We used linkage analysis and whole-genome sequencing of a multiplex consanguineous family to identify in endothelin-converting enzyme-like 1 (ECEL1) mutations that result in DA5D. Evaluation of a total of seven families affected by DA5D revealed in five families ECEL1 mutations that explain ~70% of cases overall. ECEL1 encodes a neuronal endopeptidase and is expressed in the brain and peripheral nerves. Mice deficient in Ecel1 exhibit perturbed terminal branching of motor neurons to the endplate of skeletal muscles, resulting in poor formation of the neuromuscular junction. Our results distinguish a second developmental pathway that causes congenital-contracture syndromes.
Keywords: Arthrogryposis; Consanguinity; Female; Genetic Linkage; Humans; Male; Metalloendopeptidases; Mutation; Sequence Analysis, DNA

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases

Perrault syndrome is caused by recessive mutations in CLPP, encoding a mitochondrial ATP-dependent chambered protease. - Jenkinson, Emma M; Rehman, Atteeq U; Walsh, Tom; Clayton-Smith, Jill; Lee, Kwanghyuk; Morell, Robert J; Drummond, Meghan C; Khan, Shaheen N; Naeem, Muhammad Asif; Rauf, Bushra; Billington, Neil; Schultz, Julie M; et al. (Am J Hum Genet, 2013)
Perrault syndrome is a genetically and clinically heterogeneous autosomal-recessive condition characterized by sensorineural hearing loss and ovarian failure. By a combination of linkage analysis, homozygosity mapping, and exome sequencing in three families, we identified mutations in CLPP as the likely cause of this phenotype. In each family, affected individuals were homozygous for a different pathogenic CLPP allele: c.433A>C (p.Thr145Pro), c.440G>C (p.Cys147Ser), or an experimentally demonstrated splice-donor-site mutation, c.270+4A>G. CLPP, a component of a mitochondrial ATP-dependent proteolytic complex, is a highly conserved endopeptidase encoded by CLPP and forms an element of the evolutionarily ancient mitochondrial unfolded-protein response (UPR(mt)) stress signaling pathway. Crystal-structure modeling suggests that both substitutions would alter the structure of the CLPP barrel chamber that captures unfolded proteins and exposes them to proteolysis. Together with the previous identification of mutations in HARS2, encoding mitochondrial histidyl-tRNA synthetase, mutations in CLPP expose dysfunction of mitochondrial protein homeostasis as a cause of Perrault syndrome.
Keywords: Adenosine Triphosphate; Adolescent; Adult; ATP-Dependent Proteases; Endopeptidase Clp; Exome; Female; Genes, Recessive; Gonadal Dysgenesis, 46,XX; Hearing Loss, Sensorineural; Homozygote; Humans; In Situ Hybridization; Male; Mitochondria; Mutation; Pedigree; Phenotype; Young Adult

Practices and policies of clinical exome sequencing providers: analysis and implications. - Jamal, Seema M; Yu, Joon-Ho; Chong, Jessica X; Dent, Karin M; Conta, Jessie H; Tabor, Holly K; Bamshad, Michael J (Am J Med Genet A, 2013)
Exome and whole genome sequencing (ES/WGS) offer potential advantages over traditional approaches to diagnostic genetic testing. Consequently, use of ES/WGS in clinical settings is rapidly becoming commonplace. Yet there are myriad moral, ethical, and perhaps legal implications attached to the use of ES and health care professionals and institutions will need to consider these implications in the context of the varied practices and policies of ES service providers. We developed "core elements" of content and procedures for informed consent, data sharing, and results management and a quantitative scale to assess the extent to which research protocols met the standards established by these core elements. We then used these tools to evaluate the practices and policies of each of the 6 U.S. CLIA-certified labs offering clinical ES. Approaches toward informed consent, data sharing, and results return vary widely among ES providers as do the overall potential merits and disadvantages of each, and more importantly, the balance between the two.
Keywords: Exome; Humans; Information Dissemination; Informed Consent; Morals; Organizational Policy; Practice Patterns, Physicians'; Sequence Analysis, DNA; United States

Recessive loss of function of the neuronal ubiquitin hydrolase UCHL1 leads to early-onset progressive neurodegeneration. - Bilguvar, Kaya; Tyagi, Navneet K; Ozkara, Cigdem; Tuysuz, Beyhan; Bakircioglu, Mehmet; Choi, Murim; Delil, Sakir; Çağlayan, Ahmet O; Baranoski, Jacob F; Erturk, Ozdem; Yalcinkaya, Cengiz; Karacorlu, Murat; et al. (Proc Natl Acad Sci U S A, 2013)
Ubiquitin C-terminal hydrolase-L1 (UCHL1), a neuron-specific de-ubiquitinating enzyme, is one of the most abundant proteins in the brain. We describe three siblings from a consanguineous union with a previously unreported early-onset progressive neurodegenerative syndrome featuring childhood onset blindness, cerebellar ataxia, nystagmus, dorsal column dysfuction, and spasticity with upper motor neuron dysfunction. Through homozygosity mapping of the affected individuals followed by whole-exome sequencing of the index case, we identified a previously undescribed homozygous missense mutation within the ubiquitin binding domain of UCHL1 (UCHL1(GLU7ALA)), shared by all affected subjects. As demonstrated by isothermal titration calorimetry, purified UCHL1(GLU7ALA), compared with WT, exhibited at least sevenfold reduced affinity for ubiquitin. In vitro, the mutation led to a near complete loss of UCHL1 hydrolase activity. The GLU7ALA variant is predicted to interfere with the substrate binding by restricting the proper positioning of the substrate for tunneling underneath the cross-over loop spanning the catalytic cleft of UCHL1. This interference with substrate binding, combined with near complete loss of hydrolase activity, resulted in a >100-fold reduction in the efficiency of UCHL1(GLU7ALA) relative to WT. These findings demonstrate a broad requirement of UCHL1 in the maintenance of the nervous system.
Keywords: Adult; Age of Onset; Amino Acid Sequence; Base Sequence; Child, Preschool; Exome; Female; Genes, Recessive; Homozygote; Humans; Hydrolysis; Male; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Nerve Degeneration; Neurons; Pedigree; Protein Binding; Sequence Analysis, DNA; Substrate Specificity; Syndrome; Thermodynamics; Ubiquitin; Ubiquitin Thiolesterase

Recessive mutations in DGKE cause atypical hemolytic-uremic syndrome. - Lemaire, Mathieu; Fremeaux-Bacchi, Veronique; Schaefer, Franz; Choi, Murim; Tang, Wai Ho; Le Quintrec, Moglie; Fakhouri, Fadi; Taque, Sophie; Nobili, François; Martinez, Frank; Ji, Weizhen; Overton, John D; et al. (Nat Genet, 2013)
Pathologic thrombosis is a major cause of mortality. Hemolytic-uremic syndrome (HUS) features episodes of small-vessel thrombosis resulting in microangiopathic hemolytic anemia, thrombocytopenia and renal failure. Atypical HUS (aHUS) can result from genetic or autoimmune factors that lead to pathologic complement cascade activation. Using exome sequencing, we identified recessive mutations in DGKE (encoding diacylglycerol kinase ɛ) that co-segregated with aHUS in nine unrelated kindreds, defining a distinctive Mendelian disease. Affected individuals present with aHUS before age 1 year, have persistent hypertension, hematuria and proteinuria (sometimes in the nephrotic range), and develop chronic kidney disease with age. DGKE is found in endothelium, platelets and podocytes. Arachidonic acid-containing diacylglycerols (DAG) activate protein kinase C (PKC), which promotes thrombosis, and DGKE normally inactivates DAG signaling. We infer that loss of DGKE function results in a prothrombotic state. These findings identify a new mechanism of pathologic thrombosis and kidney failure and have immediate implications for treating individuals with aHUS.
Keywords: Acute Kidney Injury; Atypical Hemolytic Uremic Syndrome; Child; Child, Preschool; Diacylglycerol Kinase; Exome; Female; Genes, Recessive; Hemolytic-Uremic Syndrome; Humans; Immunoenzyme Techniques; Infant; Male; Molecular Sequence Data; Mutation; Renal Insufficiency, Chronic; Thrombocytopenia; Thrombotic Microangiopathies

Recurrent gain-of-function mutation in PRKG1 causes thoracic aortic aneurysms and acute aortic dissections. - Guo, Dong-Chuan; Regalado, Ellen; Casteel, Darren E; Santos-Cortez, Regie L; Gong, Limin; Kim, Jeong Joo; Dyack, Sarah; Horne, S Gabrielle; Chang, Guijuan; Jondeau, Guillaume; Boileau, Catherine; Coselli, Joseph S; et al. (Am J Hum Genet, 2013)
Gene mutations that lead to decreased contraction of vascular smooth-muscle cells (SMCs) can cause inherited thoracic aortic aneurysms and dissections. Exome sequencing of distant relatives affected by thoracic aortic disease and subsequent Sanger sequencing of additional probands with familial thoracic aortic disease identified the same rare variant, PRKG1 c.530G>A (p.Arg177Gln), in four families. This mutation segregated with aortic disease in these families with a combined two-point LOD score of 7.88. The majority of affected individuals presented with acute aortic dissections (63%) at relatively young ages (mean 31 years, range 17-51 years). PRKG1 encodes type I cGMP-dependent protein kinase (PKG-1), which is activated upon binding of cGMP and controls SMC relaxation. Although the p.Arg177Gln alteration disrupts binding to the high-affinity cGMP binding site within the regulatory domain, the altered PKG-1 is constitutively active even in the absence of cGMP. The increased PKG-1 activity leads to decreased phosphorylation of the myosin regulatory light chain in fibroblasts and is predicted to cause decreased contraction of vascular SMCs. Thus, identification of a gain-of-function mutation in PRKG1 as a cause of thoracic aortic disease provides further evidence that proper SMC contractile function is critical for maintaining the integrity of the thoracic aorta throughout a lifetime.
Keywords: Acute Disease; Adolescent; Adult; Amino Acid Sequence; Aneurysm, Dissecting; Aorta, Thoracic; Aortic Aneurysm, Thoracic; Cyclic GMP; Cyclic GMP-Dependent Protein Kinase Type I; Exome; Female; Fibroblasts; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Molecular Sequence Data; Muscle Contraction; Muscle, Smooth, Vascular; Mutation; Myosin Light Chains; Pedigree

A recurrent PDGFRB mutation causes familial infantile myofibromatosis. - Cheung, Yee Him; Gayden, Tenzin; Campeau, Philippe M; LeDuc, Charles A; Russo, Donna; Nguyen, Van-Hung; Guo, Jiancheng; Qi, Ming; Guan, Yanfang; Albrecht, Steffen; Moroz, Brenda; Eldin, Karen W; et al. (Am J Hum Genet, 2013)
Infantile myofibromatosis (IM) is the most common benign fibrous tumor of soft tissues affecting young children. By using whole-exome sequencing, RNA sequencing, and targeted sequencing, we investigated germline and tumor DNA in individuals from four distinct families with the familial form of IM and in five simplex IM cases with no previous family history of this disease. We identified a germline mutation c.1681C>T (p.Arg561Cys) in platelet-derived growth factor receptor β (PDGFRB) in all 11 affected individuals with familial IM, although none of the five individuals with nonfamilial IM had mutations in this gene. We further identified a second heterozygous mutation in PDGFRB in two myofibromas from one of the affected familial cases, indicative of a potential second hit in this gene in the tumor. PDGFR-β promotes growth of mesenchymal cells, including blood vessels and smooth muscles, which are affected in IM. Our findings indicate p.Arg561Cys substitution in PDGFR-β as a cause of the dominant form of this disease. They provide a rationale for further investigations of this specific mutation and gene to assess the benefits of targeted therapies against PDGFR-β in aggressive life-threatening familial forms of the disease.
Keywords: Amino Acid Sequence; Female; Genes, Dominant; Genetic Association Studies; Germ-Line Mutation; Heterozygote; Humans; Male; Models, Molecular; Mutation, Missense; Myofibromatosis; Pedigree; Protein Structure, Tertiary; Receptor, Notch3; Receptor, Platelet-Derived Growth Factor beta; Receptors, Notch; Sequence Analysis, DNA

TM4SF20 ancestral deletion and susceptibility to a pediatric disorder of early language delay and cerebral white matter hyperintensities. - Wiszniewski, Wojciech; Hunter, Jill V; Hanchard, Neil A; Willer, Jason R; Shaw, Chad; Tian, Qi; Illner, Anna; Wang, Xueqing; Cheung, Sau W; Patel, Ankita; Campbell, Ian M; Gelowani, Violet; et al. (Am J Hum Genet, 2013)
White matter hyperintensities (WMHs) of the brain are important markers of aging and small-vessel disease. WMHs are rare in healthy children and, when observed, often occur with comorbid neuroinflammatory or vasculitic processes. Here, we describe a complex 4 kb deletion in 2q36.3 that segregates with early childhood communication disorders and WMH in 15 unrelated families predominantly from Southeast Asia. The premature brain aging phenotype with punctate and multifocal WMHs was observed in ~70% of young carrier parents who underwent brain MRI. The complex deletion removes the penultimate exon 3 of TM4SF20, a gene encoding a transmembrane protein of unknown function. Minigene analysis showed that the resultant net loss of an exon introduces a premature stop codon, which, in turn, leads to the generation of a stable protein that fails to target to the plasma membrane and accumulates in the cytoplasm. Finally, we report this deletion to be enriched in individuals of Vietnamese Kinh descent, with an allele frequency of about 1%, embedded in an ancestral haplotype. Our data point to a constellation of early language delay and WMH phenotypes, driven by a likely toxic mechanism of TM4SF20 truncation, and highlight the importance of understanding and managing population-specific low-frequency pathogenic alleles.
Keywords: Age of Onset; Aging, Premature; Asian Continental Ancestry Group; Base Sequence; Brain; Child; Child, Preschool; Chromosomes, Human, Pair 2; Exons; Female; Genetic Predisposition to Disease; Humans; Language Development Disorders; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Pedigree; Sequence Analysis, DNA; Sequence Deletion; Tetraspanins

Haploinsufficiency of SF3B4, a component of the pre-mRNA spliceosomal complex, causes Nager syndrome. - Bernier, Francois P; Caluseriu, Oana; Ng, Sarah; Schwartzentruber, Jeremy; Buckingham, Kati J; Innes, A Micheil; Jabs, Ethylin Wang; Innis, Jeffrey W; Schuette, Jane L; Gorski, Jerome L; Byers, Peter H; Andelfinger, Gregor; et al. (Am J Hum Genet, 2012)
Nager syndrome, first described more than 60 years ago, is the archetype of a class of disorders called the acrofacial dysostoses, which are characterized by craniofacial and limb malformations. Despite intensive efforts, no gene for Nager syndrome has yet been identified. In an international collaboration, FORGE Canada and the National Institutes of Health Centers for Mendelian Genomics used exome sequencing as a discovery tool and found that mutations in SF3B4, a component of the U2 pre-mRNA spliceosomal complex, cause Nager syndrome. After Sanger sequencing of SF3B4 in a validation cohort, 20 of 35 (57%) families affected by Nager syndrome had 1 of 18 different mutations, nearly all of which were frameshifts. These results suggest that most cases of Nager syndrome are caused by haploinsufficiency of SF3B4. Our findings add Nager syndrome to a growing list of disorders caused by mutations in genes that encode major components of the spliceosome and also highlight the synergistic potential of international collaboration when exome sequencing is applied in the search for genes responsible for rare Mendelian phenotypes.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Exome; Female; Haploinsufficiency; Humans; Limb Deformities, Congenital; Male; Mandibulofacial Dysostosis; Mutation; Reproducibility of Results; RNA Precursors; RNA Splicing Factors; RNA-Binding Proteins; Spliceosomes; Young Adult

Next generation analytic tools for large scale genetic epidemiology studies of complex diseases. - Mechanic, Leah E; Chen, Huann-Sheng; Amos, Christopher I; Chatterjee, Nilanjan; Cox, Nancy J; Divi, Rao L; Fan, Ruzong; Harris, Emily L; Jacobs, Kevin; Kraft, Peter; Leal, Suzanne M; McAllister, Kimberly; et al. (Genet Epidemiol, 2012)
Over the past several years, genome-wide association studies (GWAS) have succeeded in identifying hundreds of genetic markers associated with common diseases. However, most of these markers confer relatively small increments of risk and explain only a small proportion of familial clustering. To identify obstacles to future progress in genetic epidemiology research and provide recommendations to NIH for overcoming these barriers, the National Cancer Institute sponsored a workshop entitled "Next Generation Analytic Tools for Large-Scale Genetic Epidemiology Studies of Complex Diseases" on September 15-16, 2010. The goal of the workshop was to facilitate discussions on (1) statistical strategies and methods to efficiently identify genetic and environmental factors contributing to the risk of complex disease; and (2) how to develop, apply, and evaluate these strategies for the design, analysis, and interpretation of large-scale complex disease association studies in order to guide NIH in setting the future agenda in this area of research. The workshop was organized as a series of short presentations covering scientific (gene-gene and gene-environment interaction, complex phenotypes, and rare variants and next generation sequencing) and methodological (simulation modeling and computational resources and data management) topic areas. Specific needs to advance the field were identified during each session and are summarized.
Keywords: Data Mining; Gene-Environment Interaction; Genetic Variation; Genome-Wide Association Study; Humans; Molecular Epidemiology; National Institutes of Health (U.S.); Neoplasms; Phenotype; United States

Phenotype diversity in type 1 Gaucher disease: discovering the genetic basis of Gaucher disease/hematologic malignancy phenotype by individual genome analysis. - Lo, Sarah M; Choi, Murim; Liu, Jun; Jain, Dhanpat; Boot, Rolf G; Kallemeijn, Wouter W; Aerts, Johannes M F G; Pashankar, Farzana; Kupfer, Gary M; Mane, Shrikant; Lifton, Richard P; Mistry, Pramod K (Blood, 2012)
Gaucher disease (GD), an inherited macrophage glycosphingolipidosis, manifests with an extraordinary variety of phenotypes that show imperfect correlation with mutations in the GBA gene. In addition to the classic manifestations, patients suffer from increased susceptibility to hematologic and nonhematologic malignancies. The mechanism(s) underlying malignancy in GD is not known, but is postulated to be secondary to macrophage dysfunction and immune dysregulation arising from lysosomal accumulation of glucocerebroside. However, there is weak correlation between GD/cancer phenotype and the systemic burden of glucocerebroside-laden macrophages. Therefore, we hypothesized that genetic modifier(s) may underlie the GD/cancer phenotype. In the present study, the genetic basis of GD/T-cell acute lymphoblastic lymphoma in 2 affected siblings was deciphered through genomic analysis. GBA gene sequencing revealed homozygosity for a novel mutation, D137N. Whole-exome capture and massively parallel sequencing combined with homozygosity mapping identified a homozygous novel mutation in the MSH6 gene that leads to constitutional mismatch repair deficiency syndrome and increased cancer risk. Enzyme studies demonstrated that the D137N mutation in GBA is a pathogenic mutation, and immunohistochemistry confirmed the absence of the MSH6 protein. Therefore, precise phenotype annotation followed by individual genome analysis has the potential to identify genetic modifiers of GD, facilitate personalized management, and provide novel insights into disease pathophysiology.
Keywords: Adult; beta-Glucosidase; Child; Child, Preschool; Female; Gaucher Disease; Genome, Human; Hematologic Neoplasms; Humans; Individuality; Male; Pedigree; Phenotype; Sequence Analysis, DNA; Siblings